Short sleep and insomnia are associated with accelerated epigenetic age. - Kusters, Cynthia D J; Klopack, Eric T; Crimmins, Eileen M; Seeman, Teresa E; Cole, Steve; Carroll, Judith E (Psychosom Med)
OBJECTIVE: Short sleep and insomnia are each associated with greater risk for age-related disease, which suggests that insufficient sleep may accelerate biological aging. We examine whether short sleep and insomnia alone or together relate to epigenetic age among older adults. METHODS: A total of 3,795 men (46.3%) and women aged 56-100 years from the Health and Retirement Study were included. Insomnia was defined as reporting at least one insomnia symptom (difficulty falling asleep, waking up at night, or waking up too early in the morning) and feeling unrested when waking up most of the time. Those reporting <6 hours of bedtime were categorized as short sleepers. Three second- or third-generation epigenetic age acceleration clocks were derived from the 2016 HRS Venous Blood Study. The linear regression analysis was adjusted for age, sex, race/ethnicity, education, and obesity status. RESULTS: Insomnia and short sleep were associated with an 0.49 (95%CI:0.03-0.94; P:0.04) and 1.29 (95%CI:0.52-2.07; P:0.002) years acceleration of GrimAge, respectively, as well as a faster pace of aging (DunedinPACE; 0.018 (95%CI:0.004-0.033; P:0.02); 0.022(95%CI:-0.004-0.048; P:0.11)). Compared to healthy sleepers, individuals with the combination of short sleep and insomnia had an accelerated GrimAge (0.97 years; 95%CI:0.07-1.87; P:0.04) and a greater DunedinPACE (0.032; 95%CI:0.003-0.060; P:0.04). CONCLUSION: Our findings indicate short sleep, insomnia, and the combination of the two, are linked to epigenetic age acceleration, suggesting that these individuals have an older biological age that may contribute to risk for comorbidity and mortality.
Keywords: Epigenetic Age; insomnia; short sleep

The silent epidemic of loneliness: identifying the antecedents of loneliness using a lagged exposure-wide approach. - Hong, Joanna H; Nakamura, Julia S; Sahakari, Sakshi S; Chopik, William J; Shiba, Koichiro; VanderWeele, Tyler J; Kim, Eric S (Psychology of Medicine)
BACKGROUND: A large and accumulating body of evidence shows that loneliness is detrimental for various health and well-being outcomes. However, less is known about potentially modifiable factors that lead to decreased loneliness. METHODS: We used data from the Health and Retirement Study to prospectively evaluate a wide array of candidate predictors of subsequent loneliness. Importantly, we examined if changes in 69 physical-, behavioral-, and psychosocial-health factors (from ;2006/2008 to ;2010/2012) were associated with subsequent loneliness 4 years later (;2014/2016). RESULTS: Adjusting for a large range of covariates, changes in certain health behaviors (e.g. increased physical activity), physical health factors (e.g. fewer functioning limitations), psychological factors (e.g. increased purpose in life, decreased depression), and social factors (e.g. greater number of close friends) were associated with less subsequent loneliness. CONCLUSIONS: Our findings suggest that subjective ratings of physical and psychological health and perceived social environment (e.g. chronic pain, self-rated health, purpose in life, anxiety, neighborhood cohesion) are more strongly associated with subsequent loneliness. Yet, objective ratings (e.g. specific chronic health conditions, living status) show less evidence of associations with subsequent loneliness. The current study identified potentially modifiable predictors of subsequent loneliness that may be important targets for interventions aimed at reducing loneliness.
Keywords: Health behaviors; Loneliness; Older Adults; Physical Health; predictors; Psychosocial factors; Public Health

Spouses of individuals living with mild cognitive impairment or dementia in the United States: A descriptive, population-based study. - Torres, Jacqueline M; Flores Romero, Karla Renata; Kotwal, Ashwin A; Chen, Ruijia; Hill-Jarrett, Tanisha; Mitchell, Uchechi A; Glymour, Medellena Maria (Alzheimers & dementia: the journal of the Alzheimer's Association)
BACKGROUND: Little is known about the population of individuals who live with a spouse with cognitive impairment (CI) or dementia. METHODS: Using the US Health and Retirement Study, 2000 to 2018, we estimated the population of adults ≥ 50 years old co-residing with a spouse with probable CI/dementia. We described their socio-demographic and health characteristics and quantified socio-demographic inequities. RESULTS: Among community-dwelling adults ≥ 50 years old, 6% of women and 4% of men co-resided with a spouse with probable CI/dementia. Among those who were married/partnered, the prevalence of spousal dementia was greater for Black and Hispanic adults compared to their White counterparts, and for those with lower versus higher educational attainment. Among spouses, activities of daily living disability, depression, and past 2-year hospitalization was common. DISCUSSION: Millions of older adults, disproportionately Black and Hispanic people and people with lower levels of educational attainment, live with a spouse with CI while also facing their own major health challenges.
Keywords: Dementia; Epidemiology; Family; health equity; mild cognitive impairment; Spouses

State home and community-based services expenditures and unmet care needs in the United States: Has everyone benefitted equally? - Yang, Yulin; Lee, Ah-Reum; Rapp, Thomas; Chen, Ruijia; Glymour, M Maria; Torres, Jacqueline M (health services research)
OBJECTIVE: To test whether the impacts of Medicaid's Home and Community-Based Services (HCBS) expenditures have been equitable. DATA SOURCES AND STUDY SETTING: This is a secondary data analysis. We linked annual data on state-level Medicaid HCBS expenditures with individual data from U.S. Health and Retirement Study (HRS; 2006-2016). STUDY DESIGN: We evaluated the association between state-level HCBS expenditure quartiles and the risk of experiencing challenges in basic or instrumental activities of daily living (I/ADLs) without assistance (unmet needs for care). We fitted generalized estimating equations (GEE) with a Poisson distribution, log link function, and an unstructured covariance matrix. We controlled demographics, time, and place-based fixed effects and estimated models stratified by race and ethnicity, gender, and urbanicity. We tested the robustness of results with negative controls. DATA COLLECTION/EXTRACTION METHODS: Our analytic sample included HRS Medicaid beneficiaries, aged 55+, who had difficulty with ≥1 I/ADL (n = 2607 unique respondents contributing 4719 person-wave observations). PRINCIPAL FINDINGS: Among adults with IADL difficulty, higher quartiles of HCBS expenditure (vs. the lowest quartile) were associated with a lower overall prevalence of unmet needs for care (e.g., Prevalence Ratio [PR], Q4 vs. Q1: 0.91, 95% CI: 0.84-0.98). This protective association was concentrated among non-Hispanic white respondents (Q4 vs. Q1: 0.82, 95% CI: 0.73-0.93); estimates were imprecise for Hispanic individuals and largely null for non-Hispanic Black participants. We found no evidence of heterogeneity by gender or urbanicity. Negative control robustness checks indicated that higher quartiles of HCBS expenditure were not associated with (1) the risk of reporting I/ADL difficulty among 55+ Medicaid beneficiaries, and (2) the risk of unmet care needs among non-Medicaid beneficiaries. CONCLUSION: The returns to higher state-level HCBS expenditures under Medicaid for older adults with I/ADL disability do not appear to have been equitable by race and ethnicity.
Keywords: aging/elderly/geriatrics; long term care; Medicaid; Social determinants of health

Statistical Learning for Individualized Asset Allocation - Ding, Yi; Li, Yingying; Song, Rui (Journal of the American Statistical Association)
We establish a high-dimensional statistical learning framework for individualized asset allocation. Our proposed methodology addresses continuous-action decision-making with a large number of characteristics. We develop a discretization approach to model the effect of continuous actions and allow the discretization frequency to be large and diverge with the number of observations. We estimate the value function of continuous-action using penalized regression with our proposed generalized penalties that are imposed on linear transformations of the model coefficients. We show that our proposed Discretization and Regression with generalized fOlded concaVe penalty on Effect discontinuity (DROVE) approach enjoys desirable theoretical properties and allows for statistical inference of the optimal value associated with optimal decision-making. Empirically, the proposed framework is exercised with the Health and Retirement Study data in finding individualized optimal asset allocation. The results show that our individualized optimal strategy improves the financial well-being of the population. Supplementary materials for this article are available online. © 2022 American Statistical Association.
Keywords: Continuous-action decision-making; High-dimensional statistical learning; Individualization; Penalized regression

Stepfamily variation in parent–child relationship quality in later life - Lin, I-Fen; Seltzer, Judith A. (Journal of Marriage and Family)
Objective We use a family systems approach to examine how stepfamily structure is associated with both positive and negative parent–child relationships while considering mothers' and fathers' discrepant reports. Background Two in five older couples with children are in stepfamilies. Past research on later-life stepfamily dynamics has focused mainly on positive aspects of relationships and compared reports of mothers and fathers from different families. Method Using the U.S. Health and Retirement Study, we estimated multilevel models with data from married couples in which both spouses reported living children and answered all questions about positive and negative parent–child relationships (N = 2150). Results Couples in stepfamilies reported less positive and more negative relationships with their children than did couples in non-stepfamilies. Mothers reported more positive relationships than fathers, but there was no gender difference in reports of negative relationships. The patterns of perceived parent–child relationships and divergent reports between mothers and fathers also varied by stepfamily structure. Structural complexity was not consistently related to positive or negative relationships. Conclusion This study underscores the importance of considering mothers' and fathers' different points of view in the same family and examining both positive and negative parent–child interactions as negative relationships are not merely the reverse of positive relationships.
Keywords: Aging; family structure; gender; parent–child relationships; Remarriage; stepfamilies

Stressors and Pain across the Late-Life Span: Findings from Two Parent Longitudinal Studies of Aging and Health. - Brennan, Penny L (Journal of Aging and Health)
OBJECTIVE: The objective is to determine associations between stressors and pain across the late-life span. METHOD: Multilevel linear modeling was applied separately to harmonized repeated measures data from the Longitudinal Late-Life Health study (LLLH; = 342; 13-year interval) and the Health and Retirement Study (HRS; = 2959; 8-year interval). RESULTS: In both the LLLH and HRS samples, independent of age, gender, and race, participants with higher average stressor levels experienced more numerous painful conditions and higher pain severity over the study intervals. In the HRS sample, they also experienced higher levels of pain interference. In general, participants' stressor levels did not influence rates of increase in their pain. Gender and race had few moderating effects on associations between stressors and pain. DISCUSSION: Stressors and pain are associated across the late-life span. Future research should focus on the mediating mechanisms that account for this association and the moderating factors that affect its strength.
Keywords: multilevel linear modeling; pain; Stressors

Subjective memory complaints and social participation among older adults: results from the health and retirement study. - Lee, Chang Dae; Park, Sangmi; Foster, Erin R (Aging & Mental Health)
This study aims to examine whether subjective memory complaints (SMC) contribute to social participation among older adults.The study sample was 4,713 community-dwelling older adults aged 65 years and older from four waves (2010, 2012, 2014, 2016) of the Health and Retirement Study. Hierarchical linear modeling analysis was used to examine the association of SMC with social participation after controlling for factors influencing social participation. Demographic factors (i.e. age, gender, and perceived socioeconomic status) were entered in block 1, health-related factors (i.e. health conditions, perceived health, instrumental activities of daily living, memory-immediate and delayed, and depressive symptoms) were entered in block 2, environmental factors (i.e. perceived social support and strain from spouse, child, family, and friend) were entered in block 3, and SMC was entered in block 4.The result showed that factors significantly contributing to social participation are age (standardized β = -0.08,  < 0.01), perceived socioeconomic status (β = 0.16,  < 0.001), perceived health (β = 0.15,  < 0.001), instrumental activities of daily living (β = 0.12,  < 0.001), memory-immediate and delayed (β = 0.09,  < 0.001; β = 0.08,  < 0.001, respectively), social support from spouse and friend (β = 0.04,  < 0.05; β = 0.13,  < 0.001, respectively), social strain from friend (β = 0.07,  < 0.001), and SMC (β = -0.05,  < 0.001). The demographic factors explained 9.5%, health-related factors explained 8.5%, environmental factors explained 2.4%, and SMC explained 0.1% of the variance in social participation. This finding suggests that SMC may contribute to social participation in older adults.Supplemental data for this article can be accessed online at https://doi.org/10.1080/13607863.2021.1961123 .
Keywords: Social participation; subjective memory complaints

Systematic Review, Meta-Analysis, and Population Attributable Risk of Dementia Associated with Traumatic Brain Injury in Civilians and Veterans. - Gardner, Raquel C; Bahorik, Amber; Kornblith, Erica S; Allen, Isabel Elaine; Plassman, Brenda L; Yaffe, Kristine (Journal of Neurotrauma)
Traumatic brain injury (TBI) is an established risk factor for dementia. However, the magnitude of risk is highly variable across studies. Identification of sub-populations at highest risk, with careful consideration of potential sources of bias, is urgently needed to guide public health policy and research into mechanisms and treatments. We conducted a systematic review and meta-analysis of risk of all-cause dementia after all-severity TBI. We assessed for effect of participant age and sex, veteran status, research methods, and region. The search window covered January 1990 to January 2019. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting guidelines. Thirty-two studies met inclusion criteria. Data were pooled using random effects models. Population attributable risk (PAR) of dementia due to TBI in the U.S. was calculated by sex and veteran status. Pooled risk ratio (RR) for dementia after TBI was 1.66 (95% confidence interval 1.42-1.93). Younger age, male sex, and studies from Asia were associated with significantly higher risk; veteran status was not. Risk of dementia associated with "head injury/trauma" was not significantly different from that associated with "TBI" diagnosis specifically. PAR of dementia due to TBI among U.S. veterans was twice that of the general U.S. population, largely due to the high prevalence of TBI exposure in the majority male veteran population. This meta-analysis found that TBI is associated with nearly 70% increased risk of dementia. Risk may be highest among younger adults, men, and cohorts in Asia. Efforts to prevent TBI and also to prevent post-TBI dementia are of high importance. Additionally, improved methods for diagnosing and tracking TBI on a public health level, such as national registries, may improve the quality and generalizability of future epidemiological studies investigating the association between TBI and dementia.
Keywords: Dementia; systematic review; Traumatic Brain Injury; veteran

Shaping the future of behavioral and social research at NIA - Nielsen, Lis (National Institute on Aging, 2024)
Keywords: behavioral research; Social research

Sharing the caring? Dynamic interaction between siblings in the provision of care to parents - Timothy, Hunt (Department of Economics Discussion Paper Series, 2024)
I analyse strategic interaction between adult siblings in the provision of care to an elderly parent by estimating a dynamic discrete-choice game in which siblings make location, work and care choices. I find that the opportunity for strategic play exacerbates gender differences in caring responsibilities as sons in particular strategically shirk providing care as they believe their sibling is relatively likely to provide care in their absence. Counterfactual experiments show that if siblings instead took care, location and work choices independently then the gender care gap would be around 14% smaller. Also, I find that unobserved preference differences between sons and daughters are far more important in driving the gender care gap than observed differences in wages.
Keywords: adult siblings; care; Elderly

Simultaneous variable selection and estimation in semiparametric regression of mixed panel count data. - Ge, Lei; Hu, Tao; Li, Yang (Biometrics, 2024)
Mixed panel count data represent a common complex data structure in longitudinal survey studies. A major challenge in analyzing such data is variable selection and estimation while efficiently incorporating both the panel count and panel binary data components. Analyses in the medical literature have often ignored the panel binary component and treated it as missing with the unknown panel counts, while obviously such a simplification does not effectively utilize the original data information. In this research, we put forward a penalized likelihood variable selection and estimation procedure under the proportional mean model. A computationally efficient EM algorithm is developed that ensures sparse estimation for variable selection, and the resulting estimator is shown to have the desirable oracle property. Simulation studies assessed and confirmed the good finite-sample properties of the proposed method, and the method is applied to analyze a motivating dataset from the Health and Retirement Study.
Keywords: Algorithms; Computer Simulation; Likelihood Functions

Structural Racism and Health Stratification: Connecting Theory to Measurement. - Brown, Tyson H; Homan, Patricia (Journal of Health and Social Behavior, 2024)
Less than 1% of studies on racialized health inequities have empirically examined their root cause: structural racism. Moreover, there has been a disconnect between the conceptualization and measurement of structural racism. This study advances the field by (1) distilling central tenets of theories of structural racism to inform measurement approaches, (2) conceptualizing U.S. states as racializing institutional actors shaping health, (3) developing a novel latent measure of structural racism in states, (4) using multilevel models to quantify the association between structural racism and five individual-level health outcomes among respondents from the Health and Retirement Study (N = 9,020) and the Behavioral Risk Factor Surveillance System (N = 308,029), and (5) making our measure of structural racism publicly available to catalyze research. Results show that structural racism is consistently associated with worse health for Black people but not White people. We conclude by highlighting this study's contributions (theoretical, methodological, and substantive) and important avenues for future research on the topic.
Keywords: Black or African American; Health Status Disparities; Humans; systemic racism; White

Study examines hesitancy around buying an annuity - Bailey, Doug (Insurance Newsnet, 2024)
Keywords: annuities

A sudden wealth loss may lead to cognitive decline - National Institute on Aging (National Institute on Aging, 2024)
Keywords: Cognitive health; Economics; global aging; Health Disparities

Salivary telomere length and the risks of prediabetes and diabetes among middle-aged and older adults: findings from the Health and Retirement Study. - Yu, Hong-Jie; Ho, Mandy; Chau, Pui Hing; Geng, Leiluo; Fong, Daniel Yee Tak (Acta Diabetologica, 2023)
AIM: To assess the association of telomere length (TL) with prediabetes/diabetes and to explore the potential factors affecting TL among individuals with prediabetes/diabetes by weight status. METHODS: This study included 3,379 eligible adults (aged 45-85 years, males: 42%) from the US Health and Retirement Study in 2008. TL was assayed using quantitative PCR of saliva (T/S ratio). Linear and nonlinear associations between TL and prediabetes/diabetes were assessed using the logistic regression and restricted cubic spline model, respectively, adjusting for TL-plate numbers, age, sex, race, body mass index, lifestyles, diabetes medications, and cardiometabolic parameters (blood pressure, C-reactive protein, and total cholesterol). Multiple linear regression was used for testing any factors associated with TL. RESULTS: Among 3,379 participants, 868 (25.7%) had prediabetes with a mean TL of 1.34 ± 0.37 (T/S ratio) and 858 (25.4%) had diabetes with a mean TL of 1.36 ± 0.43 (T/S ratio). Neither linear nor nonlinear association of TL with prediabetes/diabetes was significant by weight status. Age was negatively associated with TL in both normal-weight (β = - 0.002, p = 0.025) and overweight/obese (β = - 0.002, p = 0.006) prediabetes, but non-significant in normal-weight and overweight/obese diabetes. BMI and cardiometabolic parameters were not associated with TL in prediabetes/diabetes by weight status. CONCLUSIONS: Salivary TL was not associated with prediabetes/diabetes among the US middle-aged and older adults. Further longitudinal studies are required to establish the link between TL and diabetes development and to identify potential factors affecting TL shortening, particularly in normal-weight diabetic patients.
Keywords: Cardiovascular Diseases; Diabetes Mellitus; Obesity; Overweight; Prediabetic State; Telomere; Telomere Shortening

Screen for depression to help prevent functional decline in seniors, clinicians urged - Lasek, Alicia (McKnights, 2023)
Keywords: depression; functional decline

Self-perception of aging and perceived medical discrimination. - Sun, Na; Xu, Ziyao; Hua, Cassandra L; Qiu, Xiao; Pittman, Amelia; Abdou, Basel; Brown, J Scott (J Am Geriatr Soc, 2023)
BACKGROUND: Individuals who perceive medical discrimination often face adverse consequences. How individuals perceive their own aging experiences may influence perceived medical discrimination due to age by generating expectations that they will receive poor treatment from clinicians, which may be amplified for individuals who also perceive discrimination because of race. This study explored the relationship between self-perceptions of aging (SPA) and perceived medical discrimination due to age, race, and other reasons. METHODS: We used three waves (2008, 2012, 2016) from the nationally representative Health and Retirement Study (HRS) data. Our sample included 10,188 community-residing individuals aged 51 and over. SPA were measured by two domains: positive SPA and negative SPA. Multinomial logistic regression that adjusted for demographic, health characteristics, and year-fixed effects was conducted to estimate the relationship between SPA and categories of perceived medical discrimination (age, race, age and race, and other). RESULTS: Approximately 11% of the population perceived discrimination because of age or race in the medical setting from 2008 to 2016. Older adults who had a positive SPA were 15% [Adjusted relative risk ratio (ARR): 0.85, 95% CI: 0.79-0.91], 13% [ARRR: 0.87, 95% CI: 0.76-1.00], and 20% [ARRR: 0.80, 95% CI: 0.74-0.88] less likely to experience perceived medical discrimination due to age, race, and the intersection of age and race, respectively, than those who did not, holding other factors constant. Those who held a negative SPA were 38% [ARRR: 1.38, 95% CI: 1.28-1.48] more likely to report perceived medical discrimination due to age and 12% [ARRR: 1.12, 95% CI: 1.03-1.21] more likely to report perceived medical discrimination due to other reasons. CONCLUSIONS: Holding a positive perception of aging may help reduce perceived medical discrimination because of age and race, which may in turn improve communication and lead to timely and appropriate treatment.
Keywords: ageism; intersection; medical environment; perspective of age.

Self-Rated Health and Mortality: Moderation by Purpose in Life. - Friedman, Elliot M; Teas, Elizabeth (Int J Environ Res Public Health, 2023)
Poor self-rated health consistently predicts reduced longevity, even when objective disease conditions and risk factors are considered. Purpose in life is also a reliable predictor of diverse health outcomes, including greater longevity. Given prior work in which we showed that purpose in life moderated the association between chronic conditions and health-related biological factors, the aim of the current study was to examine the role of purpose in life in moderating the relationship between subjective health and mortality. We also examined potential differences in these associations by race/ethnicity. Data were from two large national longitudinal studies-the Health and Retirement Study (HRS) and the Midlife in the United States (MIDUS) study-with a 12- to 14-year follow-up period for mortality estimates. Results of logistic regression analyses showed that purpose in life and self-rated health were both significantly positively associated with longevity, and that purpose in life significantly moderated the relationship between self-rated health and mortality. Stratified analyses showed similar results across all racial/ethnic groups, with the exception of Black MIDUS participants. These results suggest that greater purpose in life may provide a buffer against the greater probability of mortality associated with poor subjective health.
Keywords: ethnicity; Humans; Longevity; Longitudinal Studies; Mortality; Racial Groups; United States; White

A semiparametric alternative to the Heckman correction: application with left-censored data on parental transfers - Wang, Lu; Jiang, Yixiao; He, Zhaochen (Empirical Economics, 2023)
Using a semiparametric estimator developed by Klein and Vella (J Appl Econom 24(5):735–762, 2009b), we study the motives for parental wealth transfers to living children using left-censored data from the Health and Retirement Study. We confirm the presence of heteroskedastic errors in our data and show that the inverse Mills ratio approach employed by the Heckman correction would be biased in such a setting. Using the more flexible semiparametic approach, we find evidence of a nonlinear relationship between amount of inter vivo transfers and recipient children’s household incomes, suggesting that parents’ motives for transferring wealth may vary depending on their child’s income level. © 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Earning income tax credit (EITC); Heteroskedasticity; Inter Vivos Transfers

Sense of purpose in life and allostatic load in two longitudinal cohorts. - Lewis, Nathan A; Hill, Patrick L (J Psychosom Res, 2023)
OBJECTIVE: Sense of purpose in life has been linked with better physical health, longevity, and reduced risk for disability and dementia, but the mechanisms linking sense of purpose with diverse health outcomes are unclear. Sense of purpose may promote better physiological regulation in response to stressors and health challenges, leading to lower allostatic load and disease risk over time. The current study examined the association between sense of purpose in life and allostatic load over time in adults over age 50. METHODS: Data from the nationally representative US Health and Retirement Study (HRS) and English Longitudinal Study of Ageing (ELSA) were used to examine associations between sense of purpose and allostatic load across 8 and 12 years of follow-up, respectively. Blood-based and anthropometric biomarkers were collected at four-year intervals and used to compute allostatic load scores based on clinical cut-off values representing low, moderate, and high risk. RESULTS: Population-weighted multilevel models revealed that sense of purpose in life was associated with lower overall levels of allostatic load in HRS, but not in ELSA after adjusting for relevant covariates. Sense of purpose in life did not predict rate of change in allostatic load in either sample. CONCLUSIONS: The present investigation supports sense of purpose predicting preserved differentiation of allostatic regulation, with more purposeful individuals demonstrating consistently lower allostatic load over time. Persistent differences in allostatic burden may account for divergent health trajectories between individuals low and high in sense of purpose.
Keywords: Adult; Aging; Allostasis; Biomarkers; Humans; Longitudinal Studies; Middle Aged; Retirement

Sense of Purpose in Life and Beliefs and Knowledge of Alzheimer's Disease. - Sutin, Angelina R; Stephan, Yannick; Luchetti, Martina; Aschwanden, Damaris; Sesker, Amanda A; Zhu, Xianghe; Terracciano, Antonio (Arch Clin Neuropsychol, 2023)
OBJECTIVE: A sense of purpose in life is associated with healthier cognitive outcomes, including lower risk of Alzheimer's Disease (ad). The present research examines whether purpose is also associated with beliefs and knowledge of ad. METHOD: A random subsample (N = 1,187) of community-dwelling participants from the Health and Retirement Study completed a module on self-reported beliefs and knowledge of ad. RESULTS: Purpose in life was associated with lower perceived threat of ad and greater belief that modifiable factors (e.g., physical activity) decrease risk. Associations were not moderated by experience with ad or depressive symptoms. Purpose was unrelated to beliefs that genetics or stress increase risk or knowledge of ad. CONCLUSIONS: Individuals with a sense of purpose are less concerned about risk of developing ad and believe modifiable factors reduce risk. These beliefs may support engagement in behaviors that reduce risk and be one psychological pathway through which purpose protects against ad.
Keywords: Alzheimer's disease; beliefs; Knowledge

Sense of purpose in life and work-life tension: Perceptions of interference and enhancement - Sutin, Angelina R.; Luchetti, Martina; Stephan, Yannick; Terracciano, Antonio (Aging and Health Research, 2023)

Sensory impairment and depressive symptoms among older adults before and during the COVID-19 pandemic. - Xu, Shu; Wang, Haowei; Song, Qian; Burr, Jeffrey A (Aging Ment Health, 2023)
OBJECTIVES: This study examined the associations between sensory impairment (SI), lack of social contact during the COVID-19 pandemic, and depressive symptoms among Americans aged 50 and above. METHODS: We employed data from the 2018 and 2020 Health and Retirement Study ( = 13,460) to examine four SI groups: no SI, visual impairment (VI) only, hearing impairment (HI) only, and dual sensory impairment (DSI). First, multilevel models were employed to estimate the associations between SI and depressive symptoms before and during the pandemic using the full dataset ( = 13,460). Second, linear regression models were employed to estimate the moderation effect of lack of social contact during the pandemic using the 2020 wave data only ( = 4,133). RESULTS: Among older adults, 15.60% had VI only, 10.16% had HI only, and 9.66% had DSI. All SI groups reported significantly more depressive symptoms than the no SI group. The differences between older adults with VI and DSI and those without SI regarding depressive symptoms narrowed during the pandemic. There was no statistically significant moderation effect of lack of social contact for SI and depressive symptoms. CONCLUSION: Older adults with SI faced mental health challenges and demonstrated psychological resilience during the pandemic. Future research should examine other risk factors that may modify the relationship between SI and mental health during public health crises.
Keywords: Emotional well-being; hearing impairment; public health crisis; social networks; visual impairment.

Sensory Loss and its Association with Different Types of Departures from the Labor Force Among Older Adults in the US - Garcia Morales, Emmanuel E; Powel, Danielle S; Gray, Andrew; Assi, Lama; Reed, Nicholas S (Work, Aging and Retirement, 2023)
To investigate the association between sensory loss and the timing and type of self-reported departures from the labor force, via retirement or disability, we used data from the Health and Retirement Study, cycles 2004–2018. Based on self-reported sensory loss, we classified individuals into four groups: no sensory loss, hearing loss only, vision loss only, and dual sensory loss (vision and hearing loss). We assumed that older adults could leave the labor force either by retirement or due to disability. Because once one type of exit is observed the other type cannot be observed, we implemented a competing risk approach to estimate the instantaneous rate of departure (sub-distribution hazard rate) for leaving the labor force due to disability, treating retirement as a competing risk, and for departures via retirement, with disability as the competing risk. We found that compared to older adults with no sensory loss, adults with vision loss are at a higher risk for leaving the labor force via disability (when treating retirement as a competing risk). Compared to no sensory loss, hearing loss was associated with a higher risk for retirement in models treating disability as a competing risk. Given the differences between disability and retirement benefits (before and after retirement age), policies intended to keep people with sensory loss from early labor force departures, such as accommodations in the workplace and/or hearing and vision care coverage, might contribute to better retiring conditions and healthy aging among older adults with sensory loss.

Settling Disparities in Care and Getting Back to Treating the Whole Patient - Norris, Chuck (Creators Syndicate, 2023)
Keywords: Health Care; rural living

Sex differences in changes of depressive symptoms among older adults before and during the COVID-19 pandemic: evidence from two longitudinal cohorts. - Zheng, Fanfan; Li, Chenglong; Hua, Rong; Liang, Jie; Gao, Darui; Xie, Wuxiang (BMC Geriatrics, 2023)
BACKGROUND: Major concerns about the adverse mental health impact of the rapidly spread COVID-19 pandemic have been raised. Previous studies on changes of depressive symptoms during the COVID-19 pandemic have yielded inconsistent results regarding the sex differences. Since women have higher depressive symptoms even without the pandemic, it is essential to consider the pre-existing change of depressive symptoms of a similar period to discern the effect of the pandemic on depression. This study aimed to evaluate sex differences in depressive symptoms before and during the pandemic. METHODS: Data from the Health and Retirement Study (HRS; waves 13 to 15) and the English Longitudinal Study of Ageing (ELSA; wave 8 to COVID-19 wave 2) were analyzed. Depressive symptoms were assessed by the 8-item Center for Epidemiological Studies Depression (CES-D) scale. According to the time of COVID-19 outbreak in the US and the UK, the intervals from waves 13 to 14 surveys of the HRS and from waves 8 to 9 surveys of the ELSA were employed as pre-pandemic periods to control for the pre-existing depressive symptoms, respectively. Changes of CES-D scores during the pre-pandemic and pandemic periods were assessed by linear mixed models. RESULTS: Nine thousand, seven hundred thirty-seven participants (mean age: 66.7 ± 10.7 years) from the HRS and 5,098 participants (mean age: 68.7 ± 10.0 years) from the ELSA were included. CES-D scores among women were significantly higher than those among men at all waves in both cohorts. During the pre-pandemic period, no significant sex difference on changes of CES-D scores was detected in either the HRS or the ELSA. During the pandemic period, CES-D scores were increased in both men and women and the sex differences in CES-D increments of the two cohorts were both significant. Enlarged sex differences were demonstrated in increments of CES-D scores during the pandemic period. CONCLUSIONS: Our results suggest women suffered from worse depressive symptoms in response to the pandemic, although the changes of depression were similar between men and women before the pandemic. These findings underscore the necessity to support the vulnerable populations, especially women, to manage the distress brought by the pandemic and maintain optimal mental health status.
Keywords: COVID-19; depression; ELSA; Pandemics; Sex Characteristics

Sex differences in cognitive aging and the role of socioeconomic status: Evidence from multi-cohort studies. - Jin, Yinzi; Hong, Chenlu; Luo, Yanan (Psychiatry Res, 2023)
BACKGROUND: Sex differences exist in cognitive function, and socioeconomic status (SES) may play a role in changing these discrepancies. This study investigated the role of SES in contributing to sex differences in cognitive function. METHODS: We conducted a pooled multi-cohort study on the basis of four comparative cohort studies from the UK, the US, Europe and China to assess sex differences and the role of SES in cognitive decline by birth cohort (1930-1938, 1939-1945, 1946-1968). Cognitive function was measured in three domains based on the mean and SD of the corresponding tests: episodic memory, working memory, and time orientation. SES was the summed scores of education and household wealth. FINDINGS: 61,019 individuals were involved. Cognitive function of women declined faster than those of men as growing old (particularly after 80 years old). As SES increased, cognitive function increased more for women than for men in most cases among later-born cohorts (1930-1938, 1939-1945, 1946-1968) (e.g., episodic memory scores at 60 years old: women exhibited an increase from -0.09 [95%CI -0.12, -0.07] in low SES to 0.89 [0.86, 0.92] in high SES; men from -0.16 [-0.19, -0.14] to 0.59 [0.56, 0.62]). However, sex-specific cognitive benefits were absent in the oldest birth cohort (1895-1929). INTERPRETATION: These findings highlight the importance of considering the role of SES in the discrepancy of sex difference in cognitive aging.
Keywords: Aged, 80 and over; Aging; cognitive aging; Cohort Studies; Female; Humans; Male; Middle Aged; Sex Characteristics; Social Class; Socioeconomic factors

Shifting of Cognitive Assessments Between Face-to-Face and Telephone Administration: Measurement Considerations. - Smith, Jason R; Gibbons, Laura E; Crane, Paul K; Mungas, Dan M; Glymour, M Maria; Jennifer J Manly; Zahodne, Laura B; Mayeda, Elizabeth Rose; Richard N Jones; Gross, Alden L (The Journals of Gerontology, Series B, 2023)
OBJECTIVES: Telephone-administered cognitive assessments are a cost-effective and sometimes necessary alternative to face-to-face assessments. There is limited information in large studies concerning mode effects, or differences in cognition attributable to assessment method, as a potential measurement threat. We evaluated mode effects on cognitive scores using a population-based sample of community-living older adults. METHODS: We used data from participants aged 65-79 in the 2014 Health and Retirement Study for whom interview mode was randomized (n=6825). We assessed mode differences in test means, whether mode modifies associations of cognition with criterion variables, and formal measurement invariance testing. RESULTS: Relative to face-to-face assessment, telephone assessment was associated with higher scores for memory and calculation (0.06 to 0.013 standard deviations (SD)) and lower scores for non-memory items (-0.09 to -0.01 SD). Cognition was significantly differentially related to IADL difficulty depending on assessment mode. Measurement invariance testing identified evidence of mode differences in certain tests as a function of mode: adjusting for underlying cognition, the largest mode differences in memory and attention: immediate noun recall, delayed word recall, and serial-7s scores were higher given telephone administration. DISCUSSION: Differences by mode of administration are apparent in cognitive measurement in older adults albeit to a small degree in our study, and most pronounced for tests of memory and attention. The importance of accounting for mode differences ultimately depends on one's research question and study sample: not all associations may be affected by mode differences and such modification may only be apparent among those with lower cognitive functioning.
Keywords: Cognition; Mode effects; Psychometrics; Telephone

Shingles Vaccine Uptake Among Older Adults: Identifying Early, Later, and Nonadopters - Kang, Alice H.; Jung K Kim; Jennifer A Ailshire; Crimmins, Eileen M. (AJPM Focus, 2023)
Introduction: There is growing interest in accelerating adoptions of vaccines. This study examined factors that differentiate the acceptance and timing of uptake of the first shingles vaccine, Zostavax, among older adults in the U.S. Methods: Data from Health and Retirement Study respondents who were aged ≥62 years in 2008 were analyzed to determine whether they received a shingles vaccination from 2006 to 2016. Multinomial logistic regression was used to examine the characteristics associated with vaccine uptake and timing. Results: Of those eligible, 15.2% were vaccinated early (between 2006 and 2010), 20.2% were vaccinated later, and 64.6% remained unvaccinated 10 years after the shingles vaccine was introduced. Respondents more likely to be vaccinated were those who had higher education and income, experience with influenza vaccination, more frequent social interaction with friends, or were residing in an area with higher shingles vaccination rates. Conclusions: Shingles vaccination rates vary by social and geographic characteristics. Efforts to improve and expedite vaccination and other new preventive measures should target specific populations and geographic areas.
Keywords: adoption timing; Health and Retirement Study; Shingles vaccination

Short-term effect of retirement on health: Evidence from nonparametric fuzzy regression discontinuity design. - Ebeid, Mohamed; Oguzoglu, Umut (Health Econ, 2023)
We estimate the short-term effect of retirement on health in the US using the Health and Retirement Study survey. We use the nonparametric fuzzy regression discontinuity design to avoid assuming any functional form on the age-health profile and minimize potential bias in identifying the causal effect of retirement on health status in the short term. Estimates indicate an 8% decline in the cognitive functioning score of retirees and a 28% increase in the CESD depression scale. The likelihood of being in good health status declined by 16%. The transition from working to retirement has more significant negative impacts on males than females. In addition, retirement has more considerable adverse effects on less-educated individuals compared to high-educated individuals. The short-term effects of retirement on health are consistent and robust across different bandwidths, weighting kernel functions, and age-profile specifications. Moreover, the Treatment Effect Derivative test results highly support the external validity of the nonparametric estimates of the retirement effect on health.
Keywords: Female; Health Status; Humans; Male; Retirement; Surveys and Questionnaires

Should You Take Social Security at Age 62, 65, or 70? A Comprehensive Analysis Offers a Very Clear Answer - Williams, Sean (The Motley Fool, 2023)
Keywords: claiming age; Retirement; Social Security

A Simple Single Item Rated by an Interviewer Predicts Incident Dementia Over 15 Years. - Sutin, Angelina R; Aschwanden, Damaris; Luchetti, Martina; Stephan, Yannick; Terracciano, Antonio (J Alzheimers Dis, 2023)
Subjective memory is useful to detect cognitive deficits not apparent on objective tests. This research evaluates whether memory rated by an interviewer predicts incident dementia. Health and Retirement Study participants without cognitive impairment at baseline whose memory was rated by the interviewer were analyzed (N = 12,749). Worse interviewer-rated memory was associated with higher risk of incident dementia over 15 years (HR = 1.40, 95% CI = 1.27-1.54). The association was evident even among participants in the top quartile of objective memory performance (HR = 1.71, 95% CI = 1.26-2.32). Interviewer-rated memory may be a low-cost supplement to neuropsychological evaluation to predict dementia risk beyond self-reports and objective cognitive testing.

The Skill-Specific Automatability of Aging Workers and Its Impact on Retirement Decisions - Lee, Zeewan (Work, Aging and Retirement, 2023)
Research regarding the effects of automation on labor supply often assesses the labor force as a whole and disregards specific effects on aging workers. In light of rapid technological changes in the labor market, we assess the linkage between the automatability of aging workers and their retirement decisions. Based on the theoretical model of task-based technological changes and drawing data from the Health and Retirement Study and O*NET 2000–2018, we create an automatability index based on workers’ primary skills. Using the index as our main explanatory variable in Cox proportional hazards models and logit models, we find that skill-specific automatability increases the retirement likelihood, both in terms of their expected and actual timing of retirement. This work provides empirical evidence that individuals’ automatability renders the notion of “working at old age” less viable, despite the financial and health benefits of staying in the labor force for an extended period. Our findings offer important insights on how to better promote productive aging, for instance, by offering retraining programs for older workers to harness their soft skills to reduce automatability in the labor market.

Social Determinants of Health Contribute to Racial and Ethnic Disparities in Depression, Cognition - Nye, Jessica (Psychiatry Advisor, 2023)
Keywords: Cognition; depression; Disparities; health; Race/ethnicity; social determinants

Social factors may predict mortality risk for older adults - National Institute on Aging (National Institute on Aging, 2023)
Keywords: mortality risk; social characteristics; Social Frailty Index

Social Frailty Index: Development and validation of an index of social attributes predictive of mortality in older adults. - Shah, Sachin J; Oreper, Sandra; Jeon, Sun Young; Boscardin, W John; Fang, Margaret C; Covinsky, Kenneth E (Proc Natl Acad Sci U S A, 2023)
While social characteristics are well-known predictors of mortality, prediction models rely almost exclusively on demographics, medical comorbidities, and function. Lacking an efficient way to summarize the prognostic impact of social factor, many studies exclude social factors altogether. Our objective was to develop and validate a summary measure of social risk and determine its ability to risk-stratify beyond traditional risk models. We examined participants in the Health and Retirement Study, a longitudinal, survey of US older adults. We developed the model from a comprehensive inventory of 183 social characteristics using least absolute shrinkage and selection operator, a penalized regression approach. Then, we assessed the predictive capacity of the model and its ability to improve on traditional prediction models. We studied 8,250 adults aged ≥65 y. Within 4 y of the baseline interview, 22% had died. Drawn from 183 possible predictors, the Social Frailty Index included age, gender, and eight social predictors: neighborhood cleanliness, perceived control over financial situation, meeting with children less than yearly, not working for pay, active with children, volunteering, feeling isolated, and being treated with less courtesy or respect. In the validation cohort, predicted and observed mortality were strongly correlated. Additionally, the Social Frailty Index meaningfully risk-stratified participants beyond the Charlson score (medical comorbidity index) and the Lee Index (comorbidity and function model). The Social Frailty Index includes age, gender, and eight social characteristics and accurately risk-stratifies older adults. The model improves upon commonly used risk prediction tools and has application in clinical, population health, and research settings.
Keywords: Aged; Child; Frailty; Humans; Longitudinal Studies; Retirement; Sociological Factors

Social genetic effects: Study suggests your romantic partner’s DNA can influence your own health behaviors - Dolan, Eric (PsyPost, 2023)
Keywords: Genetics; Health Behavior; partner; spouse

SOCIAL ISOLATION ACROSS THE ADULT LIFE SPAN: VARIATIONS BY GENDER - Kaitlin Shartle (Sociology, 2023)
This dissertation uses two nationally representative surveys which span from young adulthood to late life to examine social isolation across the adult life course in the United States. In the first chapter of this dissertation, I examine patterns and trends of social isolation by age, period, cohort, and gender by conducting descriptive analyses using the National Survey of Midlife Development in the United States (MIDUS) and the Health and Retirement Study (HRS). I find that about 14 percent of U.S. adults aged 25 and older are socially isolated with this percentage growing with advancing age as well as across period-based time. Additionally, there are gender differences in social isolation which vary based on whether relationship status is included or excluded from the measure of social isolation. In the second chapter, I investigate the trajectory of social isolation across the adult life course and examine how social isolation varies by cohort and gender. This is done by testing five longitudinal models of social isolation: enduring, spontaneous, lagged effects, life course, and hybrid, using both MIDUS and HRS. This chapter shows that social isolation is relatively stable within people as they age through adulthood, which is due to both time-invariant factors and recent history. More recent birth cohorts have higher levels of social isolation. Additionally, iv while men are more isolated than women earlier in adulthood, these disparities converge before reversing at later ages. My third chapter examines the relationship between social isolation and self-rated health across adulthood and how this relationship differs by gender, again using MIDUS and HRS. This chapter demonstrates that social isolation and self-rated health influence each other in older adulthood, but not in early adulthood or midlife. There are few gender differences in the relationship between social isolation and self-rated health across adulthood, except that women in older adulthood may experience greater health risks to being socially isolated than men. In sum, this dissertation advances understanding of social isolation across the adult life course in the United States by evaluating trends within and between-individuals across time, examining connections between social isolation and health, and assessing gender differences.

Social isolation linked to higher likelihood of nursing home admission: study - Towhey, Jessica (McKnights, 2023)
Keywords: health outcomes; Nursing homes; social isolation

Social Isolation, Loneliness, and Accelerated Aging: A Multidimensional Approach Towards Aging - Qi,Xiang (ProQuest Dissertations and Theses, 2023)
Background/Objectives: Approximately 24% of US older adults experience social isolation, while 43% of those over 60 reports feeling lonely. The health risks of social isolation and loneliness (SI/L) are significant, comparable to smoking 15 cigarettes a day and potentially shortening one’s life by 15 years. However, the biopsychological mechanisms by which SI/L are associated with health outcomes are understudied. Furthermore, it’s unclear how the variability of SI/L (i.e., continuation vs. recovery) may contribute to the aging process. This dissertation aims to model the patterns and joint trajectories of SI/L and examine the biological mechanisms through which they impact accelerated aging. Methods: The study used data from a nationally-representative longitudinal dataset, the US Health and Retirement Study (HRS) 2006-2020, which included 12,709 participants aged 50 and older. Social isolation was measured by the Steptoe’s Social Isolation Index, while loneliness was measured by the 3-item UCLA Loneliness scale. Biological aging was assessed through DNA methylation-based measures (PhenoAge, GrimAge, and DunedinPoAm) from the HRS Venous Blood Study 2016. Functional aging included measures of physical function, cognitive function, and motoric cognitive risk syndrome. Statistical methods included Cox proportional hazard model, group-based joint trajectory model, and causal mediation model. Results: The findings revealed that chronic loneliness, compared to transient or no loneliness, was associated with a higher risk of functional disability in middle-aged and older adults, especially women (Manuscript 1). Five distinct trajectories of SI/L were identified. The largely unparallel changes of SI/L over time and their separate and joint contributions to accelerated biological aging provide support for the need to treat them differently. Persistently isolated/moderately lonely older adults had the highest biological aging acceleration (PhenoAge, GrimAge, and DunedinPoAm) compared to those who were rarely isolated/rarely lonely (Manuscript 2). Causal mediation analysis found that biological age acceleration mediated 6.7-11.8% in the effect of social isolation on subjective cognitive complaint, slow gait, and motoric cognitive risk syndrome. (Manuscript 3). Conclusions: The findings indicated that strategies for addressing SI/L could prevent chronic diseases and functional decline via slowing biological aging. The study provides new knowledge by identifying SI/L as the proximate determinants of deficits in healthy aging and informs public health practice and policy advancement by identifying sensitive biological measures and optimal time points for evaluating interventions and supporting healthy aging and longevity.
Keywords: 0351:Gerontology; 0493:Aging; 0569:Nursing; Aging; biological aging; Dementia; Epigenetic; Gerontology; Geroscience; Nursing; social network; social relationship

Social isolation, loneliness, and depressive symptoms: A twelve-year population study of temporal dynamics. - Luo, Mengsha (The Journals of Gerontology, Series B, 2023)
OBJECTIVES: Social isolation and loneliness are two different aspects of social connections. Whether social isolation and loneliness precede depressive symptoms, or depressive symptoms precede feelings of loneliness and social isolation, or both, has not been fully established. This study aims to examine the possible reciprocity in the relationship between the two aspects of social connections and depressive symptoms among middle-aged and older adults. METHODS: This study analyzed four waves of data (2008-2016) from the Health and Retirement Study (HRS, N = 5,393 individuals) and investigated within-person level cross-lagged associations of social isolation and loneliness with depressive symptoms using random intercept cross-lagged panel models. RESULTS: This study revealed a unidirectional relationship between social isolation and depressive symptoms and a bidirectional relationship between loneliness and depressive symptoms at the within-person level. Specifically, net of trait levels and prior states, earlier state depressive symptoms predicted future state social isolation. That is, when adults feel depressed more frequently than they usually do, they are more likely to be socially disconnected than usual at a later time. In the reverse direction, earlier state social isolation did not predict future state depressive symptoms. Within-person deviation in prior expected depressive symptoms predicted deviation in expected loneliness four years later and vice versa. Moreover, the strength of the two cross-lagged effects did not differ. DISCUSSION: Social isolation and loneliness are linked to depressive symptoms differently. Though depressive symptoms might be a potential antecedent of social isolation, they might be both a potential antecedent and an outcome of loneliness.
Keywords: perceived isolation; social disconnectedness; Social integration; social relationship; subjective isolation

Social Isolation, Sleep Disturbance, and Cognitive Functioning (HRS): A Longitudinal Mediation Study. - Qi, Xiang; Pei, Yaolin; Malone, Susan K; Wu, Bei (J Gerontol A Biol Sci Med Sci, 2023)
BACKGROUND: Social isolation is prevalent and associated with dementia, yet the directionality and mechanisms are less understood. This study examined the association between social isolation and cognitive functioning and explored the mediating role of sleep disturbance on the social isolation-cognition relationship. METHODS: Data from 5,753 dementia-free Americans aged ≥50 of 2006 (T1), 2010 (T2), and 2014 (T3) waves of the Health and Retirement Study. Social isolation was measured by the Steptoe Social Isolation Index. Cognitive functioning was measured by the Telephone Interview of Cognitive Status. Sleep disturbance was measured with the modified Jenkins Sleep Scale. We used cross-lagged panel models to determine the associations between social isolation, sleep disturbance, and cognitive functioning. RESULTS: Social isolation is significantly associated with subsequent cognitive functioning (T1 to T2: β = -0.055, standard error [SE] = 0.014, p < 0.001; T2 to T3: β = -0.044, SE = 0.016, p < 0.001). Lower cognitive functioning is significantly associated with greater subsequent social isolation (T1 to T2: β = -0.101, SE = 0.020, p < 0.001; T2 to T3: β = -0.058, SE = 0.011, p < 0.001). Sleep disturbance at T2 partially mediated the effect of social isolation (T1) on cognitive functioning (T3), accounting for 6.2% of the total effect (β = -0.003, SE = 0.001, p < 0.01). CONCLUSIONS: Social isolation may deteriorate cognitive functioning and vice versa. The association between social isolation and cognition is partially explained by sleep disturbance.
Keywords: cognitive functioning; Sleep disturbance; social isolation

Social Mediators of the Association Between Depression and Falls Among Older Adults. - Lohman, Matthew C; Fallahi, Afsaneh; Mishio Bawa, Eric; Wei, Jingkai; Merchant, Anwar T (J Aging Health, 2023)
OBJECTIVES: To investigate the role of social factors in the association between depression and falls among older adults. METHODS: The sample included data from 3443 older adults from three waves of the Health and Retirement Study (2010-2014). A Lifestyle Questionnaire was used to measure social engagement, social network contact, and neighborhood social context. Mediating effects of social factors were estimated through causal mediation analysis. Poorer social engagement and network contact were associated with greater likelihood of falls, while poorer neighborhood context was associated with greater likelihood of fall injuries. Social engagement mediated a significant portion of the effect of depression on falls (OR: 1.03, 95% CI: 1.00, 1.06), and neighborhood context mediated a portion of the effect of depression on fall injuries (OR: 1.03, 95% CI: 1.00, 1.07). The direct and indirect impacts of social factors suggest that considering them may help improve existing fall prevention approaches.

Social relationships and epigenetic aging in older adulthood: Results from the Health and Retirement Study. - Rentscher, Kelly E; Klopack, Eric T; Crimmins, Eileen M; Seeman, Teresa E; Cole, Steve W; Carroll, Judith E (Brain, behavior and immunity, 2023)
Growing evidence suggests that social relationship quality can influence age-related health outcomes, although how the quality of one's relationships directly relates to the underlying aging process is less clear. We hypothesized that the absence of close relationships as well as lower support and higher strain within existing relationships would be associated with an accelerated epigenetic aging profile among older adults in the Health and Retirement Study. Adults (N = 3,647) aged 50-100 years completed ratings of support and strain in relationships with their spouse, children, other family members, and friends. They also provided a blood sample that was used for DNA methylation profiling to calculate a priori-specified epigenetic aging measures: Horvath, Hannum, PhenoAge, GrimAge, and Dunedin Pace of Aging methylation (DunedinPoAm38). Generalized linear models that adjusted for chronological age, sex, and race/ethnicity and applied a false discovery rate correction revealed that the absence of marital and friend relationships related to an older GrimAge and faster DunedinPoAm38. Among those with existing relationships, lower support from a spouse, child, other family, and friends and higher strain with friends related to an older PhenoAge and GrimAge and faster DunedinPoAm38. In secondary analyses that further adjusted for socioeconomic and lifestyle factors, lower support from other family members and friends was associated with greater epigenetic aging. Findings suggest that the absence of close relationships and lower support within existing relationships-particularly with family members and friends-relate to accelerated epigenetic aging in older adulthood, offering one mechanism through which social relationships might influence risk for age-related declines and disease.
Keywords: biological aging; DNA Methylation; epigenetic clock; Social Relationships; Social strain; Social Support

Social relationships in later life: Does marital status matter? - Zhang, Zhenmei; Hsieh, Ning; Lai, Wen-hua (Journal of Social and Personal Relationships, 2023)
Previous research has suggested that unmarried persons may be disadvantaged in personal networks and social support. However, little is known about whether the quantity and quality of social relationships differ by marital status among older Americans. Using data from the 2006 and 2008 psychosocial questionnaires of the Health and Retirement Study, we examined the quantity and frequency of contact of three types of social relationships (i.e., friends, children, and family members) as well as the quality of these ties across six marital status groups (i.e., first married, remarried, cohabiting, divorced/separated, widowed, and never married). Our analytic sample included 13,087 respondents aged 51 and above. Multiple linear regression was used for the analysis. Our results show significant differences in social relationships by marital status. In terms of relationships with friends, compared to first-married persons, all the unmarried groups (except the cohabitors) had more frequent contact with their friends and reported greater support as well as greater strain from their friends, controlling for demographic covariates. Remarried persons and cohabitors were largely similar to their first-married counterparts except that both had fewer friends they felt close to, and the cohabitors also reported greater strain with their friends. In terms of relationships with children, all the unmarried groups except for widowed persons had fewer children they felt close to. All the unmarried groups were also disadvantaged in contact frequency and perceived social support from their children. Remarried persons were significantly disadvantaged compared to first-married persons in contact frequency and relationship quality with their children. These associations were largely robust when health and socioeconomic conditions were controlled for. In terms of relationships with family members, there were only a few significant differences across marital status groups. Our findings show the crucial role of marital status in shaping social relationships in later life. © The Author(s) 2023.
Keywords: cohabitation; confidants; gender; intergenerational relations; Marital status; relationship quality; remarriage; social network

Social support and social strain from children and subsequent health and well-being among older U.S. adults - Renae Wilkinson; Julia S. Nakamura; Eric S. Kim; Tyler J. VanderWeele (Journal of Social and Personal Relationships, 2023)
Social relationships contribute to well-being across the life course and may be especially vital resources for supporting healthy aging among older adults. This research examined associations between perceptions of social support and social strain from children assessed by older adult parents and 35 indicators of physical, behavioral, and psychosocial health and well-being. We utilized three waves of data from the Health and Retirement Study (HRS; N = 11,609), a diverse, national sample of U.S. adults over age 50. We found that increases in social support were associated with better subsequent outcomes on all psychological indicators (higher positive affect, life satisfaction, optimism, purpose in life, mastery, health mastery, financial mastery; lower depression, depressive symptoms, hopelessness, negative affect, perceived constraints) and most social factors (lower loneliness, greater likelihood of contact with children and other family) over the four-year follow-up period. Results also showed that increases in social strain were subsequently related to worse functioning across all indicators of psychological well-being and select social factors (i.e., higher loneliness) and psychological distress outcomes (i.e., higher hopelessness, negative affect, and perceived constraints). However, we did not find evidence that changes in social support and social strain were associated with physical health or health behavior outcomes.
Keywords: children; Social strain; Social Support

Social support and telomere length: a meta-analysis. - Montoya, Mariah; Uchino, Bert N (J Behav Med, 2023)
Previous studies have shown that lower social support is associated with higher all-cause mortality (Holt-Lunstad et al. in PLoS ONE Medicine 7:e1000316, 2010). While social support has been associated with system-specific biological measures (e.g., cardiovascular), there is the need to elucidate more general biological mechanisms linking social support to health risk across a number of diseases. In this meta-analytic review, the link between social support and telomere length (Cawthon et al. in Lancet 361:393-395, 2003) was conducted based on the updated PRISMA guidelines (Page et al., 2021). Across 17 studies, higher social support was not significantly related to longer telomere length (Zr = 0.010, 95% CI [- 0.028, 0.047], p > 0.05). The confidence interval indicated that the bulk of plausible values were small to null associations. Little evidence for bias was found as shown by funnel plots and Kendall's Tau. Moderator analyses focusing on the measure of support, health of sample, age, type of assay specimen, and gender were not significant. In conclusion, this review showed no significant relationship between social support and telomere length and highlights important future directions.

Sociodemographic characteristics, lifestyle behaviors, and symptoms associated with fluid overload among non-hospitalized and community-dwelling older adults with heart failure: A population-based approach. - Gharzeddine, Rida; Cypress, Brigette; Dahan, Thomas; Fu, Mei R (Geriatr Nurs, 2023)
BACKGROUND: Fluid overload is a major complication in patients with heart failure (HF) and the main reason for hospitalization. The purpose of the study was to explore the associations of fluid overload with sociodemographic characteristics, lifestyle behaviors, and symptoms among non-hospitalized and community-dwelling older adults with HF using large population data. METHODS: Descriptive and multivariate analyses were conducted on the Health and Retirement Study 2016. RESULTS: Fluid overload was prevalent in almost half of the sample. Female older adults with HF were more likely to have fluid overload (OR:1.43, p = 0.037) as well as being Black (OR:1.40, p = 0.041). Higher physical activity scores were associated with less likelihood of having fluid overload (OR:0.99, p = 0.025). Symptoms of shortness of breath (OR=2.18, p = 0.001), pain (OR=1.82, p < 0.001), and fatigue (OR=1.45, p = 0.025) were significantly associated with fluid overload. CONCLUSION: Female and Black community-dwelling older adults with HF are at higher risk of fluid overload. Symptoms of shortness of breath, pain, and fatigue are significant manifestations of fluid overload. Effective patient-centered interventions to promote fluid flow via physical activity may help older adults with HF manage fluid overload and alleviate associated symptoms.
Keywords: fluid overload; Heart Failure; lifestyle behaviors; non-hospitalized; Older Adults; sociodemographic characteristics

Sociodemographic dynamics and age trajectories of depressive symptoms among adults in mid- and later life: a cohort perspective. - Luo, Mengsha; Li, Lydia; Liu, Zhen; Li, Angran (Aging & Mental Health, 2023)
OBJECTIVES: This study explored the age trajectories of depressive symptoms across multiple cohort groups who were in middle and late adulthood; examined sociodemographic differences in these trajectories; and investigated how relevant factors contributed to depressive symptoms trends of different cohorts. METHODS: Drawing on data from the 1994-2016 Health and Retirement Study (HRS), we used growth curve models to examine the age patterns of depressive symptoms, changes in sociodemographic gaps in depressive symptoms trajectories, and predictors of changes in depressive symptoms. RESULTS: In general, adults' depressive symptoms started high in middle-adulthood, declined in young-old life, increased moderately in mid-old life, and peaked in old-old life; In detail, more nuanced cohort-specific age trajectories of depressive symptoms were observed, challenging the prevailing assumption of a common age trajectory of depressive symptoms. Later-born cohorts displayed higher levels of depressive symptoms than earlier-born cohorts at observed ages. Second, we found intra-cohort sociodemographic differences in levels of depressive symptoms, but these differences' growth rates varied by specific factors. Regardless of the cohort group, as people age, the gender gap in depressive symptoms persisted but the partnership gap reduced. A widening educational gap across cohorts was observed, but it declined with age in some cohorts. CONCLUSION: Results suggest more evidence for the persistent inequality and age-as-leveler hypotheses rather than the cumulative (dis-)advantage hypothesis. Supplemental data for this article can be accessed online at https://doi.org/10.1080/13607863.2021.2010182 .
Keywords: Health Inequality; life course; Mental Health; psychological distress

Sociodemographic Factors and Neighborhood/Environmental Conditions Associated with Social Isolation Among Black Older Adults. - Taylor, Harry O; Tsuchiya, Kazumi; Nguyen, Ann W; Mueller, Collin (Journal of Aging and Health, 2023)
To investigate sociodemographic factors and neighborhood/environmental conditions associated with social isolation (SI) among Black older adults. We utilized data from the 2014 and 2016 Leave-Behind Questionnaire from the Health and Retirement Study (HRS LBQ) among those who self-identified as Black ( = 2.323). Outcome variables for our study included SI from adult children, other family members, friends, disengagement from social participation and religious services, being unmarried, and living alone. These indicators were also combined into an overall SI index. Critical predictors included gender, age, household income, education, employment status, neighborhood cohesion, neighborhood disorder, urbanicity, and region of residence. Sociodemographic factors of gender, education and household income were significantly associated with SI indicators. Additionally, some neighborhood/environmental conditions were associated with SI indicators. SI was found to be patterned by sociodemographic factors. These results can be used to develop effective interventions to mitigate SI among Black older adults.
Keywords: African Americans; environment; Leave Behind Questionnaire; Neighborhoods; Social Support

Socioeconomic and Ethnic Inequalities in the Progress of Multimorbidity and the Role of Health Behaviors. - Mira, Rolla; Newton, Tim; Sabbah, Wael (J Am Med Dir Assoc, 2023)
OBJECTIVES: To assess socioeconomic and ethnic inequalities in the progress of multimorbidity and whether behavioral factors explain these inequalities among older Americans. DESIGN: Health and Retirement Study, a longitudinal survey of older American adults. SETTING AND PARTICIPANTS: Data pooled from 2006 to 2018 (waves 8-14), which include 38,061 participants. METHODS: We used 7 waves of the survey from 2006 to 2018. Socioeconomic factors were indicated by education, total wealth, poverty-income ratio (income), and race/ethnicity. Multimorbidity was indicated by self-reported diagnoses of 5 chronic conditions: diabetes, heart conditions, lung diseases, cancer, and stroke. Behavioral factors were smoking, excessive alcohol consumption, physical activity, and body mass index (BMI). Multilevel mixed effects generalized linear models were constructed to assess socioeconomic and ethnic inequalities in the progress of multimorbidity and the role of behavior. All variables included in the analysis were time-varying except gender, race/ethnicity, and education. RESULTS: African American individuals had higher rates of multimorbidity than White individuals; however, after adjusting for income and education, the association was reversed. There were clear income, wealth, and education gradients in the progress of multimorbidity. After adjusting for behavioral factors, the relationships were attenuated. The rate ratio (RR) of multimorbidity attenuated by 9% among participants with the lowest level of education after accounting for behavior (RR 1.21; 95% CI 1.18-1.23 and 1.11; 95% CI 1.17-1.14) in the models unadjusted and adjusted for behaviors, respectively. Similarly, RR for multimorbidity among those in the lowest wealth quartile attenuated from 1.47 (95% CI 1.44-1.51) and 1.31 (95% CI 1.26-1.36) after accounting for behaviors. CONCLUSION AND IMPLICATIONS: Ethnic inequalities in the progress of multimorbidity were explained by wealth, income, and education. Behavioral factors partially attenuated socioeconomic inequalities in multimorbidity. The findings are useful in identifying the behaviors that should be included in health promotion programs aiming at tackling inequalities in multimorbidity.
Keywords: ethnic inequalities; Health Behavior; socioeconomic

Socioeconomic and race/ethnic differences in immunosenescence: Evidence from the Health and Retirement Study. - Noppert, Grace A; Stebbins, Rebecca C; Dowd, Jennifer Beam; Aiello, Allison E (Brain, Behavior, and Immunity, 2023)
BACKGROUND: The COVID-19 pandemic has highlighted the urgent need to understand variation in immunosenescence at the population-level. Thus far, population patterns of immunosenescence have not well described. METHODS: We characterized measures of immunosenescence from the 2016 Venous Blood Study from the nationally representative U.S Health and Retirement Study (HRS) of individuals ages 50 years and older. RESULTS: Median values of the CD8+:CD4+, EMRA:Naïve CD4+ and EMRA:Naïve CD8+ ratios were higher among older participants and were lower in those with additional educational attainment. Generally, minoritized race and ethnic groups had immune markers suggestive of a more aged immune profile: Hispanics had a CD8+:CD4+ median value of 0.37 (95 % CI: 0.35, 0.39) compared to 0.30 in non-Hispanic Whites (95 % CI: 0.29, 0.31). Non-Hispanic Blacks had the highest median value of the EMRA:Naïve CD4+ ratio (0.08; 95 % CI: 0.07, 0.09) compared to non-Hispanic Whites (0.03; 95 % CI: 0.028, 0.033). In regression analyses, race/ethnicity and education were associated with large differences in the immune ratio measures after adjustment for age and sex. CONCLUSIONS: Lower educational attainment and minoritized racial ethnic status were associated with higher levels of immunosenescence. This population variation may have important implications for both risk of age-related disease and vulnerability to emerging pathogens (e.g., SARS-CoV-2).
Keywords: Academic Success; COVID-19; Health Status; Pandemics; SARS-CoV-2

Socioeconomic disparities in health outcomes in the United States in the late 2010s: results from four national population-based studies. - Kim, Yeonwoo; Vazquez, Christian; Cubbin, Catherine (Arch Public Health, 2023)
BACKGROUND: Despite the importance of monitoring health disparities by multiple socioeconomic categories, there have been no recent updates on the prevalence of general health indicators by socioeconomic categories. The present study aims to update the prevalence estimates of health indicators by education and income categories across three age groups (children, young and middle-aged adults, and older adults) in the late 2010s by using four nationally representative data sources. We also examine socioeconomic differences in health by race/ethnicity subgroups. METHODS: Data were obtained from four nationally representative data sources from the U.S.: The National Health Interview Survey (2015-2018); the National Health and Nutrition Examination Survey, NHANES (2017-2020); the Behavioral Risk Factor Surveillance System (2016-2020); and the Health & Retirement Study (2016). Respondent-rated health and obesity were selected as the health indicators of interest. Socioeconomic factors included percentages of the federal poverty level and years of educational attainment. We conducted logistic regression analyses to calculate adjusted prevalence rates of respondent-rated (or measured, in the case of obesity in NHANES) poor health and obesity by income and education categories after controlling for sociodemographic characteristics. The complex sampling designs were accounted for in all analyses. RESULTS: Prevalence rates across racial/ethnic groups and age groups demonstrated clear and consistent socioeconomic gradients in respondent-rated poor health, with the highest rates among those in the lowest income and education categories, and decreased rates as income and education levels increased. On the other hand, there were less evident socioeconomic differences in obesity rates across all data sources, racial/ethnic groups, and age groups. CONCLUSIONS: Our results confirmed earlier, persistent evidence indicating socioeconomic disparities in respondent-rated poor health across all age and race/ethnicity groups by using four nationally representative datasets. In comparison to a decade earlier, socioeconomic disparities in poor health appeared to shrink while they emerged or increased for obesity. The results suggest an urgent need for action to alleviate pervasive health disparities by socioeconomic status. Further research is needed to investigate potentially modifiable factors underlying socioeconomic disparities in health, which may help design targeted health promotion programs.
Keywords: health outcomes; socioeconomic disparities

Source of perceived social support and cognitive change: an 8-year prospective cohort study. - Du, Chenguang; Dong, XinQi; Katz, Benjamin; Li, Mengting (Aging & Mental Health, 2023)
OBJECTIVES: This study explored the longitudinal association between overall and individual sources of social support and global cognitive function in older adults.Data were drawn from three waves (2006, 2010 and 2014) of the Health and Retirement Study (HRS). The analytic sample included participants aged 65 and above who were married and had at least one child ( = 1319). Global cognitive function was measured through a 35-point Telephone Interview Cognitive Screen (TICS). Perceived social support was measured via questions across four sources of support (spouse, child, other family members, and friends). Analyses were conducted using Hierarchical Linear Modeling (HLM) with the addition of a cross-lagged panel model (CLPM). RESULTS: There was no significant association between perceived overall social support and global cognitive function over time (). However, changes in perceived support from children were positively associated with changes in global cognition ( In contrast, changes in perceived support from other family members were negatively associated with changes in cognitive function (. CONCLUSIONS: Our findings highlight the importance of examining perceived social support from specific elements of one's social networks, rather than in an aggregated variable. Although the positive effect of perceived support from children may be small to moderate, the findings could provide a target for interventions to protect the cognitive function of older adults.
Keywords: cognitive function; hierarchical linear modeling; perceived social support

Spending behavior and stimulus transfer use in response to income shocks among older Americans: evidence from the COVID-19 pandemic - Muna Sharma; Patryk Babiarz (Applied Economics Letters, 2023)
This study examines household behavioural responses to the pandemic-induced income shocks regarding their overall spending and spending out of 2020 CARES stimulus payments. Using data from the 2020 Health and Retirement Study COVID-19 project and restricting our sample to older adults (51 years old and above), we show that the negative income shocks experienced during the COVID-19 pandemic put downward pressure on household spending. Results also reveal that, relative to those who did not experience an income shock, stimulus recipients who experienced income losses were more likely to use the stimulus transfer to increase spending, pay off debt, or for other purposes rather than to save.
Keywords: COVID-19; Income shocks; Saving; Spending; stimulus checks

Spending trajectories after age 65 variation by initial wealth - Michael D Hurd; Susann Rohwedder (The Journal of the Economics of Ageing, 2023)
There has been extensive research on the importance of saving for retirement and on tools to support the accumulation of retirement wealth. Much less attention has been paid to the decumulation phase, that is, the spending down of wealth following retirement. Understanding the decumulation phase requires information about the spending patterns of older households and how those patterns evolve with age. This study uses comprehensive longitudinal data on total household spending from a survey that is representative of the older U.S. population to estimate the trajectories of spending after age 65. Based on data spanning the period 2005–2019, real spending declined for both single and coupled households after age 65 at annual rates of about 1.7 percent and 2.4 percent, respectively. Stratification by wealth holdings observed at or closely following age 65 showed sizeable variation in spending levels by wealth quartile, but little variation in rates of change in spending. The fact that spending declines broadly, including among those in the highest wealth quartile, suggests that the decline may not be related to economic position. This view is supported by an analysis of budget shares which show increases with age in the budget share for gifts and donations which suggests that economic position on average does not deteriorate with age, even as spending declines.
Keywords: Budget shares; consumption; Financial security of older adults; life-cycle model; Retirement saving

Spousal Concordance of Hypertension Among Middle-Aged and Older Heterosexual Couples Around the World: Evidence From Studies of Aging in the United States, England, China, and India. - Varghese, Jithin Sam; Lu, Peiyi; Choi, Daesung; Lindsay C Kobayashi; Ali, Mohammed K; Patel, Shivani A; LI, CHIHUA (Journal of the American Heart Association, 2023)
BACKGROUND: Health concordance within couples presents a promising opportunity to design interventions for disease management, including hypertension. We compared the concordance of prevalent hypertension within middle-aged and older heterosexual couples in the United States, England, China, and India. METHODS AND RESULTS: Cross-sectional dyadic data on heterosexual couples were used from contemporaneous waves of the HRS (US Health and Retirement Study, 2016/17, n=3989 couples), ELSA (English Longitudinal Study on Aging, 2016/17, n=1086), CHARLS (China Health and Retirement Longitudinal Study, 2015/16, n=6514), and LASI (Longitudinal Aging Study in India, 2017/19, n=22 389). Concordant hypertension was defined as both husband and wife in a couple having hypertension. The prevalence of concordant hypertension within couples was 37.9% (95% CI, 35.8-40.0) in the United States, 47.1% (95% CI, 43.2-50.9) in England, 20.8% (95% CI, 19.6-21.9) in China, and 19.8% (95% CI, 19.0-20.5) in India. Compared with wives married to husbands without hypertension, wives married to husbands with hypertension were more likely to have hypertension in the United States (prevalence ratio, 1.09 [95% CI, 1.01- 1.17), England (prevalence ratio, 1.09, 95% CI, 0.98-1.21), China (prevalence ratio, 1.26 [95% CI, 1.17-1.35), and India (prevalence ratio, 1.19 [95% CI, 1.15-1.24]). Within each country, similar associations were observed for husbands. Across countries, associations in the United States and England were similar, whereas they were slightly larger in China and India. CONCLUSIONS: Concordance of hypertension within heterosexual couples was consistently observed across these 4 socially and economically diverse countries. Couple-centered interventions may be an efficient strategy to prevent and manage hypertension in these countries.
Keywords: CHARLS; cross‐national study; ELSA; Hypertension; LASI; spousal concordance

Spousal Loneliness, Depression, and Closeness Among Older Adults Married to Persons with Dementia: A Nationally Representative Study (SA314B) - Kristie Hsu; Irena Cenzer; Krista Harrison; Christine Ritchie; Linda Waite; Linda Waite (Journal of Pain and Symptom Management, 2023)
Outcomes 1. Analyze the role of marriage in serious illness and dementia 2. Discuss interactive biopsychosocial model underlying marriage and health among older adults with serious illness, and key social measures 3. Describe the prevalence of loneliness, depression, or both among spouses married to persons with dementia 4. Discuss how one's partner's cognitive decline is associated with higher levels of loneliness and depression Background Older adults married to persons with dementia (PWD) may be at risk for loneliness and depression. However, it is unclear how often each occur and the extent to which they are distinct. Research objectives To determine the prevalence of loneliness and depression among older adults married to PWD or mild cognitive impairment (MCI) and the role of marital closeness in mediating these outcomes Methods We used a nationally representative sample of 3,666 married couples enrolled in the Health and Retirement Study (2014 and 2016). We included older adults married to PWD (N=201), married to persons with MCI (N=778), or married to persons with normal cognition (N=2,687). We determined the prevalence of loneliness using multivariable logistic regression adjusting for socio-demographic characteristics, then tested for interaction between marital closeness and degree of spousal cognitive impairment. We assessed the prevalence of depression, and both loneliness and depression, using the same method. Results The sample was 54% women and on average 67 years old (Range: 50–97). After adjustment, older adults married to PWD were more likely to be lonely (Normal: 20%, MCI: 21%, PWD: 30%; p=0.02), depressed (Normal: 7%, MCI: 14%, PWD: 16%; p< 0.01), and both (Normal: 4%, MCI: 8%, PWD: 9%; p< 0.01). The association between spousal cognition and loneliness differed by marital closeness (interaction p-value=0.01); among “close” couples, spousal cognitive impairment was associated with higher likelihood of loneliness (p=0.01). In contrast, no association existed between spousal cognitive impairment and loneliness among “not close” couples (p=0.24). Conclusion Nearly 1 in 3 spouses of PWD experienced loneliness and 1 in 6 experienced depression. The association between spousal cognition and loneliness was stronger among those with close marital bonds. Implications Findings highlight substantial opportunity to identify and address loneliness and depression among spouses of PWD with close relational bonds to improve quality of life.
Keywords: closeness; depression; Loneliness; Older Adults

Spousal synchrony in allostatic load among older couples in the Health and Retirement Study. - Yu, Yan-Liang; Juster, Robert-Paul (Psychosom Med, 2023)
OBJECTIVES: Using national data from the Health and Retirement Study, this study examined interpartner associations of allostatic load (AL) among 2,338 different-sex couples (N = 4,676 individuals) over a four-year period among older American couples from a dyadic approach. METHODS: AL was indexed by immune (c-reactive protein), metabolic (high-density lipoprotein cholesterol, total cholesterol and glycosylated hemoglobin), renal (cystatin C), cardiovascular (systolic and diastolic blood pressures, pulse rate) and anthropometric (waist and body mass index) parameters using the traditional count-based formulation. Actor-partner interdependence models were used to assess interpartner concordance in AL. RESULTS: Higher partners' baseline AL was significantly associated with higher own AL both at baseline and four years later. Additionally, partners' baseline AL was significantly associated with own AL four years later only in women but not men. Lastly, we did not observe any significant moderating effect of relationship quality on interpartner AL concordance. CONCLUSIONS: The findings suggest that older couples' physiological responses to environmental stress are not only linked concurrently, but the associations persist after four years, alluding to long-term impacts of couples' psychosocial context and physiology on each other.

Statistically Speaking, This Is the Worst Age to Claim Social Security Benefits - Williams, Sean (The Motley Fool, 2023)
Keywords: claiming age; Social Security Benefits

Stepfamily variation in parent-child relationship quality in later life - Lin, I-Fen; Seltzer, Judith A. (JOURNAL OF MARRIAGE AND FAMILY, 2023)
Objective: We use a family systems approach to examine how stepfamily structure is associated with both positive and negative parent-child relationships while considering mothers' and fathers' discrepant reports.Background: Two in five older couples with children are in stepfamilies. Past research on later-life stepfamily dynamics has focused mainly on positive aspects of relationships and compared reports of mothers and fathers from different families.Method: Using the U.S. Health and Retirement Study, we estimated multilevel models with data from married couples in which both spouses reported living children and answered all questions about positive and negative parent-child relationships (N = 2150).Results: Couples in stepfamilies reported less positive and more negative relationships with their children than did couples in non-stepfamilies. Mothers reported more positive relationships than fathers, but there was no gender difference in reports of negative relationships. The patterns of perceived parent-child relationships and divergent reports between mothers and fathers also varied by stepfamily structure. Structural complexity was not consistently related to positive or negative relationships.Conclusion: This study underscores the importance of considering mothers' and fathers' different points of view in the same family and examining both positive and negative parent-child interactions as negative relationships are not merely the reverse of positive relationships.
Keywords: Aging; family structure; gender; parent-child relationships; Remarriage; stepfamilies

Stress and Diabetes - McCarty, Richard (Stress, Health, and Behavior, 2023)
EBOOK ISBN - 9781462551712
Keywords: Diabetes; Stress

Stressor appraisals among adults in late middle age and late adulthood in the United States: Applying the intersectionality framework. - Wang, Kun; Marbut, Alexander R; Zheng, Dianhan; Peet, J. Zak (International Journal of Stress Management, 2023)
Although the intersectionality framework suggests that social identities may combine to create unique experiences of hardship, few studies have applied it to older adults’ stress appraisals. Thus, in this study, guided by the intersectionality framework, we examined whether older participants with multiple marginalized identities had more negative global stressor appraisals and whether they had specific patterns concerning individual stressor appraisals than those with singular or no marginalized identities. A sample of 6,015 participants aged 50 and older was drawn from the 2016 Health and Retirement Study. Six social identities relevant to age, gender, race/ethnicity, immigration, (dis)ability, and poverty were included. Latent class analysis was conducted to identify marginalized identity patterns. The three-step approach was applied to compare global stressor appraisals and individual stressor appraisals between the intersectional class and other classes. Three marginalized identity classes were identified: the intersectional class consisting of females and individuals living in poverty, the Black, Indigenous, and Other People of Color class, and the older adult class. Compared to the other two classes, the intersectional class reported more negative global stressor appraisals and was more likely to feel upset or very upset about self-health, family health, family substance use, work, financial, housing, and relationship stressors. Caregiving stressor appraisal was not statistically significantly different between the intersectional class and the other two classes. Overall, the findings in this study supported the intersectionality framework as it applies to stress appraisal among older adults. An intersectionality perspective may be needed in future stress research and interventions among older adults.
Keywords: Disability; gender; Immigration; intersectionality framework; Race/ethnicity; stressor appraisals

Stroke, High BP Don't Mediate Pollution's Link to Dementia - Anderson, Pauline (Medscape, 2023)
Keywords: Dementia; Hypertension; Particulate Matter; Stroke

Structural equation model of coping and life satisfaction of community-dwelling older people during the COVID-19 pandemic. - Lalani, Nasreen; Dongjuan, Xu; Cai, Yun; Arling, Greg W (J Patient Rep Outcomes, 2023)
BACKGROUND: COVID-19 put older individuals at high risk for morbidity and mortality, isolation, reduced coping, and lower satisfaction with life. Many older adults experienced social isolation, fear, and anxiety. We hypothesized that successful coping with these stressors would maintain or improve satisfaction with life, a crucial psychological outcome during the pandemic. Our study investigated relationships between older people's coping and life satisfaction during the pandemic and their optimism, sense of mastery, closeness with spouse, family, and friends, and vulnerabilities from frailty, comorbid diseases, memory problems, and dependencies in instrumental activities of daily living (IADL). METHODS: The study was based on a special COVID-19 sample of 1351 community-dwelling older adults who participated in the 2020 Health and Retirement Survey. A comprehensive structural equation modeling was used to test direct and indirect effects, with life satisfaction as the main outcome and coping as a mediator between the other variables and coping. RESULTS: Most survey respondents were female and between the ages of 65-74 years. They averaged 1.7 chronic conditions, one in seven was frail, about one-third rated their memory as fair or poor, and about one in seven reported one or more difficulties in IADL. As hypothesized-older people with increased sense of mastery and optimism were better able to cope and had greater life satisfaction. In addition, close relationships with friends and with other family members besides the spouse/partner or children contributed to more successful coping, while the interpersonal closeness of all types contributed directly to greater life satisfaction. Finally, older people with more IADL limitations reported greater difficulty coping and lower life satisfaction, and those older people who were frail or had multiple comorbid diseases reported lower life satisfaction. CONCLUSIONS: Optimism, sense of mastery and closeness with family/friends promotes coping and life satisfaction, whereas frailty and comorbidities make coping more challenging and lead to lower life satisfaction particularly during a pandemic. Our study improves on prior research because of its nationally representative sample and formal specification and testing of a comprehensive theoretical framework.
Keywords: Activities of Daily Living; Adaptation, Psychological; Aged; Child; COVID-19; Female; Frailty; Humans; Independent Living; Male; Pandemics; Personal Satisfaction

Structural Inequity and Socioeconomic Status Link to Osteoporosis Diagnosis in a Population-Based Cohort of Middle-Older-Age Americans. - Gough Courtney, Margaret; Roberts, Josephine; Godde, Kanya (Inquiry, 2023)
Socioeconomic status (SES) is an important social determinant of health inequities that has been linked to chronic conditions, including osteoporosis, but research tends to focus on socioeconomic disadvantage rather than how socioeconomic advantage may facilitate these inequities. This study accounts for structural inequities and assesses the relationship between early-life and later-life SES, and risk of osteoporosis diagnosis. Data come from the nationally representative, population-based cohort Health and Retirement Study and include individuals ages 50 to 90. The outcome variable is osteoporosis diagnosis. Logistic regression models of the relationship between SES and osteoporosis diagnosis are estimated, accounting for demographic, health, and childhood variables. Higher levels of childhood and adult SES link to lower odds of osteoporosis diagnosis. Structural inequities in income and underdiagnosis of osteoporosis among persons identifying as Black/African American were detected. Accounting for bone density scan access, inequities in osteoporosis diagnosis appear to stem from barriers to accessing health care due to financial constraints. The important role of SES and evidence of structural inequities leading to underdiagnosis suggest the critical importance of clinicians receiving Diversity, Equity, and Inclusion training to reduce health inequities.
Keywords: Adult; Aged; Aged, 80 and over; Black or African American; Humans; Income; Logistic Models; Middle Aged; Osteoporosis; Social Class; Socioeconomic factors

Study: Food Insecurity Associated With Increased Risk of Dementia - Gallagher, Ashley (Pharmacy Times, 2023)
Keywords: Dementia; Food insecurity

Study: Mid-life loneliness serves as risk factor for death later - Fischer, Kristen (McKnights, 2023)
Keywords: COVID-19; Life Expectancy; Loneliness

Study Results Indicate Purpose in Life Declines with Emergence of Cognitive Impairment - McGovern, Gillian (Pharmacy Times, 2023)
Keywords: cognitive impairment; Purpose in life

Study shows dementia more common in older adults with vision issues - Gavin, Kara (Michigan Medicine, University of Michigan, 2023)
Keywords: Dementia; Vision Disorders

Study Shows Retirees Underestimate Social Security by Nearly $2,000 — How To Resolve This Issue - Cariaga, Vance (Yahoo!, 2023)
Keywords: Retirement; Social Security

Studying Alzheimer’s in Southern Chile - Dee, Jane E. (School of Public Health, Yale University, 2023)
Keywords: Alzheimer; ELSA

Subjective Memory Complaints Predict Decline in Memory, Instrumental Activities of Daily Living, and Social Participation in Older Adults: A Fixed-Effects Model. - Lee, Chang Dae; Foster, Erin R (Am J Occup Ther, 2023)
IMPORTANCE: Although subjective memory complaints (SMCs) have been suggested to be associated with future memory impairment, limitations in instrumental activities of daily living (IADLs), and social participation restriction, these associations are still inconclusive. OBJECTIVE: To determine whether changes in SMCs over time predict decline in memory, IADLs, and social participation in older adults. DESIGN: Longitudinal study. SETTING: Community. PARTICIPANTS: Sample 1 included 2,493 community-dwelling older adults drawn from the Health and Retirement Study (HRS) data collected between 2004 and 2018. Sample 2 included 1,644 community-dwelling older adults drawn from the HRS data collected between 2008 and 2018. OUTCOMES AND MEASURES: Self-reported SMCs, memory function, self-reported IADL performance, and self-reported social participation. RESULTS: The mean age of Sample 1 at baseline was 70.16 yr; 1,468 (58.88%) were female. In Sample 1, immediate and delayed memory (all ps < .001) and IADL performance (p < .01) declined over time. Increases in SMCs over time significantly predicted future immediate and delayed memory declines (p < .01 and p < .001, respectively) and future IADL performance decline (p < .001), after controlling for depressive symptoms. The mean age of Sample 2 at baseline was 71.52 yr; 928 (56.45%) were female. In Sample 2, social participation declined over time (all ps < .001). Increases in SMCs over time significantly predicted future social participation decline (p < .05), after controlling for depressive symptoms. CONCLUSIONS AND RELEVANCE: Increases in SMCs predict future decline in memory, IADL performance, and social participation after accounting for depressive symptoms. What This Article Adds: SMCs can be used as an early indicator of future memory impairment, IADL limitations, and social participation restrictions in older adults. Furthermore, interventions that minimize SMCs may help older adults achieve successful aging.
Keywords: Activities of Daily Living; Aged; Aging; Female; Humans; Independent Living; Longitudinal Studies; Male; Memory Disorders; Social participation

Subjective Memory Decline Predicts Incident Cognitive Impairment among White-but Not Black or Hispanic-Older Adults. - Ferraro, Kenneth F; Sauerteig-Rolston, Madison R; Barnes, Lisa L; Friedman, Elliot; Sands, Laura P; Thomas, Patricia A (The Gerontologist, 2023)
BACKGROUND AND OBJECTIVES: This study investigates whether subjective memory decline in a racially diverse sample of older adults without cognitive impairment at baseline is associated with incident cognitive impairment during a 12-year follow-up period. RESEARCH DESIGN AND METHODS: With panel data from a national sample (N=9,244) of cognitively-intact Black, White, and Hispanic Americans 65 years or older in 2004, we examine if subjective memory decline is associated with the loss of normal cognition by 2016. Cognitive status was assessed every two years with a modified version of the Telephone Interview for Cognitive Status to identify the transition from normal cognition to cognitive impairment. RESULTS: Estimates from Weibull accelerated failure-time models reveal that subjective memory decline is associated with earlier incident cognitive impairment (time ratio = 0.96, p<.05). In subsequent models stratified by race-ethnicity, this association was evident among White respondents (time ratio = 0.95, p<.01) but not among Black, US-born Hispanic, or foreign-born Hispanic respondents. DISCUSSION AND IMPLICATIONS: Given that the prognostic validity of subjective memory decline differs by race and ethnicity, caution is warranted when using it as a screening or clinical tool in diverse populations.
Keywords: cognitive function; Disparities; Racial-ethnic differences; Self-reported memory

SUCCESSFUL AGING AMONG MIDLIFE BLACK WOMEN: A LATENT CLASS ANALYSIS - JOSHUA CHRISTIAN JULIAN LEWIS (Sociology, 2023)
Successful aging (SA), as outlined by Rowe and Khan, with its objective focus on disease and disability avoidance, maintaining high physical and cognitive function, and sustaining engagement in social and productive activities, was meant to be a benchmark for assessing health and aging. However, given its rigid criteria virtually no one “ages successfully” despite being in otherwise relatively good health. The assumption of unsuccessful aging in populations who experience a higher prevalence of chronic disease, illness, disability, and other health disparities, is implicit in the SA framework outlined by Rowe and Khan and would preclude many Black women from being considered to age well. Building on recent theoretical advancements and critiques of the successful aging framework I investigate how Black women successfully age intersectionally and examine how interpersonal experiences of discrimination affect these successful aging patterns. Using an uncorrected three-step process, I first conduct a latent class analysis (LCA) on data from the Health and Retirement Study to identify successful aging classes among Non-Hispanic Black women between the ages of 50 and 72 (N = 1098) along sociocultural, physical, and psychological indicators. Secondly, I assign class membership to the women of my sample. Thirdly and lastly, I estimate how perceived everyday discrimination and discrimination attributions affect membership into SA classes across social status using multinomial logistic regressions. I identified 5 unique successful aging classes among Black women indicated by differences in self-rated health, chronic conditions, resilience, life satisfaction, psychological well-being, religiosity/spirituality, social engagement, and social support. Everyday interpersonal experiences of discrimination were associated with increased odds of poorer SA among Black women and increased probabilities into poorer SA classes. My findings improve our understanding of successful aging among Black women by incorporating intersectionality and life course considerations into the successful aging framework modeled by Rowe and Khan.
Keywords: African American Women; Discrimniation; health; Successful aging; Well-being

Support from others in stressful times can ease impact of genetic depression risk - Gavin, Kara (Michigan Medicine, University of Michigan, 2023)
Study in first-year doctors and recently widowed older adults shows greatest impact of social support in those with highest polygenic risk scores for depression
Keywords: depression; Polygenic risk score; Social Support; Widowhood

Supportive later-life social relationships mediate the risk of severe frailty in adults who had negative childhood experiences - Regenstrief Institute (Regenstrief Institute, Indiana University, 2023)
Keywords: childhood experiences; Frailty; Social Relationships

Sustaining Retirement during Lockdown: Annuitized Income and Older American’s Financial Well-Being before and during the COVID-19 Pandemic - Sun, Qi; Curnutt, Gary (Journal of Risk and Financial Management, 2023)
The landscape of employer-sponsored retirement plans in the U.S. has changed dramatically during the past few decades as more and more private-sector employers have decided to freeze or terminate traditional pension plans. Defined contribution (DC) plans became the primary choice or the only choice for employees to participate in employer-sponsored retirement plans. In the next ten to twenty years, the income from pension plans will only count for a third of the total retirement income for GenXers when compared to their baby boomer counterparts. It is important for research to provide evidence on how the change in retirement income resources impacts retirees’ retirement security and financial wellness. Using Health and Retirement Study (HRS) data before and during the COVID-19 pandemic, this study examines the association between annuitized income and various measures of older Americans’ financial well-being over time, particularly during the pandemic. This study finds that receiving annuitized income has a statistically significant relationship with reduced subjective financial well-being for both measurements, while only one of the measures of objective well-being, having liquid assets greater than the median household income, has a statistically significant positive relationship with receiving annuitized income. © 2023 by the authors.
Keywords: annuitized income; defined contribution plans; Financial well-being; longevity risk

Systemic inflammation and biological aging in the Health and Retirement Study. - Meier, Helen C S; Mitchell, Colter; Karadimas, Thomas; Jessica Faul (Geroscience, 2023)
Chronic, low-level systemic inflammation associated with aging, or inflammaging, is a risk factor for several chronic diseases and mortality. Using data from the Health and Retirement Study, we generated a continuous latent variable for systemic inflammation from seven measured indicators of inflammation and examined associations with another biomarker of biological aging, DNA methylation age acceleration measured by epigenetic clocks, and 4-year mortality (N = 3,113). We found that greater systemic inflammation was positively associated with DNA methylation age acceleration for 10 of the 13 epigenetic clocks, after adjustment for sociodemographics and chronic disease risk factors. The latent variable for systemic inflammation was associated with 4-year mortality independent of DNA methylation age acceleration and was a better predictor of 4-year mortality than any of the epigenetic clocks examined, as well as mortality risk factors, including obesity and multimorbidity. Inflammaging and DNA methylation age acceleration may represent different biological processes contributing to mortality risk. Leveraging multiple measured inflammation markers to capture inflammaging is important for biology of aging research.
Keywords: Aging; Biomarkers; DNA Methylation; Epigenesis, Genetic; Humans; Inflammation; Retirement

Systemic inflammation is associated with dementia status in the health and retirement study - Higgins, Cesar; Ware, Erin B; Hicken, Margaret; Zawistowski, Matthew; Bakulski, Kelly M (2023)
BackgroundThe prevalence of dementia is expected to increase in the coming decades. The highest burden of this chronic condition will likely be borne by racial/ethnic minorities. Systemic inflammation is associated with dementia. This effect may be modified by race/ethnicity, since racial minorities are more likely to have elevated levels of systemic inflammation due to the accumulation of compounded negative experiences (e.g., discrimination, racism, and marginalization). Our goal was to test baseline systemic inflammation in relation to cognitive function in a racially/ethnically representative cohort of US adults.MethodsIn a cross‐sectional analysis of the Health and Retirement Study (2006 and 2008 waves, n=9,983), highly sensitive C‐reactive protein (hsCRP) was measured in dried blood spots. Cognitive status (dementia, cognitive impairment non‐dementia (CIND), and normal cognition) was measured and categorized using the Langa‐Weir classification of a modified telephone interview for cognition scale. We estimated the adjusted associations between hsCRP and cognitive status, using multivariable logistic regression. We stratified models by race/ethnicity to explore race‐dependent associations.ResultsOur study prevalence of dementia and CIND is 3.5% and 15.8%, respectively. Similarly, 26.7% of dementia and 30.1% of CIND cases occurred among participants with circulating hsCRP levels above the 75th quartile. We observed a racial and gender gradient in the levels of hsCRP in our cohort. For example, Black females had the highest average concentration of hsCRP (7.53 mg/L, SD =15.1) and Whites males the lowest (3.95 mg/L, SD = 7.42). Among participants with hsCRP >75th we observed higher odds of CIND (OR = 1.45; 95%CI: 1.22, 1.72) with respect to those in the . Similarly, elevated hsCRP >75th was associated with dementia (OR= 1.21; 95%CI: 0.86, 1.69), in comparison to the reference lower quartile. We did not observe a race‐dependent relationship between hsCRP and cognitive status.ConclusionsSystemic inflammation, as represented by high levels of hsCRP, was associated with concurrent cognitive status. Despite racial minorities exhibiting higher levels of hsCRP; in our study, the association between inflammation on cognition did not differ by race. Further studies should explore whether the established relationship is causal, seek larger sample sizes in diverse populations, and examine longitudinal relationships Peer Reviewed

Systemic Racism as a Stressor - McCarty, Richard (Stress, Health, and Behavior, 2023)
EBOOK ISBN - 9781462551712
Keywords: Racism; Stress

Sample Selection Bias Due to Differential Mortality: A Supplementary Measure of Old-Age Poverty. - Leslie A. Muller; John A. Turner (Journal of Aging & Social Policy, 2022)
Traditional "head count" measures of poverty at advanced older ages understate the risk of falling into poverty because of survivorship bias due to the income-mortality gradient, which indicates that people in poverty have higher mortality rates than people with higher income. Survivorship bias is a form of sample selection bias. This paper presents a supplementary measure for poverty at older ages, based on an adaption of a model for correcting survivorship bias in rate of return data for mutual funds. Using U.S. longitudinal data from the Health and Retirement Study (HRS) for 1996 and 2002-2012 for the same cohort, we develop a new estimate of poverty at older ages that suggests that traditional cross-sectional measures understate the risk of falling into poverty by roughly a quarter. This finding has important implications for social programs that relate to the causes and consequences of the selectivity bias.
Keywords: Poverty; survivorship bias

A Satellite Account for Health in the United States. - Cutler, David M; Ghosh, Kaushik; Messer, Kassandra L; Raghunathan, Trivellore; Rosen, Allison B; Stewart, Susan T (American Economic Review, 2022)
This paper develops a satellite account for the US health sector and measures productivity growth in health care for the elderly population between 1999 and 2012. We measure the change in medical spending and health outcomes for a comprehensive set of 80 conditions. Medical care has positive productivity growth over the time period, with aggregate productivity growth of 1.5% per year. However, there is significant heterogeneity in productivity growth. Care for cardiovascular disease has had very high productivity growth. In contrast, care for people with musculoskeletal conditions has been costly but has not led to improved outcomes.
Keywords: Health Care; health outcome; health spending

Save, Spend, or Give? A Model of Housing, Family Insurance, and Savings in Old Age - Barczyk, Daniel; Fahle, Sean; Kredler, Matthias (REVIEW OF ECONOMIC STUDIES, 2022)
How do housing and family shape the savings, spending, and inter-generational transfer behaviour of the elderly? Using the Health and Retirement Study, we document that inter-generational transfers to children are substantially backloaded, that homeowners dis-save much more slowly than renters but often sell their houses when entering a nursing home, and that care by children slows down nursing home entry and is linked to larger bequests, particularly of housing. To rationalise these facts, we develop a dynamic, non-cooperative model of the family with an indivisible housing asset and joint bargaining between elderly parents and their children over the housing and care arrangements of the parents. The model generates realistic savings and care choices and matches the timing of transfers and home liquidations. A key novelty is the housing-as-commitment channel: In the absence of long-run family contracts, housing provides a commitment device for more efficient savings. We find that this channel increases homeownership in old age by one-third and families' willingness to pay for houses by 5-10%. This mechanism also facilitates informal care, slows down spending, and leads to larger bequests, implications that we support empirically.
Keywords: consumption; Dynamic game; Family insurance; Inter-Generational Transfers; Saving; wealth of the elderly

Scientists identify genetic variants linked to mobility changes in aging - ScienceDaily (ScienceDaily, 2022)
Keywords: C. elegans; evolutionary biology; Genetics; Genomics

Screening recall in older cancer survivors detects differences in balance and mobility. - Blackwood, Jennifer; Sweeney, Robert; Rybicki, Kateri (Supportive Care In Cancer, 2022)
PURPOSE: Cognitive impairments have been reported by up to two-thirds of cancer survivors whose primary cancer did not occur in the central nervous system. Physical impairments as sequelae of cancer-related cognitive impairment (CRCI) have not been well described in previous studies. Furthermore, there is scarcity of literature describing differences among physical performance in those with and without CRCI. The purpose of this study is to examine the differences in physical function of older cancer survivors based on cognitive ability to determine if physical performance differs when different cognitive screening measures are employed. METHODS: Adults age 65 + with a history of cancer from the 2010 Health and Retirement Study (n = 1,953) were assigned to groups according to their cognitive ability. Between-group demographic, mobility, and cognitive differences were analyzed using chi-squared and t tests. Recall and orientation were used as cognitive variables, and physical performance outcomes included gait speed, balance, and grip strength. RESULTS: Respondents with Low Recall had more impaired balance (semi-tandem, tandem) (p < .05) and slower gait speeds (p < .05). Respondents that were Not-Oriented had slower gait speed (p < .05). Between-group differences in demographics were found by recall and orientation groups. CONCLUSIONS: Impairments in balance and gait speed are able to be detected when recall is screened in a population of older cancer survivors. When assessing how physical mobility is related to fall risk, a screen of cognition should go beyond just orientation.
Keywords: Cognition; Memory; Neoplasms; Orientation; Postural Balance; Short-term; walking speed

Is Secularization an Age-Related Process? - Idler, Ellen (The International Journal of Aging and Human Development, 2022)
Secularization has been studied for decades by sociologists of religion. Long-running surveys in the United States and Europe show steady generational decline in religious affiliation and participation, and yet this trend has largely been ignored by gerontologists and life course researchers. We examined data from the Health and Retirement Study, hypothesizing between-cohort declines in religious participation. Based on data from a sample stratified by 10-year birth cohorts, we identified variation in patterns of religious involvement from 2004 to 2016. Measures of attending religious services, feeling religion is very important, and having good friends in the congregation show age-graded patterns; older cohorts have a higher level of religiosity than those following them, with only minor exceptions. For all three measures, differences by cohort within waves of data are statistically significant. We confirm, with longitudinal data, the findings of repeated cross-sectional surveys in the United States showing a generational pattern of decline in religiousness. The consequences of this loss of a common social tie for future older cohorts are unknown, since current older cohorts still maintain a high level of religious participation. However, future generations of older adults are likely to be less familiar with social support from religious institutions, and those institutions may be less available to provide such support as the apparently inexorable processes of secularization continue.
Keywords: Religion; secularization; Social Support

Selection Factors Influencing Participation in National Alzheimer’s Coordinating Center (NACC) Studies Compared to the Nationally Representative Health and Retirement Study (HRS) - Nicole D. Evangelista; Miguel Arce Renteria; Taylor M Mobley; Joshua T. Fox-Fuller; Lex Minto; Justina F Avila; Kacie D Deters; Luis D Medina; Bri M Bettcher (Alzheimer's & Dementia, 2022)
Background Racial/ethnic disparities in ADRD are well documented such that prevalence of ADRD and known risk factors (e.g., cardiovascular disease, educational attainment) disproportionately impact Black and Latinx populations compared to their White counterparts. To generalize findings on the mechanisms and disease course and mitigate racial/ethnic disparities in ADRD, it is critical that diverse populations are well represented in studies of ADRD. We examined selection factors across racial/ethnic groups included in National Alzheimer’s Coordinating Center data (NACC) compared to the general U.S. population using data from the Health and Retirement Study (HRS). Method Analyses included baseline NACC data from 33,998 participants (Mage = 74.1yrs±8.0; Medu = 15.5±6.9; 56.7% women) and the 2010 wave of HRS weighted up to the 2010 US population aged 60+ years (weighted n = 48,726,070; Mage = 71.3yrs; Medu = 12.9yrs; 54.3% women). We assessed covariate balance between NACC and the 2010 US population aged 60+ by calculating standardized mean differences across harmonized sociodemographic factors, self-reported health characteristics, depressive symptoms, and subjective memory concerns stratified by race/ethnicity. Standardized mean differences greater than +/- 0.25 were considered strong selection factors into NACC. Result Across all racial/ethnic groups, NACC participants were more likely to be older, have higher educational attainment, and report subjective memory concerns and hearing difficulties compared to the 2010 US population aged 60+ years (Figure). Standardized mean differences for age, educational attainment, and memory concerns were larger among non-Latinx Whites compared to differences among non-Latinx Black and Latinx participants. There was greater representation of non-Latinx Black women in NACC, and non-Latinx Black and Latinx NACC participants were less likely to endorse depressive symptoms. Additionally, results suggested non-Latinx White participants were less likely to report diabetes and hypertension compared to their 2010 aged 60+ US population counterparts. Conclusion Results suggest that NACC participants are not representative of the U.S. population in key demographic and health factors and self-reported memory concerns. These selection factors differed across racial/ethnic groups and are suggestive of selection bias. Future studies should leverage statistical tools that aimed at generalizing findings to general populations. Studies should also consider mitigating these sources of bias through inclusive recruitment efforts across Alzheimer’s Disease Centers to improve generalizability.
Keywords: Alzheimer's; Dementia; racial/ethnic disparities

Selective mortality and nonresponse in the Health and Retirement Study: Implications for health services and policy research - Yue, Dahai; Susan L Ettner; Jack Needleman; Ninez Ponce (Health Services and Outcomes Research Methodology, 2022)
Selective mortality and nonresponse in longitudinal analyses would lead to biased estimates. In this study, we draw data from the 1992–2016 Health and Retirement Study and used a multinomial logit model to examine the impacts of participants' demographics, health conditions, and socioeconomic status on both follow-up status in 2016 (Always-in; Died; Other Attritors, non-death sample attrition; Ever-out, skipped some intermediate surveys) and between-wave dropout. We then applied an inverse probability weighting approach to compensate for attrition in the analysis of education and hospitalizations. We found that many demographics (e.g., sex, age, race, ethnicity, marital status), socioeconomic factors (e.g., education, house ownership, labor force participation) and health conditions (e.g., self-reported health, and chronic conditions) had large and statistically significant associations with loss of follow-up. Our results show that loss of follow-up leads to substantial underestimation of the education-hospitalization association. After correcting attrition bias in a pooled cross-sectional analysis, the association of having a high school degree, some college, and college or above with any two-year hospitalizations increased by 59.7%, 72.9%, and 42.6%, respectively. Differences in estimates before and after correcting attrition bias were only statistically significant for college graduates, but who make up 24.7% of the “always-in” sample. In the longitudinal analysis of the association between education and hospitalization, correcting attrition bias also increases estimates of education by up to 58.9%, although not statistically significant. It suggests that empirical analyses that inform health policy decisions using the Health and Retirement Study should assess attrition bias from selective mortality and nonresponse.
Keywords: Attrition bias; Education Hospitalization; Selective mortality; Survey nonresponse

Self-Employment Linked To Better Heart Health In Women: Study - Chan, Athena (International Business Times, 2022)
Keywords: BMI; Exercise; heart health; self-employed; women

Self-perceptions of aging and depressive symptoms: the mediating role of loneliness. - Dikla Segel-Karpas; Cohn-Schwartz, Ella; Liat Ayalon (Aging & Mental Health, 2022)
Depression is a major health concern for both individuals and societies. Hence, understanding the risk factors for depression is of importance. As individuals grow older, the way in which they perceive the aging process may have a significant influence on their physical and mental health. More negative perceptions of aging could put individuals at risk for social withdrawal, causing loneliness and resulting in higher levels of depressive symptoms. We use the Health and Retirement Survey, a large and longitudinal dataset spanning over a period of 8 years, to examine a model in which loneliness mediates the relationship between self-perceptions of aging and depressive symptoms. Our findings suggest that loneliness indeed mediates the relationship between self-perceptions of aging and depressive symptoms. The results highlight to the importance of the way people view the aging process in shaping their social and mental well-being. Practitioners may want to address self-perceptions of aging when helping older adults cope with loneliness and depressive symptoms.
Keywords: Depressive symptoms; Loneliness; self-perceptions of aging

Self-reported hearing loss, hearing aid use, and cognitive function among U.S. older adults - West, Jessica; Smith, Sherri; Dupre, Matthew (International Journal of Population Studies, 2022)
There has been increasing attention to the role of hearing loss as a potentially modifiable risk factor for Alzheimer’s disease and related dementias. However, more nationally-representative studies are needed to understand the co-occurring changes in hearing loss and cognitive function in older adults over time, and how hearing aid use might influence this association. The purpose of this report is to examine how age-related changes in hearing loss and hearing aid use are associated with trajectories of cognitive function in a nationallyrepresentative sample of U.S. older adults. We used 11 waves of longitudinal data from the Health and Retirement Study (HRS) from 1998 to 2018 to examine changes in self-reported hearing loss, hearing aid use, and cognitive function in adults 65 and older by race and ethnicity. Results from mixed models showed that greater levels of hearing loss were associated with lower levels of cognitive function at age 65 in non-Hispanic White, non-Hispanic Black, and Hispanic older adults. We also found that the associations diminished across age in White and Black individuals; but remained persistent in Hispanic individuals. The use of hearing aids was not associated with cognitive function in Black older adults but appeared protective for White and Hispanic older adults. Overall, the findings from this report suggest that the timely identification of hearing loss and subsequent acquisition of hearing aids may be important considerations for reducing declines in cognitive function that manifests differently in U.S. population subgroups.
Keywords: Cognitive decline; Dementia; Hearing loss; racial/ethnic disparities

Self-reported measures of limitation in physical function in late midlife are associated with incident Alzheimer's disease and related dementias. - Bardenheier, Barbara H; Resnik, Linda; Jutkowitz, Eric; Gravenstein, Stefan (Aging Clinical and Experimental Research, 2022)
BACKGROUND: Even small improvements in modifiable Alzheimer's disease and related dementias (ADRD) risk factors could lead to a substantial reduction of dementia cases. AIMS: To determine if self-reported functional limitation associates with ADRD symptoms 4-18 years later. METHODS: We conducted a prospective longitudinal study using the Health and Retirement Study of adults aged 51-59 years in 1998 without symptoms of ADRD by 2002 and followed them to 2016. Main exposure variables were difficulty with activities of daily living, mobility, large muscle strength, gross motor and upper limb activities. The outcome was incident ADRD identified by the Lange-Weir algorithm, death, or alive without ADRD. We fit two GEE multinomial models for each measure: (1) baseline measure of function and (2) change in function over time. RESULTS: In the model with baseline only and outcome, only difficulty with mobility associated with future ADRD across levels of difficulty with near dose-response effect (risk ratios (RR) difficulty with 1-5 functions respectively, compared with no difficulty: 1.82; 2.70; 1.73 2.81; 4.03). Mobility also significantly associated with ADRD when allowing for change over time among those with 3, 4 or 5 versus no mobility limitations (RR 1.76; 2.36; 2.37). DISCUSSION: The results infer that an adult in midlife reporting difficulty with mobility as well as those with no mobility limitations in midlife but who later report severe limitations may be at increased risk of incident ADRD. CONCLUSIONS: Self-reported measures of mobility limitation may be early indicators of ADRD and may be useful for public health planning.
Keywords: ADRD; Late midlife; Physical function limitation

Self-reported sense of purpose in life and proxy-reported behavioral and psychological symptoms of dementia in the last year of life. - Angelina R Sutin; Martina Luchetti; Yannick Stephan; Antonio Terracciano (Aging and Mental Health, 2022)
Behavioral and psychological symptoms of dementia (BPSD) are among the most challenging aspects of dementia for individuals living with dementia and their caregivers. Identifying factors associated with resilience to BPSD may inform interventions to reduce them. The present research examines whether purpose in life is associated with BPSD in the last year of life.Participants from the Health and Retirement Study were selected if they reported on their sense of purpose, had evidence of a memory impairment, died across the follow-up, and a proxy completed the End of Life survey that included BPSD ( = 2473). Self-reported sense of purpose was tested as a predictor of the sum of symptoms and each indivdual symptom in the last year of life.Purpose in life was associated with fewer BPSD overall. Of the individual symptoms, purpose was associated with less risk of psychological symptoms, specfiically less depression, periodic confusion, uncontrolled temper, but not with motor or perceptual symptoms. These results are consistent with growing evidence that purpose is associated with better cognitive outcomes. Purpose may be a useful target of intervention to improve outcomes across the spectrum of dementia.
Keywords: Behavioral Symptoms; BPSD; Dementia; end of life; Purpose in life

A Semiparametric Multiple Imputation Approach to Fully Synthetic Data for Complex Surveys - Yu, Mandi; He, Yulei; Trivellore E. Raghunathan (Journal of Survey Statistics and Methodology, 2022)
Data synthesis is an effective statistical approach for reducing data disclosure risk. Generating fully synthetic data might minimize such risk, but its modeling and application can be difficult for data from large, complex surveys. This article extended the two-stage imputation to simultaneously impute item missing values and generate fully synthetic data. A new combining rule for making inferences using data generated in this manner was developed. Two semiparametric missing data imputation models were adapted to generate fully synthetic data for skewed continuous variable and sparse binary variable, respectively. The proposed approach was evaluated using simulated data and real longitudinal data from the Health and Retirement Study. The proposed approach was also compared with two existing synthesis approaches: (1) parametric regressions models as implemented in IVEware; and (2) nonparametric Classification and Regression Trees as implemented in synthpop package for R using real data. The results show that high data utility is maintained for a wide variety of descriptive and model-based statistics using the proposed strategy. The proposed strategy also performs better than existing methods for sophisticated analyses such as factor analysis.
Keywords: parametric regressions model; simulated data; synthetic data

Sense of purpose in life and inflammation in healthy older adults: A longitudinal study. - Guimond, Anne-Josee; Shiba, Koichiro; Kim, Eric S; Kubzansky, Laura D (Psychoneuroendocrinology, 2022)
BACKGROUND: A higher sense of purpose in life has been linked with reduced risk of age-related chronic health conditions that share elevated inflammation as a key risk factor (e.g., neurodegenerative diseases, heart disease, and diabetes). While prior research has documented cross-sectional associations between higher sense of purpose and lower inflammation, few studies have examined the association between purpose and changes in inflammation over time. OBJECTIVE: We tested if a higher sense of purpose was prospectively associated with lower likelihood of developing unhealthy C-reactive protein levels in older adults who initially had healthy CRP levels (i.e., <3 ug/mL). METHODS: Participants were 6925 adults aged > 50 in the Health and Retirement Study who were followed for 8 years. Participants completed the purpose in life subscale of the Ryff Psychological Well-being Scales at study baseline in 2006/2008. CRP was obtained from blood spots collected at baseline and after 4 and 8 years of follow-up. Pooled logistic regression estimated discrete-time hazard ratios (HR) and 95% confidence intervals (CI) for the association between baseline purpose and onset of unhealthy CRP levels (>3 ug/mL). RESULTS: There was no strong evidence of an association between baseline continuous purpose scores and onset of unhealthy CRP levels over time in the overall analytic sample. In sex-stratified models, higher purpose was associated with lower hazards of developing unhealthy CRP levels among men, while associations were null in women (e.g., in sociodemographics-adjusted model, men: HR=0.89, 95% CI: 0.79-0.99; women: HR=0.96, 95% CI: 0.85-1.08; interaction between continuous purpose scores and sex p = 0.15). CONCLUSIONS: Findings suggest that a higher versus lower sense of purpose is associated with lower inflammation levels in older men. In specific populations, purpose may serve as a novel target for future interventions aimed at reducing inflammation.
Keywords: C-reactive protein; Epidemiology; Health psychology; Inflammation; Purpose in life

Sense of Purpose in Life and Markers of Hearing Function: Replicated Associations across Two Longitudinal Cohorts. - Angelina R Sutin; Martina Luchetti; Damaris Aschwanden; Yannick Stephan; Antonio Terracciano (Gerontology, 2022)
INTRODUCTION: A sense of purpose in life is a psychological resource that is associated with healthier outcomes. The present research examines whether a greater sense of purpose in life is associated with subjective and objective markers of hearing health and whether hearing acuity contributes to the association between purpose and episodic memory. We sought to evaluate whether these associations were replicable across 2 independent samples. METHODS: Participants in the Health and Retirement Study (N = 14,291) and the English Longitudinal Study of Ageing (N = 8,844) reported on their purpose in life and perceived hearing quality at baseline. Hearing acuity was measured using an audiometer 2-4 years later, and episodic memory was measured at baseline and 6-8 years later. RESULTS: In both samples, higher purpose in life was associated with better hearing quality measured concurrently, lower risk of either subjective or objective hearing impairment, and hearing acuity accounted for some of the longitudinal relation between sense of purpose and better episodic memory. DISCUSSION: Across samples, measures, and analytical approaches, the present research indicates replicable associations between sense of purpose in life and hearing health. It further indicates that hearing may be one factor that associates purpose with better episodic memory.
Keywords: Episodic Memory; hearing acuity; Hearing loss; Replication; Sense of purpose

Sensory impairment and cognitive decline among older adults: An analysis of mediation and moderation effects of loneliness. - Ge, Shaoqing; Pan, Wei; Wu, Bei; Plassman, Brenda L; Dong, XinQi; McConnell, Eleanor S (Front Neurosci, 2022)
BACKGROUND: Multiple studies have reported that hearing and vision impairment are linked to cognitive decline. Yet little is known about factors that may influence the association between sensory impairment and cognitive decline. This study examined if loneliness mediates or moderates the impact of sensory impairment on cognitive decline as individuals age. METHODS: This was a longitudinal study using data from the Health and Retirement Study (HRS) and The Aging, Demographics, and Memory Study (ADAMS) ( = 243). We used one timepoint of hearing and vision (ADAMS 2006-2008), one timepoint of loneliness (HRS 2006-2008), and five waves of cognition (HRS 2006-2014). Hearing impairment was defined by an inability to hear pure-tone stimuli of 25 dB at frequencies between 0.5 and 4.0 kHz in either ear. Visual impairment was defined as having corrected binocular vision worse than 20/40. Longitudinal parallel-process (LPP) analysis was conducted at a significance level of α = 0.05 (one-tailed). RESULTS: Loneliness moderated but did not mediate the association between visual impairment and the rate of cognitive decline (standardized β =-0.108, < 0.05). No moderation or mediation effect of loneliness was found for the association between hearing impairment and cognitive decline. Both vision and hearing impairment were significantly associated with increased severity of loneliness. CONCLUSION: Visual impairment combined with an elevated level of loneliness may produce a more synergistic, deleterious impact on older adults' cognitive function than visual impairment alone. This study highlights the importance of promoting a healthy social and psychological status for older adults with sensory impairment.
Keywords: Cognitive decline; Loneliness; Older Adults

Serum Cystatin-C is linked to increased prevalence of diabetes and higher risk of mortality in diverse middle-aged and older adults. - González, Kevin A; Stickel, Ariana M; Kaur, Sonya S; Ramos, Alberto R; González, Hector M; Tarraf, Wassim (PLoS One, 2022)
OBJECTIVE: Type 2 Diabetes Mellitus (henceforth diabetes) affects roughly 35 million individuals in the US and is a major risk factor for cardiovascular and kidney disease. Serum Cystatin-C is used to monitor renal function and detect kidney damage. Recent research has focused on linking Cystatin-C to cardiovascular risk and disease, but most findings focus on small sample sizes and generalize poorly to diverse populations, thus limiting epidemiological inferences. The aim of this manuscript is to study the association between Cystatin-C, diabetes, and mortality and test for possible sex or racial/ethnic background modifications in these relationships. METHODS: We analyzed 8-years of biennial panel data from Health and Retirement Study participants 50-years and older who self-identified as White (unweighted N (uN) = 5,595), Black (uN = 867), or Latino (uN = 565) for a total of uN = 7,027 individuals. We modeled diabetes and death over 8-years as function of baseline Cystatin-C (log transformed) adjusting for covariates and tested modifications in associations by race/ethnic background and sex. RESULTS: Mean log Cystatin-C at visit 1 was 0.03±0.32 standard deviation. A 10% increase in Cystatin-C levels was associated with 13% increased relative risk of diabetes at baseline (11% and 9% by years 4 and 8). A 10% increase in Cystatin-C was highly associated with increased relative risk of death (28% and 31% by years 4 and 8). These associations were present even after adjusting for possible confounders and were not modified by sex or racial/ethnic background. CONCLUSION: Despite differential risks for diabetes and mortality by racial/ethnic groups, Cystatin-C was equally predictive of these outcomes across groups. Cystatin-C dysregulations could be used as a risk indicator for diabetes and as a warning sign for accelerated risk of mortality.
Keywords: Diabetes Mellitus; Hispanic or Latino; Kidney diseases; Prevalence; Risk Factors; Type 2

The severity of depressive symptoms over time may help predict stroke risk - Christensen, Thor (American Heart Association News, 2022)
People who consistently have higher depressive symptoms may be at higher risk for a stroke, according to new research. But stroke risk did not increase in those with decreasing severity of symptoms over time, even if they had high depressive symptoms early on.
Keywords: depression; stroke risk

Sex differences in post-stroke cognitive decline: A population-based longitudinal study of nationally representative data. - Bako, Abdulaziz T; Potter, Thomas; Tannous, Jonika; Pan, Alan P; Johnson, Carnayla; Baig, Eman; Downer, Brian; Vahidy, Farhaan S (PLoS One, 2022)
BACKGROUND: Sex differences in post-stroke cognitive decline have not been systematically evaluated in a nationally representative cohort. We use a quasi-experimental design to investigate sex differences in rate of post-stroke cognitive decline. METHODS: Utilizing the event study design, we use the Health and Retirement Study (HRS) data (1996-2016) to evaluate the differences (percentage points [95% Confidence interval]) in the rate of change in cognitive function, measured using the modified version of the Telephone Interview for Cognitive Status (TICS-m) score, before and after incident stroke, and among patients with and without incident stroke. We estimated this event study model for the overall study population and separately fit the same model for male and female participants. RESULTS: Of 25,872 HRS participants included in our study, 14,459 (55.9%) were females with an overall mean age (SD) of 61.2 (9.3) years. Overall, 2,911 (11.3%) participants reported experiencing incident stroke. Participants with incident stroke (vs. no stroke) had lower baseline TICS-m score (15.6 vs. 16.1). Among participants with incident stroke, the mean pre-stroke TICS-m score was higher than the mean post-stroke TICS-m score (14.9 vs. 12.7). Event study revealed a significant short-term acceleration of cognitive decline for the overall population (4.2 [1.7-6.6] percentage points, p value = 0.001) and among female participants (5.0 [1.7-8.3] percentage points, p value = 0.003). We, however, found no evidence of long-term acceleration of cognitive decline after stroke. Moreover, among males, incident stroke was not associated with significant changes in rate of post-stroke cognitive decline. CONCLUSION: Females, in contrast to males, experience post-stroke cognitive deficits, particularly during early post-stroke period. Identifying the sex-specific stroke characteristics contributing to differences in post stroke cognitive decline may inform future strategies for reducing the burden of post-stroke cognitive impairment and dementia.
Keywords: Cognition; Cognitive Dysfunction; Female; Male; Sex Characteristics; Stroke

Sex Differences in the Association between Metabolic Dysregulation and Cognitive Aging: The Health and Retirement Study. - Chanti-Ketterl, Marianne; Rebecca C Stebbins; Obhi, Hardeep K; Daniel W. Belsky; Brenda L Plassman; Yang, Yang Claire (The Journals of Gerontology, Series A, 2022)
BACKGROUND: Dysregulation of some metabolic factors increases the risk of dementia. It remains unclear if overall metabolic dysregulation, or only certain components, contribute to cognitive aging and if these associations are sex-specific. METHODS: Data from the 2006-2016 waves of the Health and Retirement Study (HRS) was used to analyze 7,103 participants aged 65+ at baseline (58% women). We created a metabolic-dysregulation risk score (MDRS) composed of blood pressure/hypertension status, HbA1c/diabetes status, total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and waist circumference, and assessed cognitive trajectories from repeated measures of the HRS-Telephone Interview for Cognitive Status (HRS-TICS) over 10 years of follow-up. Linear mixed-effects models estimated associations between MDRS or individual metabolic factors (biomarkers) with mean and change in HRS-TICS scores and assessed sex-modification of these associations. RESULTS: Participants with higher MDRSs had lower mean HRS-TICS scores, but there were no statistically significant differences in rate of decline. Sex-stratification showed this association was present for women only. MDRS biomarkers revealed heterogeneity in the strength and direction of associations with HRS-TICS. Lower HRS-TICS levels were associated with hypertension, higher HbA1c/diabetes, and lower HDL-C and TC; while faster rate of cognitive decline was associated with hypertension, higher HbA1c/diabetes and higher TC. Participants with higher HbA1c/diabetes presented worse cognitive trajectories. Sex-differences indicated women with higher HbA1c/diabetes to have lower HRS-TICS levels while hypertensive males presented better cognitive trajectory. CONCLUSIONS: Our results demonstrate that metabolic dysregulation is more strongly associated with cognition in women compared to men, though sex-differences vary by individual biomarker.
Keywords: Biomarkers; Brain Aging; Diabetes; Epidemiology

SHAPE OF CARE: PATTERNS OF FAMILY CAREGIVING ACTIVITIES AMONG OLDER ADULTS FROM MIDLIFE TO LATER AGES IN CHINA AND THE U.S. - Duan, Haoshu (University of Maryland, 2022)
This dissertation consists of three papers that investigate the long-term family caregiving patterns among Chinese and American older adults. Family caregiving has long been an essential fabric of long-term care services. Due to the prolonged life expectancy and the declined family size, older adults today are more likely to care for multiple family members for longer years than the previous cohorts. However, studies on caregiving predominately focus on singular care experiences over a short period time. As older adults transition into and out of multiple care roles, the overall caregiving patterns are overlooked. Leveraging two rich longitudinal datasets (the China Health and Retirement Study and the Health and Retirement Study), this dissertation aims to fill this current research gap by developing long-term family caregiving typologies. The first paper develops a care typology for Chinese older adults, and thoroughly assesses how gender, hukou status, living arrangement, and significant life transitions are associated with the long-term caregiving patterns. In the second paper, using linear mixed-effects models, I continue exploring the positive and negative health consequences of each caregiving pattern among Chinese older adults. The third paper focuses on developing a long-term family caregiving pattern for American older adults. In addition to prolonged life expectancies and the decline in family size, the U.S. has experienced complex transitions in family structures over the past few decades, leading to more diverse family networks and international relations in later life. After establishing the long-term care typology, the third paper pays closer attention to the variations of family caregiving patterns across the War Babies cohort, Early Baby Boomer, and the Middle/Late Baby Boomer cohort. Moreover, I explore how gender, race, and socioeconomic status are linked with these patterns. In the context of global aging, this dissertation highlights the heterogeneity in the family caregiving experiences and identifies the most vulnerable demographic groups who shoulder the heaviest care burden over time. In the end, the findings from the dissertation provide guidance for the investment and design of long-term care services in rapidly aging contexts.
Keywords: Caregiving; CHARLS; Family

Sibling Deaths, Racial/Ethnic Disadvantage, and Dementia in Later Life. - Hyungmin Cha; Thomas, Patricia A; Debra Umberson (The Journals of Gerontology, Series B, 2022)
OBJECTIVES: Sibling loss is understudied in the bereavement and health literature. The present study considers whether experiencing the death of siblings in mid-to-late life is associated with subsequent dementia risk and how differential exposure to sibling losses by race/ethnicity may contribute to racial/ethnic disparities in dementia risk. METHODS: We use discrete-time hazard regression models, a formal mediation test, and a counterfactual simulation to reveal how sibling loss in mid-to-late life affects dementia incidence and whether unequal exposures by race/ethnicity mediate the racial/ethnic disparities in dementia. We analyze data from the Health and Retirement Study (2000-2016). The sample includes 13,589 respondents (10,607 non-Hispanic White, 1,761 non-Hispanic Black, and 1,158 Hispanic adults) aged 65 years and older in 2000 who show no evidence of dementia at baseline. RESULTS: Discrete-time hazard regression results show that sibling loss in mid-to-late life is associated with up to 54% higher risk for dementia. Sibling loss contributes to Black-White disparities in dementia risk. In addition, a simulation analysis shows that dementia rates would be 14% lower for Black adults if they experienced the lower rates of sibling loss experienced by White adults. This pattern was not observed among Hispanic adults. DISCUSSION: The death of a sibling in mid-to-late life is a stressor that is associated with increased dementia risk. Black adults are disadvantaged in that they are more likely than Whites to experience the death of siblings, and such losses contribute to the already substantial racial/ethnic disadvantage in dementia.
Keywords: Bereavement; Dementia; Minority aging; Race/ethnicity; Stress

Sick And Tired Of Being Excluded: Structural Racism In Disenfranchisement As A Threat To Population Health Equity. - Patricia Homan; Brown, Tyson H (Health Affairs, 2022)
Theoretical research suggests that racialized felony disenfranchisement-a form of structural racism-is likely to undermine the health of Black people, yet empirical studies on the topic are scant. We used administrative data on disproportionate felony disenfranchisement of Black residents across US states, linked to geocoded individual-level health data from the 2016 Health and Retirement Study, to estimate race-specific regression models describing the relationship between racialized disenfranchisement and health among middle-aged and older adults, adjusting for other individual- and state-level factors. Results show that living in states with higher levels of racialized disenfranchisement is associated with more depressive symptoms, more functional limitations, more difficulty performing instrumental activities of daily living, and more difficulty performing activities of daily living among Black people. However, there are no statistically significant relationships between racialized disenfranchisement and health among White people. These findings suggest that policies aiming to mitigate disproportionate Black felony disenfranchisement not only are essential for political inclusion but also may be valuable tools for improving population health equity.
Keywords: administrative data; disenfranchisement; health; race

Sleep Disorders as a Potential Risk Factor for Dementia in Elderly Adults - Kuhler, Cassandra; Wills, Chloe; Tubbs, Andrew; Seixas, Azizi; Turner, Arlener; Jean-Louis, Girardin; Killgore, William; Grandner, Michael (Sleep, 2022)
Introduction Sleep disorders such as insomnia are seen in the early onset of Alzheimer’s disease, the most common form of dementia. Simultaneously, sleep disorders may indicate increased risk for the development of dementia. Due to the rate of comorbidity of these two conditions seen in the elderly population, the relationship between dementia and sleep disorders is a topic of interest for researchers. A bidirectional correlation between the two could have important implications in the clinical field exploring factors that lead to dementia Methods Data was assessed from 17,146 older adults from the 2018 Health and Retirement Survey. Participants were surveyed using questionnaires regarding both incident dementia or serious memory impairment in the past 2 years and the presence of a sleep disorder, as diagnosed by a doctor or health professional. Those who reported no dementia in the previous wave (N=16,547) were asked if they had been diagnosed since they were last asked. N=185 individuals reported incident dementia in the 2-years between assessments. Responses were coded to either “Yes” or “No”. A Poisson regression analysis was conducted to explore the relationship between incident dementia and sleep disorders. Results In a sample of older adults, unadjusted results indicate that having a sleep disorder was associated with a 0.6% increased risk of new onset dementia (PRR=1.006; 95%CI[1.001,1.012]; p=0.026). These results were sustained when adjusted for sex, age, race, ethnicity, and depression (PRR=1.006; 95%CI[1.001,1.012]; p=0.013). Conclusion Chronic sleep disturbances may be a factor used to indicate increased risk for dementia and help with early detection of the disease. These results demonstrate the value of sleep disorders screening among those at risk for dementia. Further research is needed to clarify these findings (e.g., explore specific sleep disorders) and expand the follow-up window (i.e., beyond 2 years).
Keywords: Alzheimer disease; Comorbidity; Dementia; depressive disorders; Early Diagnosis; ethnic group; Health Personnel; insomnia; memory impairment; sleep disorders

Social Disconnectedness and Loneliness: Do Self-Perceptions of Aging Play a Role? - Hu, Rita Xiaochen; Li, Lydia W (The Journals of Gerontology, Series B, 2022)
OBJECTIVE: Research suggests that self-perceptions of aging (SPA) have effects on physical, mental, cognitive, and emotional well-being among older adults. Few studies have examined the effects of SPA on social well-being. This study investigates the association of SPA with trajectories of social disconnectedness and loneliness in older Americans and explores mechanisms linking SPA and the two forms of social isolation. METHOD: We conducted Latent Growth Curve Modeling and path analysis using 3-wave data spanning 8 years (2008/2010 - 2016/2018) from the Health and Retirement Study. The sample included respondents aged 65 and older (N = 3,597) at baseline (2008/2010). SPA was measured by the Attitudes Toward Own Aging Scale. Social disconnectedness was an index including 6 indicators of social networks and social engagement. Loneliness was measured using the 11-item UCLA Loneliness Scale. RESULTS: Older adults with more negative SPA at baseline were more lonely but had slower rates of increase in loneliness during the 8-year study period. More negative SPA also predicted greater social disconnectedness but was not significantly related to the rate of change in social disconnectedness over time. The effects of SPA on social disconnectedness were primarily indirect through loneliness, whereas SPA had direct effects on loneliness. Overall, SPA had a stronger association with loneliness than with social disconnectedness. DISCUSSION: The results suggest that older adults with negative SPA are at risk of loneliness which then leads to social disconnectedness. Asking about SPA during individual assessment with older adults may help to discern issues with loneliness.
Keywords: Ageism; Loneliness; social isolation; Social networks

Social epigenetics of racial disparities in aging - Yannatos, Isabel; Xie, Sharon X; Brown, Rebecca; McMillan, Corey T (Alzheimer's & Dementia, 2022)
Racial disparities in many aging-related health outcomes are persistent and pervasive among older Americans. There are well-documented inequities in the social determinants of health for older adults, including the social and physical environment, due to structural and environmental racism, but there is little understanding of the biological intermediates by which social determinants affect disparate health outcomes. Biological aging measured by DNA methylation (DNAm) is robustly associated with worse age-related outcomes and higher social adversity. We hypothesize that individual social determinants, the social environment, and air pollution exposures interact to contribute to racial disparities in DNAm aging according to GrimAge and Dunedin Pace of Aging methylation (DPoAm). Method We performed retrospective cross-sectional analyses among 3250 non-Hispanic participants (80.3% white, 19.7% Black) in the Health and Retirement Study whose 2016 epigenetic age is linked to survey responses and geographic data. DNAm aging is defined as the residual after regressing epigenetic age on chronological age. Measures of the neighborhood social environment include the Social Deprivation Index and perceived social stress. Air pollution exposures include particulate matter (PM2.5), nitrogen dioxide (NO2), and ozone. Individual-level determinants include socioeconomic status, healthcare access, health status, and health behaviors. We implemented multivariable linear regression models to identify significant associations, interactions, and mediators in the relationship between each DNAm aging measure and the social and environmental determinants. Result We found on average Black individuals have significantly accelerated DNAm aging compared to white individuals (599% and 498%) according to GrimAge and DPoAm, respectively. Individual-level factors evaluated account for approximately 43% of the disparity in GrimAge and 34% in DPoAm. Further results suggest that associations between neighborhood social environment and DNAm aging are significant and mediated by individual-level factors. PM2.5 may be associated with DPoAm acceleration in certain sub-populations. NO2 and ozone are not significantly associated with DNAm aging. We are investigating individual-level factors that mediate social environmental exposures and increase vulnerability to PM2.5. Conclusion DNAm aging may play a role in social determinants “getting under the skin” and contributing to age-related health disparities between Black and white Americans. Work is ongoing to determine the environmental and individual factors that contribute to these disparities.
Keywords: Aging; DNA Methylation; epigenetics; Racial Disparities

Social isolation and loneliness before and during the COVID-19 pandemic: a longitudinal study of US Adults over 50. - Peng, Siyun; Roth, Adam R (The Journals of Gerontology, Series B, 2022)
OBJECTIVES: The potential impact of social distancing policies during the COVID-19 pandemic on social isolation and loneliness is of increasing global concern. Although many studies focus primarily on loneliness, patterns of social isolation-particularly physical and digital isolation-are understudied. We examined changes in social isolation, physical isolation, digital isolation, and loneliness in US adults over 50 before and during the lockdown. METHODS: Two waves of the Health and Retirement Study, a national panel sample of US adults over 50 years old, were used. Fixed-effects regression models were fitted to identify within-person change from 2016 to 2020 to examine the impact of social distancing policies during the pandemic. RESULTS: There was an increase in physical isolation and social isolation among respondents during the COVID-19 social distancing policies. However, respondents experienced no change in digital isolation or loneliness. The increase in physical isolation was only present for people with high COVID-19 concern whereas people with low concern experienced no change in physical isolation. DISCUSSION: Despite an increase in physical isolation due to the social distancing policies, US adults aged over 50 stayed connected through digital contact and were resilient in protecting themselves from loneliness.
Keywords: COVID-19; Digital isolation; Mental Health; Social Relationships; Social Support

Social isolation increases from adolescence through later life but varies by gender, age, and partnership status - Umberson, Debra; Lin, Zhiyong; Cha, Hyungmin (CAPS Research Brief Series, 2022)
Substantial evidence has found that people who are socially isolated experience worse mental and physical health and are more likely to die compared to their less isolated peers. And while the negative health impacts of social isolation affect both men and women, social isolation unfolds over the life course and perhaps in different ways for men and women. In this research brief, CAPS director and PRC faculty scholar Debra Umberson, along with PRC faculty affiliate Zhiyong Lin, and CAPS/PRC graduate student trainee Hyungmin Cha, report on a recent study that explores the gendered patterns of social isolation from adolescence to old age. Using Add Health and Health and Retirement Study data, they find that social isolation increases from adolescence through later life and that men are more socially isolated than women across all age and partnership categories with one exception: after age 62, married women are more socially isolated than married men.
Keywords: Mortality; negative health impacts; social isolation

Social isolation trajectories in midlife and later-life: patterns and associations with health. - Luo, Mengsha; Li, Lydia (International Journal of Geriatric Psychiatry, 2022)
OBJECTIVES: Social isolation has objective and subjective dimensions. Few studies have simultaneously examined trajectories of both dimensions. We integrated multiple indicators of both dimensions to identify social isolation trajectory patterns and investigated how different patterns were related to adults' physical, mental, cognitive, and self-rated health. METHODS: We used latent class growth modeling to examine social isolation trajectory patterns, based on data from the 2008-2016 waves of the Health and Retirement Study (N = 6457). Mixed-effect linear models were used to examine how trajectory patterns were associated with functional limitations, depressive symptoms, memory deficits, and self-rated health over the 8-year study period. RESULTS: Four social isolation trajectory patterns were identified: severe isolation (15.4%), moderate isolation (37.6%), some objective and rare subjective isolation (35.4%), and rare objective and low subjective isolation (11.6%). Social isolation trajectory patterns showed a gradient in all health domains. The rare objective and low subjective isolation group had the best health (i.e., the fewest functional limitations, depressive symptoms, and memory deficits and the best self-rated health); the some objective and rare subjective isolation group had the next best health; the moderate isolation group had the second worst health; and the severe isolation group had the worst health. CONCLUSIONS: The prevalence and stability of severe and moderate social isolation suggest it may be necessary to address social isolation at the national level. The most favorable health outcomes associated with the rare objective and low subjective isolation group supports interventions to strengthen social networks and engagement midlife and later-life.
Keywords: Memory Disorders; Retirement; social isolation

The Social Pattern and Causes of Dementia Prevalence Decline in the United States - Lee, Mark (University of Minnesota, 2022)
Age-adjusted dementia prevalence has significantly declined in the United States over the last 25 years, despite little advancement in the biomedical treatment of Alzheimer’s Disease or improvement in proximal dementia risk factors. In this dissertation, I analyze data from the Health and Retirement Study (HRS) to improve current understanding of the descriptive trends and causal mechanisms underlying dementia prevalence decline. In my first study, I rebut the argument that dementia decline in the HRS is an artefact of unmeasured panel conditioning. I show that practice effects do not bias the estimated secular trend in dementia prevalence after accounting for selective panel attrition. In my second study, I argue that cohort trends in early life risk factors offer a more plausible explanation of the observed dementia improvement than period trends, which have been emphasized in previous research. In my third study, I empirically test the contribution of early life risk factors to cohort trends in dementia prevalence. I find that age- and sex-adjusted dementia prevalence declined 2.3 percentage points per 10-year increase in birth year for cohorts born 1892-1952. The majority (72%) of this trend was explained by increases in educational attainment for more recent cohorts. Proximal risk factors had little influence net of education and other early life factors. The trend in dementia decline was steeper for Black than White Americans, and the causal mechanisms also differed by race. In my fourth study, I document cohort trends in midlife cognitive aging. I find that, compared with those born 1942-1947, those born 1954-1959 entered midlife with lower cognitive function, but exhibited greater maintenance of cognition over time. This suggests that dementia prevalence may continue to improve as this latter-born cohort ages. Overall, this research reinforces the importance of social improvement (especially educational expansion) across the 20th century for cognitive health improvements in the 21st century. This work indicates that interventions to reduce or delay dementia and ameliorate racial disparities should be expanded to include social determinants of health across the life course.
Keywords: Cognition; Dementia; life course; Population Health

Social Relationships, Wealth, and Cardiometabolic Risk: Evidence from a National Longitudinal Study of U.S. Older Adults. - Shartle, Kaitlin; Yang, Yang Claire; Richman, Laura S; Belsky, Daniel W; Aiello, Allison E; Harris, Kathleen Mullan (Journal of Aging and Health, 2022)
To investigate multiple dimensions of social relationships related to biomarkers of cardiometabolic health and how their associations vary by wealth in older adults. Growth curve models were used to investigate the longitudinal associations between measures of both positive and negative social relationships and cardiometabolic risk (CMR) over a 10-year period from 2006 to 2016 and the moderation of this association by wealth in the Health and Retirement Study (HRS). Older adults with better social relationships had lower CMR on average. The protective effects of positive social relationships, however, waned at older ages, particularly for low-wealth individuals. Our results suggest that good social relationships promote healthy aging by buffering against harmful cardiometabolic consequences of psychosocial stress, particularly among relatively wealthy individuals. Efforts to improve old age health would be more effective when focusing simultaneously on fostering social connections and boosting financial resources.
Keywords: cardiometabolic risk; Social Relationships; Trajectories; Wealth

Social Security Claiming: COVID-19 vs. Great Recession. - Alicia H. Munnell; Chen, Anqi; Liu, Siyan (Issue in Brief, 2022)
The brief’s key findings are: In early 2020, many thought the COVID crisis – like the Great Recession – might force many workers to claim Social Security early. But the COVID economy turned out very different, with robust growth in the stock market and substantial unemployment relief. The analysis compared the relative impacts of the two recessions on early claiming by earnings group and found that: During COVID, the booming stock market induced early claiming among workers with retirement assets; while the generous unemployment benefits decreased early claiming for many lower-paid workers. Overall, the latter effect more than cancelled out the former, so COVID actually led to a slight decline in early claiming.
Keywords: COVID-19; Great Recession; Social Security claiming

Social Security Claiming: COVID-19 vs. Great Recession - Chen, Anqi; Liu, Siyan; Alicia H. Munnell (Briefs, 2022)
In early 2020, many thought the COVID crisis – like the Great Recession – might force many workers to claim Social Security early.But the COVID economy turned out very different, with robust growth in the stock market and substantial unemployment relief. The analysis compared the relative impacts of the two recessions on early claiming by earnings group and found that: During COVID, the booming stock market induced early claiming among workers with retirement assets ;while the generous unemployment benefits decreased early claiming for many lower-paid workers. Overall, the latter effect more than cancelled out the former, so COVID actually led to a slight decline in early claiming.
Keywords: COVID-19; Great Recession; Social Security claiming

Social Strain Is Associated with Functional Health in Older Adults after Major Surgery - Tang, Victoria; Finlayson, Emily; John Boscardin; Ashwin Kotwal (Journal of the American College of Surgeons, 2022)
Introduction: Psychosocial impairments in older surgical patients may predict postoperative functional recovery. We investigated the association of social strain, an under-studied and important social variable, with 1-year functional health in older adults after major surgery. Methods: With Health and Retirement Study-Medicare claims data, we identified N = 3868 participants, age ≥65 years, who underwent major surgery. Outcome included postoperative 1-year functional decline in activities of daily living (ADL) as compared with preoperative ADL function. Predictor social strain was determined by asking how often one’s spouse, children, family, or friends a) “criticize you?,” b) “make too many demands on you?,” c) “let you down,” or d) “get on your nerves?”; response of “a lot” to any classified strain from that specific relationship. Analysis included multivariable logistic regression adjusted for age, gender, race/ethnicity, education. Results: Mean age 76±5 years, 54% women, 8% Black, 5% Hispanic, 32% reported social strain from any relationship source (spouse: 14%, children: 8%, family: 7%, friends: 3%). Over 15% sustained decline within 2 years of operation. Individuals experiencing social strain from children had higher rates of 2-year functional decline (15% vs 8%, p = 0.007), those with social strain from any source had higher rates of 2-year functional decline (11% vs 5%, p = 0.001). After multivariable adjustment, social strain was significantly associated with 2-year functional decline (odds ratio [OR]=1.44 (1.02, 2.02), p value 0.04). Conclusion: Social strain was associated with 1-year ADL functional decline in older adults undergoing major surgery. Psychosocial vulnerability should be assessed preoperatively and intervention to help patients cope with social strain should be investigated in the surgical setting.
Keywords: major surgery; psychosocial impairments; Social strain

Social stress contributes to accelerated aging of the immune system, study finds - National Institute on Aging (National Institute on Aging, 2022)
Keywords: aging biology; Health Disparities; Immune System; Stress

Social stressors associated with age-related T lymphocyte percentages in older US adults: Evidence from the US Health and Retirement Study. - Klopack, Eric T; Eileen M. Crimmins; Cole, Steve W; Seeman, Teresa E; Carroll, Judith E (Proceedings of the National Academy of Sciences, 2022)
Exposure to stress is a risk factor for poor health and accelerated aging. Immune aging, including declines in naïve and increases in terminally differentiated T cells, plays a role in immune health and tissue specific aging, and may contribute to elevated risk for poor health among those who experience high psychosocial stress. Past data have been limited in estimating the contribution of life stress to the development of accelerated immune aging and investigating mediators such as lifestyle and cytomegalovirus (CMV) infection. This study utilizes a national sample of 5,744 US adults over age 50 to assess the relationship of social stress (viz., everyday discrimination, stressful life events, lifetime discrimination, life trauma, and chronic stress) with flow cytometric estimates of immune aging, including naïve and terminally differentiated T cell percentages and the ratio of CD4 to CD8 cells. Experiencing life trauma and chronic stress was related to a lower percentage of CD4 naïve cells. Discrimination and chronic stress were each associated with a greater percentage of terminally differentiated CD4 cells. Stressful life events, high lifetime discrimination, and life trauma were related to a lower percentage of CD8 naïve cells. Stressful life events, high lifetime discrimination, and chronic stress were associated with a higher percentage of terminally differentiated CD8 cells. High lifetime discrimination and chronic stress were related to a lower CD4:CD8 ratio. Lifestyle factors and CMV seropositivity partially reduced these effects. Results identify psychosocial stress as a contributor to accelerating immune aging by decreasing naïve and increasing terminally differentiated T cells.
Keywords: Aging; Immunosenescence; socioeconomic status; Stress

Societal Impact of Research Funding for Women's Health in Rheumatoid Arthritis - Baird, Matthew D.; Melanie A. Zaber; Annie Chen; Andrew W. Dick; Chloe E. Bird; Molly Waymouth; Grace Gahlon; Denise D. Quigley; Hamad Al-Ibrahim; Lori Frank (Research Reports, 2022)
Women's health has suffered from insufficient research addressing women. The research community has not widely embraced the value of this research, and the impact of limited knowledge about women's health relative to men's is far-reaching. Without information on the potential return on investment for women's health research, research funders, policymakers, and business leaders lack a basis for altering research investments to improve knowledge of women's health. As part of an initiative of the Women's Health Access Matters (WHAM) nonprofit foundation, RAND Corporation researchers examined the impact of increasing funding for women's health research on rheumatoid arthritis (RA). RA was chosen partly because of its higher prevalence in women than men, with some symptom profiles differing by sex. In this report, the authors present the results of microsimulation models used to explore the potential for enhanced investment in women's health research, in terms of the economic well-being of women and for the U.S. population.

Sociodemographic and health status differences in delaying medical care during the COVID-19 pandemic among older adults: findings from the Health and Retirement Study. - Farina, Mateo P; Jennifer A Ailshire (BMC Public Health, 2022)
BACKGROUND: During the COVID-19 Pandemic, adults in the United States reported delaying medical care, which may be tied risk of infection and local policies limiting appointment. Some populations may have been more likely to delay care than others, leading to other forms of health inequality during this period. To-date there is little research on delayed care among U.S. older adult. We determine the prevalence of delayed medical care among older adults and investigate sociodemographic and health status inequalities in delaying health care. METHOD: We used data from the first public release of the nationally representative Health and Retirement Study COVID-19 Subsample (N = 3006). Using logistic regression, we assessed whether differences in delaying health care varied by age, sex, race/ethnicity, education, self-rated health (SRH), and having any Activity of Daily Living (ADL) limitation. We also conducted additional analysis that evaluated differences in delaying care by two care subtypes: doctor and dental care visits. RESULTS: About 30% of U.S. older adults reported delaying care with the most common types of delayed care being dental or doctor visits. Adults ages 75 and older were less likely to delay care, while women, college educated, and those with poor SRH, and any ADL limitations were more likely to delay care. CONCLUSIONS: Nearly one-third of older adults delayed care during the COVID-19 pandemic. The increased likelihood of delayed care among people with worse health suggests that there may be longer-term impacts on the health care system and population health from the COVID-19 pandemic, and may contribute to health inequalities in the near future.
Keywords: COVID-19; Health Status; Health Status Disparities; Pandemics; Retirement

SOCIODEMOGRAPHIC DIFFERENCES IN IMMUNOSENESCENCE IN OLDER AGE: EVIDENCE FROM THE HEALTH AND RETIREMENT STUDY - Noppert, Grace; Stebbins, Rebecca; Dowd, Jennifer; Aiello, Allison E (Innovation in Aging, 2022)
Population patterns of immunosenescence are not well described. We characterized markers of immunosenescence and assessed sociodemographic differences in a population of individuals ages 56 years and older using newly released venous blood data from the nationally representative U.S. Health and Retirement Study (HRS) (n=8,400). Median values of the CD8+:CD4+, effector memory (em)RA:naïve CD4+ and emRA:naïve CD8+ T cell ratios were higher among older participants (more aged immune profile) and were lower among those with additional educational attainment (less aged immune profile). Racialized minority populations had immune markers suggestive of a more aged immune profile: Hispanics had a CD8+:CD4+ median value of 0.37 (95% CI: 0.35, 0.39) compared to Whites (0.30, 95% CI: 0.29, 0.31). Blacks had the highest median value of the emRA:naive CD4+ ratio (0.08; 95% CI: 0.07, 0.09) compared to Whites (0.03; 95% CI: 0.028, 0.033). Our regression analyses showed that race/ethnicity and education were associated with large differences in T-cell markers of aging, which were orders of magnitude greater than age. By standardizing regression coefficients to estimate years of immunological aging, we found that each additional level of education was associated with roughly an additional decade of immunological age, and racialized minorities had on average an immunological age two to four decades higher than Whites. As one of the first large-scale population-based investigations of immunosenescence, our study advances understanding of the immune mechanisms underlying age-related disease, with implications for risks such as vulnerability to novel pathogens (e.g., SARS-CoV-2).
Keywords: Immunosenescence; sociodemographic differences

Socio-demographic, lifestyle and health characteristics as predictors of self-reported Covid-19 history among older adults: 2006-2020 Health and Retirement Study. - Beydoun, Hind A; Beydoun, May A; Hossain, Sharmin; Alemu, Brook T; Gautam, Rana S; Weiss, Jordan; Zonderman, Alan B (American Journal of Infection Control, 2022)
BACKGROUND: To identify key socio-demographic, lifestyle, and health predictors of self-reported coronavirus disease 2019 (Covid-19) history, examine cardiometabolic health characteristics as predictors of self-reported Covid-19 history and compare groups with and without a history of Covid-19 on trajectories in cardiometabolic health and blood pressure measurements over time, among United States (U.S.) older adults. METHODS: Nationally representative longitudinal data on U.S. older adults from the 2006-2020 Health and Retirement Study were analyzed using logistic and mixed-effects logistic regression models. RESULTS: Based on logistic regression, number of household members (OR=1.26, 95% CI: 1.05, 1.52), depressive symptoms score (OR = 1.21, 95% CI: 1.04, 1.42) and number of cardiometabolic risk factors or chronic conditions ("1-2" vs "0") (OR = 0.27, 95% CI: 0.11, 0.67) were significant predictors of self-reported Covid-19 history. Based on mixed-effects logistic regression, several statistically significant predictors of Covid-19 history were identified, including female sex (OR = 3.06, 95% CI: 1.57, 5.96), other race (OR = 5.85, 95% CI: 2.37, 14.43), Hispanic ethnicity (OR = 2.66, 95% CI: 1.15, 6.17), number of household members (OR = 1.25, 95% CI: 1.10, 1.42), moderate-to-vigorous physical activity (1-4 times per month vs never) (OR = 0.38, 95% CI: 0.18, 0.78) and number of cardiometabolic risk factors or chronic conditions ("1-2" vs "0") (OR = 0.34, 95% CI: 0.19, 0.60). CONCLUSIONS: Number of household members, depressive symptoms and number of cardiometabolic risk factors or chronic conditions may be key predictors for self-reported Covid-19 history among U.S. older adults. In-depth analyses are needed to confirm preliminary findings.
Keywords: Cardiovascular Diseases; Chronic disease; COVID-19; ethnicity; Female; Life Style; Retirement; Self Report

The Socioeconomic Gradient in Epigenetic Ageing Clocks: Evidence from the Multi-Ethnic Study of Atherosclerosis and the Health and Retirement Study. - Lauren L Schmitz; Zhao, Wei; Scott M Ratliff; Goodwin, Julia; Miao, Jiacheng; Lu, Qiongshi; Guo, Xiuqing; Kent D Taylor; Ding, Jingzhong; Liu, Yongmei; Morgan E. Levine; Smith, Jennifer A (Epigenetics, 2022)
Epigenetic clocks have been widely used to predict disease risk in multiple tissues or cells. Their success as a measure of biological ageing has prompted research on the connection between epigenetic pathways of ageing and the socioeconomic gradient in health and mortality. However, studies examining social correlates of epigenetic ageing have yielded inconsistent results. We conducted a comprehensive, comparative analysis of associations between various dimensions of socioeconomic status (SES) (education, income, wealth, occupation, neighbourhood environment, and childhood SES) and eight epigenetic clocks in two well-powered US ageing studies: The Multi-Ethnic Study of Atherosclerosis (MESA) (n = 1,211) and the Health and Retirement Study (HRS) (n = 4,018). In both studies, we found robust associations between SES measures in adulthood and the GrimAge and DunedinPoAm clocks (Bonferroni-corrected -value < 0.01). In the HRS, significant associations with the Levine and Yang clocks were also evident. These associations were only partially mediated by smoking, alcohol consumption, and obesity, which suggests that differences in health behaviours alone cannot explain the SES gradient in epigenetic ageing in older adults. Further analyses revealed concurrent associations between polygenic risk for accelerated intrinsic epigenetic ageing, SES, and the Levine clock, indicating that genetic risk and social disadvantage may contribute additively to faster biological aging.
Keywords: DNA methylation age; epigenetic clock; polygenic score; socioeconomic status

Socioeconomic Status across the Life Course and Smoking Cessation among Older Adult Smokers in the U.S - Jaqueline C. Avila; Sangah Lee; Ezinwa Osuoha; Dale Dagar Maglalang; Alexander Sokolovsky; Jasjit S. Ahluwalia (Addictive Behaviors, 2022)
Socioeconomic status (SES) at different stages of the life course impacts late-life health. However, whether SES across the life course impacts smoking cessation in late-life is not known. Purpose: Assess how life course SES impacts smoking cessation among older smokers. Methods We identified 5,124 smokers, 50 years and older, from the 1998 to 2018 waves of the Health and Retirement Study. The outcome was self-reported smoking cessation. The main exposure was life course SES, defined as: low child and low adult SES (persistent low); low child, high adult SES (upward mobility); high child, low adult SES (downward mobility); and high child, high adult SES (persistent high). A multilevel mixed-effect logistic model was used to examine how life course SES predicts smoking cessation at age 65 and over time, adjusted for covariates. Results Compared to those with persistent high SES, those with persistent low SES, upward and downward SES were more likely to be Hispanic or non-Hispanic Black. The adjusted results showed that at age 65, compared to those with persistent high SES, those with persistent low SES (OR=0.69, 95% CI= [0.51-0.92]), upward SES (OR=0.49, [0.32-0.75]), and downward SES (OR=0.55, [0.40-0.76]) were less likely to quit. However, as age increased, only those with downward or persistent low SES were significantly less likely to quit compared to those with persistent high SES. Conclusion: Social mobility of SES from childhood to adulthood significantly impacts smoking cessation. Both stages of the life course should be considered to understand smoking behaviors.
Keywords: Smoking cessation; socioeconomic status; Tobacco

Socioeconomic status and immune aging in older US adults in the health and retirement study. - Klopack, Eric T; Bharat Thyagarajan; Jessica Faul; Meier, Helen C S; Ramasubramanian, Ramya; Jung K Kim; Crimmins, Eileen M (Biodemography and Social Biology, 2022)
Socioeconomic and demographic factors including educational attainment, race and ethnicity, and childhood socioeconomic status (SES) are powerful predictors of inequalities in aging, morbidity, and mortality. Immune aging, including accumulation of late-differentiated, senescent-like lymphocytes and lower levels of naïve lymphocytes, may play a role in the development of the age-related health inequalities. This study used nationally representative data from more than 9,000 US adults from the Health and Retirement Study to investigate associations between educational attainment, race and ethnicity, and childhood SES and lymphocyte percentages. Respondents with lower educational attainment, Hispanic adults, and those who had a parent with less than a high school education had lymphocyte percentages consistent with more immune aging compared to those with greater educational attainment, non-Hispanic White adults, and respondents who had parents with a high school education, respectively. Associations between education, Hispanic ethnicity, and parents' education and late differentiated senescent-like T lymphocytes (TemRA) and B cells were largely driven by cytomegalovirus (CMV), suggesting it is a factor in observed SES inequalities in immunosenescence. Naïve T lymphocytes may be particularly affected by socioeconomic position and may therefore be of particular interest to research interested in inequalities in health and aging.
Keywords: Child; Educational Status; ethnicity; Hispanic or Latino; Retirement; Social Class

Socioeconomic Status, Biological Aging, and Memory in a Diverse National Sample of Older US Men and Women. - Avila-Rieger, Justina; Turney, Indira C; Vonk, Jet M J; Esie, Precious; Seblova, Dominika; Weir, Vanessa R; Belsky, Daniel W; Jennifer J Manly (Neurology, 2022)
BACKGROUND AND OBJECTIVES: Exposure to socioeconomic disadvantage is associated with early-onset cognitive aging. Biological aging, the progressive loss of system integrity that occurs as we age is proposed as a modifiable process mediating this health inequality. We examined whether socioeconomic disparities in cognitive aging in mid-to late-life adults is explained by accelerated biological aging similarly across race, ethnicity and sex/gender. METHODS: Data was from a prospective cohort study of the U.S. Health and Retirement Study DNA-methylation sub-study. Socioeconomic status (SES) was measured from years of education and household wealth at baseline. The extent and pace of biological aging were quantified using three DNA-methylation measures: PhenoAge, GrimAge, and DunedinPoAm. Cognitive aging was measured from repeated longitudinal assessments of immediate and delayed word recall. Latent growth curve modeling estimated participants' level of memory performance and rate of decline over 2-11 follow-up assessments spanning 2-20 years. Multiple-group models were estimated to assess whether the relationship between SES and memory trajectories was mediated by biological aging across racial-ethnic by sex/gender subgroups. RESULTS: Data from a total of 3,997 adults aged 50-100 were analyzed. Participants with lower SES had lower memory performance, faster decline and exhibited accelerated biological aging (SES effect size associations (β) ranged from .08 to .41). Accelerated biological aging was associated with decreased memory performance and faster memory decline (effect-size range .03 to .23). SES-biological aging associations were strongest for White men and women and weakest for Latinx women. The relationship between biological aging measures and memory was weaker for Black participants compared with White and Latinx people. In mediation analysis, biological aging accounted for 4-27% of the SES-memory gradient in White participants. There was little evidence of mediation in Black or Latinx participants. DISCUSSION: Among a national sample of mid-to late-life adults, DNA-methylation measures of biological aging were variably associated with memory trajectories and SES across White, Black, and Latinx mid-to late-life adults. These results challenge the assumption that DNA-methylation biomarkers of aging that were developed in primarily White people can equivalently quantify aging processes affecting cognition in Black and Latinx mid-to late-life adults.
Keywords: biological aging; Cognition; DNA Methylation; Race/ethnicity; sex/gender; socio-economic status

Sole Family Survivors: Older Adults Lacking Family of Origin Kin. - Susan L. Brown; Kagan A Mellencamp; Lin, I-Fen (The Journals of Gerontology, Series B, 2022)
OBJECTIVES: We introduced a unique form of kinlessness: sole family survivorship, which describes the lack of family of origin (i.e., biological parents and siblings) kin. This form of kinlessness may be particularly consequential for older adults who experience other forms of kinlessness (e.g., no spouse/partner or no children) as they are especially likely to have relied on their family of origin for support. METHODS: Data from the 1998-2014 Health and Retirement Study (N = 148,346 person-waves) were used to estimate the prevalence of sole family survivorship among adults aged 55 and older and men and women aged 55-74 and 75+. Variation in prevalence levels of sole family survivorship across sociodemographic characteristics, health indicators, and family factors were also estimated. Finally, we tracked cohort trends in sole family survivorship. RESULTS: More than 1 in 10 adults aged 55+ were sole family survivors and this figure rose to more than 1 in 4 among those aged 75+. Adults with no spouse/partner and no children were especially likely to be sole family survivors, meaning they face a double burden of kinlessness. DISCUSSION: Sole family survivorship represents the culmination of loss of multiple, lifelong kin ties. It is more common among those lacking other close kin, signaling the presence of a uniquely vulnerable group of older adults who experience multiple forms of kinlessness. Future research should address how older adults and society at large adapt to kinlessness to ensure successful aging.
Keywords: Cohort; Death; gender; kinlessness; Marital Status

Sons and parental cognition in mid-life and older adulthood. - Wolfova, Katrin; Wu, Di; Weiss, Jordan; Cermakova, Pavla; Kohler, Hans-Peter; Skirbekk, Vegard Fykse; Stern, Yaakov; Gemmill, Alison; Tom, Sarah E (Journal of Psychiatric Research, 2022)
Prior research suggests a relationship between number of sons and maternal long-term health outcomes, including dementia. We assessed the relationship between having sons and parental cognitive aging. Specifically, we investigated the relationship between having at least 1 son and parental baseline cognition level and rate of cognitive decline, accounting for life course sociodemographic characteristics in a cohort of 13 222 adults aged ≥50 years from the US Health and Retirement Study. We included only participants with at least one child. We further explored whether this relationship varies by parental sex and whether the magnitude of the relationship increases with each additional son. Cognition was assessed biennially for a maximum of nine times as a sum of scores from immediate and delayed 10-noun free recall tests, a serial 7s subtraction test, and a backwards counting test. Associations were evaluated using linear mixed-effects models, stepwise adjusting for sociodemographic and health-related factors. In our analytic sample of parents, a total of 82.3% of respondents had at least 1 son and 61.6% of respondents were female. Parents of at least 1 son had a faster rate of cognitive decline in comparison to parents without any son. Our results also suggest that cognitive decline was faster among parents of multiple sons, compared to parents with only daughters. Thus, the results support the theory that having sons might have a long-term negative effect on parental cognition.
Keywords: cognitive aging; Dementia; offspring sex

Spenders Vs. Savers: How To Determine Your Retirement Spending Personality - T. Rowe Price (Forbes, 2022)
Keywords: Retirement; Saving; Spending

Spending Trajectories After Age 65 - Michael D Hurd; Rohwedder, Susann (Research Reports, 2022)
There is a large body of work concerned with the importance of saving for retirement and with developing tools to facilitate and support the accumulation of retirement wealth. Much less attention has been paid to the decumulation phase—that is, the spending down of wealth following retirement. Understanding the decumulation phase requires information about the spending patterns of older households and how those patterns evolve with age. The RAND Corporation has conducted extensive research on spending trajectories of older households. Building on this prior work, the authors provide statistics on household spending and its composition based on longitudinal data from the Health and Retirement Study. They present estimates of the trajectories of spending after age 65 among single and coupled households stratified by wealth holdings observed at or closely following age 65. According to the results, real spending declined for both single and coupled households. The rates of decline varied only modestly across initial wealth quartiles. The fact that spending declines broadly, even among those in the highest wealth quartile, suggests that the decline is not related to economic position. The authors discuss how the estimated trajectories can help with the prediction of households' spending needs at older ages.
Keywords: health care cost; Households; Personal finance; Retirement; retirement benefits; socioeconomic status

Spending Trajectories After Age 65: Variation by Initial Wealth - Michael D Hurd; Susann Rohwedder (Research Reports, 2022)
There is a large body of work concerned with the importance of saving for retirement and with developing tools to facilitate and support the accumulation of retirement wealth. Much less attention has been paid to the decumulation phase—that is, the spending down of wealth following retirement. Understanding the decumulation phase requires information about the spending patterns of older households and how those patterns evolve with age. The RAND Corporation has conducted extensive research on spending trajectories of older households. Building on this prior work, the authors provide statistics on household spending and its composition based on longitudinal data from the Health and Retirement Study. They present estimates of the trajectories of spending after age 65 among single and coupled households stratified by wealth holdings observed at or closely following age 65. According to the results, real spending declined for both single and coupled households. The rates of decline varied only modestly across initial wealth quartiles. The fact that spending declines broadly, even among those in the highest wealth quartile, suggests that the decline is not related to economic position. The authors discuss how the estimated trajectories can help with the prediction of households' spending needs at older ages.
Keywords: Retirement; Savings; Spending

SPOUSAL ASSOCIATIONS BETWEEN GRANDPARENT CAREGIVING AND WELL-BEING: FINDINGS FROM THE HEALTH AND RETIREMENT STUDY - Chan, Athena Chung Yin; Sneed, Rodlescia (Innovation in Aging, 2022)
Numerous studies document the impact of grandparent caregiving on the health and well-being of grandparents; however, there has been little dyadic research on how the caregiving and health-related outcomes of one grandparent influence partner couples The purpose of this study was to determine the interdependence of grandparents’ intensity of caregiving and well-being (i.e., depressive symptoms and self-rated health) over time. Participants were 7,133 dyads of American grandparents aged ≥ 50 who participated in the Health and Retirement Study, a population-based study of community-dwelling adults, in 2010 and 2012. Data on hours of grandparent caregiving in the past two years, depressive symptoms, and self-rated health were obtained via self-report. Two longitudinal, dyadic path analyses were conducted using the Actor-Partner Interdependence Model. Within individuals (actor effects), greater depressive symptoms and better self-rated health at baseline, predicted greater depressive symptoms and better self-rated health two years later. Between spouses (partner effects), an individuals’ greater depressive symptoms predicted the spouses’ greater depressive symptoms. However, grandfathers’ better self-rated health predicted subsequent better grandmothers’ self-rated health, but not vice versa. Further, greater depressive symptoms among grandmothers predicted lower subsequent caregiving intensity among both grandmothers and grandfathers. Additionally, better self-rated health among grandfathers predicted better self-rated health and lower subsequent self and spousal grandparenting caregiving intensity. Our findings demonstrate that depressive symptoms, self-rated health, and caregiving intensity are interrelated among grandparent couples. Interventions for improving well-being and caregiving outcomes that focus on couples may be more effective than those that focus on individuals.
Keywords: Caregiving; grandparent; Spouses; Well-being

Startling News: Chronic Health Conditions Are Far More Common in Recent Generations - Penn State University (SciTechDaily, 2022)
Keywords: chronic health conditions; generations; multimorbidity

State-level metabolic comorbidity prevalence and control among adults age 50-plus with diabetes: estimates from electronic health records and survey data in five states. - Mardon, Russell; Campione, Joanne; Nooney, Jennifer; Merrill, Lori; Johnson, Maurice; Marker, David; Jenkins, Frank; Saydah, Sharon; Rolka, Deborah; Zhang, Xuanping; Shrestha, Sundar; Gregg, Edward (Population Health Metrics, 2022)
BACKGROUND: Although treatment and control of diabetes can prevent complications and reduce morbidity, few data sources exist at the state level for surveillance of diabetes comorbidities and control. Surveys and electronic health records (EHRs) offer different strengths and weaknesses for surveillance of diabetes and major metabolic comorbidities. Data from self-report surveys suffer from cognitive and recall biases, and generally cannot be used for surveillance of undiagnosed cases. EHR data are becoming more readily available, but pose particular challenges for population estimation since patients are not randomly selected, not everyone has the relevant biomarker measurements, and those included tend to cluster geographically. METHODS: We analyzed data from the National Health and Nutritional Examination Survey, the Health and Retirement Study, and EHR data from the DARTNet Institute to create state-level adjusted estimates of the prevalence and control of diabetes, and the prevalence and control of hypertension and high cholesterol in the diabetes population, age 50 and over for five states: Alabama, California, Florida, Louisiana, and Massachusetts. RESULTS: The estimates from the two surveys generally aligned well. The EHR data were consistent with the surveys for many measures, but yielded consistently lower estimates of undiagnosed diabetes prevalence, and identified somewhat fewer comorbidities in most states. CONCLUSIONS: Despite these limitations, EHRs may be a promising source for diabetes surveillance and assessment of control as the datasets are large and created during the routine delivery of health care. TRIAL REGISTRATION: Not applicable.
Keywords: Comorbidity; Diabetes Mellitus; Electronic Health Records; Prevalence; Self Report

Staying Optimistic: Older Americans’ Retirement Expectations Remain Uninterrupted Despite COVID-19 Impact - Liu, Zhikun (EBRI Issue Brief, 2022)
Employees’ retirement expectations have played important roles in predicting retirement decisions, making policy proposals, and designing financial products and services to help American workers better plan for their future retirement. From stochastic retirement readiness model design to Social Security benefits projection estimations and from defined contribution (DC) plan saving strategy to Monte Carlo retirement goals success rate calculations, people’s expected retirement age is a crucial factor for industry advisors, academics, and financial planners to design retirement services and projection models, study decision behaviors, and make sound advice for their clients. In this Issue Brief, we focus on investigating the potential influence of COVID-19 on the participants’ working and financial situations in 2020, as well as their decisions regarding retirement and Social Security claiming ages.
Keywords: COVID-19; retirement expectations

Stress is a Latent Construct: Exploring the Differential Experience of Stress and Discrimination on Depressive Symptoms Among Black Older Adults. - Brown, Lauren L; García, Catherine; Reeves, Alexis N; Pamplin, John R; Mitchell, Uchechi A (Journal of Aging and Health, 2022)
While evidence highlights the detrimental mental health consequences of chronic stress exposure, the impact of this stress exposure on older Black Americans' mental health varies by exposure to other types of stressors like discrimination as well as subjective evaluations of stress like chronic stress appraisal. Using data from the 2010/2012 Health and Retirement Study, we use latent profile analysis (LPA) to describe 2,415 Black older adults experience with chronic stress exposure, appraisal, and discrimination and examine which stress contexts are associated with depressive symptomology. Analyses revealed five stress clusters-demonstrating the diversity in the stress experience for older Black adults. Black older adults with stress profiles that include lower stress appraisal report fewer depressive symptoms regardless of number of stress exposures. LPA is as an alternative approach to examining the stress-mental health link that can define stress profiles by both exposure and appraisal-based measures.
Keywords: Chronic stress; Mental Health; Racism; stress appraisal

Structural and Functional Aspects of Social Relationships and Episodic Memory: Between-Person and Within-Person Associations in Middle-Aged and Older Adults. - Hülür, Gizem (Gerontology, 2022)
OBJECTIVES: A growing body of research has documented associations between social relationships and cognitive function, while findings are less clear regarding specific aspects of social relationships that are relevant to change in cognitive function. Furthermore, it is unclear whether associations differ at the between-person and within-person levels. METHOD: The present study used 8-year longitudinal data from the Health and Retirement Study (HRS) to examine the role of structural (partnered/married, number of social network partners, and contact frequency) as well as functional (support, strain, and loneliness) aspects of social relationships for episodic memory at the between-person and within-person levels. Analyses are based on up to 3 waves of data from 19,297 participants (mean age at baseline = 66 years, SD = 10, range = 50-104; 58% women). Control variables include age at baseline, gender, education, functional health, and depressive symptoms. RESULTS: Findings showed that at the between-person level, most structural and functional aspects were related to levels of memory performance, with participants with higher numbers of social network members, more frequent contact, and more positive experiences outperforming others. An exception was a higher number of family (child or relative) relationships. At the within-person level, on occasions where participants had a higher number of close family relationships than usual, had more social contact than usual, and felt less lonely than usual, they also showed higher than usual episodic memory performance. Finally, negative effects of social strain and loneliness on episodic memory performance at the between-person level were moderated by social network size, indicating that effects were more negative among individuals with larger social networks. DISCUSSION: Both structural and functional aspects of social relationships contribute to between-person differences in levels and fluctuations of episodic memory performance. Ups and downs of relationships to relatives, social contact, and feelings of loneliness contribute to ups and downs of episodic memory. Potential mechanisms underlying these associations are discussed.
Keywords: Episodic Memory; longitudinal change; Social networks; Social Relationships; Social Support

Study: Boomers have more medical woes than their parents did at same age - Clanton, Nancy (The Atlanta Journal-Constitution, 2022)
Keywords: boomers; Chronic condition; depression

Study estimates the burden of dementia among older adults in the U.S. - Henderson, Emily (News-Medical.Net, 2022)
Keywords: cognitive impairment; Dementia; HCAP

Study Evaluates Link Between Chronic Stress and Insomnia in Aging Population - Grossi, Giuliana (HCP Live Network, 2022)
Keywords: Chronic stress; COVID-19; insomnia

Study Finds Mental Decline Is Causing Financial Trouble For Millions Of Seniors - Bradford, Beth (Health Digest, 2022)
Keywords: Cognition; Finances

Study links genetically-predicted BMI to discrimination and declining life satisfaction among older adults - Ellwood, Beth (PsyPost, 2022)
Keywords: BMI; Discrimination; polygenic scores

Study Shows Need for Geriatric Principles in Critical Care Medicine - Jacobs, Sheila (Critical Care, 2022)
Keywords: Critical Care; Dementia; Disability; Frailty; multimorbidity

Subjective Age and Falls in Older Age: Evidence from two Longitudinal Cohorts. - Fundenberger, Hervé; Stephan, Yannick; Terracciano, Antonio; Dupré, Caroline; Bongue, Bienvenu; Hupin, David; Barth, Nathalie; Canada, Brice (The Journals of Gerontology, Series B, 2022)
OBJECTIVES: Falls are a common and serious health problem. The present study examined the association between subjective age (i.e., feeling younger or older than one's chronological age) and falls in two large national samples. METHOD: Participants, aged 65 to 105 years old, were drawn from the National Health and Aging Trends Study (NHATS) and the Health and Retirement Study (HRS). Data on falls, subjective age, demographic factors, was available from 2,382 participants in HRS and 3,449 in NHATS. Falls were tracked for up to 8 (HRS) and 7 (NHATS) years. RESULTS: Cox regression analyses that included demographic covariates indicated that older subjective age increased the risk of falling in HRS (hazard ratio [HR]=1.17, 95% confidence interval [CI]=1.08-1.27), and in NHATS (HR=1.06, 95%CI=1.00-1.13). When compared to people who felt younger, people who reported an older subjective age had a higher risk of fall (HRS: HR=1.65, 95% CI=1.33-2.04; NHATS: HR=1.44, 95% CI=1.15-1.79). The associations remained significant after accounting for depressive symptoms, handgrip strength, chronic diseases, and cognitive impairment in HRS only. DISCUSSION: These results confirm the role of subjective age as an important health marker in the aging population. Subjective age assessment can help identify individuals at greater risk of falls.
Keywords: falling; Felt age; Survival Analysis

Subjective Aging and Objectively Assessed Hearing Function: A Prospective Study of Older Adults. - Yannick Stephan; Angelina R Sutin; Antonio Terracciano (The Journals of Gerontology, Series B, 2022)
OBJECTIVES: Subjective aging is consistently related to a range of health-related outcomes, but little is known about its relationship with sensory functioning. The present prospective study tested whether subjective age and self-perceptions of aging (SPA) are associated with objective hearing function. METHOD: Participants were 7,085 individuals aged 50 to 93 years (60% women, Mean= 65.15, SD= 8.71) from the Health and Retirement Study (HRS). Measures of subjective age, SPA, and information on demographic factors were obtained in 2008/2010. Objective hearing function was assessed eight years later in 2016/2018. Furthermore, potential mediating variables (c-reactive protein, body mass index, physical inactivity, and chronic conditions) were assessed in 2012/2014. RESULTS: In regression analyses that accounted for demographic factors, older subjective age and negative SPA were associated with lower hearing acuity eight years later. In addition, 1 SD older subjective age and negative SPA were related to a 9% and 7% higher likelihood of hearing impairment. Mediation analyses revealed that physical inactivity and chronic conditions partially mediated subjective age and SPA associations with hearing acuity. There was little evidence that the link between subjective aging and hearing was moderated by hearing aids and partial support for a moderating role of age. CONCLUSION: This study provides new evidence that subjective aging is prospectively related to hearing function. Individuals with older subjective age or negative SPA have unfavorable behavioral and clinical profiles that explain part of their lower hearing function. Individuals' experience with their aging process is a marker of risk for impaired hearing.
Keywords: hearing acuity; self-perceptions of aging; Subjective age

Subjective Cognitive Decline: Is a Resilient Personality Protective Against Progression to Objective Cognitive Impairment? Findings from Two Community-Based Cohort Studies. - Aschwanden, Damaris; Sutin, Angelina R; Ledermann, Thomas; Luchetti, Martina; Stephan, Yannick; Sesker, Amanda A; Zhu, Xianghe; Terracciano, Antonio (Journal of Alzheimer's Disease, 2022)
BACKGROUND: Subjective cognitive decline (SCD) is related to personality functioning and risk of subsequent objective cognitive impairment. OBJECTIVE: The aim of this study was to examine whether lower neuroticism and higher conscientiousness-resilient personality traits-protect against conversion from SCD to objective cognitive impairment in two longitudinal community-based cohorts. METHODS: Data from the Health and Retirement Study (N = 1,741, Mean age = 68.64 years, Follow-up mean = 7.34 years) and the National Health and Aging Trends Survey (N = 258, Mean age = 79.34 years, Follow-up mean = 4.31 years) were analyzed using Cox regression analysis, controlling for sociodemographic covariates, symptoms of anxiety and depression, and apolipoprotein ɛ4. RESULTS: The pooled results showed that lower neuroticism and higher conscientiousness were associated with decreased risk of conversion from SCD to objective cognitive impairment. CONCLUSION: Among individuals with SCD, those with a resilient personality may have more cognitive and psychological reserve to maintain cognitive functioning and delay conversion to objective cognitive impairment. The findings further contribute to a better understanding of personality along the cognitive continuum: The observed effect sizes were smaller than those reported in cognitively normal individuals but larger than in individuals with mild cognitive impairment. Personality could provide useful information to identify individuals with SCD who may develop objective cognitive impairment-namely those who hold a vulnerable personality (higher neuroticism, lower conscientiousness).
Keywords: Apolipoprotein E4; Cognitive Dysfunction; Personality; Personality Disorders

Subjective markers of successful aging and change in Internet use among older adults: The distinctive role of subjective health - Xiaoqing Wan; Nichole R. Lighthall; Daniel Paulson (Computers in Human Behavior, 2022)
Lower rates of Internet adoption among older adults pose significant challenges in delivering important online services to older adults. Addressing the age-related digital divide requires determining factors that can influence Internet use in aging and may be targeted for intervention. Candidate factors include self-perceptions associated with successful aging, but prior research has not determined whether changes in self-perceptions are related to changes in Internet use within individuals. The present study examined the relationship between self-perception measures (subjective age, subjective health, and life satisfaction) and Internet use among older adults, using longitudinal data from the Health and Retirement Study. Results indicated a selectively robust relationship between Internet use and better subjective health among older Americans. Further, these relationships were not altered by changes in technology adoption over time. Finally, longitudinal data over eight years revealed that change in Internet use was selectively associated with changes in subjective health. Together, these results indicate that among self-perception measures of successful aging, subjective health has a robust relationship with both current Internet use and changes in Internet use over time among older Americans. Such findings suggest that effective interventions to increase digital technology utilization likely require accommodations for older adults with poor subjective health.
Keywords: Internet use; Life Satisfaction; Self-perceptions; Subjective age; Subjective health

Subjective religiosity as resilience to stressful life events in middle-aged and older African Americans - Shari A. Brown; Frank J. Floyd (Journal of Religion, Spirituality & Aging, 2022)
This study examined stressful life events, discrimination, and well-being among older African Americans. Through a risk and resilience framework we evaluate the role of subjective religiosity as a moderator. Stressful life events and discrimination represent a double jeopardy risk profile in which discrimination exacerbates the negative relationship between stressful life events and well-being. Subjective religiosity is a resilience resource that should buffer the effect of discrimination on the stress – well-being link. Stressful life events and discrimination predicted poorer well-being, discrimination exacerbated the negative effects of stressful life events on depression and life-satisfaction, but subjective religiosity reduced these effects.
Keywords: African Americans; Discrimination; double jeopardy; Resilience; subjective religiosity

S-207 Multidimensional employment quality, retirement trajectories and cardiometabolic health in later life in the US - Sarah B. Andrea; Eisenberg-Guyot, Jerzy; Peckham, Trevor; Vanessa M Oddo; Hajat, Anjum (Occupational and Environmental Medicine, 2021)
Introduction The working lives of Americans have become less stable over the past several decades and older adults may be particularly vulnerable to these changes in employment quality (EQ).Objective We examined later-life multidimensional EQ and retirement trajectories of older Americans and the potential consequences worsening EQ may have for cardiometabolic health and health inequities in this population.Methods Using longitudinal data on employment stability, material rewards, workers’ rights, working-time arrangements, unionization, and interpersonal power relations from the Health and Retirement Study, we used principal component analysis to construct an EQ score. Then, we used sequence analysis to identify late-career EQ trajectories (age 50–70 years; N=11,958 respondents), overall and by race, gender, educational attainment, marital status. Finally, we estimated the association between trajectory-membership and post-sequence-analysis-period prevalence of poor cardiometabolic health.Results We identified ten EQ trajectories; the most prevalent trajectories were Minimally Attached and Wealthy (13.9%) and Good EQ to Good Retirement (13.7%), however, 42% of respondents were classified into suboptimal trajectories. Those in suboptimal trajectories were disproportionately women, Hispanic and/or Black, Indigenous and People of Color, and those with lower educational attainment. Moreover, those in suboptimal trajectories tended to report the worse cardiometabolic health. For example, the prevalence of hypertension was lowest for those in the Wealthy Business Owners trajectory and highest for Workers with Premature Mortality, followed by workers with Fair EQ and Good but Diminishing Wealth in Retirement.Conclusion EQ is inequitably distributed and may play a role in cardiometabolic health inequities in later life.
Keywords: cardiometabolic health; employment quality; Retirement

Same-Sex Couples and Cognitive Impairment: Evidence from the Health and Retirement Study. - Hui Liu; Hsieh, Ning; Zhang, Zhenmei; Zhang, Yan; Kenneth M. Langa (The Journals of Gerontology: Series B, 2021)
OBJECTIVES: We provide the first nationally representative population-based study of cognitive disparities among same-sex and different-sex couples in the United States. METHOD: We analyzed data from the Health and Retirement Study (2000-2016). The sample included 23,669 respondents (196 same-sex partners and 23,473 different-sex partners) aged 50 and older who contributed to 85,117 person-period records (496 from same-sex partners and 84,621 from different-sex partners). Cognitive impairment was assessed using the modified version of the Telephone Interview for Cognitive Status (TICS). Mixed-effects discrete-time hazard regression models were estimated to predict the odds of cognitive impairment. RESULTS: The estimated odds of cognitive impairment were 78% (p < .01) higher for same-sex partners than for different-sex partners. This disparity was mainly explained by differences in marital status and, to a much lesser extent, by differences in physical and mental health. Specifically, a significantly higher proportion of same-sex partners than different-sex partners were cohabiting rather than legally married (72.98% vs. 5.42% in the study sample), and cohabitors had a significantly higher risk of cognitive impairment than their married counterparts (OR = 1.53, p < .001). DISCUSSION: The findings indicate that designing and implementing public policies and programs that work to eliminate societal homophobia, especially among older adults, is a critical step in reducing the elevated risk of cognitive impairment among older same-sex couples.
Keywords: cognitive impairment; gender; Marital Status; same-sex couples; sexual minorities

A Secondary Data Analysis of the Pr y Data Analysis of the Prevalence of Reported Dementia and Subjective Cognitive Decline Across U.S. National Surveys - Picchiello, Matthew C. (Washington University, 2021)
Within the United States, many large-scale, nationally representative studies exist with the goal of tracking and monitoring aspects of health. These studies are often used to establish the prevalence of dementia and subjective cognitive decline (SCD) in the population. The goal of the current study is to examine how different population-based studies probe respondents about conditions related to cognitive impairment, and to assess similarities and differences in point estimates. We reviewed eight studies and identified comparable items related to dementia and SCD. We calculated design-appropriate point prevalence estimates and compared weighted estimates across studies, finding a wide range and statistically significantly different estimates for dementia (estimates ranging from 2.7% - 9.9%) and for SCD (5.6% - 46.6%). Close analysis of item construction revealed meaningful differences in the use of terminologies and timeframes that could account for these differences. Moreover, subtle but consequential sampling differences were also discovered within study documentation that also could be responsible. Given the importance of prevalence estimates for research, practice, and policy, our findings highlight the need for harmonization across methodology in these large studies, even at their most basic level, to establish the true burden of these conditions.
Keywords: Dementia; Prevalence; secondary data analysis; self-report; subjective cognitive decline

Self-Rated Health and Incident Dementia over Two Decades: Replication Across Two Cohorts - Yannick Stephan; Angelina R Sutin; Martina Luchetti; Damaris Aschwanden; Antonio Terracciano (Journal of Psychiatric Research, 2021)
This prospective study examined the association between self-rated health and incident dementia in two large cohorts of middle-aged and older adults. Participants were drawn from the Health and Retirement Study (HRS, N= 13,839, Mean Age= 64.32, SD= 9.04) and the English Longitudinal Study of Ageing (ELSA, N=4649, Mean Age = 64.44, SD= 9.97). Self-rated health and covariates were assessed at baseline in 1998 and 2002, and cognitive status was tracked for up to 21 years in HRS and 17 years in ELSA, respectively. Controlling for demographic factors, poorer self-rated health was associated with higher risk of incident dementia in HRS (HR: 1.18, 95%CI: 1.12-1.24, p<.001) and ELSA (HR: 1.38, 95%CI: 1.23-1.55, p<.001). These associations remained significant when diabetes, hypertension, smoking, physical inactivity, depressive symptoms, personality, and polygenic risk for Alzheimer’s Disease were included as additional covariates or when cases occurring within the first ten years of follow-up were excluded from the analyses. There was no replicable evidence that age, sex, education, race or ethnicity moderated the association. Self-rated health is a long-term, replicable predictor of incident dementia that is independent of genetic, clinical, and behavioral risk factors.
Keywords: Dementia; longitudinal; Risk Factors; Self-rated health

Self-Reported Dementia-Related Diagnosis Underestimates the Prevalence of Older Americans Living with Possible Dementia. - Ryan P McGrath; Sheria G Robinson-Lane; Brian C Clark; Suhr, Julie A; Bruno J Giordani; Brenda Vincent (Journal of Alzheimer's Disease, 2021)
BACKGROUND: Dementia screening is an important step for appropriate dementia-related referrals to diagnosis and treat possible dementia. OBJECTIVE: We sought to estimate the prevalence of no reported dementia-related diagnosis in a nationally representative sample of older Americans with a cognitive impairment consistent with dementia (CICD). METHODS: The weighted analytical sample included 6,036,224 Americans aged at least 65 years old that were identified as having a CICD without history of stroke, cancers, neurological conditions, or brain damage who participated in at least one-wave of the 2010-2016 Health and Retirement Study. The adapted Telephone Interview of Cognitive Status assessed cognitive functioning. Those with scores≤6 were considered as having a CICD. Healthcare provider dementia-related diagnosis was self-reported. Age, sex, educational achievement, and race and ethnicity were also self-reported. RESULTS: The overall estimated prevalence of no reported dementia-related diagnosis for older Americans with a CICD was 91.4%(95%confidence interval (CI): 87.7%-94.1%). Persons with a CICD who identified as non-Hispanic black had a high prevalence of no reported dementia-related diagnosis (93.3%; CI: 89.8%-95.6%). The estimated prevalence of no reported dementia-related diagnosis was greater in males with a CICD (99.7%; CI: 99.6%-99.8%) than females (90.2%; CI: 85.6%-93.4%). Moreover, the estimated prevalence of no reported dementia-related diagnosis for non-high school graduates with a CICD was 93.5%(CI: 89.3%-96.1%), but 90.9%(CI: 84.7%-94.7%) for those with at least a high school education. CONCLUSION: Dementia screening should be encouraged during routine geriatric health assessments. Continued research that evaluates the utility of self-reported dementia-related measures is also warranted.
Keywords: Aging; Cognitive Dysfunction; Geriatric Assessment; Geriatrics; Healthcare Disparities

A semi-parametric Bayesian dynamic hurdle model with an application to the health and retirement study - Kiranmoy Das; Pareek, Bhuvanesh; Brown, Sarah; Pulak Ghosh (Computational Statistics, 2021)
All developed countries are facing the problem of providing affordable and high quality healthcare in recent years. This is due to the combination of an ageing population and the technological advancement in health science which leads to an increased life expectancy. This will affect the future use of hospital inpatient and outpatient services which in turn will place a significant stress on the economy since most medical services for the elderly are apportioned and funded under a national system. Thus, understanding the demand for healthcare and other key factors influencing the demand is crucial to better serve citizens. Hospital admission is considered to be a key proxy of the demand for healthcare, especially in the context of ageing populations as experienced globally. However, modeling hospital admissions, although very important, is often complicated by zero-inflation, by the covariates with time-varying effects, and by the necessity of borrowing information across individuals. Additionally, the rate of hospital admissions might differ between the group of individuals who have been hospitalized before and the group yet to be hospitalized. Also when individuals are clustered based on their baseline self-assessed health status, the distribution of hospital admissions and its relation to predictors may be quite different across and within different groups. In this paper we propose a unified Bayesian dynamic hurdle model which accommodates these features of the data in a semi-parametric approach. We analyze the data collected by the United States Health and Retirement Study in which the rate of hospital admissions varies across different self-assessed health groups. Simulation studies are performed for assessing the usefulness of the proposed model.
Keywords: Bayesian models; Dynamic hurdle model; Hospital admissions; Lasso; Matrix Stick-Breaking Process; Zero-inflated data

Semiparametric methods for incomplete longitudinal count data with an application to Health and Retirement Study - Zubair, Seema; Sinha, Sanjoy K. (Journal of Applied Statistics, 2021)
In this paper, we propose and explore a novel semiparametric approach to analyzing longitudinal count data. We address the issue of missingness in longitudinal data and propose a weighted generalized estimations equations approach to fitting marginal mean response models for count responses with dropouts. Also, we investigate a spline regression approach to approximating the curvilinear relationship between the mean response and covariates. The asymptotic properties of the proposed estimators are studied in some detail. The empirical properties of the estimators are investigated using Monte Carlo simulations. An application is also provided using actual survey data obtained from the Health and Retirement Study (HRS).
Keywords: Generalized estimating equation; inverse probability weight; Missing response; Monte Carlo Method; semiparametric method; spline regression

Sense of Purpose in Life and Subsequent Physical, Behavioral, and Psychosocial Health: An Outcome-Wide Approach. - Eric S Kim; Chen, Ying; Julia S Nakamura; Carol D Ryff; Tyler J VanderWeele (American Journal of Health Promotion, 2021)
PURPOSE: Growing evidence indicates that a higher sense of in life () is associated with reduced risk of chronic diseases and mortality. However, epidemiological studies have not evaluated if change in is associated with subsequent health and well-being outcomes. DESIGN: We evaluated if positive change in (between t; 2006/2008 and t;2010/2012) was associated with better outcomes on 35 indicators of physical health, health behaviors, and psychosocial well-being (at t;2014/2016). SAMPLE: We used data from 12,998 participants in the Health and Retirement study-a prospective and nationally representative cohort of U.S. adults aged >50. ANALYSIS: We conducted multiple linear-, logistic-, and generalized linear regressions. RESULTS: Over the 4-year follow-up period, people with the highest (versus lowest) purpose had better subsequent physical health outcomes (e.g., 46% reduced risk of mortality (95% CI [0.44, 0.66])), health behaviors (e.g., 13% reduced risk of sleep problems (95% CI [0.77, 0.99])), and psychosocial outcomes (e.g., higher optimism (β = 0.41, 95% CI [0.35, 0.47]), 43% reduced risk of depression (95% CI [0.46, 0.69]), lower loneliness (β = -0.35, 95% CI [-0.41, -0.29])). Importantly, however, purpose was not associated with other physical health outcomes, health behaviors, and social factors. CONCLUSION: With further research, these results suggest that sense of purpose might be a valuable target for innovative policy and intervention work aimed at improving health and well-being.
Keywords: Epidemiology; psychological well-being; Purpose in life; Sense of purpose; Well-being

Sensitization or inoculation: Investigating the effects of early adversity on personality traits and stress experiences in adulthood. - Luo, Jing; Zhang, Bo; Brent W Roberts (PLoS One, 2021)
Cumulative evidence has been found for the associations between personality traits and stress experiences in adulthood. However, less is known about the moderating mechanisms underlying these associations. The present study tested whether the stress sensitization and stress inoculation hypotheses could be applied to the relationship between early adversity and personality in adulthood. Specifically, we tested the linear and curvilinear relations between early adversity (measured retrospectively) and adulthood personality traits, as well as the linear and curvilinear moderating effects of early adversity on the associations between adulthood stress and personality traits. Samples of older adults from the Health and Retirement Study (HRS; N = 6098) and middle-aged adults from the Midlife in the United States Survey (MIDUS; N = 6186) were used. Across the two samples, positive linear associations were found between retrospective early adversity and neuroticism. The results also suggested significant linear effects of early adversity on the association between ongoing chronic stressors and neuroticism such that individuals with moderate exposure to early adversity showed stronger associations between ongoing chronic stressors and neuroticism. Results from the current research were more in line with the stress sensitization model. No support was found for the stress inoculation effects on personality.
Keywords: Personality Traits; Stress

Sex, age, BMI, and C-Reactive Protein impact the odds of developing hypertension - findings based on data from the Health and Retirement Study (HRS). - Speer, H; D'Cunha, N M; Naumovski, N; McKune, A J (American Journal of Hypertension, 2021)
BACKGROUND: Hypertension is a major contributor to cardiovascular diseases and premature death. Despite widespread use of antihypertensive medication, it remains a concern, therefore determining factors that contribute to such a high burden of disease is critically important. This study examined anthropometric and physical measurements, as well as blood and saliva biomarkers, as predictors for hypertension using datasets from the 2008 Health and Retirement Study. METHODS: A total of 2924 participants (aged 74.84 ± 6.45 years) were included. Binary logistic regression was performed to ascertain the effects of sex, age, telomere length, C-reactive protein (CRP), BMI, and additional markers on the odds of developing hypertension. RESULTS: Males had 2.3 times the odds (OR = 2.313 CI 95% (1.391, 3.845); p = 0.001) of being hypertensive if they were obese, females had 1.7 times the odds (OR = 1.788 CI 95% (1.260,2.536); p = 0.001) if overweight, and 2.4 times (OR = 2.479 CI 95% (1.693, 3.630); p < 0.001) if obese. Age in females was an independent predictor where every one-year increase in age was tied to a 5.1% increase in being hypertensive (OR = 1.051 CI 95% (1.027, 1.075); p <0.001) and, CRP (>3mg/L) had 1.4 times the odds (OR = 1.447 CI 95% (1.079, 1.942); p = 0.014). CONCLUSIONS: This study provides verification for BMI as a predictor for hypertension and proposes age and CRP as predictors for females. Specific sex differences and life stage should be considered when evaluating hypertension risk to improve clinical outcomes and promote healthy aging.
Keywords: BMI; C-reactive protein; Hypertension; Inflammation; Telomere length

Sex and racial/ethnic associations with post-stroke cognitive decline: longitudinal analyses from the health and retirement study - Bako, Abdulaziz; Potter, Thomas; Pan, Alan; Smith, M. (World Stroke Congress, 2021)
Background and Aims Evidence on sex and race/ethnic disparities in post-stroke cognitive decline have largely been inconclusive. We investigate these disparities using a series of quasi-experimental models. Methods Using the Health and Retirement Study (HRS), a biennial survey of a nationally representative sample of community dwellers in the US aged 51 years and older, we applied the two-way fixed effects model, event study design, and Bacon’s weighted difference-in-differences (DiD) estimation for survey panel data (1996 − 2016), to evaluate the differences in the modified Telephone Interview for Cognitive Status (TICS-m) score (lower scores representing lower cognitive functioning) between patients with and without self-reported incident stroke, while controlling for observed and unobserved time-invariant baseline participant characteristics such as age and education, as well as time-specific confounders. Results Of the 35,451 HRS participants that met the inclusion criteria (Figure.1), 4,620 (13.03%) had incident stroke. The mean (SD) TICS-m score post vs pre incident stroke was 12.8 (0.02) vs. 15.5 (0.07). The two-way fixed effects estimator for the relationship between incident stroke and cognitive decline was −1.21(95% CI:−1.32,−1.10), which was similar to the weighted DiD estimate of −1.25(95% CI:−1.38,−1.13). Event study revealed a continuous decline in TICS-m score, up to 10 years after stroke incidence in the overall sample, as well as among females and white non-Hispanics (Figure.1). However, the decline in TICS-m score plateaued from the third wave post-stroke for males and second wave post-stroke for black non-Hispanics. Conclusions Sex and race differences may illuminate variations in cognitive decline associated with stroke.
Keywords: Cognitive decline; post-stroke; Racial/ethnic differences; sex

Sex differences in functional limitations and the role of socioeconomic factors: a multi-cohort analysis - Mikaela Bloomberg; Aline Dugravot; Benjamin Landré; Annie Britton; Andrew Steptoe; Archana Singh-Manoux; Séverine Sabia (The Lancet Healthy Longevity, 2021)
Summary Background Women are more likely to have functional limitations than are men, partly because of greater socioeconomic disadvantage. However, how sex differences vary by severity of functional limitations remains unclear. We examined sex differences in functional limitations, with attention to socioeconomic factors and severity of limitations. Methods Longitudinal data on limitations in basic activities of daily living (ADL) and instrumental activities of daily living (IADL) and mobility activities were drawn from 62 375 participants from 14 countries. For ADL, IADL, and mobility, participants were categorised based on number of limited activities (0, 1, 2, or ≥3). Sex differences in limitations in four birth cohorts (1895–1929, 1930–38, 1939–45, and 1946–60) were analysed before and after adjustment for socioeconomic factors (education and labour force status). Findings The prevalence of IADL and ADL limitations was higher in women than in men. After adjustment for socioeconomic factors, this sex difference was attenuated. The sex difference in IADL limitations at age 75 years (in the 1895–1929 cohort) was 3·7% before adjustment for socioeconomic factors (95% CI 2·6–4·7) and 1·7% (1·1–2·2) after adjustment. For ADL, the sex difference in limitations at age 75 years (in the 1895–1929 cohort) was 3·2% (2·3–4·1) before adjustment for socioeconomic factors and 1·4% (0·9–1·8) after adjustment. Sex differences in mobility limitations (16·1%, 95% CI 14·4–17·7) remained after adjustment for socioeconomic factors (14·3%, 12·7–15·9). After age 85 years, women were more likely to have three or more IADL or mobility limitations and men were more likely to have one or two limitations. Interpretation Socioeconomic factors largely explain sex differences in IADL and ADL limitations but not mobility. Sex differences in mobility limitations in midlife are important targets for future research and interventions. Funding National Institute on Aging, UK National Institute for Health Research, European Commission, and US Social Security Administration.
Keywords: Activities of Daily Living; ELSA; Functional limitations; Sex differences; SHARE; Sister studies; Socioeconomic factors; TILDA

Sex differences in mortality: results from a population-based study of 12 longitudinal cohorts - Wu, Yu-Tzu; Niubo, Albert Sanchez; Daskalopoulou, Christina; Moreno-Agostino, Dario; Stefler, Denes; Bobak, Martin; Oram, Sian; Prince, Martin; Matthew Prina (CMAJ, 2021)
BACKGROUND: Women generally have longer life expectancy than men but have higher levels of disability and morbidity. Few studies have identified factors that explain higher mortality in men. The aim of this study was to identify potential factors contributing to sex differences in mortality at older age and to investigate variation across countries.METHODS: This study included participants age >= 50 yr from 28 countries in 12 cohort studies of the Ageing Trajectories of Health: Longitudinal Opportunities and Synergies (ATHLOS) consortium. Using a 2-step individual participant data meta-analysis framework, we applied Cox proportional hazards modelling to investigate the association between sex and mortality across different countries. We included socioeconomic (education, wealth), lifestyle (smoking, alcohol consumption), social (marital status, living alone) and health factors (cardiovascular disease, diabetes, mental disorders) as covariates or interaction terms with sex to test whether these factors contributed to the mortality gap between men and women.RESULTS: The study included 179 044 individuals. Men had 60% higher mortality risk than women after adjustment for age (pooled hazard ratio [HR] 1.6; 95% confidence interval 1.5–1.7), yet the effect sizes varied across countries (I2 = 71.5%, HR range 1.1–2.4). Only smoking and cardiovascular diseases substantially attenuated the effect size (by about 22%).INTERPRETATION: Lifestyle and health factors may partially account for excess mortality in men compared with women, but residual variation remains unaccounted for. Variation in the effect sizes across countries may indicate contextual factors contributing to gender inequality in specific settings.
Keywords: CHARLS; ELSA; JSTAR; KLoSA; Men; Mortality; SHARE; women

Sex, Race, and Age Differences in Prevalence of Dementia in Medicare Claims and Survey Data - Zhu, Yingying; Chen, Yi; Eileen M. Crimmins; Julie M Zissimopoulos (The Journals of Gerontology: Series B, 2021)
This study provides the first comparison of trends in dementia prevalence in the US population using three different dementia ascertainments/data sources: neuropsychological assessment, cognitive tests, and diagnosis codes from Medicare claims.We used data from the nationally representative Health and Retirement Study and Aging, Demographics and Memory Study, and a 20% random sample of Medicare beneficiaries. We compared dementia prevalence across the three sources by race, gender, and age. We estimated trends in dementia prevalence from 2006 to 2013 based on cognitive tests and diagnosis codes utilizing logistic regression.Dementia prevalence among older adults aged 70 and above in 2004 was 16.6% (neuropsychological assessment), 15.8% (cognitive tests), and 12.2% (diagnosis codes). The difference between dementia prevalence based on cognitive tests and diagnosis codes diminished in 2012 (12.4% and 12.9% respectively), driven by decreasing rates of cognitive test-based and increasing diagnosis codes-based dementia prevalence. This difference in dementia prevalence between the two sources by sex and for age groups 75 to 79 and 90 and above vanished over time. However, there remained substantial differences across measures in dementia prevalence among blacks and Hispanics (10.9 and 9.8 percentage points respectively) in 2012.Our results imply that ascertainment of dementia through diagnosis may be improving over time, but gaps across measures among racial/ethnic minorities highlight the need for improved measurement of dementia prevalence in these populations.
Keywords: cognitive tests; diagnosis codes; neuropsychological assessment; racial/ethnic minorities; Trends

Sexual Identity and Self-Rated Health in Midlife: Evidence from the Health and Retirement Study - Liu, Hui; Hsieh, Ning; Lai, Wen-hua (Health Equity, 2021)
Purpose: This study examined health disparities among U.S. sexual minority people in midlife—a critical life course stage that is largely overlooked in the sexual minority health literature. Methods: Data were drawn from the 2016 Health and Retirement Study. We restricted the analysis to respondents aged 50–65. The final sample consisted of 3623 respondents, including 3418 self-identified heterosexual individuals, 99 self-identified gay/lesbian individuals, 38 self-identified bisexual individuals, and 68 respondents who identified as “something else.” Ordinal logistic regression models were estimated to predict the odds of reporting better health. Results: Bisexual midlifers reported significantly worse health than their heterosexual counterparts after age, gender, and race-ethnicity are controlled for (OR=0.43, 95% CI=0.25–0.76); this health disparity is mostly explained by marital status, socioeconomic status, and health behaviors (in particular smoking and exercising). We did not find evidence of a self-rated health disadvantage among gay and lesbian midlifers relative to their heterosexual counterparts. Conclusion: These findings highlight the diversity of the sexual minority population in midlife. Public policies and programs should be designed and implemented at the interpersonal and institutional levels to eliminate health and other social disadvantages among sexual minority people, in particular bisexual people, in midlife.
Keywords: Self-rated health; sexual identity

She Bought a Truck on eBay, Then Forgot It. A Dementia Diagnosis Came Later. - Andrews, Michelle (The New York Times, 2021)
Impulsive purchases, out-of-control spending: These behaviors can be early signs of Alzheimer’s disease or other cognitive decline.
Keywords: Alzheimer's disease; Cognition; Dementia

Should I Stay or Should I Go? Mexican Return Migration across the Life Course - Mara Getz Sheftel (Sociology, 2021)
Foreign-born individuals make up a growing share of older adults in the US. Older immigrants offer an important vantage point from which to investigate integration because outcomes at older ages can be considered “final” measures providing empirical evidence for theoretical understandings of the forces impacting immigrant trajectories. However, considering the non-negligible portion of immigrants that ultimately return to their country of origin it is impossible to get the full range of immigrant outcomes without considering returnees. Further, patterns of return may differ across the life course with distinct economic, social, and health considerations at older ages. However, the impact of selective return migration, including considerations of heterogeneity by life stage, on immigrant outcomes at older ages remains understudied.
Keywords: life course; Mexico; MHAS; Migration

A Simple Question Goes a Long Way: A Wording Experiment on Bank Account Ownership - Marco Angrisani; Mick P. Couper (Journal of Survey Statistics and Methodology, 2021)
Ownership of a bank account is an objective measure and should be relatively easy to elicit via survey questions. Yet, depending on the interview mode, the wording of the question and its placement within the survey may influence respondents’ answers. The Health and Retirement Study (HRS) asset module, as administered online to members of the Understanding America Study (UAS), yielded substantially lower rates of reported bank account ownership than either a single question on ownership in the Current Population Survey (CPS) or the full asset module administered to HRS panelists (both interviewer-administered surveys). We designed and implemented an experiment in the UAS comparing the original HRS question eliciting bank account ownership with two alternative versions that were progressively simplified. We document strong evidence that the original question leads to systematic underestimation of bank account ownership. In contrast, the proportion of bank account owners obtained from the simplest alternative version of the question is very similar to the population benchmark estimate. We investigate treatment effect heterogeneity by cognitive ability and financial literacy. We find that questionnaire simplification affects responses of individuals with higher cognitive ability substantially less than those with lower cognitive ability. Our results suggest that high-quality data from surveys start from asking the right questions, which should be as simple and precise as possible and carefully adapted to the mode of interview.
Keywords: Cognitive Ability; Financial literacy

Skilled Nursing Facilities Modify the Relationship Between Depressive Symptoms and Hospital Readmissions but Not Health Outcomes Among Older Adults. - Leah R. Abrams; Geoffrey J Hoffman (Journal of Aging and Health, 2021)
Despite detrimental effects of depressive symptoms on self-care and health, hospital discharge practices and the benefits of different discharge settings are poorly understood in the context of depression. This retrospective cohort study comprised 23,485 hospitalizations from Medicare claims linked to the Health and Retirement Study (2000-2014). Respondents with depressive symptoms were no more likely to be referred to home health, whereas the probability of discharge to skilled nursing facilities (SNFs) went up a half percentage point with each increasing symptom, even after adjusting for family support and health. Rehabilitation in SNFs, compared to routine discharges home, reduced the positive association between depressive symptoms and 30-day hospital readmissions (OR = 0.95, = 0.029) but did not prevent 30-day falls, 1-year falls, or 1-year mortality associated with depressive symptoms. Depressive symptoms were associated with discharges to SNFs, but SNFs do not appear to address depressive symptoms to enhance functioning and survival.
Keywords: depression; Medicare; post-acute care; Readmissions; Rehabilitation

Sleep disturbance and pain in U.S. adults over 50: Evidence for reciprocal, longitudinal effects - Sarah C. Griffin; Ravyts, Scott G.; Bourchtein, Elizaveta; Ulmer, Christi S.; Leggett, Melanie K.; Joseph M. Dzierzewski; Patrick S Calhoun (Sleep Medicine, 2021)
ObjectiveTo examine the relationship between sleep disturbance and pain over a 14-year period.MethodsThis study used data from the 2002-2016 waves of the Health and Retirement Study (HRS), an observational study of U.S. adults over age 50 (n=17,756). Sleep disturbance was measured via four items (assessing difficulty falling asleep, staying asleep, and waking up too early as well as restedness) and pain via two items assessing the presence and degree of pain. Analyses consisted of path analysis; more specifically, random intercept cross-lagged panel modeling (RI-CLPM) was used to examine how pain and sleep disturbance predict one another over two-year intervals after accounting for the trait-like nature of both factors.ResultsThere was evidence of reciprocal effects between sleep disturbance and pain across some, but not all, intervals. Moreover, the latent variables representing the trait-like nature of sleep disturbance and pain both showed significant variance (p <.001), indicating stable differences between persons in sleep and pain. These trait-like characteristics were strongly associated (β=.51, p <.001). The findings remained after adjusting the model for baseline age, self-reported health, partner status, depression, years of education, and sex.ConclusionSleep disturbance and pain are stable experiences. Moreover, there was some evidence that sleep disturbance and pain are bidirectionally linked across time among adults over 50, whereby across some intervals deviations in one’s typical level of sleep disturbance predicted corresponding deviations in one’s typical level of pain and vice versa. Clinically, this comorbidity and potential longitudinal bidirectionality underscore the importance of evidence-based interventions that target both sleep and pain among older individuals. Further studies should replicate these findings by collecting validated and/or objective sleep and pain measures on a more frequent basis.
Keywords: pain; path analysis; RI-CLPM; Sleep

Smoking and Alcohol Consumption Following a New Dementia Diagnosis. - Arora, Kanika; Bhagianadh, Divya (The Journals of Gerontology: Series B, 2021)
OBJECTIVES: Despite extensive research on lifestyle factors that influence the risk of developing dementia, limited evidence exists on whether older adults adopt healthier habits post-diagnosis in the hope of preserving their quality of life. METHOD: Using panel data (1998-2014) from the Health and Retirement Study, this study investigated whether individuals who received a new dementia diagnosis were more likely to modify smoking and drinking behaviors than those without such a diagnosis. Propensity score weighting was used to adjust for observable differences between groups. RESULTS: Older adults with a new dementia diagnosis were 2.8 times more likely to reduce alcohol consumption than those without such a diagnosis. This result was mainly attributable to "light" drinkers at baseline and appeared to fade over time. We found no statistically significant effect of a dementia diagnosis on smoking cessation or on reduction in the number of cigarettes smoked. These results were robust to multiple sensitivity tests, including the use of cognition scores to indicate dementia onset instead of self-reported physician diagnosis. DISCUSSION: A new dementia diagnosis can serve as a window of opportunity that prompts some older adults to change habits related to alcohol consumption. This has important implications for clinical practice surrounding dementia diagnosis disclosure, the rates of which are currently much lower than other medical conditions.
Keywords: alcohol; Dementia; dementia diagnosis; Smoking

Social Determinants of Change in Smoking Status over a 26-Year Follow up Period among Middle-Aged and Older Americans - Shervin Assari (Journal of Biosciences and Medicines, 2021)
Educational attainment and income are among major socioeconomic status (SES) indicators that are inversely associated with cigarette smoking. Marginalization-related Diminished Returns (MDRs), however, are weaker protective effects of SES indicators for racial and ethnic minority groups compared to non-Hispanic White people. The aim is to test whether racial and ethnic differences exist in the effects of educational attainment and income on cigarette smoking of middle-aged and older American adults. This is a 26-year longitudinal study using data from the Health and Retirement Study (HRS), a nationally representative study of middle-aged and older adults in the US. A total number of 11,316 middle-aged and older adults (age ≥ 50) were followed for up to 26 years. The independent variables were educational attainment and income. The dependent variables were always smoking and being quitters over the follow-up time. Age, gender, self-rated health, and chronic medical conditions were the covariates. Race/ethnicity was the moderator. Logistic regressions were used to analyze the data. Most participants were never smokers (n = 7950), followed by quitters (n = 1765), always smokers (n = 1272), and initiators (n = 329). Overall, high educational attainment (OR = 0.92, 95% CI = 0.90 - 0.95) and income (OR = 0.99, 95% CI = 0.99 - 0.99) reduced the odds of being always smoker. High educational attainment (OR = 1.05, 95% CI = 1.02 - 1.08) was associated with higher odds of being a quitter. Ethnicity, however, showed significant interactions with education on both outcomes suggesting that the effects of educational attainment on reducing the odds of always being a smoker (OR = 1.24, 95% CI = 1.14 - 1.35) and increasing the odds of quitting (OR = 0.84, 95% CI = 0.75 - 0.93) were smaller for Hispanics than non-Hispanics. In the United States, middle-aged and older Hispanic adults remain at high risk of smoking cigarettes despite high educational attainment. That is, high educational attainment may better help non-Hispanic than Hispanic middle-aged and older adults to avoid cigarette smoking. As a result, we may observe a more than expected burden of tobacco use in middle class Hispanic middle-aged and older adults. Policymakers should not reduce racial and ethnic tobacco inequalities to SES gap, as ethnic tobacco disparities may persist in high SES levels as well.
Keywords: race; Smoking; socioeconomic status; Tobacco Use

Social Engagement and Cognitive Function of Older Adults in Mexico and the United States: How Universal Is the Interdependence in Couples? - Bret Howrey; Jaqueline C Avila; Brian Downer; Rebeca Wong (The Journals of Gerontology: Series B, 2021)
OBJECTIVES: Increased social engagement in older adults has been linked to positive cognitive outcomes; however, it is unclear if the social engagement of husbands and wives influences their own cognition as well as each other's cognition. Moreover, it is unknown if any such patterns persist in different country contexts. METHODS: Data from the 2001 Mexican Health and Aging Study (MHAS) and the 2000 Health and Retirement Study (HRS) were combined, and comparable samples of married couples without cognitive impairment at baseline were drawn. Follow-up cognition data was obtained from the 2012 MHAS and the 2012 HRS. Structural equation models (SEM) were used to test the actor-partner interdependence model with moderating effect of country on the association of social engagement with cognition. RESULTS: Significant actor effects were observed for wives in both countries. Actor effects for husbands were observed in the United States only. In Mexico, a significant partner effect was observed where wives' social engagement benefited their own cognition as well as their husbands', but not vice versa. Partner effects were not observed in the United States. No moderation effects of country were observed. DISCUSSION: Our results suggest asymmetric patterns of actor-partner interdependence in Mexico, which may be reflective of the more traditional social role of women, and codependence within the couple. On the other hand, our results for the United States, where each spouse had significant actor effects but no partner effects, may suggest more independence within the couple.
Keywords: Cohort Analysis; Cross-country study; Marriage; MHAS

SOCIAL ISOLATION AND LONELINESS AMONG ADULTS AGED 50 YEARS AND OLDER IN THE UNITED STATES: AN ANALYSIS OF THE COGNITIVE DISCREPANCY THEORY - Jillian M. Minahan Zucchetto (Psychology, 2021)
Keywords: Cognition; Loneliness; social isolation

Social Isolation, Loneliness, and Physical and Mental Health Among Black Older Adults - Taylor, Harry O (Annual Review of Gerontology and Geriatrics, Volume 41, 2021: Black Older Adults in the Era of Black Lives Matter, 2021)
Social isolation and loneliness are consistently associated with worse health and well-being outcomes among older adults. However, many studies have not examined their concurrent impact on health and well-being, and even fewer studies examine their influence among Black older adults. The 2014 and 2016 waves of the Health and Retirement Study were used to examine the influence of social isolation and loneliness among a nationally representative sample of Black older adults. Social isolation was measured using a social network index based on marital and household status, contact with family members and friends, and participation in social and religious activities. Loneliness was measured by the 3-item loneliness scale. Health outcomes were self-rated physical health and number of chronic health conditions, depressive symptoms, and lifetime occurrence of a psychiatric disorder. Each health outcome was examined using: (a) social isolation, (b) loneliness, and (c) social isolation and loneliness, controlling for sociodemographic covariates. Social isolation was associated with self-rated health and depressive symptoms, while loneliness was associated with all health outcomes. When examined jointly, social isolation was associated with self-rated health, while loneliness was associated with all health outcomes. Study findings suggest that due to its association with multiple physical and mental health measures, loneliness may be a more significant factor for health that should be routinely assessed in working with Black older adults.
Keywords: African Americans; Black older adults; Loneliness; Mental Health; Social determinants of health; social isolation

Social Media Communication and Loneliness Among Older Adults: The Mediating Roles of Social Support and Social Contact. - Zhang, Kunyu; Kim, Kyungmin; Nina M Silverstein; Song, Qian; Jeffrey A Burr (Gerontologist, 2021)
BACKGROUND AND OBJECTIVES: Social media communication offers a medium for helping older people stay socially and emotionally connected with others. This study investigated the association between social media communication with close social ties and loneliness among community-dwelling older adults. The study also examined the mediating roles of social support and social contact. RESEARCH DESIGN AND METHODS: Four waves of data from the Health and Retirement Study (2010/2012 and 2014/2016) were used to address the research questions (N = 7,524). A path model was estimated to examine the association between social media communication and older adults' loneliness. We also examined whether the association between social media communication and loneliness was mediated by perceived social support from close social ties (children, other family members, and friends) and frequency of contact with social network members (phone, in-person contact, and writing letters/email). RESULTS: The results showed that frequent social media communication was associated with lower levels of loneliness, adjusting for previous levels of loneliness. The relationship between social media communication and loneliness was mediated by perceived social support and social contact. Thus, social media communication was associated with higher levels of perceived social support and social contact, which were related to lower levels of loneliness among older adults. DISCUSSION AND IMPLICATIONS: These findings suggested that social media communication may be considered an intervention to reduce loneliness among older people by increasing levels of social support and social contact.
Keywords: Directed communication; Emotional Health; Internet use; Social Networking Sites

Social Network Typology and Cognitive Status Among African Americans: Findings From the Health and Retirement Study - Lincoln, Karen D.; Nguyen, Ann W. (Annual Review of Gerontology and Geriatrics, Volume 41, 2021: Black Older Adults in the Era of Black Lives Matter, 2021)
Social network diversity has been linked to cognitive status in older adults. While social network diversity is often operationalized by the proportion of social roles represented within one’s network, the additive effect of social roles is often unrecognized. Moreover, very few studies examine social relationships and cognitive status among African American older adults-a population with a high risk of cognitive impairment. The current study examined the relationship between social network diversity and cognitive status in a nationally representative sample of middle-aged and older African Americans. Data from the Health and Retirement Study (N = 2, 308) and latent class analysis were used to identify a social network typology using children, extended family members, and friends as social network indicators. Multinomial logistic regression was used to determine the association between social network types and cognitive status. Three social network types were identified-friend-focused, diverse, and restricted network types. African Americans with higher cognitive status were more likely to be assigned to the friend-focused social network type rather than the diverse or restricted network types. Neither the diverse nor restricted social network types were associated with cognitive status. A social network typology accounted for heterogeneity within the social networks of African American middle-aged and older adults and identified a unique social network type that appears to be protective for their cognitive health. Findings have implications for the measurement and operationalization of social networks and cognitive status and the role of social networks in maintaining cognitive functioning in African Americans.
Keywords: African Americans; cognitive function; cognitive impairment; Network diversity; Social networks; Social Support

Social resources, pension policy, and older adults’ mental, physical, and cognitive health: A cross-national comparison between China, England, Mexico, and the United States - Lu, Peiyi (Gerontology, 2021)
Population aging is accelerating across the globe. A cross-national comparison perspective is imperative and important because such comparison provides an opportunity to contrast experiences of different countries and learn from each other. Promoting healthy aging is one of the ultimate goals of social policies related to older adults. Guided by the integrative theoretical framework based on the social ecological model and life course perspective, this dissertation investigates the relationship of social resources with older adults’ physical, mental, and cognitive health in China, the United States, England, and Mexico using the Harmonized Health and Retirement Study (HRS) dataset and its international sister studies. Four countries were chosen primarily based on their geographic location, different level of economic development, and availability in the Harmonized HRS dataset. The dissertation comprises three projects.The first project explored the relationship between retirement/pension and depressive symptoms of older adults across the life course. Regression models were estimated using structural equation modelling. Results indicated that retirement was associated with higher levels of depressive symptoms for the U.S. and with lower levels of depressive symptoms for Mexico and England. Having a public pension was associated with lower levels of depressive symptoms for Mexico and with higher levels of depressive symptoms for the U.S. and China. Having a private pension was associated with lower levels of depressive symptoms for the U.S., China, and England. The study showed that continuity theory demonstrates cross-national variation in explaining the association between retirement and depressive symptoms. The second project tested the cross-cultural applicability of the shared resource hypothesis in explaining mental health concordance among older couples. Dyadic data were analyzed to examine the actor and partner effects of demographic, health, and household variables on depressive symptoms using both multilevel model and structural equation model. Results indicated both husbands’ and wives’ depressive symptoms were associated with their own and the spouses’ social and health status. Most couple-level resources were nonsignificant predictors for Chinese and Mexican couples’ concordance, but having more social and financial resources was associated with higher concordance among British and American couples. It is concluded that the shared resource hypothesis was more applicable to depressive symptom concordance within couples in the U.S. and England, but not in China and Mexico. The third project examined health inequalities between genders and countries in the context of cumulative dis/advantage (CDA) and welfare state theories. Regression models were fitted to examine the moderation roles of country and gender. Health patterns across age groups were cross-examined by linear regression models and negative binomial models. Results indicated older Chinese and Mexican respondents had poorer health status than their British and American counterparts consistently except for Mexicans’ memory. Cumulative health gaps between developing and developed countries existed only for functional ability. However, there is no evidence of gender gaps in health status across age groups. CDA explains the increasing gaps of functional ability across age groups between countries. General health and mental health, however, may depend more on individuals’ intrinsic capacity and human agency. Findings from these interconnected projects corroborate the person-in-environment perspective and suggest older adults’ health is influenced by multilevel factors including micro demographic characteristics, meso household resources, and macro culture/policy contexts across countries. The cross-national comparisons provide a unique perspective on variables associated with older adults’ health in different societal contexts. Suggestions were recommended for clinical practice to work with diverse aging population and for decision makers to improve policy design, with the ultimate goal to promote healthy aging and reduce health disparity in later life.
Keywords: CHARLS; Cognitive health; ELSA; Mental Health; MHAS; pension policy; Physical Health

Social Support and Depressive Symptoms among Trauma-Impacted Older Adults. - Cho, Seungjong; Bulger, Morgan (Journal of Evidence-Based Social Work (2019), 2021)
: The present study investigates the association between social support and depressive symptomatology among older adults who have been impacted by trauma. Previous studies have not sufficiently explored this topic to date. : The current study analyzed public-use data from the 2012 Health and Retirement Study ( = 4,195), focusing specifically on community-dwelling older adults (> 50). They had at least one traumatic event in their lifetime. : This study found that higher levels of social support were significantly associated with lower levels of depressive symptoms after controlling for life satisfaction, age, gender, race, ethnicity, and education.. : The recent emergence of trauma-informed research has consistently emphasized the importance of social interaction for mental health. The current study shows that social support can reduce depressive symptoms of those who have experienced trauma.
Keywords: depression; Social Support; trauma-impacted older adults; trauma-informed research

Social vulnerability and aging of elderly people in the United States - Ana Lucia Abeliansky; Devin Erel; Holger Strulik (SSM - Population Health, 2021)
We use 7 waves of the Health and Retirement Study and construct a social vulnerability index (SVI) for elderly U.S. Americans (born 1913–1966). We show that the SVI is mildly larger for men than for women and increases in age from above age 60 onwards for both genders. Social vulnerability of men (but not of women) is lower in the West and Midwest than in other regions and higher income mildly reduces the SVI for men (but not for women). In cohort analysis we find an increase of the SVI for individuals born in the late 1940s or later, which is, however, statistically significant only for women. In order to investigate the nexus between social vulnerability and aging, we construct a frailty index from the same data. We find that socially vulnerable persons display more health deficits at any age. Using the initial SVI (at first interview) we find that social vulnerability exerts a significant impact on subsequent accumulation of health deficits, which is of about the same size for men and women. A one standard deviation increase in the initial SVI leads to a 20 percent increase of the frailty index at any age.
Keywords: frailty index; health; Social capital; Social vulnerability

Societal Impact of Research Funding for Women's Health in Alzheimer's Disease and Alzheimer's Disease - Related Dementias - Baird, Matthew D.; Melanie A. Zaber; Andrew W. Dick; Chloe E. Bird; Annie Chen; Molly Waymouth; Grace Gahlon; Denise D. Quigley; Hamad Al Ibrahim; Lori Frank (Research Report, 2021)
Women's health has suffered from insufficient research addressing women. The research community has not widely embraced the value of this research, and the impact of limited knowledge about women's health relative to men's is far-reaching. Without information on the potential return on investment for women's health research, research funders, policymakers, and business leaders lack a basis for altering research investments to improve knowledge of women's health. As part of an initiative of the Women's Health Access Matters (WHAM) nonprofit foundation, RAND Corporation researchers examined the impact of increasing funding for women's health, beginning with a focus on Alzheimer's disease and Alzheimer's disease–related dementias (AD/ADRD), which result in substantial illness burden, health care costs, caregiving burden, and mortality. In this report, the authors present the results of microsimulation models used to explore the potential for enhanced investment in women's health research, in terms of the economic well-being of women and for the U.S. population.
Keywords: Alzheimer's disease; Dementia; health; women

Socioeconomic disparities and risk of hypertension among older Americans: the Health and Retirement Study. - Neufcourt, Lola; Zins, Marie; Lisa F Berkman; Grimaud, Olivier (Journal of Hypertension, 2021)
BACKGROUND: Reducing hypertension represents a critical point of intervention to lower the burden of cardiovascular disease worldwide. Although the relationship between lower socioeconomic status and higher rates of hypertension is well documented, most of the evidence comes from prevalence studies involving young adult population. AIM: To investigate the independent association of wealth, education and income with incident hypertension among older adults living in the United States. METHODS: This cohort study included 16 587 individuals aged 50 years and older, free of hypertension and cardiovascular disease at baseline from the Health and Retirement Study over the period 1992-2014. We used Cox proportional hazards models to examine longitudinal associations between wealth, education, and income at baseline and self-reported diagnosis of incident hypertension. RESULTS: During a median follow-up of 7.8 years, 6817 participants declared an occurrence of hypertension (incidence rate: 45.3 [95% confidence interval (CI) = 44.2-46.4] per 1000 person-years). Overall, those in low as compared with high socioeconomic status groups had a higher risk of developing hypertension in late life. In particular, adjusted hazard ratios [95% CI] across decreasing wealth quartiles were 1.0 (reference), 0.97 [0.88-1.08], 1.17 [1.05-1.30], and 1.20 [1.07-1.35] in men, and 1.0 (reference), 1.28 [1.17-1.41], 1.21 [1.09-1.33], and 1.28 [1.16-1.42] in women. In multivariate analyses, wealth remained strongly associated with incident hypertension among women after accounting for other socioeconomic, behavioral and anthropometric risk factors. CONCLUSIONS: Socioeconomic status, especially wealth, is a strong independent predictor of incident hypertension in older adults. Our findings support population-based interventions tailored to those in disadvantaged socioeconomic groups to reduce the risk of hypertension.
Keywords: Cox proportional hazards models; hypertention; socioeconomic disparities

Socioeconomic status across the life course and dementia-status life expectancy among older Americans - Hyungmin Cha; Mateo P Farina; Mark D Hayward (SSM - Population Health, 2021)
This study examines how socioeconomic status (SES) across the life course is associated with individuals’ lifetime dementia experience – the years of life persons can expect to live and without with dementia. Conceptually, dementia-free life expectancy reflects the ability to postpone dementia onset while dementia life expectancy reflects the average lifetime period with the condition. How SES across the life course contributes to dementia-status life expectancy is the focus of this study. We assess whether persons who are advantaged in their lifetime SES live the most years without dementia and the fewest years with dementia compared to less advantaged persons. Using the Health and Retirement Study (2000–2016), we examine these questions for U.S. adults aged 65 and older using multistate life tables and a microsimulation approach. The results show that higher SES persons can expect to live significantly more years of life without dementia and that the period of life with dementia is compressed compared to less advantaged persons. The results also underscore that importance of cumulative exposure, showing that adults from disadvantaged childhoods who achieve high education levels often have dementia experiences that are similar to or better than those of adults from advantaged childhoods who achieved low education levels.
Keywords: Dementia; Life Expectancy; Mortality; socioeconomic status

Solo Seniors with Social Support Are Less Likely to Need Nursing Home Care - Leigh, Suzanne (News, 2021)
Keywords: Long-term Care; Social Support

Spousal Bereavement and the Cognitive Health of Older Adults in the US: New Insights on Channels, Single Items, and Subjective Evidence - Zhao, Yuejun; Inder, Brett; Kim, Jun Sung (Economics & Human Biology, 2021)
This study provides novel insights into older adults’ cognitive functioning before and after widowhood onset and possible effect channels. It further examines gender heterogeneity in the adaptation to (anticipated or actual) spousal bereavement, comparing objective evidence with subjective evidence of cognitive abilities. We used longitudinal data of up to 26,584 participants of the Health and Retirement Study, aged over 50 at recruitment, assessed biennially between 1998 and 2016. Two-way fixed effects with dynamic treatment effects were estimated for various cognitive measures, including six aggregated indices and six single item scales. After adjusting for effect channels including depression, social vulnerability, and stress, there remained significant widowhood effects on older adults’ cognitive health. Using single item scales, we established the adverse contemporaneous and adaptation effects on bereaved older females’ short-term memory, semantic memory, and numeracy. For bereaved older males, working memory and focus-of-attention deteriorated after widowhood onset. Meanwhile, subjective memory rating remained intact, contrary to objective evidence. We conclude that cognitive transitions to and from widowhood can exhibit distinctive patterns across objective and subjective cognitive domains. With the effect channels in mind, cognitive intervention for widowed older adults should be tailored to the temporal distance to spousal loss, gender, and task.
Keywords: Anticipatory widowhood effects; Dynamic treatment effects; Gender heterogeneity; Subjective memory rating

SPOUSAL LABOR SUPPLY AND THE WELFARE IMPLICATIONS OF DISABILITY INSURANCE REFORM - Kellogg, Maxwell Dylan (Economics, 2021)
This paper uses a life cycle model to study interactions between household self-insurance and the U.S. Disability Insurance (DI) system. The model is motivated and guided by evidence from panel data on disability onset in U.S. households, showing that married workers benefit from both higher self-insurance capacity and higher utilization of DI compared to unmarried workers—who are left, by contrast, more exposed to the costs of disability. These responses are consistent with adverse selection, whereby the long application process and strict work limitations of the DI system screen out worse self-insured workers. Accounting for household self-insurance and the implicit costs of utilizing the DI system, the model delivers novel insights into the welfare implications of DI reform. Welfare gains from DI reforms are large, especially ones that lower the costs of acquiring DI benefits and consequently provide income support to households that value it highly. Accounting for the substantial insurance value that expansionary reforms provide is important for drawing these welfare conclusions. On the other hand, accounting for the self-insurance provided by spousal labor supply and pooled family savings is also important, as it reduces welfare gains from DI reforms by as much as 25 percent.
Keywords: disability insurance; Labor Supply; reform; Welfare

Statistical Significance of Hyperparameter Tuning for Varying Levels of Class Imbalance - Hancock, J.; Khoshgoftaar, T.M.; Landset, S. (26th ISSAT International Conference on Reliability and Quality in Design, RQD 2021, 2021)
Researchers experimenting with classification tasks for Machine Learning have a choice to use optimized or default values for their algorithms' hyperparameters. Our contribution is to conduct experiments with balanced and imbalanced datasets to show hyperparameter tuning has a significant, positive impact on classification results regardless of class ratio. To the best of our knowledge, this is the first study to investigate whether hyperparameter tuning has a statistically significant impact on the classification of balanced and imbalanced datasets derived from the Health and Retirement Study.We conduct a series of experiments with three classifiers, and five datasets. The classifiers are well-known, widely used classifiers in Machine Learning research. The datasets are based on a survey on cognition in human subjects. Three of the datasets are balanced, and two of them are imbalanced. We perform Analysis of Variance and Tukey's Honestly Significant Difference tests to determine the effect of hyperparameter tuning. Our results show that, regardless of class imbalance, using optimized hyperparameter values yields better results in a statistically significant sense.
Keywords: Class imbalance; Cognition; Logistic Regression; Machine learning; Random forest

Stress Proliferation and Disability over the Life Course - Jessica S West (Sociology, 2021)
For decades, life course and stress process scholars have documented that negative, stressful experiences have consequences for health across the life course. However, less attention has been paid to hearing impairment, a highly prevalent functional limitation that has significant implications for the quality of life of older adults. Hearing impairment is common at older ages (reported by 27.3% of those aged 65-74 and 45.1% of those aged 75 and older) and has negative consequences for the quality of life not only of the focal individual but also for those close to them (CDC 2017, Ciorba et al. 2012, Dalton et al. 2003, Wallhagen et al. 2004). The aim of this dissertation is to apply a life course and stress process framework to the experience of hearing impairment via two studies that each use nationally representative, longitudinal data from the Health and Retirement Study (HRS). My findings contribute to our understanding of marriage, family, gender, and health by moving beyond the traditional approach that focuses on individuals with disabilities to explore the impacts of disability on spouses. In Chapter 2, I build on the stress process framework by conceptualizing hearing impairment as a chronic stressor that impacts mental health and examining the role of social support in this relationship. Using fixed-effects regression models applied to three waves of HRS data (2006, 2010, 2014), I found that worse self-rated hearing is associated with a significant increase in depressive symptoms, and that social support interacted with hearing impairment: low levels of social support were associated with more depressive symptoms but only among people with poor self-rated hearing. Moreover high levels of social support reduced depressive symptoms for those with poor hearing. These findings suggest that hearing impairment is a chronic stressor in individuals' lives, and that responses to this stressor vary by the availability of social resources. Chapter 3 examines stress proliferation among married couples. While decades of research show the health benefits of marriage, stress proliferation suggests that chronic stressors such as disability may undermine social relations, thus limiting their role as a coping resource. For this study, I matched couples by household identification number over ten waves of the HRS (1998-2016). Fixed-effects regression models revealed that wives’ hearing impairment is associated with an increase in husbands’ depressive symptoms, but that husbands’ hearing impairment is not associated with wives’ depressive symptoms. This could be because women in heterosexual marriages have traditionally been expected to monitor their husbands’ health, but not vice versa. Since men are less used to serving as caregivers, they may find their wives’ hearing impairment distressing. Also, wives usually find social support outside of the marriage, while husbands traditionally rely on their wives for companionship. This would provide wives, but not husbands, with external resources to cope with their spouses’ hearing impairment. These findings reveal that the stress of hearing impairment does spill over from one spouse to another, depending on gender. Overall, this dissertation demonstrates that hearing impairment is a chronic stressor that has major implications for individuals’ mental health. Moreover, the mental health consequences of hearing impairment are not only limited to individuals but can also spill over to impact spouses. Further research is needed to extend our understanding of how disability, in general, and hearing impairment, specifically, shapes health across the life course for individuals and those close to them.
Keywords: hearing impaired; life course; stress process

Study shows working in agriculture poses higher risk of developing dementia - Great Plains Center for Agricultural Health (Press Release, 2021)
This first-of-its-kind study in the U.S. asks: Are agricultural workers at greater risk than non-agricultural workers of developing dementia? The answer, according to University of Iowa researchers is: “Yes.”
Keywords: agriculture; Dementia; worker

Subjective age and informant-rated cognition and function: A prospective study. - Yannick Stephan; Angelina R Sutin; Martina Luchetti; Antonio Terracciano (Psychology and Aging, 2021)
The present study examined whether subjective age is related to informant-rated cognition. Participants were adults ( = 2,337, mean age = 69.84 years, = 7.45) from the Health and Retirement Study who provided subjective age and demographic factors in 2008/2010 and informant-rated cognition in 2016 as part of the Harmonized Cognitive Assessment Protocol. An older subjective age was associated with informant reports of steeper cognitive decline, worse cognitive function, lower ability, and loss of ability to do everyday activities. The present study indicates that subjective age predicts cognitive function in everyday life as observed by knowledgeable informants. (PsycInfo Database Record (c) 2020 APA, all rights reserved).
Keywords: Cognition; HCAP; Subjective age

Subjective age and multiple cognitive domains in two longitudinal samples - Yannick Stephan; Angelina R Sutin; Martina Luchetti; Damaris Aschwanden; Antonio Terracciano (Journal of Psychosomatic Research, 2021)
Objective Subjective age is consistently related to memory performance and global cognitive function among older adults. The present study examines whether subjective age is prospectively related to specific domains of cognitive function. Method Participants were drawn from the Health and Retirement Study (HRS, NÂ =Â 2549, Mean AgeÂ =Â 69.66, SDÂ =Â 7.36) and the Midlife in the United States Survey (MIDUS, NÂ =Â 2499, Mean AgeÂ =Â 46.24, SDÂ =Â 11.25). In both samples, subjective age, depressive symptoms, chronic conditions, and demographic factors were assessed at baseline. Four domains of cognition were assessed 8Â years later in the HRS and almost 20Â years later in the MIDUS: episodic memory, speed-attention-executive, verbal fluency, and numeric reasoning. HRS also assessed visuospatial ability. Results Regression analysis revealed that an older subjective age was related to worse performance in the domains of episodic memory and speed-attention-executive in both samples. The effect size for the difference between a younger and an older subjective age was dÂ =Â 0.14 (MIDUS) and dÂ =Â 0.24 (HRS) for episodic memory and dÂ =Â 0.25 (MIDUS) and dÂ =Â 0.33 (HRS) for speed-attention-executive. Feeling older was related to lower verbal fluency in HRS (dÂ =Â 0.30) but not in MIDUS, whereas no association was found with numeric reasoning in either sample. An older subjective age was related to lower visuospatial ability in HRS (dÂ =Â 0.25). Conclusion Subjective age is prospectively related to performance in different cognitive domains. The associations between subjective age and both episodic memory and speed-attention-executive functions were replicable and robust over up to 20Â years of follow-up.
Keywords: Adulthood; Cognition; Executive function; Memory; numeric reasoning; Subjective age; verbal fluency; Visuospatial ability

Subjective Age and Verbal Fluency among Middle Aged and Older Adults: A Meta-Analysis of Five Cohorts - Yannick Stephan; Angelina R Sutin; Martina Luchetti; Damaris Aschwanden; Antonio Terracciano (Archives of Gerontology and Geriatrics, 2021)
Objectives This study aimed to examine the relation between subjective age and verbal fluency in five large samples of older adults to advance knowledge on the role of subjective age in a complex cognitive function that is an intermediate marker of cognitive impairment and dementia risk. Methods Participants (N > 27,000), aged 32 to 99 years old, predominantly white, were from the Wisconsin Longitudinal Study Graduate (WLSG) and Siblings (WLSS) samples, the Health and Retirement Study (HRS), the Midlife in the United States Study (MIDUS), and the English Longitudinal Study of Ageing (ELSA). They provided complete data on subjective age, demographic factors and verbal fluency. Estimates from each sample were combined in a meta-analysis. Results Across each of the five samples and in the meta-analysis, an older subjective age was related to lower performance on the verbal fluency task. This association was independent of chronological age and was not moderated by age, sex, nor education. The difference in fluency between individuals with an older and younger subjective age ranged from d= .09 to d= .37 across the five samples. Conclusions This study found replicable evidence for an association between an older subjective age and lower verbal fluency, extending knowledge about an intermediate marker of cognitive function.
Keywords: Adulthood; ELSA; Sister studies; Subjective age; verbal fluency

Subjective age, depressive symptoms, and cognitive functioning across five domains. - Morris, Emily P; Afsara B. Zaheed; Sharifian, Neika; Sol, Ketlyne; A Zarina Kraal; Laura B Zahodne (Journal of Clinical and Experimental Neuropsychology, 2021)
: Younger subjective age predicts better episodic memory and executive functioning performance independent of chronological age. This study examined whether subjective age is associated with performance in five cognitive domains, quantified the extent to which these relationships are mediated by depressive symptoms, and tested whether these associations are moderated by chronological age. Participants in this cross-sectional study included 993 adults aged 65 and older from the Health and Retirement Study's 2016 Harmonized Cognitive Assessment Protocol. Moderated mediation models estimated direct and indirect effects of subjective age on factor scores representing episodic memory, executive functioning, language, visuoconstruction, and speed through depressive symptoms and tested whether associations differed according to chronological age. Depressive symptoms explained 21-32% of the associations between subjective age and language, speed, episodic memory, and executive functioning. Chronological age moderated the indirect effect involving language, such that depressive symptoms were more strongly related to worse language performance at older chronological ages. After accounting for indirect effects, direct effects of younger subjective age remained for language and speed domains. This study extends research on the cognitive correlates of subjective age and demonstrates that depressive symptoms partly mediate these relationships. Subjective age may bemost strongly associated with language among individuals at older chronological ages not because they are more sensitive to the negative mental health impact of feeling older than they are but because they may be particularly vulnerable to the negative effects of depressive symptoms on language ability. Additional longitudinal research is needed to determine whether links between subjective age and cognition are causal versus predictive.
Keywords: Cognition; cognitive aging; Depressive symptoms; HCAP; Subjective age

Subjective Aging and Incident Cardiovascular Disease. - Yannick Stephan; Angelina R Sutin; Wurm, Susanne; Antonio Terracciano (The Journals of Gerontology: Series B, 2021)
OBJECTIVES: Subjective aging, including subjective age and self-perceptions of aging (SPA), predicts health-related outcomes in older adults. Despite its association with cardiovascular risk factors, little is known about the association between subjective aging and the incidence of cardiovascular disease. Therefore, the present study examined whether subjective age and SPA are related to the incidence of heart conditions and stroke. METHODS: The sample comprises 10,695 participants aged 50-100 years from the Health and Retirement Study. Subjective age, SPA, demographic factors, and health-related behaviors, body mass index (BMI), hypertension, diabetes, and depressive symptoms were assessed at baseline. Self-reported physician diagnosis of heart conditions and stroke were assessed biennially over up to 9 years of follow-up. RESULTS: Controlling for demographic factors, an older subjective age and more negative SPA were related to a higher risk of incident heart conditions and stroke. Feeling older and holding negative SPA were associated with around 40% higher risk of experiencing heart conditions over time. An older subjective age and negative SPA were related to almost twofold and 30% higher risk of incident stroke, respectively. Health risk behaviors, BMI, hypertension, diabetes, and depressive symptoms accounted for part of the associations between subjective aging and heart diseases and stroke. CONCLUSIONS: Consistent with the literature on subjective aging and cardiovascular risk factors, this large prospective study indicates that an older subjective age and negative SPA increase the risk of incident stroke and other cardiovascular diseases.
Keywords: ardiovascular disease; self-perceptions of aging; Stroke; Subjective age

Subtle mistakes in self-report surveys predict future transition to dementia - Stefan Schneider; Junghaenel, Doerte U.; Elizabeth Zelinski; Erik Meijer; Arthur A. Stone; Kenneth M. Langa; Arie Kapteyn (Alzheimer's & Dementia: Diagnosis, Assessment & Disease Monitoring, 2021)
Introduction We investigate whether indices of subtle reporting mistakes derived from responses in self-report surveys are associated with dementia risk. Methods We examined 13,831 participants without dementia from the prospective, population-based Health and Retirement Study (mean age 69 ± 10 years, 59% women). Participants’ response patterns in 21 questionnaires were analyzed to identify implausible responses (multivariate outliers), incompatible responses (Guttman errors), acquiescent responses, random errors, and the proportion of skipped questions. Subsequent incident dementia was determined over up to 10 years of follow-up. Results During follow-up, 2074 participants developed dementia and 3717 died. Each of the survey response indices was associated with future dementia risk controlling for confounders and accounting for death as a competing risk. Stronger associations were evident for participants who were younger and cognitively normal at baseline. Discussion Mistakes in the completion of self-report surveys in longitudinal studies may be early indicators of dementia among middle-aged and older adults.
Keywords: cognitive impairment; Dementia; early detection; Epidemiology; functional abilities; self-report surveys

Sarcopenia Definition & Outcomes Consortium Defined Low Grip Strength in Two Cross-Sectional, Population-Based Cohorts - Patel, Sheena M.; Kate A Duchowny; Douglas P Kiel; Correa-de-Araujo, Rosaly; Fielding, Roger A.; Travison, Thomas; Magaziner, Jay; Manini, Todd; Xue, Qian-Li; Anne B Newman; Pencina, Karol M.; Santanasto, Adam J.; et al. (JOURNAL OF THE AMERICAN GERIATRICS SOCIETY, 2020)
BACKGROUND/OBJECTIVES The extent to which the prevalence of muscle weakness in the US population varies by different putative grip strength constructs developed by the Sarcopenia Definitions and Outcomes Consortium (SDOC) has not been described. DESIGN Cross-sectional analysis. SETTING Two nationally representative cohorts-2010 and 2012 waves of the Health and Retirement Survey and round 1 (2011) of the National Health and Aging Trends Survey. PARTICIPANTS Adults aged 65 years and older (n = 12,984) were included in these analyses. MEASUREMENTS We analyzed three constructs of muscle weakness developed by the SDOC, and found to be associated with mobility disability for men and women, respectively: absolute grip strength (<35.5 kg and 20 kg); grip strength standardized to body mass index (<1.05 kg/kg/m(2) and 0.79 kg/kg/m(2)); and grip strength standardized to weight (<0.45 kg/kg and 0.337 kg/kg). We estimated the prevalence of muscle weakness defined by each of these constructs in the overall older US population, and by age, sex, race, and ethnicity. We also estimated the sensitivity and specificity of each of the grip strength constructs to discriminate slowness (gait speed <0.8 m/s) in these samples. RESULTS The prevalence of muscle weakness ranged from 23% to 61% for men and from 30% to 66% for women, depending on the construct used. There was substantial variation in the prevalence of muscle weakness by race and ethnicity. The sensitivity and specificity of these measures for discriminating slowness varied widely, ranging from 0.30 to 0.92 (sensitivity) and from 0.17 to 0.88 (specificity). CONCLUSIONS The prevalence of muscle weakness, defined by the putative SDOC grip strength constructs, depends on the construct of weakness used.
Keywords: Gait; muscle; Physical performance; sarcopenia

Self-Perceptions of Aging and Control of Life in Late Adulthood: Between-Person and Within-Person Associations - Luo, M.S.; Lydia W Li; Ernest Wing Tak Chui (Journal of Aging and Health, 2020)
Objectives: This study aimed to examine the longitudinal relationship between two central concepts in aging research—self-perceptions of aging (SPA) and perceived control of life (COL). Method: The data came from three measurement points over a 9-year period in the Health and Retirement Study (HRS). A random intercepts cross-lagged panel model (RI-CLPM) was estimated. Results: The covariations between SPA and COL across 9 years were evident at both the between-person level and the within-person within-time level. The results revealed a reciprocal relationship between SPA and COL: Higher than usual negative SPA predicted within-person decreases in COL 4 years later, and lower than usual COL predicted future within-person increases in negative SPA. Furthermore, SPA were found to have a somewhat larger effect on COL than the corresponding influence of COL on SPA. Discussion: This study enriches the stereotype embodiment theory and the practice by documenting a reciprocal interrelationship between SPA and COL.
cited By 0
Keywords: attitude toward aging; control belief; Self-efficacy; sold age

Self-perceptions of aging and domain-specific health outcomes among midlife and later-life couples. - Luo, Meng Sha; Lydia W Li; Rita Xiaochen Hu (Journal of Aging and Health, 2020)
This study places the self-perceptions of aging (SPA)-health link in the couple context and examines how changes in one's own and spouse's SPA influence multiple health domains and how such associations differ by gender. : Fixed-effects regression models were estimated. Data were drawn from the Health and Retirement Survey ( = 5972). For both husbands and wives, almost all health domains declined when their own SPA became more negative. The spouse's SPA were associated with one's self-rated health, regardless of gender. Gender differences existed in some cross-spousal health effects; while the husband's SPA were associated with his wife's depressive symptoms, the wife's SPA were associated with her husband's physical disability, functional limitations, and chronic diseases. The SPA-health association extends beyond the individual in married persons, demonstrating intertwined health trajectories in older couples. The detrimental effects of ageism might be underestimated if the spillover effects were not considered.

Self-Perceptions of Aging: Factorial Structure and Invariance by Gender - Turner, Shelbie G; Hooker, Karen; G John Geldhof (The Gerontologist, 2020)
Self-perceptions of aging (SPA)—the appraisals people place on their own aging processes—predict well-being in later life. Researchers are increasingly hypothesizing that the overarching construct of SPA is comprised of two factors—positive SPA and negative SPA—and that SPA are gendered. The purpose of this study was to empirically test the hypothesized two-factor structure of SPA and to analyze how the two-factor structure varies between men and women.Data come from the 2012 wave of the Health and Retirement Study (N = 7,029; Mage = 68.08), which includes an 8-item SPA scale. We used confirmatory factor analysis (CFA) to assess (i) the positive SPA and negative SPA two-factor solution for the 8-item scale and (ii) whether the two-factor solution had configural, strong, or weak invariance across men and women.CFAs indicated a two-factor latent structure of the 8-item scale, with SPA being comprised of both a positive SPA factor and a negative SPA factor. The latent structure was the same for both men and women.Results suggest that SPA is a broader construct made up of positive and negative latent factors. Researchers should consider separating the SPA by positive and negative factors to analyze how each factor uniquely shapes health. Moreover, the two-factor solution was equivalent across men and women, possibly because of the generalized nature of the 8-item scale. Researchers can use the 8-item scale similarly for men and women and should continue to elucidate possible gender differences in SPA.
Keywords: Confirmatory factor analyses; Measurement; Views on aging

Self-Related Views of Aging After Age 50: The Long-Term Effects of Poor Health in Childhood - Jacqui Smith; Larkina, Marina (Innovation in Aging, 2020)
Age stereotypes and expectations about one’s own aging commence in childhood but most research focuses on predictive associations with midlife health behaviors, later-life chronic conditions, and longevity. Surprisingly little is known about the role of poor childhood health in these associations. This study aims to fill this gap. Using data from the Health and Retirement Study (HRS: N = 5807; aged 50-98), we investigated whether diagnosed chronic illness before age 16 and self-rated childhood health predict late-life self-perceptions of aging (SPA) and subjective age discrepancy (AD). We conducted multivariate multiple regressions to determine the joint and unique effects of childhood health. Models included controls for current health (functional limitations), memory status, and demographic covariates (age, gender, race/ethnicity, marital status, and education). Multivariate tests (Pillai’s trace) revealed that both childhood health indicators were significant predictors. Over and above all covariates and the covariation of the two views of one’s own aging, univariate models showed that the number of childhood diagnoses was significant predictor of AD (p < .007) but not for SPA. In contrast, self-rated childhood health was a significant predictor of SPA (p < .001) but not for AD. This study provides new insight into precursors of self-evaluations of aging. Whereas childhood diagnoses of chronic illness attenuated the extent that individuals felt younger than their actual age, ratings of poor childhood health enhanced negative SPA. The non-normative experience of poor health in early life is a lifelong foundation for both late life beliefs and health.
Keywords: Childhood; health; Self-Assessment

Self-Reported Instances of Major Discrimination, Race/Ethnicity, and Inflammation Among Older Adults: Evidence from the Health and Retirement Study. - Ryon J. Cobb; Lauren J Parker; Roland J. Thorpe Jr. (Journals of Gerontology, Series A: Biological Sciences & Medical Sciences, 2020)
BACKGROUND: This study examines the relationship between self-reported instances of major discrimination and inflammation among older adults, and explores whether this relationship varies in accordance with race/ethnicity. We hypothesized that self-reported instances of major discrimination would be associated with higher levels of high-risk inflammation, and that this relationship would be stronger for racial/ethnic minorities than Whites. METHODS: Data from the 2006/2008 Health and Retirement Study (HRS), an ongoing biennial nationally representative sample of older adults in the United States, was used to collect measures of self-reported instances of major discrimination and high-risk C-reactive protein (CRP), which was assayed from blood samples. Modified Poisson regression with robust standard errors was applied to estimate the prevalence ratios of self-reported instances of major discrimination, as it relates to high-risk CRP (CRP≥ 22 kg/m2), and test whether this relationship varies by race/ethnicity. RESULTS: Respondents who experienced any instances of major discrimination had a higher likelihood of high-risk CRP (prevalence ratio [PR]: 1.14, 95% confidence interval [CI] = 1.07-1.22) than those who did not report experiencing any instances of major discrimination. This association was independent of differences in newly diagnosed health conditions and socioeconomic status. The relationship between any self-reported instance of major discrimination and high-risk CRP was weaker for Blacks than Whites (PR: 0.81, 95% CI = 0.69-0.95). CONCLUSIONS: Our study confirms that self-reported instances of major lifetime discrimination is a psychosocial factor that is adversely associated with high-risk CRP among older adults; this association is especially pronounced among older Whites. Future studies among this population are required to examine whether the relationship between self-reported instances of major discrimination and high-risk CRP changes over time.
Keywords: Discrimination; Racial/ethnic differences; Self-reports

Self-reported vision and hallucinations in older adults: results from two longitudinal US health surveys - Ali G Hamedani; Thibault, Dylan P; Shea, Judy A; Allison W Willis (Age and Ageing, 2020)
Vision loss may be a risk factor for hallucinations, but this has not been studied at the population level.To determine the association between self-reported vision loss and hallucinations in a large community-based sample of older adults, we performed a cross-sectional and longitudinal analysis of two large, nationally representative US health surveys: the National Health and Aging Trends Study (NHATS) and the Health and Retirement Study (HRS). Visual impairment and hallucinations were self- or proxy-reported. Multivariate single and mixed effects logistic regression models were built to examine whether visual impairment and history of cataract surgery were associated with hallucinations.In NHATS (n = 1520), hallucinations were more prevalent in those who reported difficulty reading newspaper print (OR 1.77, 95% confidence interval (CI): 1.32–2.39) or recognising someone across the street (OR 2.48, 95% CI: 1.86–3.31) after adjusting for confounders. In HRS (n = 3682), a similar association was observed for overall (OR 1.32, 95% CI: 1.08–1.60), distance (OR 1.61, 95% CI: 1.32–1.96) and near eyesight difficulties (OR 1.52, 95% CI: 1.25–1.85). In neither sample was there a significant association between cataract surgery and hallucinations after adjusting for covariates.Visual dysfunction is associated with increased odds of hallucinations in the older US adult population. This suggests that the prevention and treatment of vision loss may potentially reduce the prevalence of hallucinations in older adults.
afaa043
Keywords: blindness; Hallucinations; Health Surveys; Older adult; Proxy; self-report; vision

Semiparametric partially linear marginal models for binary and count longitudinal data with dropouts - Zubair, Seema (Ottawa-Carleton Institute for Mathematics and Statistics, 2020)
In this thesis, we investigate semiparametric partially linear marginal models for binary and count longitudinal data with dropouts. Specifically, we focus on the joint estimation of the marginal mean, association and dispersion parameters through generalized second-order estimating equations where the marginal mean response model is partially linear. We discuss a series of weighted generalized estimating equations (GEEs) to fit regression models to binary and count longitudinal responses when dropouts occur. The proposed method offers efficient estimators of the model parameters under a specified missing data mechanism. Simulations are conducted to examine the robustness characteristics of the method suggested under both accurately defined and inaccurately stated correlation frameworks. The approach is also demonstrated using some real missing longitudinal data on patterns of smoking, where the goal is to study the development of coronary arteries in young adults. A semiparametric approach for analyzing binary and longitudinal count data is also developed. We used the second-order GEE approach to examine longitudinal responses in partially linear models. Additionally, the smoothing technique is suggested for estimating the nonparametric part of the model based on a spline approximation. In simulations, the analytical properties of the proposed method are evaluated. The proposed estimator effectively takes into consideration the association within the subject/cluster and is easy to implement. Our simulation study shows that when the underlying model is partly linear, the proposed method offers unbiased and efficient estimators. Next, we propose a weighted regression spline second-order GEE approach for simultaneous estimation of the nonlinear function, regression, association and dispersion parameters in partially linear models with dropouts. As an application of the proposed semiparametric weighted GEE, we analyzed some longitudinal count data obtained from a health survey, referred to as the Health and Retirement study (HRS)(HRS, 2019), where the mean response function shows a nonlinear trend in terms of associated covariates. The results from the data analysis appear to be very encouraging. From this application it is evident that our proposed methods can be used to improve the efficiency of the estimates obtained from an ordinary GEE model for longitudinal binary and count data with dropouts.
Keywords: semiparametric; Statistics

A semi-parametric quantile regression approach to zero-inflated and incomplete longitudinal outcomes - Biswas, Jayabrata; Pulak Ghosh; Kiranmoy Das (AStA Advances in Statistical Analysis, 2020)
Quantile regression models are typically used for modeling non-Gaussian outcomes, and such models allow quantile-specific inference. While there exists a vast literature on conditional quantile regression (where the model parameters are estimated precisely for one prefixed quantile level), relatively less work has been reported on joint quantile regression. The challenge in joint quantile regression is to avoid quantile crossing while estimating multiple quantiles simultaneously. In this article, we propose a semi-parametric approach of handling non-Gaussian zero-inflated and incomplete longitudinal outcomes. We use a two-part model for handling the excess zeros, and propose a dynamic joint quantile regression model for the nonzero outcomes. A multinomial probit model is used for modeling the missingness. We develop a Bayesian joint estimation method where the model parameters are estimated through Markov Chain Monte Carlo. The unknown distribution of the outcome can be constructed based on the estimated quantiles. We analyze data from the health and retirement study and model the out-of-pocket medical expenditure through the proposed joint quantile regression method. Simulation studies are performed to assess the practical usefulness and efficiency of the proposed approach compared to the existing methods.
Keywords: Health Insurance; Joint quantile models; Missing data; Probit model; Varying coefficients models; Zero-inflated longitudinal data

Sense of Control and Frailty among Older Adults - Kim, Bon (Gerontology, 2020)
While research on control beliefs and frailty as separate concepts is rapidly expanding, few studies have investigated the relationship between control beliefs and frailty. Frailty is an integrated clinical syndrome that is closely associated with adverse health outcomes and mortality. It is important to more fully understand the relationship between sense of control and frailty because the protective effects of sense of control may benefit older adults at risk of frailty. This research uses data from the Health and Retirement Study (HRS) and examines the relationship between sense of control and frailty of older adults by taking multilevel factors into account. Further, the impact of financial loss on the level of sense of control is examined. Logistic regression and cross-lagged model are used to examine sense of control and frailty at the individual level (n = 7,695). Multilevel multinomial regression model and Actor Partner Interdependence model are conducted to investigate sense of control and frailty at the couple level (n = 1,509). Difference-in-differences model and linear regression model are used to explore the impact of financial loss on change in sense of control (n = 16,936). The results suggest that sense of control is positively associated with lower risk of frailty among older individuals and older couples. Furthermore, there is a reciprocal relationship between sense of control and frailty. Additionally, actual financial loss, as well as perceived financial loss have a negative impact on sense of control. Programs or interventions to enhance sense of control should be developed and available. Intervention programs targeting married couples should emphasize the spousal effects of sense of control. Married couples, could be a source of social support and influence each other’s level of frailty. Moreover, sense of control tends to decline over time, and financial loss may expedite this trajectory. Special attention should therefore be given to those who experience financial loss in an effort to minimize the associated detrimental effects.
Keywords: Frailty; Older Adults; Sense of control

Sense of purpose in life and five health behaviors in older adults - Eric S Kim; Shiba, Koichiro; Boehm, Julia K.; Laura D Kubzansky (Preventive Medicine, 2020)
Accumulating evidence shows that a higher sense of purpose in life is associated with lower risk of chronic conditions and premature mortality. Health behaviors might partially explain these findings, however, the prospective association between sense of purpose and health behaviors is understudied. We tested whether a higher sense of purpose at baseline was associated with lower likelihood of developing unhealthy behaviors over time. Prospective data were from the Health and Retirement Study, a national sample of U.S. older adults. Our sample included 13,770 adults assessed up to five times across eight years. Among people who met recommended guidelines for a given health behavior outcome at baseline, those in the top versus lowest quartile of purpose in life had 24% lower likelihood of becoming physically inactive (95% CI: 0.68–0.85), 33% lower likelihood of developing sleep problems (95% CI: 0.58–0.79), and 22% lower likelihood of developing unhealthy body mass index (BMI) (95% CI: 0.69–0.87) in sociodemographic-adjusted models. Further there was a marginal reduction in smoking relapse (HR = 0.65, 95% CI: 0.41–1.03) and no association with heavy alcohol use (HR = 1.02, 95% CI: 0.81–1.29). Findings for physical inactivity, sleep problems, and unhealthy BMI remained evident after further adjusting for baseline health status and depression. Our results, suggest that a sense of purpose in life might emerge (with further research) as a valuable target to consider for interventions aimed at helping older adults maintain some health behaviors.
Keywords: Alcohol Consumption; Body Weight; Epidemiology; Health behaviors; Health psychology; Physical activity; psychological well-being; Purpose in life; Sleep; Smoking

Sense of Purpose in Life and Likelihood of Future Illicit Drug Use or Prescription Medication Misuse. - Eric S Kim; Carol D Ryff; Hassett, Afton; Brummett, Chad; Yeh, Charlotte; Victor J Strecher (Psychosomatic Medicine, 2020)
OBJECTIVE: In the United States, 28.6 million people used illicit drugs or misused prescription drugs in the last 30 days. Thus, identifying factors linked with lower likelihood of future drug misuse is an important target for research and practice. Sense of purpose in life has been linked with better behavioral and physical health outcomes. Furthermore, a higher sense of purpose may reduce the likelihood of drug misuse because it has been linked with several protective factors including enhanced ability to handle stress, higher pain tolerance, and lower impulsivity. However, the association between sense of purpose and drug misuse has been understudied. Thus, we tested whether people with a higher sense of purpose at baseline had a lower likelihood of future drug misuse 9 to 10 years later. METHODS: This study included 3535 middle-aged adults from the Midlife in the United States Study who were not misusing drugs at baseline. Using multiple logistic regression models, we assessed whether baseline purpose in life was associated with risk of misusing drugs 9 to 10 years later. RESULTS: Among respondents not misusing drugs at baseline, people in the highest quartile of purpose (versus lowest quartile) had a substantially lower likelihood of future drug misuse in a model adjusting for demographic variables (odds ratio = 0.50, 95% confidence interval = 0.31-0.83). Associations remained evident after additionally adjusting for psychological distress, baseline health, and health behaviors. CONCLUSIONS: A growing knowledge base suggests that a sense of purpose can be increased. Additional research is needed to evaluate sense of purpose as a novel target in the prevention and reduction of drug misuse.
Keywords: Drug use; Sense of purpose

Shades of blue and gray: A comparison of the Center for Epidemiologic Studies Depression Scale and the Composite International Diagnostic Interview for Assessment of Depression Syndrome in later life. - Dang, Linh; Dong, Liming; Briana Mezuk (Gerontologist, 2020)
BACKGROUND AND OBJECTIVES: Psychiatric research lacks the equivalent of a thermometer, that is, a tool that accurately measures mental disorder regardless of context. Instead, the psychometric properties of scales that purport to assess psychopathology must be continuously evaluated. To that end, this study evaluated the diagnostic agreement between the eight-item Center for Epidemiologic Studies Depression Scale (CESD-8) and the Composite International Diagnostic Interview-short form (CIDI-SF) in the Health and Retirement Study (HRS). RESEARCH DESIGN AND METHODS: Data come from 17,613 respondents aged >50 from the 2014 wave of the HRS. Kappa coefficients were used to assess the agreement between the 2 instruments on depression classification across a range of thresholds for identifying case status, including variation across subgroups defined by age, race/ethnicity, and gender. RESULTS: The point prevalence of depression syndrome estimated by the CESD was higher than that estimated by the CIDI-SF (CESD: 9.9%-19.5% depending on the cutoff applied to the CESD vs CIDI-SF: 7.7%). Assuming CIDI-SF as the gold standard, the CESD yielded a sensitivity of 56.2%-70.2% and specificity of 84.7%-94.0% across the range of cutoffs. The agreement on depression classification was weak (κ = 0.32-0.44). DISCUSSION AND IMPLICATIONS: Depression cases identified by the CESD have poor agreement with those identified by the CIDI-SF. Conceptually, psychological distress as measured by the CESD is not interchangeable with depression syndrome as measured by the CIDI-SF. Population estimates of depression among older adults based on the CESD should be interpreted with caution.
Keywords: Depressive symptoms

The Shared Non-cognitive Roots of Health and Socioeconomic Status: Evidence from the US - Bucciol Alessandro; Coriele, Chiara; Zarri Luca (Department of Economics Working Paper Series, 2020)
A voluminous literature established a strong relationship between subjective health and socioeconomic status measures. We test the idea that self-reported health and subjective socioeconomic status have “shared non-cognitive roots”, i.e., that the same personality traits significantly affect both status variables, even after controlling for the complex relationships involving objective and subjective measures across the two domains. To this aim, we estimate a bivariate model based on longitudinal large-scale data (30,675 observations) from six waves (2006-2016) of the US Health and Retirement Study. Our findings strongly support our conjecture, as all the “Big Five” traits are significantly related to self-reported health and subjective socioeconomic status with the same sign, even after controlling for both objective measures and once the other subjective measure is considered. These results point to a novel, direct channel through which non-cognitive factors similarly influence self-evaluations across distinct, though strongly intertwined, domains.
Keywords: Bivariate Model; Non-Cognitive Factors; Self-reported Health Status; Subjective Socioeconomic Status

Sleep Difficulties and Cognition over a 10-Year Period in a National Sample of U.S. Older Adults - Robbins, Rebecca; Amanda Sonnega; Robert W. Turner; Jean-Louis, Girardin; Butler, Mark; Osorio, Ricardo M; Kenneth M. Langa (Innovation in Aging, 2020)
Sleep difficulties are common among older adults and are associated with cognitive decline. We used data from a large, nationally representative longitudinal survey of adults over the age of 50 in the U.S. to examine the relationship between specific sleep difficulties and cognitive function over time.Longitudinal data from the 2004-2014 waves of the Health and Retirement Study were used in the current study. We examined sleep difficulties and cognitive function within participants and across time (n=16,201). Sleep difficulty measures included difficulty initiating sleep, nocturnal awakenings, early morning awakenings, and waking feeling rested from rarely/never (1) to most nights (3). The modified Telephone Interview for Cognitive Status (TICS-m) was used to measure cognitive function. Generalized Linear Mixed Models (GLMM) were used with time varying covariates to examine the relationship between sleep difficulties and cognitive function over time.In covariate-adjusted models, compared to “never” reporting sleep difficulty, difficulty initiating sleep “most nights” was associated with worse cognitive function over time (Year 2014: b=-0.40, 95%CI: -0.63 to -0.16, p<.01) as was difficulty waking up too early “most nights” (Year 2014: b=-0.31, 95%CI: -0.56 to -0.07, p<.05). In covariate-adjusted analyses, compared to “never” reporting waking up feeling rested, cognitive function was higher among those who reported waking up feeling rested “some nights” (Year 2010: b=0.21, 95%CI: 0.02 to 0.40, p<.05).Our findings highlight an association between early morning awakenings and worse cognitive function, but also an association between waking feeling rested and better cognitive function over time.Sleep difficulties are common among older adults yet reduce quality of life and also contribute to the development of and potentially accelerate cognitive decline. This study examines specific sleep difficulties (e.g., difficulty falling asleep) and their unique relationship to cognition over time among older adults in the U.S. The primary aim of this work is to illuminate the specific sleep difficulties that are most concerning from the standpoint of cognitive impairment so as to inform the design of future tailored sleep improvement programs for older adults.
Keywords: cognitive function; Gerontology; healthy aging; Sleep; Translational medicine

Sleep disturbance as a moderator of the association between physical activity and later pain onset among American adults aged 50 and over: evidence from the Health and Retirement Study - Whibley, Daniel; Heidi M Guyer; Swanson, Leslie M; Braley, Tiffany J; Kratz, Anna L; Galit L Dunietz (BMJ Open, 2020)
Objective To examine whether sleep disturbance modifies the association between physical activity and incident pain.Design Prospective population-based study.Setting Health and Retirement Study.Participants American adults aged >=50 years who reported no troublesome pain in 2014 were re-assessed for pain in 2016. Of 9828 eligible baseline respondents, 8036 (82%) had complete follow-up data for adjusted analyses (weighted analysis population N=42 407 222).Exposures Physical activity was assessed via interview with questions about time spent in moderate and vigorous physical activity. Sleep disturbance, assessed using a modified form of the Jenkins Sleep Scale, was examined as a potential moderator.Main outcome measure Troublesome pain.Results In weighted analyses, 37.9% of the 2014 baseline pain-free sample participated in moderate or vigorous physical activity once a week or less, with an overall mean Physical Activity Index Score of 9.0 (SE=0.12). 18.6% went on to report troublesome pain in 2016. Each one-point higher on the Physical Activity Index Score was associated with a reduced odds ratio (OR) of incident pain for those who endorsed sleep disturbance never/rarely (OR=0.97, 95% CI 0.94 to 0.99), but not for those who endorsed sleep disturbance sometimes (OR=0.99, 95% CI 0.97 to 1.01) or most of the time (OR=1.01, 95% CI 0.99 to 1.03). The analysis of possible interaction demonstrated that frequency of sleep disturbance moderated the physical activity and incident pain association (Wald test: p=0.02).Conclusions The beneficial association of physical activity on reduced likelihood of later pain was only observed in persons who endorsed low levels of sleep disturbance.
Keywords: pain; Physical activity; sleep disorders

Sleep Disturbance Mediates the Association Between Loneliness and Health in Older Americans - Sarah C. Griffin; Samantha N Mladen; Williams, Allison Baylor; Dautovich, Natalie D.; Lageman, Sarah K.; Joseph M. Dzierzewski; Paul B. Perrin; Bruce D. Rybarczyk (International Journal of Behavioral Medicine, 2020)
Background As the research documenting loneliness as a risk factor for morbidity and mortality continues to grow, it becomes increasingly critical to understand the mechanics of this relationship. This study assessed whether sleep disturbance mediates the relationship between loneliness and health. Method Data came from the 2006, 2010, and 2014 waves of the Health and Retirement Study, a longitudinal study of older Americans; participants ≥ 65 who completed the Psychosocial and Lifestyle Questionnaire in 2006 were included (n = 5067). Measures include the Hughes loneliness scales, a modified version of the Jenkins sleep scale, and self-reported health. Cross-lagged mediation models (i.e., path analysis) were used to model the relationships between loneliness, sleep disturbance, and self-reported health over the 8-year span. Results Loneliness predicted subsequent sleep disturbance, which in turn predicted subsequent self-reported health. Moreover, there was evidence of both direct and indirect effects (via sleep disturbance) of loneliness on self-reported health. These effects remained after controlling for demographics, isolation, and depression. Conclusion Sleep disturbance partially mediates the relationship between loneliness and self-reported health over 8 years. These findings are not attributable to isolation or depression. Further research is necessary to develop and assess a more comprehensive model of how loneliness shapes health. This study indicates that targeting sleep disturbance may mitigate the health risks of loneliness in older Americans.
Keywords: Aging; health; Loneliness; Older Adults; Sleep

Smoking Behavior of Older Adults: A Panel Data Analysis Using HRS - Kajal Chatterji Lahiri; Xian Li (Journal of Quantitative Economics volume, 2020)
Using longitudinal data from Health and Retirement Surveys over 1992–2010, this paper analyzes decisions by older American to continue smoking and the number of cigarettes to consume using two-part hurdle models with correlated effects. We build on the existing literature by incorporating a myriad of factors including cigarette prices, health shocks and smoke-free laws in one econometric framework. Our estimates indicate that higher cigarette prices play an important role in both reducing participation and the intensity of consumption even for this adult population. In addition, health shocks, as measured by newly diagnosed diseases, raise the probability of quitting, highlighting the ‘curative’ aspects of cessation. However, we find very little effect of health on smoking intensity if an older adult does not quit after a health shock. Per capita cigarette consumption in the US declined by over 64% during the period. We show that increased cigarette prices and health shocks together contribute almost equally to explain nearly 86% of the decline, with little that can be attributed to smoking bans and anti-smoking sentiment.
Keywords: Smoking; Smoking cessation

The social and genetic inheritance of educational attainment: Genes, parental education, and educational expansion - Meng-Jung Lin (SOCIAL SCIENCE RESEARCH, 2020)
Recently, several genome-wide association studies of educational attainment have found education-related genetic variants and enabled the integration of human inheritance into social research. This study incorporates the newest education polygenic score (Lee et al., 2018) into sociological research, and tests three gene-environment interaction hypotheses on status attainment. Using the Health and Retirement Study (N = 7599), I report three findings. First, a standard deviation increase in the education polygenic score is associated with a 58% increase in the likelihood of advancing to the next level of education, while a standard deviation increase in parental education results in a 53% increase. Second, supporting the Saunders hypothesis, the genetic effect becomes 11% smaller when parental education is one standard deviation higher, indicating that highly educated parents are more able to preserve their family's elite status in the next generation. Finally, the genetic effect is slightly greater for the younger cohort (1942-59) than the older cohort (1920-41). The findings strengthen the existing literature on the social influences in helping children achieve their innate talents.
Keywords: Cohort; Educational attainment; Educational expansion in higher education; Gene-Environment Interaction; Parental education

Social capital and cost-related medication nonadherence (CRN): A retrospective longitudinal cohort study using the Health and Retirement Study data, 2006-2016. - Majercak, Kayleigh R; Magder, Laurence S; Villalonga-Olives, Ester (SSM Population Health, 2020)
Prescription drug spending and other financial factors (e.g., out-of-pocket costs) partially explain variation in cost-related medication nonadherence (CRN). Indicators of social capital such as neighborhood factors and social support may influence the health and well-being of older adults as they may rely on community resources and support from family and peers to manage conditions. Previous research on the relationship of social capital and CRN has limited evidence and contradictory findings. Hence, our objective is to assess the relationship of social capital indicators (neighborhood social cohesion, neighborhood physical disorder, positive social support, and negative social support) and CRN using a longitudinal design, 2006 to 2016, in a nationally representative sample of older adults in the United States (US). The Health and Retirement Study is a prospective panel study of US adults aged ≥ 50 years evaluated every two years. Data was pooled to create three waves and fitted using Generalized Estimating Equation modelling adjusting for both baseline and timevarying covariates (age, sex, education, race, total household income, and perceived health status). The three waves consisted of 11,791, 12,336, and 9,491 participants. Higher levels of neighborhood social cohesion and positive social support were related with lower CRN (OR 0.92, 95% CI 0.88-0.95 and OR 0.77, 95% CI 0.70-0.84, p<0.01). In contrast, higher levels of neighborhood physical disorder and negative social support were related to higher CRN (OR 1.07, 95% CI 1.03-1.11 and OR 1.46, 95% CI 1.32-1.62, p<0.01). Interventions targeting social capital are needed, reinforcing positive social support and neighborhood social cohesion and diminishing neighborhood physical disorder and negative social support for older adults.
Keywords: Cost-related medication nonadherence; Negative social support; Neighborhood physical disorder; neighborhood social cohesion; Positive social support; Social capital

Social capital and health status: Longitudinal race and ethnicity differences in older adults from 2006 to 2014. - Villalonga-Olives, Ester; Josue Almansa; Knott, Cheryl L.; Ransome, Yusuf (International Journal of Public Health, 2020)
AbstractObjectivesWe examined the longitudinal associations of social capital on self-rated health and differences by race/ethnicity in older adults.MethodsWe used Health and Retirement Study, a nationally representative sample of US adults aged ≥ 50 years evaluated every 2 years (2006–2014) (N = 18,859). We investigated the relationship between social capital indicators (neighborhood social cohesion/physical disorder, positive/negative social support) with self-rated health accounting for age, gender, education and stratified by race/ethnicity. We used structural equation multilevel modeling estimating the associations: within-wave and between-persons.ResultsWe observed between-persons-level associations among social capital indicators and self-rated health. Individuals with overall levels of positive social support and neighborhood social cohesion tended to have overall better self-rated health [correlations 0.21 (p < 0.01) and 0.29 (p < 0.01), respectively]. For Hispanics, the corr
Keywords: Health Status; longitudinal; Multilevel; No terms assigned; Older Adults; Racial differences; Social capital

Is social capital protective against hospital readmissions? - Zlotnick, Hanna; Geoffrey J Hoffman; Nuliyalu, Ushapoorna; Engler, Tedi A.; Kenneth M. Langa; Ryan, Andrew M. (BMC Health Services Research, 2020)
To evaluate the association between social capital and 30-day readmission to the hospital among Medicare beneficiaries overall, beneficiaries with dementia and related memory disorders, and beneficiaries with dual eligibility for Medicaid.
Keywords: Aging; Cohort Analysis; health policy

Social determinants of health: Predictors of risk of substance use in older adults - Young, Jennifer (University of the Cumberlands, 2020)
Substance use in older adults is a public health concern, having both mental health and physical health impacts. The social determinants of health (SDOH) framework can aid in developing effective interventions to ensure healthy aging and coping in the older adult population. This study uses the SDOH framework to evaluate risk factors that contribute to substance use to cope with stress in older adults. A multiple regression analysis was used for secondary data analysis of the Health and Retirement Study to examine predictors of substance use to cope with stress in older adults. The main findings indicated predictors of substance use to cope with stress were social and community context, followed by the SDOH categories of health and healthcare, and neighborhood physical cohesion. The findings identify the importance of emphasizing access to equitable healthcare and healthy aging in communities. Implications for clinical practice include the implementation of policies and services that provide support to communities in which older adults reside. The social determinants of health framework may be an essential tool to develop policies and solutions addressing substance use, barriers to health, and community wellness. As the population ages, policy changes and community programs can counteract the stressors associated with aging to promote healthy aging and coping in communities.
Keywords: coping; Older Adults; Social determinants of health; Stress; substance use

Social Engagement and Cognitive Function of Older Adults in Mexico and the United States - Bret Howrey; Jaqueline C Avila; Brian Downer; Rebeca Wong (Innovation in Aging, 2020)
Social engagement is linked to better cognition, but it is unclear if the social engagement of husbands and wives influences their own cognition as well as each other’s cognition in two very different country contexts. Data on married couples come from the 2001 Mexican Health and Aging Study (MHAS) and the 2000 Health and Retirement Study (HRS), with follow-up cognition measured in 2012. Structural equation models (SEM) were used to test the actor-partner interdependence model on the association of social engagement with cognition. In Mexico wives’ social engagement benefited their own cognition as well as their husbands’, but husband’s social engagement was unrelated to cognition. In the U.S. both wives’ and husbands’ social engagement benefited their own cognition, but not each other’s. Results suggest asymmetric patterns of actor-partner interdependence in Mexico, possibly reflecting more traditional social roles of women and co-dependence within couples, but more independence within U.S. couples.
Keywords: Cognition; Mexico; MHAS; social engagement

Social hallmarks of aging: Suggestions for geroscience research - Eileen M. Crimmins (Ageing Research Reviews, 2020)
This paper focuses on the idea that there are clear social hallmarks of aging including low lifetime socioeconomic status, adversity in childhood and adulthood, being a member of a minority group, adverse health behaviors, and adverse psychological states. The “Social Hallmarks of Aging” are analogous to the “Geroscience Hallmarks of Aging” in reflecting a set of underlying and interrelated social causes of multiple agerelated health outcomes. This paper presents empirical work incorporating the social hallmarks of aging with indicators of multiple biological hallmarks of aging as well downstream biology in explaining a range of health outcomes in order to show the relative strength of the associations of social and biological measures with important health outcomes. Social factors are strongly related to physical and cognitive functioning and multimorbidity in this older population and this remains true when the significant number of biological measures are controlled. This can be interpreted to mean that a significant amount of social variance in age-related health outcomes is not explained by these measures of biology. Indicators of the geroscience hallmarks of aging only relate modestly to the variability in human health outcomes. Attention to the social hallmarks related to human aging can usefully be incorporated into work on the biological hallmarks of aging to make greater progress in understanding human aging.
Keywords: Biological age – chronological age; Hallmarks of aging; Social determinants of aging

Social integration, self-rated health . . . and genes? - Aniruddha Das (Journal of Aging and Health, 2020)
OBJECTIVE: This study examined genetic roots of later life social integration, and their confounding of this social factor's health linkages. METHOD: Data were from the 2010 wave of the Health and Retirement Study. Two dimensions of integration were examined: with one's "stakeholder" network of family and friends and with the community. Genetic measures included polygenic scores for extraversion and educational attainment. RESULTS: Ties to one's stakeholder network had no genetic associations. The extraversion polygenic score was linked to community integration among Blacks as well as Whites. Among the latter, the same was true of one's genetic propensity for educational attainment. Although this score also influenced self-rated health, neither confounded associations of social integration with this indicator. DISCUSSION: Later life social integration seems influenced by genetically rooted propensities for both sociability and human capital accumulation. Health linkages of integration, however, may not reflect mutual dependencies on the same genetic substrates.
Keywords: Genetics; Self Report; Social Support

Social isolation’s influence on loneliness among older adults. - Harry Owen Taylor (Clinical Social Work Journal, 2020)
Social isolation and loneliness are significant risks to health among older adults. Previous studies have found a significant association between social isolation and loneliness; however, few studies examined the association between social isolation and loneliness in a multivariate context and how specific types of social isolation influence loneliness. This study fills this gap by examining social isolation’s overall influence on loneliness and how specific social isolation indicators influence loneliness. Data comes from 2014 Wave of the Health and Retirement Study, a nationally representative study of adults aged 50 and older. Social isolation was operationalized using seven indicators as social isolation from: (1) adult–children, (2) other family members, (3) friends, (4) living alone, (5) being unmarried, and (6) not participating in social groups or (7) religious activities. Loneliness was operationalized by the Hughes 3-item loneliness scale. Loneliness was regressed on social isolation and key socio-demographic factors. Results found when social isolation indicators were combined into an index, every unit increase in overall social isolation was associated with an increase in loneliness. Furthermore older adults who were isolated from other family members and from friends, lived alone, were single, and did not participate in social groups or religious activities reported greater loneliness. Study findings demonstrate that greater overall social isolation and specific social isolation indicators are associated with greater loneliness. Clinical practice with older adults can be enhanced by understanding the connections between social isolation and loneliness and which forms of social isolation are more meaningful for perceived loneliness.
Keywords: Loneliness; No terms assigned; Older Adults; social isolation; Social networks

Social Media Communication and Loneliness Among Older Adults: The Mediating Roles of Social Support and Social Contact - Zhang, Kunyu; Kim, Kyungmin; Nina M Silverstein; Song, Qian; Jeffrey A Burr (The Gerontologist, 2020)
Social media communication offers a medium for helping older people stay socially and emotionally connected with others. This study investigated the association between social media communication with close social ties and loneliness among community-dwelling older adults. The study also examined the mediating roles of social support and social contact.Four waves of data from the Health and Retirement Study (2010/2012 and 2014/2016) were used to address the research questions (N = 7,524). A path model was estimated to examine the association between social media communication and older adults’ loneliness. We also examined whether the association between social media communication and loneliness was mediated by perceived social support from close social ties (children, other family members, and friends) and frequency of contact with social network members (phone, in-person contact, and writing letters/email).The results showed that frequent social media communication was associated with lower levels of loneliness, adjusting for previous levels of loneliness. The relationship between social media communication and loneliness was mediated by perceived social support and social contact. Thus, social media communication was associated with higher levels of perceived social support and social contact, which were related to lower levels of loneliness among older adults.These findings suggested that social media communication may be considered an intervention to reduce loneliness among older people by increasing levels of social support and social contact.
Keywords: Directed communication; Emotional Health; Internet use; Social Networking Sites

Social Relationships as Resources in Later Life: The Dynamics of Structural and Functional Support - Brittany M. King (Sociology, 2020)
The field of sociology has long acknowledged the importance of social relationships. Some of the most well-known research in sociology on relationships stems from the foundational work of Durkheim (1951), who found those who were socially integrated were less likely to commit suicide than those who were socially isolated. Durkheim’s was among the first sociological studies to argue that social relationships are critical to health and wellbeing. Over the last several decades, scholars have begun to parse out casual explanations regarding social relationships and health (House, 1987; House, Landis, & Umberson, 1988; Siebert, Mutran, & Reitzes, 1999). Social support emerged as a key social resource protective of health, shown to be associated with adaptive behaviors, and a buffer to negative health outcomes (Cassel, 1976; Cobb, 1976). More recent sociological research has explored the relevance of social support at different phases of the life course, with a specific focus on later life (Krause, 2006; Pearlin et al., 2005) establishing older adults as proactive in managing their social network to fit their social needs (Carstensen, 1992; Rook, 2009; Streeter et al., 2019). This work acknowledges the contextual forces shaping social support (Elder et al., 2003; Moen & Hernandez, 2009) and shows that social support changes over the life course (Antonucci & Akiyama, 1987). Despite growing attention to social support in sociological research, there are several key gaps in current scholarship that can be addressed by looking to theories and research grounded in other disciplines. Although social support is typically treated as a stable resource (Norris & Kaniasty, 1996; Sarason et al., 1986), much like other resources, growing evidence suggests that social support changes throughout the life course and is likely to be influenced by important role losses and life transitions (Rook, 2009). Understanding the dynamic nature of social support is a necessary step for exploring how it serves as a resource for health. When individuals experience role losses or social losses in later life, the composition of one’s social network and frequency of interactions with others are likely to change (Antonucci et al., 2014; Antonucci & Akiyama, 1987; Carstensen, 1992; Pearlin, 2010; Rook, 2009). Sociology alongside scholarship in fields such as psychology, social work, public health, and economics collectively show that role losses related to driving cessation, retirement, widowhood in later life, and life are particularly likely to influence the composition, quality, and frequency of our social interactions and relationships (Chihuri et al., 2016; C. D. Lee & Bakk, 2001; Powers et al., 2014; Wrzus et al., 2013). Understanding the ways these kinds of life course changes relate to changes in our social relationships are critical to understanding how our health is subsequently affected. This dissertation aims to fill gaps in sociological scholarship about changes in dynamic social resources that occur during later life. Specifically, I examine changes to structural and functional support in association with three role losses that have been shown to have important health consequences in later life – the loss of driving (Study #1), retirement (Study #2), and widowhood (Study #3) – and whether the associations between these three role losses in later life and changes in social resources vary by race, class, gender, or marital status. The findings from this dissertation show that social relationships are both stable and dynamic resources in later life. Later life is associated with multiple stressful role losses, which each have the potential to impact our social relationships with children, relatives, and friends in unique ways. Evidence suggests that certain social locations are especially important in shaping whether functional and structural support changes in association with a role loss, particularly race (retirement and widowhood), class (widowhood), and marital status/household composition (driving cessation and retirement).
Keywords: loss of driving; Retirement; Widowhood

Social Security Eligibility Age and the Health Outcomes and Health Behaviors of the Elderly - Jun Hyun Yun (113th Annual Conference on Taxation, 2020)
I use a regression discontinuity design to investigate the causal relationship between Social Security eligibility age and the health outcomes and health behaviors of elderly individuals. Specifically, I examine changes when individuals attain the Earliest Eligibility Age (EEA) of 62. Given the aging of the U.S. population and the heated debate about whether the EEA should be increased to solve Social Security’s fiscal imbalance problem, understanding such a relationship is important. I use data from the Health and Retirement Study (HRS) to explore this relationship. I find that at the EEA, the probability of receiving Social Security benefits increases by over 30 percentage points. However, there is no evidence that the EEA impacts health. This finding coincides with the idea that health is a stock, the change in which is slow. There is little evidence that the EEA influences mental health. I also show suggestive evidence that when people reach the EEA, they reduce their smoking. I find that males drink more frequently when they reach the EEA. Retirement might be one of the main mechanisms behind the changes in health behaviors.
Keywords: health; Health Behavior; Social Security; Social Security Benefits; Social Security Eligibility

Social Security Is a Great Equalizer - Wenliang Hou; Geoffrey T. Sanzenbacher (Center for Retirement Research, 2020)
As the U.S. population becomes more diverse, it will be increasingly important for policymakers addressing Social Security’s solvency to understand the extent to which various racial and ethnic groups rely on Social Security versus other sources of retirement wealth. Yet, to date, studies on retirement wealth have tended not to focus on race and ethnicity and have largely ignored the role of Social Security. This brief, based on a recent paper, uses data from the Health and Retirement Study (HRS) to document the retirement resources of white, black, and Hispanic households at various points in the wealth distribution for five cohorts of 51-56 year olds between 1992 and 2016. The discussion proceeds as follows. The first section explains the calculation of retirement wealth. The second section shows how Social Security reduces retirement wealth inequality by race and ethnicity for typical households in each cohort. The third section looks at the impact of Social Security on retirement wealth inequality across wealth quintiles in a single year. The fourth section shifts from wealth to income to examine replacement rates – the ratio of projected retirement income to pre-retirement earnings. The final section concludes that, as policymakers consider changes to bring Social Security into fiscal balance, the distributional impact of any benefit cuts with respect to minority groups may be worth considering.
Keywords: Social Security

Social Security Reform with Heterogeneous Mortality - John Bailey Jones; Li, Yue (Richmond Federal Working Paper Series, 2020)
Using a heterogeneous-agent, life-cycle model of Social Security claiming, labor supply and saving, we consider the implications of lifespan inequality for Social Security reform. Quantitative experiments show that welfare is maximized when baseline benefits are independent of lifetime earnings, the payroll tax cap is kept roughly unchanged, and claiming adjustments are reduced. Eliminating the earnings test and the income taxation of Social Security benefits provides additional gains. The Social Security system that would maximize welfare in a “2050 demographics” scenario, characterized by longer lifespans and an increased education-mortality gradient, is similar to the one that would maximize welfare today.
Keywords: Labor Supply; Mortality; Social Security; Welfare

Social Security Wealth, Inequality, and Life-cycle Saving: An Update - Sabelhaus, J.; Alice Henriques Volz (MRRC Working Paper, 2020)
Social Security wealth (SSW) is the present value of future benefits an individual will receive less the present value of future taxes they will pay. When an individual enters the labor force, they generally face a lifetime of taxes to pay before they will receive any benefits and, thus, their initial SSW is generally low or negative. As an individual works and pays into the system their SSW grows and generally peaks somewhere around typical Social Security benefit claiming ages. The accrual of SSW over the working life is most important for lower income workers because the progressive Social Security benefit formula means that taxes paid while working are associated with proportionally higher benefits in retirement. We estimate SSW for individuals in the Survey of Consumer Finances (SCF) for 1995 through 2019 using detailed labor force history and expectations modules. We use a pseudo-panel approach to empirically demonstrate life-cycle patterns of SSW accumulation and drawdown. We also show that including SSW in a comprehensive wealth measure generally reduces estimated levels of U.S. wealth inequality, but does not reverse the upward trend in top wealth shares.
Keywords: Inequality; life-cycle saving; social security wealth

Social Support and Depressive Outcomes in Older Adults: An Analysis of the Health and Retirement Study - Julia E Tucker; Nicholas J Bishop (Innovation in Aging, 2020)
Given population aging and impact of both spousal and social support on the health of older adults, the protective role of social support amongst recently bereaved older adults represents an important area of research. The aim of this study is to identify the relationship between recent widowhood and change in depressive symptoms in older adults, and how social support moderates this association. Utilizing observations from the nationally representative Health and Retirement Study, the analytic sample consisted of 2,890 adults age 50 and over who were partnered or married in 2012. Depression was measured using the Center for Epidemiological Studies Depression scale short form (CESD-8). Positive social support was measured as perceived social support from family, friends, and children. Widowhood was a dichotomous measure indicating mortality of spouse between 2012 and 2014. Autoregressive multiple regression was used to determine if widowhood was associated with change in depression from 2012-2104 and whether positive social support moderated this relationship. Widowhood was associated with an increase in depressive symptoms from 2012-2014 (b=0.967, SE=0.145, p <.001) and social support was negatively associated with change in depression (b=-0.021, SE=0.004, p <.001). Social support appeared to moderate the association between widowhood and change in depression (b=0.068, SE=0.026, p =.010), though widowed older adults with higher social support appear to have more rapid increase in depression than those with lower social support. These preliminary findings and implications for supporting bereaved older adults will be discussed.
Keywords: depressive outcomes; Social Support

Social Support, Everyday Discrimination, and Depressive Symptoms Among Older African Americans: A Longitudinal Study - Qin, Weidi; Ann W Nguyen; Mouzon, Dawne M; Tyrone C Hamler; Wang, Fei (Innovation in Aging, 2020)
The purpose of the study is to explore the long-term effects of everyday discrimination on depressive symptoms among older African Americans, as well as the moderating role of social support in this association.Mixed-effects negative binomial regression analyses were performed on data selected from six waves of the Health and Retirement Study (2006-2016; baseline N=1144). The number of depressive symptoms was calculated based on an 8-item CES-D measure. Everyday discrimination was measured by using a 6-item scale. Contact with and perceived support from extended family and friends were assessed.Older African Americans who experienced more frequent perceived discrimination had more depressive symptoms over time. Significant interactions between discrimination and perceived support from extended family and friends were found, indicating that among older African Americans who reported higher support from extended family and friends, perceived discrimination was positively associated with depressive symptoms over time. However, perceived discrimination and depressive symptoms were not longitudinally related among those who reported lower levels of perceived support.This is one of the few studies to examine the effects of discrimination on depressive symptoms over time and the first longitudinal study to test the role of social support in coping with discrimination in older African Americans. This study extends cross-sectional works on discrimination and mental health, indicating that experiences of discrimination can result in worse mental health over time. The significant interactions are consistent with the resource mobilization framework, which suggests that individuals who are more negatively affected by discrimination (more depressive symptoms) are more likely to reach out to friends and family to cope with discrimination.Older African Americans who experience more discrimination and depressive symptoms are more likely to seek support from extended family and friends for coping with discrimination over time. The study findings suggest that older African Americans may benefit from interventions based on stress coping resources via support from extended family and friends in coping with discrimination.
Keywords: Black older adults; family social support networks; friendship social support networks; Mental Health; unfair treatment

Socioeconomic disparities in smoking are partially explained by chronic financial stress: marginal structural model of older US adults - Parnia, Abtin; Siddiqi, Arjumand (Journal of Epidemiology & Community Health, 2020)
Background A persistent socioeconomic gradient in smoking has been observed in a variety of populations. While stress is hypothesised to play a mediating role, the extent of this mediation is unclear. We used marginal structural models (MSMs) to estimate the proportion of the effect of socioeconomic status (SES) on smoking, which can be explained by an indicator of stress related to SES, experiences of chronic financial stress.Methods Using the Health and Retirement Study (waves 7–12, 2004–2014), a survey of older adults in the USA, we analysed a total sample of 15 260 people. A latent variable corresponding to adult SES was created using several indicators of socioeconomic position (wealth, income, education, occupation and labour force status). The main analysis was adjusted for other factors that influence the pathway from adult SES to stress and smoking, including personal coping resources, health-related factors, early-life SES indicators and other demographic variables to estimate the proportion of the effect explained by these pathways.Results Compared with those in the top SES quartile, those in the bottom quartile were more than four times as likely to be current smokers (rate ratio 4.37, 95% CI 3.35 to 5.68). The estimate for the MSM attenuated the effect size to 3.34 (95% CI 2.47 to 4.52). Chronic financial stress explained 30.4% of the association between adult SES and current smoking (95% CI 13 to 48).Conclusion While chronic financial stress accounts for part of the socioeconomic gradient in smoking, much remains unexplained.

Socioeconomic Inequalities in Disability-free Life Expectancy in Older People from England and the United States: A Cross-national Population-Based Study - Zaninotto, Paola; G David Batty; Stenholm, Sari; Ichiro Kawachi; Hyde, Martin; Goldberg, Marcel; Westerlund, Hugo; Vahtera, Jussi; Head, Jenny (The Journals of Gerontology: Series A, 2020)
We examined socioeconomic inequalities in disability-free life expectancy in older men and women from England and the United States and explored whether people in England can expect to live longer and healthier lives than those in the United States.We used harmonized data from the Gateway to Global Aging Data on 14,803 individuals aged 50+ from the U.S. Health and Retirement Study (HRS) and 10,754 from the English Longitudinal Study of Ageing (ELSA). Disability was measured in terms of impaired activities and instrumental activities of daily living. We used discrete-time multistate life table models to estimate total life expectancy and life expectancy free of disability.Socioeconomic inequalities in disability-free life expectancy were of a similar magnitude (in absolute terms) in England and the United States. The socioeconomic disadvantage in disability-free life expectancy was largest for wealth, in both countries: people in the poorest group could expect to live seven to nine fewer years without disability than those in the richest group at the age of 50.Inequalities in healthy life expectancy exist in both countries and are of similar magnitude. In both countries, efforts in reducing health inequalities should target people from disadvantaged socioeconomic groups.
Keywords: Cross-National; Disability; Healthy life expectancy; socioeconomic status

Socioeconomic Status and the Experience of Pain: An Example from Knees - David M Cutler; Meara, Ellen; Stewart, Susan (NBER Working Paper, 2020)
Reports of pain differ markedly across socioeconomic groups and are correlated with outcomes such as functional limitations and disability insurance receipt. This paper examines the differential experience of pain by education. We focus on knee pain, the most common musculoskeletal complaint. Comparing clinical interpretation of knee x-rays of people with and without pain, there are few differences in presence or clinical severity of arthritis across education groups. In contrast, less educated people report more pain for any given objective measure of arthritis. After confirming that reported pain maps to objective measures like walking speed and range of motion, we test four theories for differential experience of pain: differences in obesity, physically demanding occupations, psychological factors, and medical treatment differences. We find that physical demands on the job and obesity each explain about one-third of the education gradient in knee pain. There is an interaction between the two; physical requirements on the job are associated with knee pain primarily in those who are obese. In contrast, psychological traits and access to medical care explain little of the difference in reported pain by education level. These findings imply that educational gradients in pain are likely to persist or even widen as the need for physically demanding occupations—like home health aides and personal service workers—grows in importance with the aging population, and the working population continues to be obese.
Keywords: pain; socioeconomic status

Spending in retirement: How you just might find what you want and what you need - Perna, Matthew; Stempien, Jeremy (PGIM, 2020)
As the defined contribution (DC) industry recognizes the need to shift its focus from accumulation to more holistic strategies designed to provide lifetime income, the challenge of portfolio decumulation and providing sustainable income through retirement needs to be thoughtfully addressed. In doing so, having a strong understanding of the retirement spending objectives for workers is the critical component. Historically, most investment solutions have been designed under the assumption that retirement spending is the same for all individuals, but the reality is the characteristics of retiree expenses vary greatly. For solutions to be successful in providing retirement income, they will need to better address the different types of spending workers will experience after they leave the workforce. We believe plan sponsors should evolve their DC plans to be more supportive of lifetime income, including more outcome-focused asset allocation, technology customized to the individual, institutional investments including non-guaranteed liability-driven investments, and guaranteed income solutions. In this paper, we focus onbetter understanding expenses in retirement and discuss the idea of using a “Needs and Wants” framework for designing income-oriented investment solutions. It is our view that this type of approach to how spending in retirement is viewed may be able to provide better solutions and outcomes for workers.

Spousal Activity Limitations and Depressive Symptoms: Benefits of Spousal Caregiving and Costs of Spousal Pain - Sae Hwang Han; Kim, Kyungmin; Jeffrey A Burr (Innovation in Aging, 2020)
Experiencing difficulties in performing basic activities of daily living poses significant challenges for older adults living with such limitations and also for their spouses. A growing body of evidence demonstrates cross-spousal linkages between activity limitations and depressive symptoms. However, under what conditions these linkages may be strengthened or weakened has received little attention in the literature. We addressed this gap by examining whether a) providing spousal caregiving and b) spousal pain moderated the link between spousal activity limitations and one’s own depressive symptoms. We used seven waves of longitudinal household data from the Health and Retirement Study (2004-2016; N=12,369) to estimate within-person associations between spousal activity limitations and depressive symptoms, focusing on the moderating roles of caregiving behavior and spousal pain. In particular, asymmetric fixed effects models were used to estimate the unique effects of transitioning into a spousal caregiver role in the context of spousal activity limitations. Results from multilevel models were gendered. For wives (but not for husbands), transitioning into a caregiver role to provide spousal care alleviated depressive symptoms associated with spousal activity limitations, whereas depressive symptoms were increased when husbands with activity limitations also reported frequent, moderate to severe pain. Our findings indicate that the link between spousal activity limitations and depressive symptoms is not uniform, and that the cross-spousal association may best be understood when relevant contextual factors are considered. The findings are also in line with recent studies showing that caregiving may also lead to enhanced well-being and reduced mortality risk under some circumstances.
Keywords: activity limitations; Caregiving; Depressive symptoms; pain; Spouses

Spousal education and cognitive functioning in later life. - Minle Xu (The Journals of Gerontology, Series B: Psychological Sciences & Social Sciences, 2020)
Objectives: Numerous studies have documented the relationship between education and cognitive functioning at the individual level. Yet few studies have examined whether a spouse's education spills over to influence the other spouse's cognitive functioning. This study, therefore, investigated the association between spousal education and cognitive functioning, the pathways that may account for this association, and gender differences in this association. Method: Growth curve models were analyzed by using longitudinal couple data from the Health and Retirement Study (N=5,846 individuals). Results: More years of spousal education is associated with higher level of cognitive functioning at age 65 (γ000=.0532, 95% confidence interval [CI]=.0163.0901) and slower decline in cognitive functioning in later adulthood (γ100 =.0054, 95% CI=.0026.0082). The positive association between spousal education and the level of cognitive functioning at age 65 was fully explained by economic resources. The association of spousal education with the rate of cognitive decline decreased but remained significant after controlling for economic resources and health behaviors (γ100 =.0043, 95% CI =.0014.0072). The association between spousal education and cognitive functioning was similar for men and women. Discussion: Findings suggest that more years of spousal education may slow decline in cognitive functioning for men and women in later life.
Keywords: Cognition & Reasoning; Education; Marriage

The State of Mental Health Among the Elderly Chinese - Chen, Yi; Fang, Hanming (NBER Working Paper Series, 2020)
China introduced its stringent family planning policies from the early 1970s, known as the "Later, Longer, Fewer" policies, and followed it with the One-Child Policy from 1979. The number of children born to Chinese parents significantly decreased from 5.7 in late 1960s to 2.5 in 1988. In Chen and Fang (2019), we show that family planning policies have drastically different effects on elderly parents' physical and mental well-beings. Whereas parents more exposed to the family planning policies consume more and enjoy slightly better physical health status, they report more severe depression symptoms. In this paper, we present a more complete picture of the difference in mental health among residents in rural and urban areas, between males and females, between different education groups, between those with one child and those with more than one children, and between widowed and non-widowed. We highlight the role of family support (from children and spouse) for the mental health status among the elderly Chinese.
Keywords: China; Mental Health

Still shortchanged: An update on women's retirement preparedness - Bond, Tyler; Saad-Lessler, Joelle; Christian Weller (National Institute on Retirement Security, 2020)
Most Americans struggle to adequately save for retirement, but women face unique challenges in saving, largely stemming from a gender pay gap that persists into a retirement wealth gap. This update of previous research from the National Institute on Retirement Security (NIRS) takes a fresh look at the data on women’s retirement preparedness. Relying on data from the 2014 Survey of Income and Program Participation (SIPP), this research finds that older women receive approximately 80 percent of the retirement income that older men receive - nearly identical to the gender pay gap for American women. The data also reveals that different groups of women have very different retirement experiences, with older women in a first marriage faring better than the rest, and widows, especially those age 80 and older, seeing a marked decline in income. The report’s key findings are as follows: • In 2016, women age 65 and older had a median household retirement income of $47,244 or 83 percent of median household income for men ($57,144). • Women earn less than men over the course of their career. Men with savings in a defined contribution (DC) plan far surpass the earnings trajectory of women with savings in a DC plan, and earn significantly more than women without DC savings. • Women experience a steep decline in income past age 80. Women age 80 and older are much more likely to be widows and widowhood presents challenges on both the income and cost side of retirement. • There are stark differences in the sources of income for women in the top and bottom income quintiles. Women with less than $20,000 of income in retirement are much more dependent on Social Security income, whereas women with income above $80,000 receive much more from earnings and property income. • Divorce presents a complex set of issues relating to retirement preparedness. The timing of divorce seems to matter, as does the division of assets following a divorce. • Caregiving, especially spousal caregiving, has a strong effect on retirement preparedness, and this particularly impacts women as they remain much more likely to provide caregiving than men.
Keywords: Caregiving; Divorce; Retirement Planning; women

Stressors and Pain Over the Late-Life Course: Findings from Two Parent Longitudinal Studies of Aging and Health - Penny L. Brennan (Innovation in Aging, 2020)
With this study we sought to determine how older adults’ stressors influence their levels and rates of change in pain during the late-life span. We harmonized repeated measures data from two parent longitudinal studies of aging and health, Longitudinal Late-Life Health (LLLH; n=1,1884) and the Health and Retirement Study (HRS; n=7,703), to determine how participants’ stressor levels in the domains of finances, spouse, children, extended family, and friends, and in stressors overall, influenced their average levels and rates of change in painful conditions, pain severity, and pain interference over 13-year (LLLH) and 8-year (HRS) intervals. Participants’ within-person stressor levels declined somewhat, whereas their number of painful conditions, pain severity, pain interference, and prescription painkiller use increased steadily, over these intervals. In both the LLLH and HRS samples, participants who experienced higher average stressor levels over the 13- and 8-year intervals had more numerous painful conditions and higher pain severity over these intervals. In the HRS sample, they also experienced higher levels of pain interference. These effects occurred independent of the demographic characteristics of age, gender, and race. In general, participants’ stressor levels did not influence rates of increase in their pain. Gender and race had some moderating effects on associations between stressors and pain, but these occurred only within certain specific stressor and pain domains. These findings demonstrate an association between stressors and pain across the late-life course. Further research is needed to determine the mediating mechanisms that account for this association and the moderating factors that affect its strength.
Keywords: pain; Stressors

Structural Social Support and Changes in Depression during the Retirement Transition: "I Get by With a Little Help from My Friends". - Ben Lennox Kail; Dawn C Carr (Journals of Gerontology Series B Psychological Sciences and Social Sciences, 2020)
OBJECTIVES: This study evaluated whether (a) retirement was associated with increased depressive symptoms, (b) four sources social support were associated with decreased depressive symptoms, and (c) whether the relationship between retirement and depressive symptoms varied across four sources social support. METHOD: Health and Retirement Study data were used to assess whether four measures of structural support moderated the association between transitioning to full retirement (relative to remaining in full time work) and symptoms of depression. RESULTS: Results from two stage mixed-effects multilevel models indicated (a) on average retirement was associated with a small but significant increase in depressive symptoms after adjusting for pre-retirement social support, (b) on average, social support not associated with changes in symptoms of depression, but (c) social support from friends moderates the association between retirement and symptoms of depression such that at low levels of social support, retirement was associated with a sizeable increase in depressive symptoms, but this association decreased as level of social support from friends increased. DISCUSSION: Results suggest people with low levels of social support may benefit from actively cultivating friendships in retirement to help mitigate some of deleterious effects of retirement.
Keywords: depression; Retirement; Social Support

Study finds ‘no evidence’ that racial disparities in dementia have decreased - Ernst, Julia (Race and Medicine, 2020)
Rates and incidence of dementia among non-Hispanic Black individuals remained substantially higher compared with non-Hispanic white individuals in the U.S. from 2000 through 2016, according to findings published in JAMA Neurology.
Keywords: cognition impairment; Dementia; Health Disparities; Neurology

Study Protocol: Social Capital as a Resource for the Planning and Design of Socially Sustainable and Health Promoting Neighborhoods- A Mixed Method Study. - Santosa, Ailiana; Ng, Nawi; Zetterberg, Liv; Eriksson, Malin (Front Public Health, 2020)
Promoting inclusive, safe, resilient, and sustainable communities is one of the 17 Sustainable Development Goals ratified in 2015 by 193 UN member states, not least in Sweden. Social sustainability involves preserving particular societal values (e.g., local identity) as well as developing values (e.g., social cohesion) that are perceived as needed. Socially sustainable development also implies promoting integration and preventing segregation. Social capital is one important indicator to measure how socially sustainable an area is. This project aims to explore how social capital can be used as a conceptual tool in developing housing policy for social sustainability in Umeå Municipality. The three sub-studies in this project combine quantitative and qualitative methods. We will conduct a review of the municipality's documents to understand how the ideas of social sustainability have influenced political declarations and implemented social and housing policies and interventions during the period 2006-2020. The quantitative study includes a longitudinal follow-up to the 2006 survey's respondents to assess the longitudinal impacts of neighborhood social capital on health and well-being; as well as a new repeated cross-sectional survey to investigate how social capital has changed in local neighborhoods from 2006 to 2020. The qualitative study includes case studies in neighborhoods with different social capital dynamics to understand how different resident sub-groups perceive their neighborhoods and how implemented social and housing policies have influenced the social capital dynamics and responded to the needs of different sub-groups. The project is run in close collaboration with the Commission for a Socially Sustainable Umeå. This project will create new and unique perspectives on long-term structural changes of relevance for a socially sustainable housing policy; knowledge that is highly valuable for continuous municipal planning; and will outline recommendations to guide local housing policies for social sustainable neighborhoods in Umeå Municipality. This study has been assessed and approved by the Swedish Ethics Review Authority (Dnr: 2019-04395; Dnr: 2020-00160; Dnr 2020-02757). The dissemination goals of this project are (1) sustained engagement of key stakeholders throughout the project and (2) dissemination of the research findings through popular science, conferences, and scientific papers.
Keywords: Cross-Sectional Studies; Housing; Residence Characteristics; Review Literature as Topic; Social capital; Sweden

Study: Racial disparities exist in cognitive health expectancies, despite educational attainment - Deann Gayman (Nebraska Today, 2020)
There are more than 5 million Americans living with Alzheimer’s disease, and 50 million with other dementias, according to figures from the Alzheimer’s Association. Research into these diseases and how to prevent them is key as more and more Americans live longer, raising their risk for developing cognitive impairment.
Keywords: Alzheimer disease; Dementia; Education; race

Subjective well-being among male veterans in later life: The enduring effects of early life adversity. - Mai See Yang; Lien Quach; Lee, Lewina O; Avron Spiro III; Jeffrey A Burr (Aging & Mental Health, 2020)
OBJECTIVES: This study investigated the association between childhood and young adult adversities and later-life subjective well-being among older male veterans. We also explored whether early-life parent-child relationships and later-life social engagement served as moderators and mediators, respectively. METHODS: Data were from the 2008 to 2012 waves of the Health and Retirement Study for male veterans ( = 2026). Subjective well-being measures included depressive symptoms, self-rated health, and life satisfaction. Linear regression with the macro was employed to estimate the relationships. RESULTS: Adverse childhood experiences (ACEs) were positively associated with number of depressive symptoms and negatively related to life satisfaction. Combat exposure, a young adulthood adversity experience, was positively associated with depressive symptoms, but not with self-rated health or life satisfaction. Later-life social engagement mediated the relationship between ACEs and subjective well-being indices. Parent-child relationship quality did not moderate the association between the measures of adversity and any measure of subjective well-being. DISCUSSION: Childhood adversity and combat exposure were related to worse later life subjective well-being. Also, later-life social engagement mediated the association of two early life adversity measures and subjective well-being. Future research should examine subjective well-being and early life adversity for female veterans and should employ more detailed information about combat exposure.
Keywords: Adversity; depression; Life Satisfaction; Military service; Self-rated health

Sampling Weights: Revised for Tracker 2.0 & Beyond - HRS Staff (Survey Research Center, Institute for Social Research, University of Michigan, 2019)

Scared to death? Information avoidance and diagnostic testing - Yi Zhong (Economics, 2019)
The use of preventive care in the U.S. is half the recommended level. Previous economic studies suggest that price is not the only significant deterrent. In fact, empirical evidence suggests that some people are health information avoidant: they prefer not knowing information about their health even when diagnostic testing is free and very accurate. This study evaluates the roles of many contributors to an individual's demand for type-2 diabetes screening. To explain the puzzle of information avoidance, I apply insights from the economics theoretical literature to incorporate health anxiety, which represents the stress or disutility associated with the anticipation of bad outcomes, as another psychic cost of taking a test. With data from the Health and Retirement Study, I jointly estimate a set of quasi-structural equations derived from a forward-looking individual's optimization problem regarding diabetes screening. In the model, the individual chooses the number of doctor visits (at which a diabetes screening is a stochastic outcome to reflect provider differences and additional individual behaviors) and lifestyle behaviors. Underlying disease governs her diabetes state and she has imperfect information about her true health. Results suggest that health anxiety, as well as monetary costs, time costs, subjective health and longevity expectations are each important contributors to an individual's diabetes screening behavior. Individuals' lifestyle behaviors also respond to health information associated with screening tests. Multiple policy experiments aiming to improve screening behavior and population health are evaluated using the estimated dynamic model.
Keywords: Decision making; Diabetes; Screenings

SeaTE: Subjective ex ante Treatment Effect of Health on Retirement - Giustinelli, Pamela; Matthew D. Shapiro (National Bureau of Economic Research Working Paper Series, 2019)
The Subjective ex ante Treatment Effect is the difference between the probabilities of an outcome conditional on a treatment. The SeaTE yields ex ante causal effects at the individual level. The paper gives an interpretation in two workhorse econometric frameworks: potential outcomes and dynamic programming. It finds large effect heterogeneity of health on work in two surveys of older workers, the VRI and the HRS. It shows how reduced-form estimates of health on work are biased when there is unobserved heterogeneity in taste for work. Using the VRI’s panel structure, it validates the elicited conditional probabilities of work given health.
Author contact info:Pamela GiustinelliDepartment of EconomicsBocconi UniversityMilan, ItalyE-Mail: pamela.giustinelli@gmail.comMatthew D. ShapiroDepartment of EconomicsUniversity of Michigan611 Tappan StAnn Arbor, MI 48109-1220Tel: 734/764-5419Fax: 734 764-2769E-Mail: shapiro@umich.edu
Keywords: health; Retirement; SeaTE

Self-Perceptions of Aging and Health: The Embodiment of Age Stereotypes. - Jennifer K Sun (Psychology, 2019)
Age stereotypes are pervasive in contemporary American society. A growing body of research has shown that the internalization of societal age stereotypes can affect older adults’ self-perceptions of aging (SPA), or attitudes towards their own aging process, in ways that can have significant implications for health and well-being. Based on Levy’s stereotype embodiment theory, this dissertation used data from the Health and Retirement Study to examine the behavioral, biological, and psychological processes that potentially underlie the relationship between SPA and health among older US adults. On a behavioral level, Study 1 found that, over a 1-year follow-up, individuals with negative SPA were more likely to delay necessary medical care and report more barriers to care, such as limited access to transportation and disliking going to the doctor. On a biological level, Study 2 considered the association between SPA, perceived discrimination, and changes in cystatin c (a biomarker of kidney function). Over the 4-year follow-up, having more negative SPA was associated with larger increases in cystatin c (e.g., worse kidney functioning) among those who reported being the target of discrimination. On a psychological level, Study 3 investigated the relationship between two different perceptions of the self, self-perceptions of grip strength and SPA, in predicting 4-year change in mobility limitations among adults over age 65. Individuals with more positive SPA had fewer mobility limitations four years later, even after adjusting for measured/perceived grip strength and other risk factors. Having more positive SPA, however, was only predictive of fewer mobility problems among respondents who also perceived their grip strength to be strong, highlighting the importance of considering both domain-specific and domain-general self-perceptions when designing interventions to improve functional health. Together, these studies extend the literature linking SPA and health by investigating proposals about three underlying processes. The final chapter discusses the implications of study findings, with a special focus on the design of interventions to promote more positive attitudes toward aging and the need to change age-related attitudes among health care professionals.
Keywords: Aging; health; Self-perception; Stereotypes

Self-Reported Personality Traits and Informant-Rated Cognition: A 10-Year Prospective Study - Angelina R Sutin; Yannick Stephan; Antonio Terracciano (Journal of Alzheimer's Disease, 2019)
Personality traits, such as higher Neuroticism and lower Conscientiousness, are associated with risk of Alzheimer's disease and other dementias. A diagnosis of dementia relies, in part, on informant ratings of the individual's cognitive status. Here we examine whether self-reported personality traits are associated with four measures of informant-rated cognition up to a decade later. Participants from the Health and Retirement Study (N = 2,536) completed a five-factor model measure of personality in 2006 or 2008. Informants completed the 2016 Harmonized Cognitive Assessment Protocol (HCAP), which included ratings of the participant's current cognitive functioning and change in cognitive function over the last decade assessed with the IQCODE, Blessed, 1066, and CSID. Controlling for characteristics of the participant, informant, and their relationship, higher Neuroticism and lower Conscientiousness were associated consistently with worse informant-rated cognition. The association between Openness and better informant-rated cognition was due primarily to higher baseline cognitive function. Extraversion and Agreeableness were associated with better informant-rated cognition only among participants who were cognitively intact at follow-up. The present research suggests that knowledgeable informants are able to detect cognitive deficits associated with personality. © 2019 - IOS Press and the authors. All rights reserved.
cited By 0
Keywords: Aged; agreeableness; Article; Cognition; Conscientiousness; extraversion; Female; follow up; human; major clinical study; Male; neurosis; openness; Personality; priority journal; prospective study; Self Report

Self-Reported Prescription Drug Use for Pain and for Sleep and Incident Frailty - Cil, G.; Juyoung Park; Bergen, A.W. (Journal of the American Geriatrics Society, 2019)
OBJECTIVES: We aimed to estimate incident frailty risks of prescription drugs for pain and for sleep in older US adults. DESIGN: Longitudinal cohort. SETTING: Health and Retirement Study. PARTICIPANTS: Community-living respondents aged 65 years and older, excluding individuals who received recent treatment for cancer (N = 14 208). Our longitudinal analysis sample included respondents who were not frail at baseline and had at least one follow-up wave with complete information on both prescription drug use and frailty, or date of death (N = 7201). MEASUREMENTS: Prescription drug use for pain and sleep, sociodemographics, other drug and substance use, and Burden frailty model components. Multivariable drug use stratified hazard models with death as a competing risk evaluated frailty risks associated with co-use and single use of prescription drugs for pain and for sleep. RESULTS: Proportions endorsing prescription drug use were 22.1% for pain only, 6.8% for sleep only, and 7.7% for both indications. Burden frailty model prevalence was 41.0% and varied significantly by drug use. Among non-frail individuals at baseline, proportions endorsing prescription drug use were 14.9%, 5.6%, and 2.2% for the three indications. Prescription drug use was associated with increased risk of frailty (co-use adjusted subhazard ratio [sHR] = 1.95; 95% confidence interval [CI] = 1.6-2.4; pain only adjusted sHR = 1.58; CI = 1.4-1.8; sleep-only adjusted sHR = 1.35; CI = 1.1-1.6; no use = reference group). Cumulative incidence of frailty over 8 years for the four groups was 60.6%, 50.9%, 45.8%, and 34.1%. Sensitivity analyses controlling for chronic diseases associated with persistent pain resulted in minor risk reductions. CONCLUSION: Prescription pain and sleep drug use is significantly associated with increased incidence of frailty. Research to estimate effects of pain and sleep indications and of drug class–specific dosage and duration on incident frailty is indicated before advocating deprescribing based on these findings. © 2019 The American Geriatrics Society
cited By 0
Keywords: pain; prescription drugs; Sleep

Seniors who feel their life has purpose may live longer - Carroll, Linda (Reuters, 2019)
Keywords: Longevity; News; Purpose in life

A sense of purpose could prolong your life - Ephrat Livni (Quartz, 2019)
Keywords: Longevity; News; Purpose in life

Sex differences in the association between salivary telomere length and multimorbidity within the US Health & Retirement Study - Niedzwiedz, Claire L.; Katikireddi, Srinivasa Vittal; Pell, Jill P.; Smith, Daniel J. (Age and Ageing, 2019)
Background Telomere length is associated with several physical and mental health conditions, but whether it is a marker of multimorbidity is unclear. We investigated associations between telomere length and multimorbidity by sex. Methods Data from adults (N = 5,495) aged ≥50 years were taken from the US Health and Retirement Study (2008–14). Telomere length was measured in 2008 from salivary samples. The cross-sectional associations between telomere length and eight chronic health conditions were explored using logistic regression, adjusting for confounders and stratified by sex. Logistic, ordinal and multinomial regression models were calculated to explore relationships between telomere length and multimorbidity (using a binary variable and a sum of the number of health conditions) and the type of multimorbidity (no multimorbidity, physical multimorbidity, or multimorbidity including psychiatric problems). Using multilevel logistic regression, prospective relationships between telomere length and incident multimorbidity were also explored. Results In cross-sectional analyses, longer telomeres were associated with reduced likelihood of lung disease and psychiatric problems among men, but not women. Longer telomeres were associated with lower risk of multimorbidity that included psychiatric problems among men (OR=0.521, 95% CI: 0.284 to 0.957), but not women (OR=1.188, 95% CI: 0.771 to 1.831). Prospective analyses suggested little association between telomere length and the onset of multimorbidity in men (OR=1.378, 95% CI: 0.931 to 2.038) nor women (OR=1.224, 95% CI: 0.825 to 1.815). Conclusions Although telomere length does not appear to be a biomarker of overall multimorbidity, further exploration of the relationships is merited particularly for multimorbidity including psychiatric conditions among men.
Keywords: Comorbidity; Genetics; Telomeres; Women and Minorities

Smoking, life expectancy, and chronic disease in South Korea, Singapore, and the United States: A microsimulation model - Kim, Daejung; Chen, Cynthia; Tysinger, Bryan; Park, Sungchul; Chong, Ming Zhe; Wang, Lijia; Zhao, Michelle; Yuan, Jian-Min; Koh, Woon-Puay; Yoong, Joanne; Bhattacharya, Jay; Eggleston, Karen (Health Economics, 2019)
Abstract The substantial social and economic burden attributable to smoking is well-known, with heavy smokers at higher risk of chronic disease and premature mortality than light smokers and nonsmokers. In aging societies with high rates of male smoking such as in East Asia, smoking is a leading preventable risk factor for extending lives (including work-lives) and healthy aging. However, little is known about whether smoking interventions targeted at heavy smokers relative to light smokers lead to disproportionately larger improvements in life expectancy and prevalence of chronic diseases and how the effects vary across populations. Using a microsimulation model, we examined the health effects of smoking reduction by simulating an elimination of smoking among subgroups of smokers in South Korea, Singapore, and the United States. We found that life expectancy would increase by 0.2 to 1.5 years among light smokers and 2.5 to 3.7 years among heavy smokers. Whereas both interventions led to an increased life expectancy and decreased the prevalence of chronic diseases in all three countries, the life-extension benefits were greatest for those who would otherwise have been heavy smokers. Our findings illustrate how smoking interventions may have significant economic and social benefits, especially for life extension, that vary across countries.
Keywords: healthy aging; heavy smokers; KLoSA; microsimulation; Singapore; smoking interventions; South Korea; tobacco control

So Help Me, God: Religiosity and End-of-Life Choices in a Nationally Representative Sample. - Hoe, Deborah F; Enguidanos, Susan (Journal of Palliative Medicine, 2019)
Studies show significant associations between the various dimensions of religiousness and end-of-life (EOL) decisions, such as individuals with high religiosity are more likely to choose aggressive care at EOL. However, these studies focused largely on smaller cancer populations. To our knowledge, there is no existing literature about the association between religiosity and EOL decisions within a national sample of older adults. The objective of this study was to investigate the association between religiosity and advance directive (AD) completion, and among those with an AD, documented EOL care preferences, using a nationally representative sample. This was an observational study. Descriptive statistics and logistic regression were conducted with 6051 decedents from the Health and Retirement Study using self-reported frequency of religious service attendance, importance of religion, and religious affiliation. The dependent variables were AD completion and care preference. The independent variables were self-reported frequency of religious service attendance, importance of religion, and religious affiliation. Protestants and Catholics had significantly lower odds of AD completion, compared with those with no religious preferences. Decedents who reported religion as very important had significantly lower odds of AD completion than decedents who said religion is not too important. Furthermore, decedents who attended religious services at least once a week, compared with those who do not attend, had significantly higher odds of completing an AD. Among those who completed an AD, neither religiosity nor religious affiliation was significantly associated with preference for prolonged care. Our study demonstrates the influence religiosity has on the development of ADs, prompting seriously ill patients' religious needs to be recognized and supported. It further suggests that religious services may provide a good opportunity for promoting knowledge and completion of ADs.
Keywords: End-of-Life Choices; Religion

Social Engagement Among Older Adults With Mild Cognitive Impairment and Conversion to Dementia - Amano, Takashi (Social Work, 2019)
Promoting social engagement is a promising approach to prevent or delay conversion from cognitive impairment no dementia (CIND) to dementia. However, little is known about social engagement among people with CIND. This dissertation project aimed to improve understanding of social engagement among people with CIND by addressing gaps in the literature. It had three specific aims including: to describe and identify factors associated with heterogeneity of social engagement among older adults with CIND, to assess the association between heterogeneity of social engagement and conversion from CIND to dementia, and to investigate the relationship among heterogeneity of social engagement, other types of activity engagement, and conversion from CIND to dementia. Data from two waves (2010 and 2014) of the Health and Retirement Study (HRS) were used. The sample consisted of 1,227 people who were classified as having CIND in 2010. To identify the heterogeneity of social engagement, Latent Class Analysis (LCA) was utilized. Multinomial logistic regression analysis was conducted to assess the association between factors and patterns of social engagement. Using LCA, three groups were identified: Formal and informal social engagement group, Informal social engagement only group, and Low social engagement group. Some factors from four domains of WHO’s ICF model were associated with probability of having certain patterns of social engagement. To assess the relationship between heterogeneity of social engagement and conversion from CIND to dementia, binary logistic regression was utilized. The result showed that people in the formal and informal social engagement group and informal social engagement only group had significantly lower probabilities of converting to dementia in four years. To investigate the relationship among different types of activity engagement and conversion from CIND to dementia, path analysis with structural equation model was utilized. The result revealed that the relationship between having the pattern of formal and informal social engagement and lower probability of converting to dementia in four years was mediated by having higher cognitive engagements. Findings suggest that social engagement is heterogeneous among people with CIND and there are some modifiable factors to promote social engagement among them. Results of this study also imply that promoting social engagement may be promising intervention to prevent or delay conversion from CIND to dementia. Findings further indicate that promoting social engagement may be more effective and efficient strategy since it promotes other activity engagements that may prevent or delay conversion from CIND to dementia.
Keywords: Cognition; cognitive impairment; Dementia; social engagement

Social isolation in chronic kidney disease and the role of mobility limitation - Ranjani N Moorthi; Kenzie Latham-Mintus (Clinical kidney journal, 2019)
BACKGROUND: Chronic kidney disease (CKD) is associated with multiple comorbidities, hospitalizations and mortality. In older adults, social isolation and poor mobility contribute to these outcomes. We tested the hypothesis that a glomerular filtration rate (GFR) <45 mL/min/1.73 m(2) (CKD Stages 3b-5) is associated with social isolation and that mobility limitation is a key driver of social isolation in patients with CKD. METHODS: Data from 9119 participants, ages 57-107 years, from the 2016 wave of the Health and Retirement Study's Venous Blood Study were used for this cross-sectional analysis. Kidney function measured by estimated GFR (eGFR) was the predictor and patients were classified as CKD Stages 3b-5 or non-CKD Stages 3b-5 (eGFR ≤45 or >45 mL/min/1.73 m(2)). The outcomes tested were mobility limitation assessed by self-report and social contact and participation measures assessed by the Psychosocial Life Questionnaire. The associations among kidney function, mobility and social isolation were examined with logistic and ordinary least squares regression, adjusted for covariates and testing for interaction with gender. RESULTS: Participants with CKD Stages 3b-5 (N = 999) compared with non-CKD Stages 3b-5 were older (74.9 versus 68.2 years, P < 0.001) and fewer were female (15% versus 58%, P < 0.001). CKD Stages 3b-5 were associated with higher odds of difficulty walking several blocks [odds ratio 1.44 (95% confidence interval 1.16-1.78)]. Participants with CKD Stages 3b-5 had reduced social contact and social participation (B = -0.23, P < 0.05; B = -0.62, P < 0.05, respectively). Women with CKD Stages 3b-5 were 2.7 times more likely to report difficulty walking several blocks than men with CKD Stages 3b-5, but social isolation in CKD Stages 3b-5 did not vary by gender. In CKD Stages 3b-5 patients, mobility limitation was a risk factor for reduced social contact and participation but did not explain the poor social contact and participation. CONCLUSION: CKD Stages 3b-5 was associated with both mobility limitation and social isolation in a population-based study of older adults. In contrast to older adults without CKD Stages 3b-5, mobility limitation did not explain the lack of social contact and poor social participation, suggesting other factors are more important.
Keywords: CKD; Elderly; mobility; outcomes; social isolation

Social relations and age-related change in memory. - Laura B Zahodne; Kristine J. Ajrouch; Sharifian, Neika; Toni C Antonucci (Psychology and Aging, 2019)
Previous research suggests that social relations are associated with age-related memory change. However, social relations are complex and multidimensional, and it is not yet clear which aspects (structure, quality) may be beneficial over time. Further, the strength and direction of associations may differ depending on relationship type (partner, children, other family, friends). Using longitudinal data from the Health and Retirement Study (n = 10,390; Mage = 69, SD = 9.53 at baseline), latent growth curve models tested which aspects of social relations predicted 6-year episodic memory trajectories. Both structure and quality of social relations were associated with initial memory level, such that being married/partnered, reporting more frequent contact with children and friends, reporting less support from family members other than partners and children, and reporting less strain across relationship types were each independently associated with better initial memory. In contrast, only structure was associated with subsequent memory decline. Specifically, being married/partnered and reporting more frequent contact with friends were each independently associated with slower memory decline. No evidence of bidirectionality was found, as baseline memory did not predict subsequent changes in social relations. This longitudinal study helps to clarify which aspects of social relations are most likely to influence late-life episodic memory trajectories. Future intervention studies may focus on increasing social interactions with nonfamily members to minimize memory decline with age. (PsycINFO Database Record (c) 2019 APA, all rights reserved).
Keywords: Cognitive Ability; Family Roles/Relationships; Memory; Social Support

Social Relationships and Progression of Frailty: Exploring the Reciprocal Association of Social Ties and Physical Vulnerability in Later Life - Ji Hyun Lee (Human Development and Family Studies, 2019)
Frailty is described as a state of heightened vulnerability and functional impairment due to the cumulative declines across multiple physiological systems. When faced with stressor events, older adults with frailty are in higher risk of adverse health outcomes. While the prevalence of frailty generally increases with age, there are considerable heterogeneity in onset and progression of frailty among older population. Growing attention is given to identifying the psychosocial factors related to the development of frailty. Social relationships often serve as a vital context of health, where older adults experience multidimensional and dynamic exchange with close others as they age. In this dissertation, two studies are conducted to investigate complex and reciprocal nature of social relationships and frailty progression in older adulthood. The data are from the six waves (2006-2016) of the Health and Retirement Study (HRS), a nationally representative study of older adults in U.S. aged 50 and older. The first study utilized the convoy model of social relations to provide comprehensive investigation of how different aspects of social relations are associated with frailty progression over a decade. There were three distinctive subpopulations following a different frailty progression trajectory. When social network and relational quality with spouse, children, family, and friends were examined, higher frequency of contact with friends were associated with lesser frailty. Negative relationship quality with social ties were detrimental to frailty progression, such that strain with spouse and kin (children and extended family) had an additive effect on belonging to high frailty or steep increase frailty trajectory groups. The perceived loneliness partially explained the negative effect of spousal strain, but the negative effect of large family size and strain with kin were independent from loneliness. The second study explored the health contexts of older couple’s marital quality, specifically focusing on the presence of frailty and depression within- and across-person in the marital relationship. Using three waves of dyadic data from HRS, I found that one’s own and partner’s higher frailty and higher depression all had independent associations with one’s higher marital strain. For one’s marital support, one’s own higher frailty, higher depression, and partner’s higher depression had negative effects. There was an across-person interaction effect of frailty, such that one’s marital quality was affected by their partner’s higher level of frailty only when their own health was good. Having a husband with higher frailty was associated with higher marital strain for wives. Most effects were stable over time. Overall, the findings illustrate the significance of social relationship context as a predictor for different trajectory of frailty progression. The size, frequency of contact, positive, and negative quality were linked to frailty differentially by relationship type, underscoring the benefits of comprehensive examination of social experiences. Further, the level of frailty and depression were linked to perceived marital quality of both members of the couple, especially in damaging manner when healthier spouse is faced with partner's health problems. Taken together, my dissertation demonstrated the importance of studying linked lives in context of health conditions prevalent in older adulthood. The findings can be useful to practitioners and policy makers in understanding the intricate link between social relations and frailty as well as in identifying modifiable factors for frailty prevention.
Copyright - Database copyright ProQuest LLC; ProQuest does not claim copyright in the individual underlying works; Last updated - 2019-10-03
Keywords: 0344:Social research; 0351:Gerontology; 0621:Psychology; Aging; Frailty; Gerontology; Health and Retirement Study; Marriage; Older Adults; Psychology; Social Relationships; Social research

Social Relationships and Salivary Telomere Length Among Middle-Aged and Older African American and White Adults. - Karen D Lincoln; Donald A Lloyd; Ann W Nguyen (Journals of Gerontology Series B: Psychological Sciences and Social Sciences, 2019)
Objectives: A common mechanism underlying premature morbidity may be accelerated biological aging as reflected by salivary telomere length (STL). This study examined the extent to which social relationships, both positive and negative, can be protective or confer risk relative to biological aging. Method: Data from the Health and Retirement Study and multiple regression were used to examine cross-sectional associations between STL, self-reported social support, and negative interaction (e.g., conflict, criticism) with family in a nationally representative sample of African American and non-Hispanic White middle-aged and older adults (N = 4,080). Results: Social support from family was associated with shorter STL. Negative interaction with family had no main effect on STL but interactions characterized by high social support and more frequent negative interactions were associated with longer STL. Negative interaction with family was negatively associated with STL for African Americans and Whites but the magnitude of the effect was greater for African Americans. Discussion: Study findings highlight the role of social relationships in physiological deterioration among middle-aged and older adults and identify a potential mechanism whereby race is linked to accelerated biological aging. Findings highlight the importance of considering positive and negative aspects of social relationships to understand the consequences of social connections for cellular aging in diverse populations.
Keywords: African Americans; Social Relationships; Telomeres; Women and Minorities

Social Status Perception and Individual Social Capital: Evidence from the US - Alessandro Bucciol; Cicognani Simona; Zarri Luca (The B.E. Journal of Economic Analysis & Policy, 2019)
This paper provides evidence that individual social capital contributes to our understanding of where individuals locate themselves in the social ladder, also when their objective location within society (measured in terms of income, wealth, education and job) is considered. Using large-scale longitudinal data from the US Health and Retirement Study, we assess individual social capital by means of a multidimensional approach and consider (number, intensity and quality of) respondents’ friendships, prosocial behavior, social engagement and neighborhood cohesion. Our findings indicate that individual social capital plays a role in affecting subjective status, as self-perceived status correlates positively with neighborhood cohesion and negatively with negative support from friends, after controlling for objectively measured social status.
Keywords: Perception; Social capital; Social status

Social support and monetary resources as protective factors against food insecurity among older Americans: findings from a health and retirement study - Nicholas J Bishop; Wang, Kaipeng (Food Security, 2019)
We examined the association between social support, monetary resources, and food insecurity among a nationally representative sample of older Americans. Analyses included 1164 Americans aged 65 and above from the 2012 Health and Retirement Study and the 2013 Health Care and Nutrition Study. Logistic regression analyses were used to estimate the likelihood of food insecurity as a function of social support (including social contact, emotional support, and social strain), monetary resources (including household income and household assets), and covariates. We found older adults with greater social strain and lower emotional support were at increased risk of food insecurity. Greater monetary resources were associated with lower risk of food insecurity. Select indicators of social support appeared to moderate the effect of monetary resources on food insecurity, with increasing social strain reducing the protective benefits of greater household assets, and low emotional support reducing the protective effect of increased household income to non-significance. Emotional support and social strain are aspects of social relationships that may play important roles in the relationship between monetary resources and food insecurity. Interventions seeking to reduce the burden of food insecurity should consider the quality and quantity of social relationships as potential risk factors.
Keywords: Assets; Emotional support; Food insecurity; Income; Social strain

Social Support and Preventive Healthcare Behaviors Among Couples in Later Life. - Sae Hwang Han; Kyungmin Kim; Jeffrey A Burr (Gerontologist, 2019)
Background and Study Objectives: Intimate partners and close friends represent two major sources of social support that are central to one's health and health behaviors in later life. The aim of this study was to examine dyadic linkages between perceived social support (from spouses and friends) and preventive healthcare behaviors among coupled-individuals. Design and Methods: Prospective data from the Health and Retirement Study (2010, 2012) were used to analyze a sample of coupled-individuals (dyad N = 1,902). A series of multilevel logistic regression (actor-partner interdependence) models were estimated to evaluate whether perceived social support from spouses and friends was associated with the likelihood of using two common forms of preventive healthcare services (i.e., influenza vaccination and cancer screenings). Results: Apart from the role of perceived support from spouse on flu vaccinations, wives' preventive healthcare behaviors were unrelated to perceived social support. In contrast, husbands' preventive healthcare behaviors showed consistent associations with perceived social support from friends for the 2-year observation period. Further, husbands' receipt of prostate cancer screening was associated with wives' perceptions of social support from spouse as well as friends. Discussion and Implications: These findings contributed to our understanding of the health advantages associated with being in a marital relationship for preventive healthcare behaviors, especially for men. Future research should unpack the pathways through which social support of various forms is associated with obtaining needed preventive health services.
Keywords: Marriage; Preventative Care; Social Support

Socioeconomic Status, Dietary Patterns, and Cardiovascular Risk Factors in an Aging Population - Li, Wenchao (Epidemiological Science, 2019)
As the leading cause of death in the United States (U.S.), cardiovascular disease (CVD) is responsible for 17% of national health expenditures. The health and economic burden of CVD is especially high in older adults. As a consequence of population aging, it has been projected by the American Heart Association that by 2030, 40.5% of the U.S. population will have some form of CVD, assuming no change to current prevention strategies. In order to address this rising public health issue with more effective prevention strategies, a better understanding of CVD risk factors and their interrelationship is needed. Obesity, type 2 diabetes (T2D), and hypertension (HTN) are each a leading and proximal CVD risk factor. In addition, they tend to coexist with each other and form multimorbidities, which are associated with substantially further elevated CVD risk. Using a life course approach, this dissertation examined the complex interrelationship among childhood socioeconomic status (SES), adulthood SES, adulthood dietary patterns, and the health outcomes of obesity, T2D, and HTN, individually and in the form of multimorbidities. Each of the three aims in this dissertation used a cross-sectional study design and was based on data from the Health and Retirement Study (HRS), a large nationally representative longitudinal study of U.S. adults aged over 50. Indicators of childhood SES included paternal education, maternal education and childhood financial strain. Indicators of adulthood SES included education and wealth. Two dietary patterns, prudent and Western, were initially identified using principal component analysis (PCA). The first aim examined the associations of childhood SES with adulthood dietary patterns using linear regression models. Results of this aim showed that, in selected sociodemographic groups, higher paternal education is associated with healthier dietary habits in adulthood, independent of adulthood SES. The second aim examined the associations of adulthood dietary patterns with obesity, T2D, and HTN, separately, accounting for potential confounding by childhood and adulthood SES and using logistic regression models. Under the potential influence of reverse causation and survival bias, results of this aim showed positive associations of both the prudent and Western dietary patterns with the health outcomes. SES, whether in childhood or in adulthood, did not appear to be a strong confounder to these associations. The third aim used multinomial logistic regression models to explore the associations of childhood SES, adulthood SES, and adulthood dietary patterns with the multimorbidity of obesity, T2D, and HTN. Results of this aim showed that the multimorbidity of obesity, T2D, and HTN is highly prevalent among older U.S. adults, and under the potential influence of reverse causation and survival bias, it is independently associated with lower paternal education, lower participant’s education and wealth, and greater adherence to the prudent and Western dietary patterns. Overall, this dissertation provides further evidence that childhood environment and conditions may underlie adulthood dietary habits and proximal CVD risk factors (e.g. obesity, T2D, and HTN), individually and in the form of multimorbidity. More studies, especially prospective studies, are needed to further evaluate the potential impact of paternal education on later life CVD risk, as well as whether dietary behavior is an underlying pathway linking childhood SES to later life CVD risk.
Keywords: Diabetes; diet; Hypertension; Obesity; Older Adults; socioeconomic status

Spousal breadwinning across 30 years of marriage and husbands' health: A gendered life course stress approach. - Kristen W Springer; Lee, Chioun; Deborah Carr (Journal of Aging and Health, 2019)
OBJECTIVE: Wives increasingly outearn their husbands, and gender relations theory suggests this arrangement may undermine men's well-being. We explore how long-term histories of spousal breadwinning may be associated with older men's self-rated mental and physical health, and risk of nine health diagnoses. METHOD: Using 30 years of couple-level income data from the Health and Retirement Study ( n = 1,095 couples), we use latent class analyses to identify six classes that differ with respect to the timing and level of wife breadwinning. We link these classes to older husbands' later-life health. RESULTS: Classes that transitioned from husband breadwinning to wife breadwinning in early or later adulthood were associated with husbands' poorer overall physical health and risk of cardiometabolic and stress-related diseases. Patterns persist net of sociodemographics, depressive symptoms, health behaviors, and adolescent health. DISCUSSION: Violating cultural expectations, such as the masculinity ideal of male breadwinning, is associated with older men's poorer health.
Keywords: Gender Differences; Income; Marriage; Women and Minorities

Spousal caregivers are caregiving alone in the last years of life - Katherine A Ornstein; Jennifer L. Wolff; Bollens-Lund, Evan; Rahman, Omari-Khalid; Amy Kelley (Health Affairs, 2019)
Caregiving in the last years of life is associated with increased depression and negative health outcomes for surviving spouses, many of whom are themselves in poor health. Yet it is unclear how often spouses are caregiving alone, how they differ from supported spouses, and whether lack of support affects postbereavement outcomes. We hypothesized that spouses who were solo caregivers—that is, the only caregivers (paid or unpaid) who provided assistance with a spouse’s self-care or household activities—would experience more depression after bereavement than supported spouses would. Using information from the Health and Retirement Study, we found that 55 percent of the spouses of community-dwelling married people with disability were solo caregivers. Solo caregiving was even common among people who cared for spouses with dementia and those with adult children living close by. Bereavement outcomes did not differ between solo and supported caregiving spouses. Caregiving spouses are often isolated and may benefit from greater support, particularly during the final years before bereavement. While some state and federal policy proposals aim to systematically recognize and assess caregivers, further innovations in care delivery and reimbursement are needed to adequately support seriously ill older adults and their caregivers. Ultimately, the focus of serious illness care must be expanded from the patient to the family unit.
Keywords: Activities of Daily Living; Caregiving; Community-dwelling; Couples

Stability of clinically relevant depression symptoms in old-age across 11 cohorts: a multi-state study - de la Torre-Luque, A.; de la Fuente, J.; Albert Sánchez-Niubó; Francisco Félix Caballero; Matthew Prina; Muniz-Terrera, G.; Haro, J. M.; J. L. Ayuso-Mateos (Acta Psychiatrica Scandinavica, 2019)
Aims To study the temporal dynamics of depression symptom episodes in old‐age and the related influence of risk factors. Methods Data from 41 362 old adults (54.61% women; mean age = 75.30, SD = 6.20) from the Ageing Trajectories of Health – Longitudinal Opportunities and Synergies (ATHLOS) project were used. Depressive symptoms were followed over an 18‐year period. A multi‐state model, comprising three statuses (no depression, new clinically relevant episode of symptoms and episode persistence), was fitted. Multinomial regression was used to study the role of risk factors in status transition. Results Almost 85% of participants showed no depression, but prevalence became lower over time (B = −0.25, P < 0.001). New episode point prevalence was over 5.30% with a significant probability of moving to persistence status (transition probability = 0.27). Episode persistence became evident in 9.86% of episode status transitions, with increasing rate over time (B = 0.54, P < 0.01). Loneliness was proven to be the strongest predictor of episode emergence (OR = 17.76) and persistence (OR = 5.93). Conclusions The course of depression tends to become chronic and unremitting in old‐age. This study may help to plan interventions to tackle symptom escalation and risk factor influence.
Keywords: ATHLOS project; clinically relevant symptom episode; late-life depression; Loneliness; multi-state model

Stress and inflammation among older adults: The moderating role of religiosity - Jane Tavares; Corina R Ronneberg; Edward Alan Miller; Jeffrey A Burr (Journal of Religion, Spirituality & Aging, 2019)
Chronic stress weakens the immune system and leads to heightened bodily inflammation, which in turn is linked with serious health conditions. This study examined whether religiosity moderates the relationship between stress and inflammation (measured by C-reactive Protein (CRP)). A sample of 4,734 community-dwelling older adults was drawn from the 2006 wave of the Health and Retirement Study. Logistic regression was used to analyze the relationship between chronic stress (8-item index), inflammation (high CRP level), and religiosity (organizational, nonorganizational, and intrinsic), controlling for other factors. Higher levels of stress were significantly associated with high inflammation/CRP (p =.039). Further, intrinsic religiosity acted as a moderator of this relationship (p =.024), such that the relationship between stress and inflammation is lessened for persons with higher levels of intrinsic religiosity. Higher intrinsic religiosity attenuated the effects of stress on inflammation, suggesting that individuals with stronger religious commitment/motivation may better cope with stress.
Keywords: Depressive symptoms; Religion; Social Factors

Stress and salivary telomere length in the second half of life: A comparison of life-course models - Willis, Margaret; Ursula M. Staudinger; Factor-Litvak, Pam; Calvo, Esteban (Advances in Life Course Research, 2019)
Keywords: Biomarkers; Depressive symptoms; Telomeres

Subjective Age and Cystatin C Among Older Adults. - Yannick Stephan; Angelina R Sutin; Antonio Terracciano; Shevaun Neupert (Journals of Gerontology, Series B: Psychological Sciences & Social Sciences, 2019)
Objective: Cystatin C (CysC) is a marker of kidney function that is relevant for the health and cognition of older adults. Little is known about the link between psychological factors and CysC. Therefore, the present study examined whether subjective age is related to CysC level and changes in CysC over time. Method: Participants were 5,066 individuals drawn from the Health and Retirement Study aged from 50 to 107 years (60% women, mean age = 69.36 years, SD = 9.54). They provided data on subjective age, demographic covariates, and CysC at baseline. CysC was assessed again 4 years later. Results: Analysis revealed that an older subjective age was related to higher level of CysC at baseline and to an increase in CysC over 4 years, controlling for demographic factors. An older subjective age was also related to higher risk of exceeding the clinical threshold of CysC at baseline and 4 years later. Additional analysis revealed that disease burden, depressive symptoms, physical inactivity, and BMI partly mediated these associations. Conclusion: The present study provides new evidence on the role of subjective age as a psychological factor associated with individuals' risk of kidney dysfunction, an association beyond chronological age.
Keywords: Cystatin C; Health Conditions and Status; Subjective age

Successful Aging among Bridge Employment Workers - Campbell,Tiffany C. (Clinical Psychology and Industrial-Organizational Psychology, 2019)
As life expectancy rates expand and health care advancements continue to improve, countless older workers have the capacity to work in older age, and many are opting to participate in bridge employment rather than full retirement (Topa, Alcover, Moriano, & Depolo, 2014). Due to this surge in bridge employment participation, there has been an increased interest in the topic (Müller, De Lange, Weigl, Oxfart, & Van der Heijden, 2013; Munnell & Sass, 2008; Topa et al., 2014; Zhan, Wang, Liu, & Shultz, 2009). Therefore, the current study attempts to explore the experience of aging among the population of individuals who have elected to participate in bridge employment. In the current study, two of the most commonly used theoretical perspectives of successful aging: continuity theory, and resource-based dynamic theory, have been examined. Using this integrated perspective, the current study has attempts to explain the relationships between subjective socioeconomic status continuity and individual resources, and their impact on the change of successful aging over time among bridge employment workers. The analyses were conducted on data from a panel dataset collected by the Health and Retirement Study (HRS). This dataset included a large representative sample of U.S. older adults and used a longitudinal design. The analyses revealed that continuity theory is a suitable theoretical perspective to use when investigating the change of successful aging among bridge employment workers. Additionally, continuity in subjective socioeconomic status was found to have a significant, positive relationship with the level of successful aging among bridge employment workers and the change of successful aging over time. The results from the current study underscore the importance of stability in one’s sense of standing in the social hierarchy and its impact of successful aging among this population.
Copyright - Database copyright ProQuest LLC; ProQuest does not claim copyright in the individual underlying works; Last updated - 2019-05-23
Keywords: 0624:Occupational psychology; 0703:Organizational behavior; Bridge employment; Full retirement; Occupational psychology; Organizational behavior; Psychology; Social Sciences; Successful aging

Systematic mortality improvement trends and mortality heterogeneity: Insights from individual-level HRS data - Xu, Mengyi; Sherris, Michael; Meyricke, Ramona (North American Actuarial Journal, 2019)
Providers of life annuities and pensions need to consider both systematic mortality improvement trends and mortality heterogeneity. Although how mortality improvement varies with age and gender at the population level is well studied, how trends vary with risk factors remains relatively unexplored. This article assesses how systematic mortality improvement trends vary with individual risk characteristics using individual-level longitudinal data from the U.S. Health and Retirement Study between 1994 and 2009. Initially a Lee-Carter model is used to assess mortality improvement trends by grouping individuals with similar risk characteristics of gender, education, and race. We then fit a longitudinal mortality model to individual-level data allowing for heterogeneity and time trends in individual-level risk factors. Our results show how survey data can provide valuable insights into both mortality heterogeneity and improvement trends more effectively than commonly used aggregate models. We show how mortality improvement differs across individuals with different risk factors. Significantly, at an individual level, mortality improvement trends have been driven by changes in health history such as high blood pressure, cancer, and heart problems rather than risk factors such as education, marital status, body mass index, and smoker status.
Keywords: Mortality

S. Rept. 115-289 - DEPARTMENTS OF LABOR, HEALTH AND HUMAN SERVICES, AND EDUCATION, AND RELATED AGENCIES APPROPRIATION BILL, 2019 (United States Government, 2018)
Keywords: Government; Policy

Secular Trends in Dementia and Cognitive Impairment of U.S. Rural and Urban Older Adults - Margaret M Weden; Regina A Shih; Mohammed U Kabeto; Kenneth M. Langa (American Journal of Preventive Medicine, 2018)
Introduction This is a nationally representative study of rural−urban disparities in the prevalence of probable dementia and cognitive impairment without dementia (CIND). Methods Data on non-institutionalized U.S. adults from the 2000 (n=16,386) and 2010 (n=16,311) cross-sections of the Health and Retirement Study were linked to respective Census assessments of the urban composition of residential census tracts. Relative risk ratios (RRR) for rural−urban differentials in dementia and CIND respective to normal cognitive status were assessed using multinomial logistic regression. Analyses were conducted in 2016. Results Unadjusted prevalence of dementia and CIND in rural and urban tracts converged so that rural disadvantages in the relative risk of dementia (RRR=1.42, 95% CI=1.10, 1.83) and CIND (RRR=1.35, 95% CI=1.13, 1.61) in 2000 no longer reached statistical significance in 2010. Adjustment for the strong protective role of educational attainment reduced rural disadvantages in 2000 to statistical nonsignificance, whereas adjustment for race/ethnicity resulted in a statistically significant increase in RRRs in 2010. Full adjustment for sociodemographic and health factors revealed persisting rural disadvantages for dementia and CIND in both periods with RRR in 2010 for dementia of 1.79 (95% CI=1.31, 2.43) and for CIND of 1.38 (95% CI=1.14, 1.68). Conclusions Larger gains in rural adults’ cognitive functioning between 2000 and 2010 that are linked with increased educational attainment demonstrate long-term public health benefits of investment in secondary education. Persistent disadvantages in cognitive functioning among rural adults compared with sociodemographically similar urban peers highlight the importance of public health planning for more rapidly aging rural communities.
Keywords: Cognitive Ability; Dementia; Religion; Rural Settings; urban life

Selected Health Implications of Low Body Mass: Determinants and Health Outcomes - Holcombe,Andrea L. (Epidemiology, 2018)
While the role of obesity in health outcomes has been well described, the role of low body mass index (BMI), body weight relative to height, has largely been ignored. Those with low BMI are commonly excluded completely or combined with the normal BMI category in BMI studies. However, there have been some studies indicating poorer health outcomes among those with lower BMI, particularly that of increased risk of mortality. The purpose of this study is to explore the role of low BMI throughout the lifespan. Data from the Health and Retirement Study was used to evaluate 1) the association between childhood health and socioeconomic status (SES) exposures and low BMI in midlife adulthood, 2) the association between low BMI and health related outcomes in midlife adulthood (ages 50 to 65), and 3) the association between low BMI in midlife and health related outcomes, including mortality, over a longer follow-up (maximum of 20 years). To increase sample size, two low BMI definitions were used: the traditional <18.5 definition and a definition of ≤20 based on the J-shaped curves found in BMI mortality studies. Few significant results were found. Low BMI status was consistently associated with older age and female gender as well as current smoking status. Childhood exposure of respiratory disease and greater SES disadvantages was more common among those with low BMI in adulthood. In midlife adulthood, low BMI status was associated with increased difficulties with activities of daily living with either definition of low BMI. Increased risk of fracture was associated with a low BMI definition of <18.5. Increased risk of lung disease and decreased risk of high blood pressure was associated with a low BMI definition of ≤20. An analysis of those 30 years old or older found low BMI to be associated with increased risk of mortality and decreased risk of diabetes regardless of low BMI definition. When low BMI was defined as <18.5, those with low BMI were also more likely to experience difficulty with one or more activities of daily living. When low BMI was defined as ≤20, low BMI status was associated with greater risk of lung disease and decreased risk of high blood pressure. Further research is needed to fully characterize the role of low BMI on health outcomes as well as the role of SES on low BMI. Additionally, there is a need for greater understanding of the potential biological mechanisms of low BMI for health outcomes. Currently, there are few studies evaluating health outcomes and SES of low BMI. Limiting studies to the extreme upper end of the BMI spectrum limits the overall understanding of the role of BMI in health and may overlook unique characteristics and challenges those with low BMI may face.
Copyright - Database copyright ProQuest LLC; ProQuest does not claim copyright in the individual underlying works; Last updated - 2019-03-04
Keywords: 0573:Public health; BMI; Health and environmental sciences; HRS; Life-course; Public Health; Underweight

Self-employment in later life: Implications for financial, physical, and mental well-being - Cal J. Halvorsen (Social Work, 2018)
More than one in five working Americans aged 50 and older are self-employed, yet scholarship that examines the relationships between self-employment and personal health and financial well-being is limited. Using data from six biennial waves of the Health and Retirement Study, a nationally-representative panel study of Americans past 50 years of age, this quasi-experimental dissertation documents the characteristics of self-employed older adults in comparison to wage-and-salary workers, as well as compares self-employed and wage-and-salary workers in later life on a set of financial well-being and personal health outcomes. This study incorporates inverse probability of treatment weighting (also referred to as propensity score weighting) to control for selection into the “treatment” of concern, self-employment. Among older Americans, this dissertation revealed that age, being male, reporting better health, and having higher levels of risk tolerance were predictive of self-employment, among other factors. Further, it found strong evidence that self-employment leads to reduced earnings from work, with some evidence that it increases health and wealth. This dissertation builds upon previous work while contributing to discussions about the causal effects of later-life self-employment, as well as program and policy developments to support longer working lives.
Keywords: Employment and Labor Force; Self-employment; Well-being

Self-perceptions of aging mediate the longitudinal relationship of hopelessness and depressive symptoms. - Amber M Gum; Liat Ayalon (International Journal of Geriatric Psychiatry, 2018)
OBJECTIVES: The purpose of the current study was to examine the hypothesis that the prospective relationship between hopelessness and depressive symptoms is mediated by self-perceptions of aging. METHODS: Data from 3 waves of the US Health and Retirement Study (2008, 2012, and 2014) were used (N = 4606; age M = 65.3, 55.5% female). In mediation analyses, hopelessness in 2008 was the independent variable, self-perceptions of aging in 2012 were the mediator, and depressive symptoms in 2014 were the outcome variable. RESULTS: After controlling for covariates, hopelessness in 2008 was an independent predictor of self-perceptions of aging in 2012 (β = -.10, P < .001), and self-perceptions of aging in 2012 was an independent predictor of depressive symptoms in 2014 (β = -.41, P < .001). Hopelessness in 2008 showed both direct (β = .09, P < .001) and indirect (β = .03, P < .001) effects on depressive symptoms in 2014, indicating partial mediation by change in self-perceptions of aging. CONCLUSIONS: As hypothesized, change in self-perceptions of aging partially mediated the relationship of hopelessness with depressive symptoms 6 years later. Findings are consistent with a conceptualization of hopelessness as broad negative expectations about the future that may contribute to negative self-perceptions of aging and subsequent changes in depressive symptoms. Reducing hopelessness, increasing hope, and improving self-perceptions of aging have potential to reduce and prevent depressive symptoms for older adults. Future research should examine the mechanisms of these interrelationships and other aging outcomes.
Keywords: Depressive symptoms; Health Conditions and Status; Optimism; Self-reported health

Self-reported personality traits are prospectively associated with proxy-reported behavioral and psychological symptoms of dementia at the end of life. - Angelina R Sutin; Yannick Stephan; Martina Luchetti; Antonio Terracciano (International Journal of Geriatric Psychiatry, 2018)
OBJECTIVE: Behavioral and psychological symptoms of dementia (BPSD) are among the most challenging aspects of Alzheimer disease for patients and their families. Previous studies have found associations between informant-reported retrospective personality and BPSD; we test whether prospective, self-reported personality predicts who will experience these symptoms. METHODS: Deceased participants from the Health and Retirement Study who had evidence of cognitive impairment at the end of life (N = 1988) were selected to examine whether self-reported five-factor model personality traits, measured up to 8 years before death, were associated with proxy-reported BPSD. RESULTS: Neuroticism was associated with increased risk of the 7 BPSD: got lost in familiar places, wandered off, were not able to be left alone, experienced hallucinations, suffered from depression, had periodic confusion, and an uncontrolled temper. These associations were not moderated by age, gender, race, or education. Conscientiousness was associated with fewer symptoms overall and especially with lower risk of getting lost in familiar places and not being able to be left alone. CONCLUSIONS: The present research indicates that self-reported personality, particularly Neuroticism, is associated prospectively with risk for a wide range of behavioral symptoms for individuals who had cognitive impairment at the end of life. The use of self-reported personality traits can help aid in identifying who is most at risk for behavioral symptoms. Such information may be useful for nonpharmacological interventions tailored to the individual's personality to reduce the prevalence and burden of these BPSD.
Keywords: Cognitive Ability; Dementia; Personality; Self-reported health

Self–Employment, Wealth and Start–up Costs: Evidence from a Financial Crisis - Koffi Elitcha; Raquel Fonseca (The B.E. Journal of Economic Analysis & Policy, 2018)
Using individual-level data from three uniquely comparable surveys (Survey of Health, Ageing and Retirement in Europe, English Longitudinal Study of Ageing and Health and Retirement Study) in Europe and the United States, as well as the World Bank's Doing Business data, this paper empirically zeroes in on the impact of start-up costs on the self-employment-wealth relationship. The longitudinal nature of the data enables us to investigate the potential effects of the last global financial crisis. Results confirm the strong positive relationship between the entrepreneurial choice and wealth as well as the negative effect that stems from the increase in start-up costs. Interestingly, although there is no strong evidence that wealth in itself played a bigger role during the crisis, we find that the negative impact of start-up costs on the entrepreneurship-wealth relationship proved to be significantly pronounced during the last crisis.
Keywords: Entrepeneurship; Household; Longitudinal data; Self-employment

Semi-parametric methods of handling missing data in mortal cohorts under non-ignorable missingness. - Wen, Lan; Shaun R Seaman (Biometrics, 2018)
We propose semi-parametric methods to model cohort data where repeated outcomes may be missing due to death and non-ignorable dropout. Our focus is to obtain inference about the cohort composed of those who are still alive at any time point (partly conditional inference). We propose: i) an inverse probability weighted method that upweights observed subjects to represent subjects who are still alive but are not observed; ii) an outcome regression method that replaces missing outcomes of subjects who are alive with their conditional mean outcomes given past observed data; and iii) an augmented inverse probability method that combines the previous two methods and is double robust against model misspecification. These methods are described for both monotone and non-monotone missing data patterns, and are applied to a cohort of elderly adults from the Health and Retirement Study. Sensitivity analysis to departures from the assumption that missingness at some visit t is independent of the outcome at visit t given past observed data and time of death is used in the data application.
Keywords: Data collection; Datasets; Survey Methodology

Sense of Control, Job Stressors, and Well-Being: Inter-relations and Reciprocal Effects Among Older U.S. Workers - Liu, Mengqiao; McGonagle, Alyssa K.; Gwenith G Fisher (Work, Aging and Retirement, 2018)
The purpose of this study was to examine dynamic relations among job stressors, sense of control, and well-being among older working adults. Sense of control can be especially important among older adults given their potential vulnerability due to declining resources in health and work ability. Drawing on the conservation of resources (COR) theory, we examined relations between job stressors and sense of control as they relate to older workers' well-being, along with reciprocal relations between sense of control and both job and life satisfaction. Using 3 waves of survey data from 477 older working U.S. adults (age 51+) in the Health and Retirement Study, we examined cross-lagged model results and found reciprocal relations between sense of control and both job and life satisfaction. Results highlight the key role of sense of control in maintaining well-being among older workers. These findings resonate with COR, suggesting that sense of control both affects and is affected by individuals' well-being. Our study sheds light on dynamic processes involving job stressors, sense of control, and well-being and underscores the importance of promoting sense of control for older working adults.
Keywords: Depressive symptoms; Health Conditions and Status; Life Satisfaction; Stress; Well-being

Sensitization or inoculation: Investigating the effects of early adversity on the development of personality traits and stress experiences in adulthood. - Luo, Jing (Psychology, 2018)
Cumulative evidence has been found for the concurrent and longitudinal associations between personality traits and stress experiences in adulthood. However, less is known about the etiology underlying these associations. The present study tested the effects of early adversity on the development of personality traits and stress experiences in adulthood, as well as their concurrent and longitudinal associations. Two samples of older adults from the Health and Retirement Study (HRS) and one sample of middle-aged adults from the Midlife in the United States Survey (MIDUS) were used. Across three studies, positive linear effects of early adversity were found on the level and changes in stress experiences in adulthood. The results also suggested significant linear effects of early adversity on the level of neuroticism across studies and the level of other personality traits in the middle-aged cohort. For the concurrent and longitudinal covariances between personality traits and stress experiences, some evidence was found for linear effects of early adversity in the middle-aged sample but not the older cohorts.
Keywords: Childhood; Inoculation; Personality; Sensitization; Stress

Six ways to protect yourself and your loved ones against elder fraud - Powell, Robert (USA Today, 2018)
Keywords: Editorial; Elder fraud; News

Smoking Cessation and Changes in Body Mass Index Among Middle Aged and Older Adults. - Sharma, Andy (J Appl Gerontol, 2018)
OBJECTIVE: This study contributes to the body of literature examining smoking cessation and body mass index (BMI) for adults aged 50 and older. METHOD: Utilizing the 2004 and 2010 waves of the RAND Health and Retirement Study, this analysis utilized Fixed Effects (FE) regression on a sample of 1,316 adults aged 50 and older. RESULTS: Older adults undergo a small change in BMI after a transition from smoking to nonsmoking during a 6-year period, and this occurs after accounting for individual-level unobserved heterogeneity. More specifically, men experience a BMI gain of 1.24 ( p< .01) and women experience a BMI gain of 1.58 ( p< .01). DISCUSSION: Gerontologists/health professionals can use these results to inform older adults about the potential for a small increase in BMI and, in the process, assuage any apprehensions about excessive weight gain. This insight may encourage a greater number of older adults to cease smoking.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Female; Humans; Male; Middle Aged; Models, Statistical; Smoking cessation; Weight Gain

Smoking, education and the ability to predict own survival probabilities - Bruno Arpino; Valeria Bordone; Sergei Scherbov (Advances in Life Course Research, 2018)
Subjective survival probabilities (SSPs) are a good predictor of mortality, go beyond the aggregate description of survival defined by life tables, and are important for individuals' decision-making in later life. However, despite the well-known mortality differentials by education as well as by characteristics such as smoking, little investigation has focused on SSPs by population sub-groups defined as a combination of these two characteristics. We use data on individuals aged 50-89 from the Health and Retirement Study (HRS) carried out in the USA between 2000 and 2012 (N = 23,895). Respondents were asked to assess the probability to survive to a given target age according to their age at the time of the survey. We assess how individuals' SSPs and estimated objective survival probabilities (OSPs) vary by education and smoking and calculate, for each respondent, the gap between them. Consistently with real mortality patterns, smokers report the lowest SSPs in each of the three considered education groups. When comparing SSPs and OSPs we find that all groups tend to underestimate survival. Within each education group, past smokers better predict their survival probability. Current smokers with low education show the highest probability to overestimate their survival. Smokers are aware of their lower life expectancy. Still, a considerable proportion of them overestimate their survival probabilities, independently of their level of education.
Keywords: Decision making; Education; Mortality; Probability; Smoking

Smoking, education and the ability to predict own survival probabilities - Bruno Arpino; Valeria Bordone; Sergei Scherbov (Advances in Life Course Research, 2018)
Abstract Subjective survival probabilities (SSPs) are a good predictor of mortality, go beyond the aggregate description of survival defined by life tables, and are important for individuals’ decision-making in later life. However, despite the well-known mortality differentials by education as well as by characteristics such as smoking, little investigation has focused on SSPs by population sub-groups defined as a combination of these two characteristics. We use data on individuals aged 50–89 from the Health and Retirement Study (HRS) carried out in the USA between 2000 and 2012 (N = 23,895). Respondents were asked to assess the probability to survive to a given target age according to their age at the time of the survey. We assess how individuals’ SSPs and estimated objective survival probabilities (OSPs) vary by education and smoking and calculate, for each respondent, the gap between them. Consistently with real mortality patterns, smokers report the lowest SSPs in each of the three considered education groups. When comparing SSPs and OSPs we find that all groups tend to underestimate survival. Within each education group, past smokers better predict their survival probability. Current smokers with low education show the highest probability to overestimate their survival. Smokers are aware of their lower life expectancy. Still, a considerable proportion of them overestimate their survival probabilities, independently of their level of education.
Keywords: Education; Life Expectancy; Smoking

Social and Genetic Pathways in Multigenerational Transmission of Educational Attainment - Hexuan Liu (American Sociological Review, 2018)
This study investigates the complex roles of the social environment and genes in the multigenerational transmission of educational attainment. Drawing on genome-wide data and educational attainment measures from the Framingham Heart Study (FHS) and the Health and Retirement Study (HRS), I conduct polygenic score analyses to examine genetic confounding in the estimation of parents’ and grandparents’ influences on their children’s and grandchildren’s educational attainment. I also examine social genetic effects (i.e., genetic effects that operate through the social environment) in the transmission of educational attainment across three generations. Two-generation analyses produce three important findings. First, about one-fifth of the parent-child association in education reflects genetic inheritance. Second, up to half of the association between parents’ polygenic scores and children’s education is mediated by parents’ education. Third, about one-third of the association between children’s polygenic scores and their educational attainment is attributable to parents’ genotypes and education. Three-generation analyses suggest that genetic confounding on the estimate of the direct effect of grandparents’ education on grandchildren’s education (net of parents’ education) may be inconsequential, and I find no evidence that grandparents’ genotypes significantly influence grandchildren’s education through non-biological pathways. The three-generation results are suggestive, and the results may change when different samples are used.
Keywords: Education; Genetics; Genome; Multigenerational

Social Exclusion and Switching Barriers in Medicare Part D Choices - Ko, Dong; Bae, Young; Han, Jayoung (Sustainability, 2018)
Previous studies have shown that Medicare beneficiaries do not tend to switch their prescription drug plans (Part D), even though they can greatly save on the money spent on drugs by switching plans. To explore this occurrence, the present study focused on the concept of social exclusion-one of the most important characteristics prevalent in the elderly. This study compared the impact of two types of social exclusion on the association between psychological cost and plan switching: active (or rejected) social exclusion and passive (or ignored) social exclusion. The study's aim was to examine the moderating effect of social exclusion on the relationship between the cost of switching and willingness to switch plan to build sustainable health care system. The Prescription Drug Study supplementary to the Health and Retirement Study (HRS) data were utilized for analysis by applying a Hierarchical Linear Model (HLM) (N = 1042). The findings suggest that active social exclusion moderates the relationship between the switching cost and willingness to switch plan. This study's findings will help policymakers better understand the elderly's decision-making process pertaining to plans and promote their informed plan decisions to build sustainable health care system.
Keywords: Healthcare; Medicare; Medicare Part D; Prescription Medication

Social exclusion factors influencing life satisfaction among older adults - Lee, Joonyup; John G. Cagle (Journal of Poverty and Social Justice, 2018)
This study aims to examine the relative impact of social exclusion factors on older adults' life satisfaction. This study conducted a cross-sectional analysis of psychosocial measures from the 2012 wave of the Health and Retirement Study (N=4,139). Results found that social exclusion factors indeed affect life satisfaction. Health had the strongest effect on life satisfaction. Good social relationships also positively affect life satisfaction. These findings call for considering multidimensionality of social exclusion in the future research. Researchers and practitioners could pay greater attention to social exclusion, ways to measure it, and its impact on life satisfaction through this study.
Keywords: Depressive symptoms; Life Satisfaction; Social capital; Social Support

Social integration and age-related decline in lung function. - Crittenden, Crista N.; Murphy, Michael L. M.; Cohen, Sheldon (Health Psychology, 2018)
We tested the hypothesis that social integration, measured as number of social roles, is associated with less age-related loss of lung function, an important marker of health and longevity. We also investigated possible psychological factors through which social integration might influence lung health. Methods: Data were analyzed from the Health and Retirement Study (ages 52-94, n = 4,224). Results and Conclusions: Each additional social role reported at baseline was associated with less of a decline in lung function between baseline and the ifollow-up assessment four years later. The association withstood controls for demographics, weight, and height and was mediated by more positive and less negative affect and lower rates of cigarette smoking and more physical activity. Roles were mostly substitutable, with both high (spouse, parent, friends, relatives) and low (employee, religious service attendee, volunteer, members of other groups) intimacy roles independently contributing to less age related decline in lung function.
Keywords: Lung Volume Measurements; Mortality; Population Health; Social Support

Social Networks over the Life Course: Continuity, Context, and Consequences - Jasmine A Manalel (Psychology, 2018)
Social relations have far-reaching influences on health and well-being across the lifespan. Social networks refer to the constellation of different interpersonal relationships that individuals maintain through their lives. Considering life course perspectives has illuminated the ways in which social networks develop and influence health and well-being at different life stages. The aim of this dissertation is to examine the multidimensionality, continuity, and consequences of social networks for well-being. The tenets of the convoy model are used as a guiding framework in conjunction with lifespan developmental perspectives to capture the unique challenges and circumstances of each developmental period examined. Most studies of children’s social relations focus on specific relationships, despite robust evidence that children’s social networks are comprised of a diverse range of social partners. The first study identified patterns of social relations among a regionally representative sample of children aged 7 to 14 (N=203), and investigated distinguishing sociodemographic factors between them. Further, links to childhood depressive symptomology were examined. Three typologies were identified: Varied Family (55%), Close Family (22.5%), and Friend and Family (22.5%). Whites were more likely to be in the Friend and Family networks. There were no other sociodemographic differences between typologies. Additionally, membership in the Friend and Family typology was associated with greater depressive symptomology, but this link was not observed after accounting for significant life events. The findings highlight the importance of family-centric networks in childhood. Previous studies document differences in social networks across the lifespan, but longitudinal studies of intraindividual change in social networks are limited. The second study investigated continuity in social networks from childhood to adulthood using three waves of longitudinal data spanning 23 years. Results of growth curve analyses indicated that the majority of social network characteristics changed. Four patterns of social networks were identified in early adulthood (Mage=23): Diverse Distal, Varied Family, Close Family, and Friend-Focused. Descriptive data on transitions between social network patterns from childhood to adulthood suggest that most respondents experienced an expansion and diversification of social networks. This study demonstrated that changes in social networks from childhood to adulthood are consistent with the developmental goals of the transition to adulthood. The third study focused on older adults’ social networks and loneliness. Given the prominence of activity engagement in models of successful and active aging, the broader social integration derived from activity engagement was expected to protect against loneliness. The purpose of this study was to identify activity engagement patterns, and use these patterns to disentangle links between activity engagement, social network characteristics, and loneliness. Three classes of activity engagement were identified in a sample from the Health and Retirement Study (N=7,731): Restricted Activities (24%), Average Activities (46%), and Diverse Activities (30%). Activity engagement had direct and moderating effects on loneliness. Specifically, diverse activity engagement buffered the negative effects of having few close ties with children. These findings suggest that social integration through activity engagement may compensate for inadequate social networks. Taken together, these findings underscore the importance of studying social networks with a consideration for the developmental context in which they are formed, evolve, and exert influences on well-being. Using innovative pattern-centered approaches, these studies illuminate alternative ways of conceptualizing and measuring social networks. Findings from this dissertation provide insight into how social networks can be most effectively leveraged to promote successful development and aging.
Copyright - Database copyright ProQuest LLC; ProQuest does not claim copyright in the individual underlying works; Last updated - 2018-08-19
Keywords: 0451:Social psychology; Lifespan; Psychology; Social psychology; Social relations

Social Relationships and Obesity in Later Life - Jane Tavares (Gerontology, 2018)
The majority of U.S. older adults are overweight or obese. Social relationships are a key factor linked to obesity among younger age groups, but there are no known investigations of this association among older adults. This study examined the association between quantitative and qualitative indicators of social relationships and obesity among middle-aged and older adults. Further, this study investigated psychosocial and health behavior variables as mediators and moderators of the association between social relationships and obesity as well as explored demographic differences in this relationship. Using the 2004, 2006, and 2010 waves of the Health and Retirement Study, a series of ordinary least squared (OLS) regression models were used to examine the hypothesized association between social relationships and obesity both cross-sectionally and longitudinally. Psychosocial and health behaviors variables were sequentially added into the OLS regression models to explore the potential mediation of these variables and interaction terms were utilized to estimate their moderation effects. The sample was stratified by age, gender, and race to investigate demographic differences in the cross-sectional and longitudinal regression model analyses. In summary, the analyses showed that only qualitative indicators of social relationships were significantly related to obesity for the full sample. Specifically, results indicated that higher positive social support and lower negative social support were associated with lower waist circumference cross-sectionally and longitudinally. Daily exercise was observed to be a full mediator of these associations and anxiety was a partial mediator; both variables also acted as moderators. Longitudinal analyses also revealed that higher positive support and lower negative support were associated with decreased self-reported BMI from 2004 to 2010. In the stratified analyses, higher loneliness was associated with lower waist circumference for those 65 and older compared to middle-aged adults and higher social participation and weekly contact with friends were associated with lower waist circumference for non-Hispanic blacks compared to non-Hispanic whites. There were generally no other significant demographic differences. Findings from this study highlight several conceptual, programmatic, and policy implications and recommendations based upon these findings are presented. Healthcare providers are encouraged to inquire about older adults’ levels of social support and loneliness in order to achieve a more comprehensive assessment of wellness. Service providers and policymakers are encouraged to develop and fund programs that provide widespread and ample opportunities for older adults to engage socially, particularly those that incorporate or encourage physical activity and healthy eating.
Copyright - Database copyright ProQuest LLC; ProQuest does not claim copyright in the individual underlying works; Last updated - 2018-07-04
Keywords: 0384:Behavioral psychology; 0451:Social psychology; 0493:Aging; Aging; Behavioral psychology; Health and environmental sciences; Obesity; Psychology; Social psychology; Social Relationships; Social structural location; Social Support; Weight Change

Socioeconomic status, non-communicable disease risk factors, and walking speed in older adults: multi-cohort population based study - Stringhini, Silvia; Carmeli, Cristian; Markus Jokela; Mauricio Avendano; McCrory, Cathal; d’Errico, Angelo; Bochud, Murielle; Barros, Henrique; Costa, Giuseppe; Chadeau-Hyam, Marc; Delpierre, Cyrille; Gandini, Martina; et al. (BMJ, 2018)
Objective To assess the association of low socioeconomic status and risk factors for non-communicable diseases (diabetes, high alcohol intake, high blood pressure, obesity, physical inactivity, smoking) with loss of physical functioning at older ages. Design Multi-cohort population based study. Setting 37 cohort studies from 24 countries in Europe, the United States, Latin America, Africa, and Asia, 1990-2017. Participants 109 107 men and women aged 45-90 years. Main outcome measure Physical functioning assessed using the walking speed test, a valid index of overall functional capacity. Years of functioning lost was computed as a metric to quantify the difference in walking speed between those exposed and unexposed to low socioeconomic status and risk factors. Results According to mixed model estimations, men aged 60 and of low socioeconomic status had the same walking speed as men aged 66.6 of high socioeconomic status (years of functioning lost 6.6 years, 95% confidence interval 5.0 to 9.4). The years of functioning lost for women were 4.6 (3.6 to 6.2). In men and women, respectively, 5.7 (4.4 to 8.1) and 5.4 (4.3 to 7.3) years of functioning were lost by age 60 due to insufficient physical activity, 5.1 (3.9 to 7.0) and 7.5 (6.1 to 9.5) due to obesity, 2.3 (1.6 to 3.4) and 3.0 (2.3 to 4.0) due to hypertension, 5.6 (4.2 to 8.0) and 6.3 (4.9 to 8.4) due to diabetes, and 3.0 (2.2 to 4.3) and 0.7 (0.1 to 1.5) due to tobacco use. In analyses restricted to high income countries, the number of years of functioning lost attributable to low socioeconomic status by age 60 was 8.0 (5.7 to 13.1) for men and 5.4 (4.0 to 8.0) for women, whereas in low and middle income countries it was 2.6 (0.2 to 6.8) for men and 2.7 (1.0 to 5.5) for women. Within high income countries, the number of years of functioning lost attributable to low socioeconomic status by age 60 was greater in the United States than in Europe. Physical functioning continued to decline as a function of unfavourable risk factors between ages 60 and 85. Years of functioning lost were greater than years of life lost due to low socioeconomic status and non-communicable disease risk factors. Conclusions The independent association between socioeconomic status and physical functioning in old age is comparable in strength and consistency with those for established non-communicable disease risk factors. The results of this study suggest that tackling all these risk factors might substantially increase life years spent in good physical functioning.
Keywords: Cross-National; Gait speed; Risk Factors; Socioeconomic factors

The Sociogenomics of Polygenic Scores of Reproductive Behavior and Their Relationship to Other Fertility Traits - Melinda C Mills; Nicola Barban; Felix C Tropf (RSF: The Russell Sage Foundation Journal of the Social Sciences, 2018)
Human reproductive behavior until relatively recently has been explained exclusively via individual and social characteristics. This article applies results from a recent Genome-Wide Association Study that combined sixty-two data sources to isolate twelve genetic loci associated with reproductive behavior. We create polygenic scores that allow us to include a summary variable of genetic factors into our statistical models. We use four datasets: the U.S. Health and Retirement Study, Dutch LifeLines, TwinsUK and the Swedish Twin register. First, we provide a brief overview of the dominant explanations of reproductive behavior. Second, we test the predictive power of polygenic scores. Third, we interrogate the robustness of our models using a series of sensitivity analyses to take into account possible confounders due to population stratification and selection.
Keywords: Education; Fertility; Genetics; GWAS; PGS

Spending Patterns in Retirement: Retirees are Slow to Exhaust their Assets (Fast Facts, 2018)
The analysis examines spending patterns of retirees with low pre-retirement non-housing assets (less than $200,000), moderate pre-retirement non-housing assets (between $200,000 and $500,000), and substantial preretirement non-housing assets (at least $500,000).
Keywords: Retirement Planning and Satisfaction; Spending; Wealth management

Spotting Alzheimer’s Early Could Save America $7.9 Trillion - Levingston, Ivan (Bloomberg, 2018)
Keywords: Alzheimer's disease; Dementia; News

Spousal concordance in telomere length: New evidence from older adults in the US. - Jason M. Fletcher (PLoS One, 2018)
Telomere length (TL) has been associated with a range of aging outcomes as well as mortality. Recent research has shown both high heritability (~70%) of TL as well as moderate spousal similarity (r~0.3) using European datasets. This paper explores the level of spousal concordance in telomere length in the Health and Retirement Study, a national sample of adults in the US. The results show that the spousal correlations are lower (r~0.11). Regression-based associations in TL in the US are low (beta~0.08) and also vary by the number of times respondents have been married, where spouses married a single time have higher associations in TL (beta~.12) than spouses married more once (beta~0.03). I also find variation in spousal TL association levels based on husband's education level. These findings suggest the possibility of both assortative mating patterns related to telomere length as well as likelihood of shared environmental factors that cause TL similarity in people who are socially connected.
Keywords: Biomarkers; Couples; Marriage; Telomeres

State-level estimation of diabetes and prediabetes prevalence: Combining national and local survey data and clinical data. - David A Marker; Mardon, Russ; Jenkins, Frank; Campione, Joanne; Nooney, Jennifer; Li, Jane; Saydeh, Sharon; Zhang, Xuanping; Shrestha, Sundar; Deborah B. Rolka (Statistics in Medicine, 2018)
Many statisticians and policy researchers are interested in using data generated through the normal delivery of health care services, rather than carefully designed and implemented population-representative surveys, to estimate disease prevalence. These larger databases allow for the estimation of smaller geographies, for example, states, at potentially lower expense. However, these health care records frequently do not cover all of the population of interest and may not collect some covariates that are important for accurate estimation. In a recent paper, the authors have described how to adjust for the incomplete coverage of administrative claims data and electronic health records at the state or local level. This article illustrates how to adjust and combine multiple data sets, namely, national surveys, state-level surveys, claims data, and electronic health record data, to improve estimates of diabetes and prediabetes prevalence, along with the estimates of the method's accuracy. We demonstrate and validate the method using data from three jurisdictions (Alabama, California, and New York City). This method can be applied more generally to other areas and other data sources.
Keywords: Bias; California; Diabetes Mellitus; Electronic Health Records; Health Surveys; Humans; Insurance Claim Review; New York City; Nutrition Surveys; Prediabetic State; Prevalence; Statistics as Topic; United States

Step-grandparenthood in the United States. - Jenjira J Yahirun; Sung S Park; Judith A Seltzer (Journals of Gerontology Series B: Psychological Sciences & Social Sciences, 2018)
Objectives: This study provides new information about the demography of step-grandparenthood in the United States. Specifically, we examine the prevalence of step-grandparenthood across birth cohorts and for socioeconomic and racial/ethnic groups. We also examine lifetime exposure to the step-grandparent role. Methods: Using data from the Panel Study of Income Dynamics and the Health and Retirement Study, we use percentages to provide first estimates of step-grandparenthood and to describe demographic and socioeconomic variation in who is a step-grandparent. We use life tables to estimate the exposure to step-grandparenthood. Results: The share of step-grandparents is increasing across birth cohorts. However, individuals without a college education and non-Whites are more likely to become step-grandparents. Exposure to the step-grandparent role accounts for approximately 15% of total grandparent years at age 65 for women and men. Discussion: A growing body of research finds that grandparents are increasingly instrumental in the lives of younger generations. However, the majority of this work assumes that these ties are biological, with little attention paid to the role of family complexity across three generations. Understanding the demographics of step-grandparenthood sheds light on the family experiences of an overlooked, but growing segment of the older adult population in the United States.
Keywords: Adult children; Family Roles/Relationships; Grandparents

Structural racism in the workplace: Does perception matter for health inequalities? - Courtney L McCluney; Lauren L Schmitz; Margaret T Hicken; Amanda Sonnega (Social Science & Medicine, 2018)
Structural racism has been linked to racial health inequalities and may operate through an unequal labor market that results in inequalities in psychosocial workplace environments (PWE). Experiences of the PWE may be a critical but understudied source of racial health disparities as most adults spend a large portion of their lives in the workplace, and work-related stress affects health outcomes. Further, it is not clear if the objective characteristics of the workplace are important for health inequalities or if these inequalities are driven by the perception of the workplace. Using data from the 2008 to 2012 waves of the Health and Retirement Study (HRS), a probability-based sample of US adults 50 years of age and older and the Department of Labor's Occupational Information Network (O*NET), we examine the role of both standardized, objective (O*NET) and survey-based, subjective (as in HRS) measures of PWEs on health and Black-White health inequalities. We find that Blacks experience more stressful PWEs and have poorer health as measured by self-rated health, episodic memory function, and mean arterial pressure. Mediation analyses suggest that these objective O*NET ratings, but not the subjective perceptions, partially explain the relationship between race and health. We discuss these results within the extant literature on workplace and health and health inequalities. Furthermore, we discuss the use of standardized objective measures of the PWE to capture racial inequalities in workplace environment.
Keywords: Health Disparities; Racial/ethnic differences; Racism

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Gail Davies; Lam, Max; Sarah E Harris; Joey W Trampush; Luciano, Michelle; W David Hill; Hagenaars, Saskia P; Ritchie, Stuart J; Riccardo E Marioni; Fawns-Ritchie, Chloe; David C Liewald; Okely, Judith A; et al. (Nature Communications, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cognition; Genetic Loci; Genetic Predisposition to Disease; Humans; Mental Disorders; Middle Aged; Multifactorial Inheritance; Neurodegenerative Diseases; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Reaction Time; Young Adult

Subjective Age and Mortality in Three Longitudinal Samples. - Yannick Stephan; Angelina R Sutin; Antonio Terracciano (Psychosomatic Medicine, 2018)
OBJECTIVE: Subjective age has been implicated in a range of health outcomes. The present study extends existing research by providing new data on the relation between subjective age and mortality in three large national samples. METHODS: Participants (total N > 17,000) were drawn from the Health and Retirement Study (HRS, 2008-2014), the Midlife in the United State Survey (MIDUS, 1995-2014), and the National Health and Aging Trends Study (NHATS, 2011-2014). Subjective age, demographic factors, disease burden, functional limitations, depressive symptoms, and physical inactivity were assessed at baseline and mortality data were tracked for up to 20 years. Cognition was also included as a covariate in the HRS and the NHATS. RESULTS: Individuals felt on average 15% to 16% younger relative to their chronological age. Feeling approximately 8, 11, and 13 years older in the MIDUS, HRS, and NHATS, was related to an 18%, 29% and 25% higher risk of mortality, respectively. This pattern was confirmed by a meta-analysis of the three samples (HR = 1.24; 95%CI = 1.17-1.31, p<.001). Multivariate analyses showed that disease burden, physical inactivity, functional limitations, and cognitive problems, but not depressive symptoms, accounted for the associations between subjective age and mortality. CONCLUSIONS: The present study provides robust evidence for an association between an older subjective age and a higher risk of mortality across adulthood. These findings support the role of subjective age as a biopsychosocial marker of aging.
Keywords: Mortality; Subjective age; Subjective Expectations

Is subjective memory change in old age based on accurate monitoring of age-related memory change? Evidence from two longitudinal studies. - Hertzog, Christopher; Hülür, Gizem; Denis Gerstorf; Ann Pearman (Psychology and Aging, 2018)
Subjective memory change (SMC) in adulthood involves the perception that one's memory has declined from earlier levels of function. SMC has been conjectured to be more accurate than concurrent subjective memory because people use themselves as a standard of comparison. We used data from two longitudinal studies to contrast the accurate-monitoring-of-change hypothesis-actual memory change predicts SMC-against a constructed-judgment hypothesis that rated SMC is a function of rescaling concurrent memory beliefs without accessing actual memory change. It states that actual memory change has no predictive validity for SMC independent of concurrent memory beliefs. Data from both the Berlin Aging Study and the Health and Retirement Study (HRS) showed that older adults' current memory complaints strongly predicted current SMC, and that there was little relationship of longitudinally measured memory change to SMC, controlling on memory complaints. In the HRS there were reliable latent-growth-curve slope correlations of over .20 for change in episodic memory with both slopes of change in SMC and in memory complaints, yet little relationship of SMC slopes to episodic memory slopes, controlling on memory-complaint slopes. The results falsify the accurate-monitoring-of-change hypothesis regarding the origins of SMC in older adults.
Keywords: Memory; Self Report; Subjective Expectations

Subjective memory problems and availability of emotional support - Jung-Hwa Ha; Pai, Manacy (Research on Aging, 2018)
This study examines (1) whether subjective memory problems (SMP) influence perceived emotional support from and frequency of contact with family and friends; and, (2) the extent to which this relationship is moderated by gender, education, and functional limitations. We use the 2014 wave of the Health and Retirement Study, a nationally representative panel survey of adults aged 51 and over in the United States. While SMP does not affect perceived emotional support for younger group (YG; aged 51-64), in older group (OG; aged 65+), SMP is associated with reduced perceived support from friends. Also, SMP is predictive of fewer writing-based contact with children and friends among OG but not among YG. Lastly, we find that the effect of SMP on support from children is contingent upon activity of daily living (YG) and gender (OG), while the effect of SMP on writing-based contact with both children and friends is contingent upon education (YG only).
Keywords: Cognition & Reasoning; Depressive symptoms; Memory; Social Support

Subjective Social Status Predicts Late-Life Memory Trajectories through Both Mental and Physical Health Pathways - Laura B Zahodne; A Zarina Kraal; Afsara B. Zaheed; Sol, Ketlyne (Gerontology, 2018)
Background: Subjective social status (SSS) is associated with mental and physical health, independent of objective socioeconomic status (SES), but its association with late-life cognitive decline is unknown. Objective: This study characterizes the association between SSS and late-life memory trajectories in a large, nationally representative sample of older adults in the United States. Methods: Using data from 8,530 participants aged 65 years and older in the Health and Retirement Study, structural equation models tested associations between SSS, objective SES (i.e., educational attainment, occupation, income, and wealth), physical and mental health, and 6-year memory trajectories, controlling for sociodemographic characteristics. Results: Independent of objective SES, lower SSS was associated with worse initial memory but not subsequent memory decline. The association between SSS and initial memory was separately mediated by chronic diseases, stroke, and depressive symptoms. Conclusion: Results provide preliminary behavioral evidence for the deleterious effects of social stress on cognitive aging. These results may help inform the development of policies and interventions to reduce cognitive morbidity among older adults who perceive a low position on the social hierarchy.
Keywords: Cognitive Ability; Depressive symptoms; Health Conditions and Status; Late-life Health; Memory

The suddenly hot job market for workers over 50 - Halpert, Julie (CNBC, 2018)
Keywords: Employment and Labor Force; News

Survival Advantage Mechanism: Inflammation as a Mediator of Positive Self-Perceptions of Aging on Longevity. - Becca R Levy; Bavishi, Avni (J Gerontol B Psychol Sci Soc Sci, 2018)
OBJECTIVE: Previous studies have found that positive self-perceptions of aging (SPA) are associated with longer survival; however, a biological mechanism was unknown. We examined whether C-reactive protein (CRP), a marker of cumulative stress-related inflammation, mediates the relationship between SPA and survival. METHOD: The SPA of participants aged 50 and older in the Health and Retirement Study (N = 4,149) were assessed at baseline. Inflammation was measured by the level of CRP 4 years later. Survival was followed for up to 6 years. RESULTS: As hypothesized, CRP mediated the impact of SPA on survival. Following the steps of a mediation analysis, positive SPA at baseline predicted lower CRP after 4 years (β = -.29, p = .03) and longer survival in the 2 years following the CRP measurement (β = .20, p =.003); additionally, lower CRP predicted longer survival, after adjusting for positive SPA (β = -.02, p = .0001). All models adjusted for baseline age, CRP, health, sex, race, and education. DISCUSSION: It was found that lower CRP partially mediates the relationship between positive SPA and longer survival. Hence, this study presents a novel pathway to explain the process by which positive SPA extend longevity.
10.1093/geronb/gbw035
Keywords: Aged; Aged, 80 and over; Aging; Biomarkers; C-reactive protein; Female; Humans; Inflammation; Longevity; Male; Middle Aged; Self Concept; Surveys and Questionnaires; Survival Analysis

Systematic review of self-reported cognitive function in cancer patients following chemotherapy treatment - Bray, Victoria J.; Dhillon, Haryana M.; Vardy, Janette L. (Journal of Cancer Survivorship, 2018)
Cognitive symptoms are common in cancer patients, with up to 70% reporting cognitive symptoms following chemotherapy. These symptoms can have a major impact on how an individual functions in all aspects of their lives. This review evaluates self-reported cognitive function and its associations with neuropsychological tests and patient-reported outcomes in adult cancer patients who received chemotherapy treatment for a solid cancer.
Keywords: Cancer; Chemotherapy

Sample Sizes and Response Rates - HRS Staff (Survey Research Center, Institute for Social Research, University of Michigan, 2017)

Saving and wealth inequality - Mariacristina De Nardi; Fella, Giulio (Review of Economic Dynamics, 2017)
Why are some people wealth rich while others are poor? To what extent can governments affect inequality? Which instruments should they use? Answering these questions requires understanding why people save. Dynamic quantitative models of wealth inequality can help us to understand and quantify the determinants of the outcomes that we observe in the data and to evaluate the consequences of policy reform. This paper surveys the savings mechanisms generated by the transmission of bequests and human capital, by preference heterogeneity, by rate of return heterogeneity, by entrepreneurship, by richer earnings processes, and by medical expenses. It concludes that the transmission of bequests and human capital, entrepreneurship, and medical-expense risk are crucial determinants of savings and wealth inequality and that we need to look at more data to measure their relative importance.
Keywords: Consumption and Savings; Wealth Inequality

Self-perceptions of aging and perceived barriers to care: Reasons for health care delay - Jennifer K Sun; Jacqui Smith (The Gerontologist, 2017)
Abstract Background and Objectives: Self-perceptions of aging (SPA), or attitudes toward one’s aging experience, have been linked to health through multiple pathways. Few studies, however, have investigated how older adults’ views on aging influence their care-seeking behaviors. Research Design and Methods: Using two independent subsamples from the Health and Retirement Study (2011 Health Care Mail Survey: N = 2,866; 2013 Health Care and Nutrition Study: N = 2,474), logistic regression and negative binomial regression were used to examine the association between SPA and health care delay over the next 12 months. Subsequently, we used latent class analysis to identify subgroups reporting different reasons for delay. With multinomial logistic regression, we then examined if, compared with the no delay group, SPA differentiated membership in the delay subgroups. Results: In both samples, more negative aging self-perceptions were associated with a higher likelihood of health care delay and more perceived barriers to care, after adjusting for predisposing, enabling, and need factors. Latent class analysis revealed three subgroups characterized by different reasons for delay: (a) limited health care access, (b) too busy to go to the doctor, and (c) dislike of going to the doctor. In fully adjusted models, individuals with more negative SPA were more likely to belong to “limited-access” and “dislike” subgroups compared with the no delay group. Discussion and Implications: SPA may affect decision-making processes regarding whether to seek care for worrisome symptoms. Efforts to promote more positive SPA may encourage older adults to be more proactive in addressing their health care needs.
Keywords: Accessibility; Perception; Self-reported health

Senate (Special Committee on) Aging Committee Hearing (Senate (Special Committee on) Aging Committee, 2017)
Keywords: Government; Hearings; Public Policy

Seniors and Pets: Health Benefits and Challenges - Esposito, Lisa (U.S. News & World Report, 2017)
Keywords: Depressive symptoms; Loneliness; Pets

Sensory functioning and personality development among older adults. - Yannick Stephan; Angelina R Sutin; Bosselut, Grégoire; Antonio Terracciano (Psychology and Aging, 2017)
Deficits in sensory functioning, such as poor vision and hearing, take a significant toll on quality of life. Little is known, however, about their relation with personality development across adulthood. This study examined whether baseline and change in vision and hearing were associated with personality change over a 4-year period. Participants (N = 7,471; Mage = 66.89; 59% women) were drawn from the Health and Retirement Study. They provided data on vision, hearing, and personality both at baseline and 4 years later. Poor vision and hearing at baseline and declines in vision and hearing over time were independently related to steeper declines in extraversion, agreeableness, openness, and conscientiousness, and less decline in neuroticism, controlling for demographic factors, disease burden, and depressive symptoms. Sensory functioning was generally a stronger predictor of personality change than disease burden or depressive symptoms. Consistent with evidence that poor and worsening sensory functions compromise individuals' interactions with the social and physical environment, this study found deficits in hearing and vision were also associated with maladaptive personality trajectories in older adults.
Keywords: Older Adults; Personality

The shock of falling among older Americans - Kelly, Inas Rashad (The Journal of the Economics of Ageing, 2017)
Direct medical costs associated with falls have been shown to be $34 billion in 2013, an underestimate since full costs are not factored in. Using the 1998-2012 waves of the Health and Retirement Study and several econometric methods to address the endogeneity of falls, this study seeks to answer the question of how much worse physical and mental health outcomes are for individuals who fall compared to their steadier counterparts. Results across various specifications suggest that falling leads to lower activities of daily living, more depression, and more psychological problems. It leads to greater probabilities of being in poor health, having heart problems, and having a stroke. These results survive several robustness checks.
Keywords: Depressive symptoms; Falls; Health Conditions and Status; Health Shocks

The shock of falling among older Americans - Kelly, Inas Rashad (Working Paper Series, 2017)
Direct medical costs associated with falls have been shown to be $34 billion in 2013, an underestimate since full costs are not factored in. Using the 1998-2012 waves of the Health and Retirement Study and several econometric methods to address the endogeneity of falls, this study seeks to answer the question of how much worse physical and mental health outcomes are for individuals who fall compared to their steadier counterparts. Results across various specifications suggest that falling leads to lower activities of daily living, more depression, and more psychological problems. It leads to greater probabilities of being in poor health, having heart problems, and having a stroke. These results survive several robustness checks.
Keywords: Falls; Health Shocks

Single-trait and multi-trait genome-wide association analyses identify novel loci for blood pressure in African-ancestry populations. - Liang, Jingjing; Le, Thu H; Digna R Velez Edwards; Bamidele O Tayo; Gaulton, Kyle J; Smith, Jennifer A; Lu, Yingchang; Jensen, Richard A; Chen, Guanjie; Yanek, Lisa R; Schwander, Karen; Tajuddin, Salman M; et al. (PLoS Genetics, 2017)
Hypertension is a leading cause of global disease, mortality, and disability. While individuals of African descent suffer a disproportionate burden of hypertension and its complications, they have been underrepresented in genetic studies. To identify novel susceptibility loci for blood pressure and hypertension in people of African ancestry, we performed both single and multiple-trait genome-wide association analyses. We analyzed 21 genome-wide association studies comprised of 31,968 individuals of African ancestry, and validated our results with additional 54,395 individuals from multi-ethnic studies. These analyses identified nine loci with eleven independent variants which reached genome-wide significance (P < 1.25×10-8) for either systolic and diastolic blood pressure, hypertension, or for combined traits. Single-trait analyses identified two loci (TARID/TCF21 and LLPH/TMBIM4) and multiple-trait analyses identified one novel locus (FRMD3) for blood pressure. At these three loci, as well as at GRP20/CDH17, associated variants had alleles common only in African-ancestry populations. Functional annotation showed enrichment for genes expressed in immune and kidney cells, as well as in heart and vascular cells/tissues. Experiments driven by these findings and using angiotensin-II induced hypertension in mice showed altered kidney mRNA expression of six genes, suggesting their potential role in hypertension. Our study provides new evidence for genes related to hypertension susceptibility, and the need to study African-ancestry populations in order to identify biologic factors contributing to hypertension.
Keywords: African Americans; Animals; Basic Helix-Loop-Helix Transcription Factors; Blood pressure; Cadherins; Case-Control Studies; Female; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Male; Membrane Proteins; Mice; Multifactorial Inheritance; Polymorphism, Single Nucleotide

Smoking, Education and the Ability to Predict Own Survival Probabilities: An Observational Study on US Data - Bruno Arpino; Valeria Bordone; Sergei Scherbov (IIASA Working Paper, 2017)
Background: Subjective survival probabilities (SSPs) are a good predictor of mortality, go beyond the aggregate description of survival defined by life tables, and are important for individuals’ decision-making in later life. Despite the well-known mortality differentials by education as well as by characteristics such as smoking, little investigation has focused on SSPs by population sub-groups. Methods: We use data on individuals aged 50-89 from the Health and Retirement Study(HRS) carried out in the USA between 2000 and 2012 (N=23,895). Each respondent was asked to assess the probability to survive to a given target age according to their age at the time of the survey. We assess how individuals’ SSPs and estimated objective survival probabilities (OSPs) vary by education and smoking and calculate, for each respondent, the gap between them. Results: Consistently with real mortality patterns, smokers report the lowest SSPs, both among lower and higher educated people. When comparing SSPs and OSPs we find that, irrespectively of the smoking status, higher educated people are more likely to correctly predict their survival probabilities than their lower educated counterparts. Within both education groups, past smokers better predict their survival probability. Current smokers with low education show the highest probability to overestimate their survival probability. Conclusions: Lower educated people and smokers are aware of their lower life expectancy. Still, they overestimate their survival probabilities more than the higher educated and non-smokers. Our findings emphasize the need for policy makers to disseminate information about the risks of smoking, targeting people with lower education.
Keywords: Education; Life Expectancy; Smoking

Smoking Response to Health and Medical Spending Changes and the Role of Insurance. - Marti, Joachim; Michael R. Richards (Health Econ, 2017)
Severe health shocks provide new information about one's personal health and have been shown to influence smoking behaviors. In this paper, we suggest that they may also convey information about the hard to predict financial consequences of illnesses. Relevant financial risk information is idiosyncratic and unavailable to the consumer preceding illness, and the information search costs are high. However, new and salient information about the health as well as financial consequences of smoking after a health shock may impact smoking responses. Using variation in the timing of health shocks and two features of the US health care system (uninsured spells and aging into the Medicare program at 65), we test for heterogeneity in the post-shock smoking decision according to plausibly exogenous changes in financial risk exposure to medical spending. We also explore the relationship between smoking and the evolution of out-of-pocket costs. Individuals experiencing a cardiovascular health shock during an uninsured spell have more than twice the cessation effect of those receiving the illness while insured. For those uninsured prior to age 65 years, experiencing a cardiovascular shock post Medicare eligibility completely offsets the cessation effect. We also find that older adults' medical spending changes separate from health shocks influence their smoking behavior. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: Cardiovascular Diseases; Female; Health Behavior; Health Expenditures; Health Surveys; Humans; Insurance, Health; Male; Medically Uninsured; Medicare; Middle Aged; Risk Factors; Smoking; Socioeconomic factors; United States

Social Activities, Incident Cardiovascular Disease, and Mortality. - Sae Hwang Han; Jane Tavares; Evans, Molly; Jane S Saczynski; Jeffrey A Burr (J Aging Health, 2017)
OBJECTIVE: This study examined the relationships between social activities, incident cardiovascular disease (CVD), and non-CVD mortality among older adults in the United States. METHOD: Data from the Health and Retirement Study (2006-2010) were employed. Two measures of social engagement, volunteering and informal helping, along with two measures of social participation, attendance at religious services and social group meetings, were included. Mediation models for health behaviors were estimated. RESULTS: Multinomial logistic regression models demonstrated that volunteering provided the most consistent results in terms of a lower risk of incident CVD and mortality. Furthermore, volunteering at higher time commitments is related to lower CVD incidence and death; informally helping others at a modest time commitment is related to lower risk of death only. Health behaviors mediated the relationships. Social participation was not related to either CVD or mortality. DISCUSSION: Social activity is a modifiable behavior that may be considered a potential health intervention.
Keywords: Aged; Aged, 80 and over; Cardiovascular Diseases; Female; Humans; Incidence; Leisure activities; Logistic Models; Male; Middle Aged; Retirement; United States

Social Capital and Unretirement: Exploring the Bonding, Bridging, and Linking Aspects of Social Relationships. - Guillermo Ernest Gonzales; Nowell, William Benjamin (Res Aging, 2017)
Working longer is an important area of research given extended life expectancy, shortfalls of retirement income, desires to remain socially engaged, and solvency concerns of social insurance programs. The purpose of this longitudinal population-based study of older adults is to examine how different types of social resources (social bonding, bridging, and linking) relate to returning to work after retirement. Data were drawn from the Health and Retirement Study of fully retired older adults aged 62+ in 1998 ( N = 8,334) and followed to 2008. After controlling for a comprehensive set of fixed and time-varying covariates, findings suggest that social bridging (informal volunteering) and social linking (formal volunteering, partnered with an employed spouse) were strongly and positively related to returning to work (Hazard Ratio [HR]: 1.49, p < .001; HR: 1.58, p < .0001; and HR: 1.75, p < .0001, respectively). Social bonding resources were not significantly associated with returning to work. Implications for social policy are discussed.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cross-Sectional Studies; Employment; Female; Humans; Longitudinal Studies; Male; Middle Aged; Retirement; Social capital; United States

Social connectedness, perceived isolation, and dementia: Does the social environment moderate the relationship between genetic risk and cognitive well-being? - Judith L Poey; Jeffrey A Burr; J Scott Roberts (Gerontologist, 2017)
Purpose of the Study: This study examined whether the social environment moderates the relationship between the APOE e4 allele and cognitive functioning. Design and Methods: The Aging, Demographics, and Memory Study (ADAMS) data and multinomial logistic regression models were used to investigate these relationships for a nationally representative sample of U.S. adults aged 70 and older (n = 779). Results: Living alone (relative risk ratio [RRR] = 5.814; p = .000) and self-reported loneliness (RRR = 1.928, p = .049) were associated with a greater risk of cognitive difficulty. Living arrangements, perceived social support, and loneliness were found to moderate the relationship between the APOE e4 allele and cognitive function. Implications: The results support the need to consider the social context when examining cognitive well-being in later life. These findings also indicate a need for the development of policies and services that promote a rich social environment.
Keywords: Cognitive Ability; Dementia; Depressive symptoms; Genetics; Isolation; Older Adults; Social Support

Social determinants, multimorbidity, and patterns of end-of-life care in older adults dying from cancer. - Siran M Koroukian; Nicholas K Schiltz; David F Warner; Charles W Given; Mark Schluchter; Owusu, Cynthia; Nathan A. Berger (J Geriatr Oncol, 2017)
OBJECTIVE: Most prior studies on aggressive end-of-life care in older patients with cancer have accounted for social determinants of health (e.g., race, income, and education), but rarely for multimoribidity (MM). In this study, we examine the association between end-of-life care and each of the social determinants of health and MM, hypothesizing that higher MM is associated with less aggressive care. METHODS: From the linked 1991-2008 Health and Retirement Study, Medicare data, and the National Death Index, we identified fee-for-service patients age ≥66years who died from cancer (n=835). MM was defined as the occurrence or co-occurrence of chronic conditions, functional limitations, and/or geriatric syndromes. Aggressive care was based on claims-derived measures of receipt of cancer-directed treatment in the last two weeks of life; admission to the hospital and/or emergency department (ED) within the last month; and in-hospital death. We also identified patients enrolled in hospice. In multivariable logistic regression models, we analyzed the associations of interest, adjusting for potential confounders. RESULTS: While 61.2% of the patients enrolled in hospice, 24.6% underwent cancer-directed treatment; 55.1% were admitted to the hospital and/or ED; and 21.7% died in the hospital. We observed a U-shaped distribution between income and in-hospital death. Chronic conditions and geriatric syndromes were associated with some outcomes, but not with others. CONCLUSIONS: To improve quality end-of-life care and curtail costs incurred by dying patients, relevant interventions need to account for social determinants of health and MM in a nuanced fashion.
Keywords: Age Factors; Aged; Aged, 80 and over; Emergency Service, Hospital; Female; Health Surveys; Hospices; Hospital Mortality; Humans; Logistic Models; Male; multimorbidity; Neoplasms; Population Surveillance; Quality of Health Care; Risk Factors; Socioeconomic factors; Terminal Care

Social Inequalities in Inflammation: Age Variations in Older Persons. - Uchechi A Mitchell; Carol S Aneshensel (J Aging Health, 2017)
OBJECTIVE: Systemic inflammation is an important risk factor for cardiovascular diseases and inequalities by race/ethnicity, gender, and education have been documented. However, there is incomplete knowledge as to how these disparities present across age, especially in late life. This study assesses whether differences in C-reactive protein (CRP), a marker of inflammation, are contingent on age among older persons. METHOD: Data are from the 2006/2008 Health and Retirement Study ( n = 10,974) biomarker assessment. CRP was regressed on interactions between age and other status characteristics. RESULTS: Racial/ethnic differences in inflammation do not vary significantly by age. However, gender and education differences are greatest at younger ages and then narrow steadily with increasing age. DISCUSSION: There is considerable heterogeneity in how disparities in inflammation present across age and characteristics such as race/ethnicity, gender, and education. Understanding status differences in the influence of age on factors affecting late-life health is useful for health disparities research.
Keywords: Age Factors; Aged; Aged, 80 and over; Biomarkers; C-reactive protein; Female; Health Status Disparities; Humans; Inflammation; Male; Middle Aged; Racial Groups; Self Report; Socioeconomic factors

Social Isolation and Medicare Spending: Among Older Adults, Objective Isolation Increases Expenditures While Loneliness Does Not - Jonathan G Shaw; Farid, Monica; Claire Noël-Miller; Joseph, Neesha; Houser, Ari; Steven Asch; Bhattacharya, Jay; Flowers, Lynda (Journal of Aging and Health, 2017)
Objective: The purpose of this study was to evaluate the impact of objective isolation and loneliness on Medicare spending and outcomes. Method: We linked Health and Retirement Study data to Medicare claims to analyze objective isolation (scaled composite of social contacts and network) and loneliness (positive response to three-item loneliness scale) as predictors of subsequent Medicare spending. In multivariable regression adjusting for health and demographics, we determined marginal differences in Medicare expenditures. Secondary outcomes included spending by setting, and mortality. Results: Objective isolation predicts greater spending, US$1,644 (p <.001) per beneficiary annually, whereas loneliness predicts reduced spending, 'US$768 (p <.001). Increased spending concentrated in inpatient and nursing home (skilled nursing facilities [SNFs]) care; despite more health care, objectively isolated beneficiaries had 31% (p <.001) greater risk of death. Loneliness did not predict SNF use or mortality, but predicted slightly less inpatient and outpatient care. Discussion: Objectively isolated seniors have higher Medicare spending, driven by increased hospitalization and institutionalization, and face greater mortality. Policies supporting social connectedness could reap significant savings.
Keywords: Depressive symptoms; Isolation; Loneliness; Medicare expenditures; Medicare linkage; Medicare/Medicaid/Health Insurance; Social Support

Social Security and Total Replacement Rates in Disability and Retirement - Khan, Mashfiqur R.; Matthew S. Rutledge; Geoffrey T. Sanzenbacher (Working Papers, 2017)
Social Security provides higher replacement rates to disability insurance beneficiaries than retired beneficiaries. This fact reflects two factors: 1) Disability Insurance (SSDI) beneficiaries have lower career earnings, and Social Security benefits are progressive; and 2) SSDI benefits are not reduced for claiming early. This project uses the 1992-2010 waves of the Health and Retirement Study (HRS) linked to Social Security Administration earnings records to decompose the differences between the Social Security replacement rates for retired worker and SSDI beneficiaries into these two factors. The project also examines how the total replacement rate – which accounts for other sources of income in addition to Social Security – differs between retirees and SSDI beneficiaries to capture the difference in overall retirement security between the two groups. The results indicate that about half of the 10-percentage-point advantage in Social Security replacement rates for SSDI beneficiaries is due to the actuarial adjustment applied to retirement benefits, implying that career earnings are not that different between retired workers and SSDI beneficiaries. But total replacement rates are substantially lower for SSDI beneficiaries, which indicates that, despite Social Security’s vital role in providing a reliable income source, SSDI beneficiaries have much lower post-career well-being than retired workers.
Keywords: Consumption and Savings; Disabilities; Retirement Planning and Satisfaction; Social Security

Social Security Claiming and the Annuity Puzzle - Shepard, Mark (Harvard University, 2017)
Life cycle theory predicts that individuals facing uncertain mortality will annuitize all or most of their retirement wealth. Researchers seeking to explain why retirees rarely purchase annuities have focused on imperfections in commercial annuities – including actuarially unfair pricing, lack of bequest protection, and illiquidity in the case of risky events like medical shocks. I study the annuity choice implicit in the timing of Social Security claiming and show that none of these can explain why most retirees claim benefits as early as possible, effectively choosing the minimum annuity. Most early claimers in the Health and Retirement Study had sufficient liquidity to delay Social Security longer than they actually did and could have increased lifetime consumption by delaying. Because the marginal annuity obtained through delay is better than actuarially fair, standard bequest motives cannot explain the puzzle. Nor can the risk of out-of-pocket nursing home costs, since these are concentrated at older ages past the break-even point for delayed claiming. Social Security claiming patterns, therefore, add to the evidence that behavioral explanations may be needed to explain the annuity puzzle.
Keywords: Social Security

Social Security giveth, medical costs taketh away - Andrews, Michelle (Chicago Tribune, 2017)
Keywords: Medical Expenses; News; Social Security

Social support, social strain, and cognitive function among community-dwelling U.S. Chinese older adults. - Ge, Shaoqing; Bei Wu; Donald E. Bailey Jr.; Dong, XinQi (Journals of Gerontology Series A: Biological Sciences and Medical Sciences, 2017)
Background: Limited research is available on the relationship between social support, social strain, and cognitive function among community-dwelling U.S. Chinese older adults. This study aims to examine the associations between social support/strain and cognitive outcomes. Methods: Data were drawn from the Population-Based Study of Chinese Elderly (N = 3,159). Cognitive function was measured by a battery of tests including the East Boston Memory Test, the Digit Span Backwards assessment, and the Symbol Digit Modalities Test. Social support and strain were measured by the scales drawn from the Health and Retirement study. Multiple regression analyses were conducted. Results: Social support was significantly associated with global cognitive function (β = .11, SE = .02, p < .001), episodic memory (β = .11, SE = .03, p < .001), working memory (β = .18, SE = .08, p < .05), and executive function (β = 1.44, SE = .37, p < .001). Social strain was significantly associated with global cognitive function (β = .23, SE = .05, p < .001), episodic memory (β = .27, SE = .07, p < .001), working memory (β = .34, SE = .17, p < .05), and executive function (β = 2.75, SE = .85, p < .01). In terms of sources of social support/strain, higher support from friends was significantly associated with higher global cognitive function (β = .04, SE = .02, p < .05), higher episodic memory (β = .05, SE = .02, p < .05), and higher executive function (β = .71, SE = .29, p < .05). Higher strain from spouse was significantly associated with higher global cognitive function (β = .10, SE = .03, p < .01), higher episodic memory (β = .11, SE = .04, p < .01), and higher executive function (β = 1.28, SE = .49, p < .01). Higher strain from friends was significantly associated with higher executive function (β = 3.59, SE = 1.17, p < .01). Conclusions: Social support and strain were associated with cognitive outcomes. Future longitudinal studies should be conducted.
Keywords: Adult children; Cognitive Ability; Community-dwelling

Sociodemographic disparities in chronic pain, based on 12-year longitudinal data. - Grol-Prokopczyk, Hanna (Pain, 2017)
Existing estimates of sociodemographic disparities in chronic pain in the United States are based on cross-sectional data, often treat pain as a binary construct, and rarely test for nonresponse or other types of bias. This study uses 7 biennial waves of national data from the Health and Retirement Study (1998-2010; n = 19,776) to describe long-term pain disparities among older (age 51+) American adults. It also investigates whether pain severity, reporting heterogeneity, survey nonresponse, and/or mortality selection might bias estimates of social disparities in pain. In the process, the article clarifies whether 2 unexpected patterns observed cross-sectionally-plateauing of pain above age 60, and lower pain among racial/ethnic minorities-are genuine or artefactual. Findings show high prevalence of chronic pain: 27.3% at baseline, increasing to 36.6% thereafter. Multivariate latent growth curve models reveal extremely large disparities in pain by sex, education, and wealth, which manifest primarily as differences in intercept. Net of these variables, there is no racial/ethnic minority disadvantage in pain scores, and indeed a black advantage vis-à-vis whites. Pain levels are predictive of subsequent death, even a decade in the future. No evidence of pain-related survey attrition is found, but surveys not accounting for pain severity and reporting heterogeneity are likely to underestimate socioeconomic disparities in pain. The lack of minority disadvantage (net of socioeconomic status) appears genuine. However, the age-related plateauing of pain observed cross-sectionally is not replicated longitudinally, and seems partially attributable to mortality selection, as well as to rising pain levels by birth cohort.
Keywords: Age Distribution; Age Factors; Aged; Aged, 80 and over; Chronic disease; Ethnic Groups; Female; Healthcare Disparities; Humans; Longitudinal Studies; Male; Middle Aged; Sex Factors; Social Class

Solo agers plan to age alone without the help of nearby family or close friends - Marak, Carol (The Kentucky Standard, 2017)
Keywords: Marriage; News; Singles; Social Support

SOS2 and ACP1 Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (Journal of the American Society of Nephrology, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Spending in retirement…or not? - Wolfe, Bruce; Brazier, Robert (Savings & Investing, 2017)
Something unexpected has been the shared experience for our most recent generation of retirees. The vast majority haven't been spending their retirement savings—leaving nest eggs mostly untouched and living on ready sources of income instead. However, future retirees may be less fortunate.
Keywords: Financial Health; Retirement Planning and Satisfaction; Spending

Staying mentally fit by helping others - Steinke, Andy (The Herald-Palladium, 2017)
Keywords: Meta-analyses; News; Volunteerism

Stimulus Effects of Investment Tax Incentives: Production versus Purchases - Christopher L House; Mocanu, Ana Maria; Matthew D. Shapiro (NBER Working Paper Series, 2017)
The distinction between production and purchases of investment goods is essential for quantifying the response to changes in investment tax incentives. If investment goods are tradeable, a large fraction of the demand from changes in tax subsidies will be met from abroad. This difference between production and purchases implies that investment tax incentives will lead to more capital accumulation, but less stimulus to economic activity relative to a no-trade counterfactual. Domestic capacity to produce investment goods is less than perfectly elastic because of quasi-fixed factors of production, adjustment costs, and specialization of labor. This paper builds these features into a DGSE model where key parameters are estimated to match the reduced-form response of investment production and purchases to tax incentives. Typical investment tax policies result in equipment purchases that are split roughly half between domestic and foreign production of equipment.
Keywords: Economics; Stimulus effects; Taxes

Stress, self-regulation, and context: Evidence from the Health and Retirement Survey. - Briana Mezuk; Scott M Ratliff; Jeannie B. Concha; Cleopatra M Abdou; Rafferty, Jane; Lee, Hedwig; James S Jackson (SSM - Population Health, 2017)
Health-related behaviors, such as smoking, alcohol use, exercise, and diet, are major determinants of physical health and health disparities. However, a growing body of experimental research in humans and animals also suggests these behaviors can impact the ways our bodies respond to stress, such that they modulate (that is, serve as a means to self-regulate or cope with) the deleterious impact of stressful experiences on mental health. A handful of epidemiologic studies have investigated the intersection between stress and health behaviors on health disparities (both mental and physical), with mixed results. In this study we use a novel instrument designed to explicitly measure the self-regulatory motivations and perceived effectiveness of eight health-related self-regulatory behaviors (smoking, alcohol, drug use, overeating, prayer, exercise, social support, talking with a councilor) in a subset of the Health and Retirement Study (N=1,354, Mean age=67, 54% female). We find that these behaviors are commonly endorsed as self-regulatory stress-coping strategies, with prayer, social support, exercise, and overeating used most frequently. The likelihood of using particular behaviors as self-regulatory strategies varied significantly by sex, but not by race/ethnicity, education, or wealth. We also find that greater stress exposure is associated with higher likelihood of using these behaviors to self-regulate feelings of emotional distress, particularly health-harming behaviors like smoking, alcohol, and overeating. These findings provide an important link between sociological and psychological theoretical models on stress and empirical epidemiological research on social determinants of health and health disparities.
Keywords: Depressive symptoms; Health Disparities; Stress

Study reveals factors that increase people’s fear of developing Alzheimer’s - Magdalena Kegel (Alzheimer's News Today, 2017)
Keywords: Alzheimer's disease; News

Study Shows One Way to Extend Working Years - Lisa Ward (Journal Reports: Wealth Management, 2017)
Keywords: Employment and Labor Force; News; Older Adults

Subjective age and sleep in middle-aged and older adults. - Yannick Stephan; Angelina R Sutin; Bayard, Sophie; Antonio Terracciano (Psychology & Health, 2017)
OBJECTIVE: Chronological age is commonly used to explain change in sleep. The present study examines whether subjective age is associated with change in sleep difficulties across middle adulthood and old age. DESIGN: Participants were drawn from the second (2004-2005) and third (2013-2014) waves of the Midlife in the United States Survey (MIDUS, N = 2350; Mean Age: 55.54 years), the 2008 and 2014 waves of the Health and Retirement Study (HRS, N = 4066; Mean Age: 67.59 years) and the first (2011) and fourth (2014) waves of the National Health and Aging Trends Survey (NHATS, N = 3541; Mean Age: 76.46). In each sample, subjective age, sleep difficulties, depressive symptoms, anxiety and chronic conditions were assessed at baseline. Sleep difficulties was assessed again at follow-up. MAIN OUTCOME MEASURES: Sleep difficulties. RESULTS: An older subjective age at baseline was related to an increase in sleep difficulties over time in the three samples, and was mediated, in part, through more depressive symptoms, anxiety and chronic conditions. Feeling older was associated with an increased likelihood of major sleeping difficulties at follow-up in the three samples. CONCLUSION: Subjective age is a salient marker of individuals' at risk for poor sleep quality, beyond chronological age.
Keywords: Anxiety; Depressive symptoms; Sleep

Subjective and objective cognitive function among older adults with a history of traumatic brain injury: A population-based cohort study. - Raquel C Gardner; Kenneth M. Langa; Kristine Yaffe (PLoS Medicine, 2017)
BACKGROUND: Traumatic brain injury (TBI) is extremely common across the lifespan and is an established risk factor for dementia. The cognitive profile of the large and growing population of older adults with prior TBI who do not have a diagnosis of dementia, however, has not been well described. Our aim was to describe the cognitive profile associated with prior TBI exposure among community-dwelling older adults without dementia-an understudied but potentially vulnerable population. METHODS AND FINDINGS: In this population-based cohort study, we studied 984 community-dwelling older adults (age 51 y and older and their spouses) without dementia who had been randomly selected from respondents to the 2014 wave of the Health and Retirement Study to participate in a comprehensive TBI survey and who either reported no prior TBI (n = 737) or prior symptomatic TBI resulting in treatment in a hospital (n = 247). Mean time since first TBI was 38 ± 19 y. Outcomes assessed included measures of global cognitive function, verbal episodic memory, semantic fluency, and calculation as well as a measure of subjective memory ("How would you rate your memory at the present time?"). We compared outcomes between the two TBI groups using regression models adjusting for demographics, medical comorbidities, and depression. Sensitivity analyses were performed stratified by TBI severity (no TBI, TBI without loss of consciousness [LOC], and TBI with LOC). Respondents with TBI were younger (mean age 64 ± 10 y versus 68 ± 11 y), were less likely to be female, and had higher prevalence of medical comorbidities and depression than respondents without TBI. Respondents with TBI did not perform significantly differently from respondents without TBI on any measure of objective cognitive function in either raw or adjusted models (fully adjusted: global cognitive function score 15.4 versus 15.2, p = 0.68; verbal episodic memory score 4.4 versus 4.3, p = 0.79; semantic fluency score 15.7 versus 14.0, p = 0.21; calculation impairment 22% versus 26%, risk ratio [RR] [95% CI] = 0.86 [0.67-1.11], p = 0.24). Sensitivity analyses stratified by TBI severity produced similar results. TBI was associated with significantly increased risk for subjective memory impairment in models adjusted for demographics and medical comorbidities (29% versus 24%; RR [95% CI]: 1.26 [1.02-1.57], p = 0.036). After further adjustment for active depression, however, risk for subjective memory impairment was no longer significant (RR [95% CI]: 1.18 [0.95-1.47], p = 0.13). Sensitivity analyses revealed that risk of subjective memory impairment was increased only among respondents with TBI with LOC and not among those with TBI without LOC. Furthermore, the risk of subjective memory impairment was significantly greater among those with TBI with LOC versus those without TBI even after adjustment for depression (RR [95% CI]: partially adjusted, 1.38 [1.09-1.74], p = 0.008; fully adjusted, 1.28 [1.01-1.61], p = 0.039). CONCLUSIONS: In this population-based study of community-dwelling older adults without dementia, those with prior TBI with LOC were more likely to report subjective memory impairment compared to those without TBI even after adjustment for demographics, medical comorbidities, and active depression. Lack of greater objective cognitive impairment among those with versus without TBI may be due to poor sensitivity of the cognitive battery or survival bias, or may suggest that post-TBI cognitive impairment primarily affects executive function and processing speed, which were not rigorously assessed in this study. Our findings show that among community-dwelling non-demented older adults, history of TBI is common but may not preferentially impact cognitive domains of episodic memory, attention, working memory, verbal semantic fluency, or calculation.
Keywords: Brain injury; Cognitive Ability; Older Adults

Subjective survival expectations and observed survival: How consistent are they? - Alberto Palloni; Beatriz Novak (Vienna Yearbook of Population Research, 2017)
In this paper, we use new models to convert subjective expectations elicited from individual responses into conditional survival functions.We also estimate the effects of individual characteristics and assess the impact of health shocks on individual updates of subjective expectations. We use Health and Retirement Study (HRS) data from 1992 to 2006. By and large, our results confirm past empirical findings, but also identify patterns not documented in previous research. We show that the subjective probabilities are remarkably close to the results of actual life tables constructed from observed data, that whites underestimate their survival chances more than blacks, that women underestimate their survival chances more than men, and that the subjective underestimation of conditional survival increases with age in all population subgroups. We find significant differences in the survival outlooks of the original HRS cohort and a more recent HRS cohort (1992 versus 2004). These differences persist after introducing suitable controls. The observed mortality differentials between smokers and non-smokers, obese and non-obese individuals, and high-education and low-education groups are quite close to those of these subgroups' subjective survival expectations. Finally, we find large updating effects that result from recent health shocks on subjective expectations.
Keywords: Longevity; Self-reported health; Subjective age; Subjective Expectations

Successful Aging as the Intersection of Individual Resources, Age, Environment, and Experiences of Well-being in Daily Activities. - Shannon T. Mejia; Lindsay H Ryan; Gonzalez, Richard; Jacqui Smith (J Gerontol B Psychol Sci Soc Sci, 2017)
Objective: We conceptualize successful aging as a cumulative index of individual resources (the absence of disease and disability, high cognitive and physical functioning, social embeddedness) in the service of successful aging outcomes (global well-being, experienced well-being, and vital status), and conditioned by age, social structure, and environment. Method: The study used baseline and follow-up data from the 2008-2014 waves of the Health and Retirement Study (N = 17,230; age = 51-101). Linear, multilevel, and logistic models compared individual resources at baseline as independent, cumulative, and binary predictors of outcomes 4 years later. Results: Individual resources were unequally distributed across age group and social structures (education, wealth, race, gender) and had a cumulative effect on all successful aging outcomes. For experienced well-being, individual resources were most important at midlife and for groups with lower education. Person-environment congruence (social cohesion, city satisfaction) was associated with all successful aging outcomes and conditioned the effect of individual resources on experienced well-being. Discussion: A cumulative index allows for gradations in resources that can be compensated for by external factors such as person-environment congruence. This index could guide policy and interventions to enhance resources in vulnerable subgroups and diminish inequalities in successful aging outcomes.
Keywords: Activities of Daily Living; Adult; Aged; Aged, 80 and over; Aging; environment; Female; Follow-Up Studies; Health Status; Humans; Male; Middle Aged; Personal Satisfaction; Social Support; United States

Successful Aging in the Context of the Disablement Process: Working and Volunteering as Moderators on the Association Between Chronic Conditions and Subsequent Functional Limitations. - Ben Lennox Kail; Dawn C Carr (J Gerontol B Psychol Sci Soc Sci, 2017)
Objectives : This study evaluated the successful aging model by assessing the impact of two forms of productive engagement-working and volunteering-as potential interventions in the process of disablement. Method : The Health and Retirement Study was used to (a) estimate two-stage selection equations of (i) currently working part time and full time and (ii) currently volunteering less than 100 hours and volunteering 100 hours or more per year (net of chronic health problems) and (b) assess whether, net of selection, working, and volunteering moderate the association between chronic conditions and subsequent functional limitations. Results : Chronic conditions were associated with elevated levels of subsequent functional limitations, whereas both working and volunteering were associated with lower levels of subsequent functional limitations. Moreover, workers and volunteers of less than 100 hours per year experienced a reduction in the association of chronic conditions on subsequent functional limitations. Discussion : This research highlights the role of productive engagement as a key element in successful aging. Not only do work and volunteering have direct associations with health outcomes themselves, but they also act as potential interventions in the process of disablement by attenuating the way in which chronic conditions are translated into subsequent functional limitations. This suggests that (a) future research should apply successful aging models to health processes as well as health outcomes and (b) policy makers should support social institutions that foster late-life productive engagement.
Keywords: Aged; Aged, 80 and over; Aging; Disabled Persons; Employment; Female; Humans; Male; United States; Volunteers

Survey Measurement of Probabilistic Macroeconomic Expectations: Progress and Promise - Charles F Manski (NBER Working Paper Series, 2017)
Economists commonly suppose that persons have probabilistic expectations for uncertain events, yet empirical research measuring expectations was long rare. The inhibition against collection of expectations data has gradually lessened, generating a substantial body of recent evidence on the expectations of broad populations. This paper first summarizes the history leading to development of the modern literature and overviews its main concerns. I then describe research on three subjects that should be of direct concern to macroeconomists: expectations of equity returns, inflation expectations, and professional macroeconomic forecasters. I also describe work that questions the assumption that persons have well-defined probabilistic expectations and communicate them accurately in surveys. Finally, I consider the evolution of thinking about expectations formation in macroeconomic policy analysis. I favorably observe the increasing willingness of theorists to study alternatives to rational expectations assumptions, but I express concern that models of expectations formation will proliferate in the absence of empirical research to discipline thinking. To make progress, I urge measurement and analysis of the revisions to expectations that agents make following occurrence of unanticipated shocks.
Keywords: Survey Methodology

Survival, functional status, and eating ability after percutaneous endoscopic gastrostomy tube placement for acute stroke - Meisel, Karl; Robert M. Arnold; Irena Cenzer; W John Boscardin (Journal of the American Geriatrics Society, 2017)
OBJECTIVES: To determine the long-term survival and independence of individuals with stroke and percutaneous endoscopic gastrostomy (PEG) tube placement. DESIGN: Retrospective cohort study. SETTING: A longitudinal nationally representative community-based sample of older adults. PARTICIPANTS: Individuals with stroke who had a PEG tube placed (N = 174, mean age 79, 51% female, 29% African American). MEASUREMENTS: Functional status before incident stroke was determined based on data from the Health and Retirement Study (HRS), a national longitudinal survey of community-dwelling older adults, from 1993 to 2012. Hospitalizations for stroke and PEG placement were determined according to Medicare claims. HRS participants were interviewed, and outcomes of survivors interviewed in the 2 years after hospitalization are described. Survival and functional and eating ability of the cohort were examined. Groups were compared according to age and prestroke functional disability in activities of daily living (ADLs) because it was hypothesized that ADL disability would predict worse outcomes. RESULTS: In the 2 years after hospitalization, overall mortality was 66%. Fifteen participants survived and regained independent ADL function (9%). Of those who survived to a follow-up interview, 33 (56%) could not eat independently, and 31 (53%) required assistance to walk across the room. Age of 85 and older was associated with worse outcomes (10% vs 29% at 2 years, P < .001), but baseline ADL disability was not. CONCLUSION: In this community-based sample, individuals who had had a stroke and a PEG tube placed had high mortality, and survivors were unlikely to be functional or mobile or to recover eating ability after hospitalization. A palliative care discussion including goals of care should occur before PEG tube placement is considered.
Keywords: Gastrostomy; Palliative care; Stroke

Satisfaction with Aging Results in Reduced Risk for Falling - Liat Ayalon (International Psychogeriatrics, 2016)
Background: Falls are highly frequent in older adults and are associated with increased morbidity and mortality. The present study was designed to assess the role of satisfaction with one's aging process as a predictor of the risk for falling over a four-year period and to identify potential mediators of this relationship. Methods: The Health and Retirement Study (HRS) is a US nationally representative sample of individuals over the age of 50 years and their spouse of any age. The present study was based on the 2008 2012 waves of the HRS. Analyses were restricted to 4,121 respondents over the age of 50 years, who had fall data in 2008 and 2012 and were eligible to complete the satisfaction with aging measure as part of the 2008 psychosocial questionnaire. Results: Overall, 38.1 of the sample reported having fallen at least once between 2006 and 2008 and 40.7 reported having fallen at least once between 2010 and 2012. Higher levels of satisfaction with aging in 2008 were found to be protective against falls assessed in 2012 (OR 95 CI = 0.88 0.79 0.98 ) even after adjustment for age, gender, education, ethnicity, medical status, functional status, cognitive functioning, walking speed, balance, vision, depressive symptoms, physical activities, and past falls. Bootstrap procedures have shown that the effect of satisfaction with aging on falls is partially accounted for through its effect on functional decline. Conclusions: The findings point to the important role of satisfaction with aging as a potential protective mechanism against falls. The results call for the development of psychosocial interventions to reduce falls in older adults.
Keywords: Health Conditions and Status; Healthcare

Savings After Retirement: A Survey - Mariacristina De Nardi; Eric French; John Bailey Jones (Annual Review of Economics, 2016)

Self-Reported Hearing in the Last 2 Years of Life in Older Adults. - Christine S Ritchie; Yinghui Miao; W John Boscardin; Margaret Wallhagen (J Am Geriatr Soc, 2016)
OBJECTIVES: To assess the prevalence and correlates of self-reported hearing loss during the last 2 years of life. DESIGN: Observational cohort study. SETTING: The Health and Retirement Study (HRS), a longitudinal nationally representative cohort of adults aged 50 and older (2000-13). PARTICIPANTS: Older adults (N = 5,895, mean age at death 78, 53% female, 20% nonwhite). MEASUREMENTS: The HRS interview closest to death was used (mean 12.2 months before death). Participants rated their hearing (excellent, very good, good, fair, poor) and indicated whether they used hearing aids. The prevalence and correlates of fair and poor ratings are described, adjusted for age and sex. RESULTS: Thirty-two percent (95% confidence interval (CI) = 31-34%) of all participants and 60% (95% CI = 57-64%) of the 7% of participants who used hearing aids rated their hearing as fair or poor. The prevalence of fair or poor hearing was highest in participants interviewed closest to death (29% 19-24 months before death, 36% 1-6 months before death, P for trend = .01). Correlates of fair or poor hearing during the last 2 years of life included age at death (50-59, 22%; 60-69, 21%; 70-79, 26%; 80-89, 38%; ≥90, 50%), sex (men 35%, women 30%), race and ethnicity (Hispanic 42%, white 33%), wealth (lowest quartile 38%, highest quartile 27%), history of heart disease (yes 38%, no 27%), activity of daily living dependence (yes 42%, no 26%), difficulty taking medications (yes 46%, no 29%), and probable dementia (yes 44%, no 24%). CONCLUSION: Self-reported hearing loss increases during the last 2 years of life and is associated with physical and social vulnerability.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; California; Demography; Female; Hearing aids; Hearing loss; Humans; Longitudinal Studies; Male; Middle Aged; Prevalence; Quality of Life; Risk Factors; Self Report; Vulnerable Populations

Self-reported herpes zoster, pain, and health care seeking in the Health and Retirement Study: implications for interpretation of health care-based studies. - Hales, Craig M; Harpaz, Rafael; Bialek, Stephanie R (Ann Epidemiol, 2016)
PURPOSE: To describe self-reported herpes zoster (HZ) and explore factors that could impact interpretation of results from health care-based HZ studies. METHODS: We performed logistic regression using data from the 2008 Health and Retirement Study (HRS) to evaluate risk factors for having a history of HZ and experiencing severe HZ pain, and predictors for seeking health care for HZ. RESULTS: Among 14,564 respondents aged ≥55 years, women were more likely than men to report a history of HZ (15.7% vs. 11.6%, P < .01). Blacks (6.4% vs. 14.7% in whites, P < .01) and respondents with less than a high school diploma (12.2% vs.14.2% in respondents with at least a high school diploma, P = .01) were less likely to report a history of HZ. Women, blacks, Hispanics, and those with less than a high school diploma were more likely to report severe HZ pain. Most (91.1%) respondents sought health care for HZ; Hispanics (64.2% vs. 92.1% in whites, P < .001) and those with recurrent HZ were less likely to seek health care for HZ, whereas those with severe pain were more likely (95.4% vs. 87.9% in those without severe pain, P < .01). CONCLUSIONS: HRS provides a new platform for studies of HZ, one which allowed us to uncover issues that warrant particular attention when interpreting results of health care-based studies.
Keywords: Age Factors; Aged; Aged, 80 and over; Cross-Sectional Studies; Female; Health Surveys; Herpes Zoster; Humans; Independent Living; Logistic Models; Male; Middle Aged; Outcome Assessment, Health Care; pain; Pain Measurement; Patient Acceptance of Health Care; Reproducibility of Results; Retirement; Risk Assessment; Self Report; Severity of Illness Index; Sex Factors; Treatment Outcome; United States

Service-Related Exposures and Physical Health Trajectories Among Aging Veteran Men - Miles G Taylor; Urena, Stephanie; Ben Lennox Kail (The Gerontologist, 2016)
PURPOSE OF THE STUDY: We examined the association of military service-related exposures (SREs) with physical health trajectories to establish whether combat and other hazards have lasting connections to health in later life. We also examined potential confounders and mechanisms to further understand the associations. DESIGN AND METHODS: We used the 2013 HRS Veterans Mail Survey linked to the longitudinal Health and Retirement Study (HRS) to examine military service experiences and health over a decade (2000-2010) among veteran men. We employed latent class analysis to disaggregate trajectories of health in later life. RESULTS: Most veteran men experienced good health over the decade. Although we found a connection between combat and later health, it was driven primarily by hazardous or traumatic exposures. Service-related disability, current health behaviors, and mental health were not likely explanations for these associations. IMPLICATIONS: The measurement of service experiences is primary in understanding health implications of military service and projecting the health service needs of aging veterans. SREs are varied and complex and have differential connections to health. These connections remain unexplained by current behaviors and mental health, suggesting the need to examine earlier life course pathways and mechanisms.
Keywords: Demographics; Healthcare

Sex, race and age differences in muscle strength and limitations in community dwelling older adults: Data from the Health and Retirement Survey (HRS) - Cassandra M Germain; Elizabeth Vasquez; John A. Batsis; Douglas R McQuoid (Archives of Gerontology and Geriatrics, 2016)
Background: Aging-related muscle weakness is associated with increased risk of functional limitations and disability. This study examined the association between varying degrees of hand grip strength on functional ability in community-dwelling older adults. Methods: Cross-sectional analysis of 4289 men and 5860 women 60 from 2006 and 2008 waves of the population-based Health and Retirement Study (HRS) were stratified by sex-specific grip strength tertiles (low, mid, high). Prevalence and adjusted odds of physical limitations (PL), and ADL/IADL limitation were calculated by sex, race/ethnicity and age group (60-69, 70-79, 80 ). Models were weighted, adjusted for age, sex, race/ethnicity, education, smoking status, BMI, comorbidities and participation in physical activity. Results: Prevalence of PL, ADL and IADL limitations were significantly lower among adults in the highest grip category as compared to those in the lowest grip category. Adjusted odds for PL OR 0.41 0.33,0.52 ; ADL OR.51 0.39,0.67 , and IADL OR 0.47 0.38-0.59 limitations were significantly lower among adults in the highest grip compared to the lowest grip category. However, notable differences were observed in the strength of these associations by gender, race and age group. Conclusion: Demographic characteristics are important factors to consider for risk stratification and the development of effective grip strength training interventions for older adults.
Keywords: Health Conditions and Status

Sex-Specific and Time-Varying Associations Between Cigarette Smoking and Telomere Length Among Older Adults. - Zhang, Chenan; Diane S. Lauderdale; Brandon L Pierce (Am J Epidemiol, 2016)
Inconsistent associations between smoking and telomere length (TL) have been reported in epidemiologic studies, perhaps because of the time-varying nature of smoking behaviors. We estimated the associations of TL, which was measured by quantitative polymerase chain reaction using saliva DNA, with concurrent and past smoking status reported biennially for up to 16 years before TL measurement in 5,624 participants in the Health and Retirement Study (1992-2008). Smoking was associated with reduced TL when we used prospective data on smoking statuses among men and women, but the association was strongly attenuated among men in cross-sectional analyses. This attenuation was largely due to a higher rate of smoking cessation during the study period among men with shorter TL than among men with longer TL. Short TL was also associated with poorer overall health in men, which suggests that male smokers with short TL were more likely to quit smoking because of poor health. Analyses of years since cessation, smoking duration, and pack-years of smoking all support the hypothesis that increased cigarette use shortens TL. Our results provide a potential explanation for the inconsistent associations between smoking and TL reported in previous cross-sectional studies. Time-varying associations should be considered in future studies of smoking behavior, TL, aging, and disease risk.
Keywords: Aged; Aged, 80 and over; Aging; Biomarkers; DNA; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Oxidative stress; Polymerase Chain Reaction; Prospective Studies; Saliva; Sex Distribution; Smoking; Smoking cessation; Telomere Shortening

Skin Cancer in U.S. Elderly Adults: Does Life Expectancy Play a Role in Treatment Decisions? - Linos, Eleni; Chren, Mary-Margaret; Irena Cenzer; Kenneth E Covinsky (J Am Geriatr Soc, 2016)
OBJECTIVES: To examine whether life expectancy influences treatment pattern of nonmelanoma skin cancer, or keratinocyte carcinoma (KC), the most common malignancy and the fifth most costly cancer to Medicare. DESIGN: Nationally representative cross-sectional study. SETTING: Nationally representative Health and Retirement Study linked to Medicare claims. PARTICIPANTS: Treatments (N = 9,653) from individuals aged 65 and older treated for basal or squamous cell carcinoma between 1992 and 2012 (N = 2,702) were included. MEASUREMENTS: Limited life expectancy defined according to aged 85 and older, medical comorbidities, Charlson Comorbidity Index score of 3 or greater, difficulty in at least one activity of daily living (ADL), and a Lee index of 13 or greater. Treatment type (Mohs micrographic surgery (MMS) (most intensive, highest cost), excision, or electrodesiccation and curettage (ED&C) (least intensive, lowest cost)), according to procedure code. RESULTS: Most KCs (61%) were treated surgically. Rates of MMS (19%), excision (42%), and ED&C (39%) were no different in participants with limited life expectancy and those with normal life expectancy. For example, 19% of participants with difficulty or dependence in ADLs, 20% of those with a Charlson comorbidity score greater than 3, and 15% of those in their last year of life underwent MMS; participants who died within 1 year of diagnosis were treated in the same way as those who lived longer. CONCLUSION: A one-size-fits-all approach in which advanced age, health status, functional status, and prognosis are not associated with intensiveness of treatment appears to guide treatment for KC, a generally nonfatal condition. Although intensive treatment of skin cancer when it causes symptoms may be indicated regardless of life expectancy, persons with limited life expectancy should be given choices to ensure that the treatment matches their goals and preferences.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Carcinoma, Basal Cell; Carcinoma, Squamous Cell; Comorbidity; Cost-Benefit Analysis; Cross-Sectional Studies; Curettage; Decision Support Techniques; Disability Evaluation; Electrosurgery; Female; Humans; Keratinocytes; Life Expectancy; Male; Mohs Surgery; Prognosis; Skin Neoplasms

Sleep and Aging in Population Research - Diane S. Lauderdale (National Institute on Aging, 2016)
Sleep is very important to older adults, and research studies about sleep, particularly those that identify problems with sleep and consequent ill health, receive significant media attention. However, making sure that research findings about sleep are accurate and informative is quite challenging. Incorporating sleep into studies of health and aging is complicated both conceptually and practically. Sleep is not a single entity, and no single approach to measuring sleep can capture all the dimensions that may be relevant for health, nor is there a summary number that describes it. Sleep is multi-faceted with behavioral, social, psychological, and biological components. Adding to the complexity of learning about sleep from individual respondents is the problem that they do not observe many aspects of sleep. Thus, the reporting challenges for sleep are different and perhaps even greater than health behaviors well recognized to be challenging for individuals to report accurately such as diet and physical activity. In addition, sleep research has multiple disciplinary origins, and they approach the conceptualization and measurement of sleep in different ways. Psychological approaches often rely on instruments with multiple questions that are designed to tap into latent constructs; epidemiological approaches query quantifiable characteristics; and clinical sleep medicine focuses on diagnosing defined sleep disorders or “diseases.” This paper will first sketch out why sleep is so complicated by describing some of the dimensions of sleep that may be relevant for population studies and the ways sleep has been most often measured in population research. As with any variable employed in research about groups of respondents, random noise is much less of a problem for inferences than is biased measurement. Finally, there will be a summary of outstanding questions about sleep and health that studies of older adults might investigate.
Keywords: Sleep

Social Security and Retirement Programs Around the World: The Capacity to Work at Older Ages - Introduction and Summary - Courtney Coile; Kevin Milligan; David A Wise (Cambridge, MA: National Bureau of Economic Research, 2016)
This is the introduction and summary to the seventh phase of an ongoing project on Social Security Programs and Retirement Around the World. The project compares the experiences of a dozen developed countries and uses differences in their retirement program provisions to explore the effect of SS on retirement and related questions. The first three phases of this project document that: 1) incentives for retirement from SS are strongly correlated with labor force participation rates across countries; 2) within countries, workers with stronger incentives to delay retirement are more likely to do so; and 3) changes to SS could have substantial effects on labor force participation and government finances. The fourth volume explores whether higher employment among older persons might increase youth unemployment and finds no link between the two. The fifth and sixth volumes focus on the disability insurance (DI) program, finding that changes in DI participation are more closely linked to DI reforms than to changes in health and that reducing access to DI would raise labor supply. This seventh phase of the project explores whether older people are healthy enough to work longer. We use two main methods to estimate the health capacity to work, asking how much older individuals today could work if they worked as much as those with the same mortality rate in the past or as younger individuals in similar health. Both methods suggest there is significant additional health capacity to work at older ages.
Keywords: Disabilities; Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction; Social Security

Social Supports as Enabling Factors in Nursing Home Admissions: Rural, Suburban, and Urban Differences - Cohen, Adrienne; Jennifer R. Bulanda (Journal of Applied Gerontology, 2016)
This study investigates differences in social support and nursing home admission by rurality of residence. We use discrete-time event history models with longitudinal data from seven waves (1998-2010) of the Health and Retirement Study to prospectively examine the risk of spending 30 or more days in a nursing home (n = 5,913). Results show that elders with a health problem who live in rural areas of the South or Midwest have approximately 2 times higher odds of nursing home entry than elders living in urban areas in the Northeast. Rural elders report somewhat higher social support than non-rural elders, and controlling for these forms of social support does not explain the higher risk of a nursing home stay for Southerners and Midwesterners living in rural areas. Results suggest that social support has a similar association with nursing home entry for rural, suburban, and urban elders.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Retirement Planning and Satisfaction

Socioeconomic Status Across the Life Course and Cognitive Function Among Older Adults: An Examination of the Latency, Pathways, and Accumulation Hypotheses - Jiyoung Lyu; Jeffrey A Burr (Journal of Aging and Health, 2016)
Objective: This study investigated the relationship between life course socioeconomic status (SES) and cognitive function among older adults in the United States over a 12-year observation period. The mediation of adult SES on the association between childhood SES and cognition was examined, along with the relationship between cumulative SES and cognition. Method: Using a nationally representative sample from the Health and Retirement Study, cognitive status and change in cognition from 1998 to 2010 were examined using growth curve models. Results: The results showed that cognitive function varied within-persons and between-persons. SES disadvantage in childhood was associated with lower cognitive function at baseline. Adult SES mediated the relationship between childhood SES and cognitive function. Persons with higher cumulative SES demonstrated an advantage in cognitive function. Discussion: Childhood SES and adult SES both had relationships with cognitive status and, to a lesser degree, change in cognition in later life.
Keywords: Adult children; Demographics; Event History/Life Cycle; Health Conditions and Status

Somatic, positive and negative domains of the Center for Epidemiological Studies Depression (CES-D) scale: a meta-analysis of genome-wide association studies. - Demirkan, A; J. Lahti; Nese Direk; Viktorin, A.; Kathryn L Lunetta; Antonio Terracciano; Michael A Nalls; Toshiko Tanaka; Karin Hek; Myriam Fornage; Jürgen Wellmann; Marilyn C Cornelis; et al. (Psychol Med, 2016)
BACKGROUND: Major depressive disorder (MDD) is moderately heritable, however genome-wide association studies (GWAS) for MDD, as well as for related continuous outcomes, have not shown consistent results. Attempts to elucidate the genetic basis of MDD may be hindered by heterogeneity in diagnosis. The Center for Epidemiological Studies Depression (CES-D) scale provides a widely used tool for measuring depressive symptoms clustered in four different domains which can be combined together into a total score but also can be analysed as separate symptom domains. METHOD: We performed a meta-analysis of GWAS of the CES-D symptom clusters. We recruited 12 cohorts with the 20- or 10-item CES-D scale (32 528 persons). RESULTS: One single nucleotide polymorphism (SNP), rs713224, located near the brain-expressed melatonin receptor (MTNR1A) gene, was associated with the somatic complaints domain of depression symptoms, with borderline genome-wide significance (p discovery = 3.82 × 10-8). The SNP was analysed in an additional five cohorts comprising the replication sample (6813 persons). However, the association was not consistent among the replication sample (p discovery+replication = 1.10 × 10-6) with evidence of heterogeneity. CONCLUSIONS: Despite the effort to harmonize the phenotypes across cohorts and participants, our study is still underpowered to detect consistent association for depression, even by means of symptom classification. On the contrary, the SNP-based heritability and co-heritability estimation results suggest that a very minor part of the variation could be captured by GWAS, explaining the reason of sparse findings.
Keywords: depression; Depressive Disorder, Major; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Receptor, Melatonin, MT1; Somatoform Disorders

Spousal Characteristics and Older Adults' Hospice Use: Understanding Disparities in End-of-Life Care. - Katherine A Ornstein; Melissa D. Aldridge; Christine A Mair; Rebecca Jean Gorges; Albert L Siu; Amy Kelley (J Palliat Med, 2016)
BACKGROUND: Hospice use has been shown to benefit quality of life for patients with terminal illness and their families, with further evidence of cost savings for Medicare and other payers. While disparities in hospice use by patient diagnosis, race, and region are well documented and attention to the role of family members in end-of-life decision-making is increasing, the influence of spousal characteristics on the decision to use hospice is unknown. OBJECTIVES: To determine the association between spousal characteristics and hospice use. DESIGN: We used data from the Health and Retirement Study (HRS), a prospective cohort study, linked to the Dartmouth Atlas of Health Care and Medicare claims. SETTING: National study of 1567 decedents who were married or partnered at the time of death (2000-2011). MEASURES: Hospice use at least 1 day in the last year of life as measured via Medicare claims data. Spousal factors (e.g., education and health status) measured via survey. RESULTS: In multivariate models controlling for patient factors and regional variation, spouses with lower educational attainment than their deceased spouse had decreased likelihood of hospice use (odds ratio [OR] = 0.58; 95% confidence interval [CI] = 0.40-0.82). Health of the spouse was not significantly associated with likelihood of decedent hospice use in adjusted models. IMPLICATIONS: Although the health of the surviving spouse was not associated with hospice use, their educational level was a predictor of hospice use. Spousal and family characteristics, including educational attainment, should be examined further in relation to disparities in hospice use. Efforts to increase access to high-quality end-of-life care for individuals with serious illness must also address the needs and concerns of caregivers and family.
Keywords: Hospice Care; Hospices; Humans; Medicare; Prospective Studies; Quality of Life; Terminal Care; United States

Spousal labor market effects from government health insurance: Evidence from a veterans affairs expansion. - Melissa A. Boyle; Joanna N Lahey (J Health Econ, 2016)
Measuring the total impact of health insurance receipt on household labor supply is important in an era of increased access to publicly provided and subsidized insurance. Although government expansion of health insurance to older workers leads to direct labor supply reductions for recipients, there may be spillover effects on the labor supply of uncovered spouses. While the most basic model predicts a decrease in overall household work hours, financial incentives such as credit constraints, target income levels, and the need for own health insurance suggest that spousal labor supply might increase. In contrast, complementarities of spousal leisure would predict a decrease in labor supply for both spouses. Utilizing a mid-1990s expansion of health insurance for U.S. veterans, we provide evidence on the effects of public insurance availability on the labor supply of spouses. Using data from the Current Population Survey and Health and Retirement Study, we employ a difference-in-differences strategy to compare the labor market behavior of the wives of older male veterans and non-veterans before and after the VA health benefits expansion. Although husbands' labor supply decreases, wives' labor supply increases, suggesting that financial incentives dominate complementarities of spousal leisure. This effect is strongest for wives with lower education levels and lower levels of household wealth and those who were not previously employed full-time. These findings have implications for government programs such as Medicare and Social Security and the Affordable Care Act.
Keywords: Employment; Female; Government Programs; Humans; Insurance, Health; Male; Middle Aged; Spouses; Surveys and Questionnaires; United States; Veterans

Stepparenthood and Depressive Symptoms in Later Life: The Mediating Role of Parent-Child Contact and Interactions. - Cassandra Jean Cupka (Sociology, 2016)
In the United States the share of middle-age and older adults who are stepparents has increased over the recent decades. Prior studies have shown that stepparents generally experience more depressive symptoms than parents with only biological children, but most of this literature has focused on stepparents of minor children. The few studies that have examined the relation between stepparenthood and depressive symptoms in later life find either a positive or a null association. The mixed findings could be attributable to different definitions of stepparenthood used in these studies. Individuals can become simple stepparents when they have only stepchildren or they can become complex stepparents when they have both biological children and stepchildren. To fill this gap in the literature, I used the 2008 and 2010 waves of Health and Retirement Study to examine how simple stepparents, complex stepparents, and parents with only biological children differ in their depressive symptoms, with particular attention given to the mediating roles of parent-child contact and interactions. Women and men were also analyzed separately in this study. The results showed that stepparenthood was not associated with depressive symptoms for women and men. Contact and interactions with children did not mediate the association between parental status and depressive symptoms for either men or women. Potential avenues for future stepfamily research is discussed. Advisors/Committee Members: Lin, I-Fen (Advisor).
Keywords: Adult children; Depressive symptoms; Divorce

Stress and Negative Relationship Quality among Older Couples: Implications for Blood Pressure. - Kira S. Birditt; Nicky J Newton; James A. Cranford; Lindsay H Ryan (J Gerontol B Psychol Sci Soc Sci, 2016)
OBJECTIVES: The cardiovascular system may represent a significant pathway by which marriage and stress influence health, but research has focused on married individuals cross-sectionally. This study examined associations among chronic stress, negative spousal relationship quality, and systolic blood pressure over time among middle-aged and older husbands and wives. METHOD: Participants were from the nationally representative longitudinal Health and Retirement Study. A total of 1,356 (N = 2,712) married and cohabitating couples completed psychosocial and biomeasure assessments in waves 2006 and 2010. Analyses examined whether Wave 1 (2006) relationship quality and stress were associated with changes in blood pressure over time. RESULTS: The effects of stress and negative relationship quality were dyadic and varied by gender. Husbands had increased blood pressure when wives reported greater stress, and this link was exacerbated by negative spousal relationship quality. Negative relationship quality predicted increased blood pressure when both members of the couple reported negative quality relations. DISCUSSION: Findings support the dyadic biopsychosocial model of marriage and health indicating: (a) stress and relationship quality directly effect the cardiovascular system, (b) relationship quality moderates the effect of stress, and (c) the dyad rather than only the individual should be considered when examining marriage and health.
Keywords: Aged; Aging; Blood pressure; Family Relations; Female; Humans; Hypertension; Longitudinal Studies; Male; Marriage; Middle Aged; Stress, Psychological

Stressed-Out Mate Bad for Your Weight - Kathleen Doheny (WebMD, 2016)
Keywords: BMI; Marriage; Older Adults

A study of telomere length as a prospective biomarker of cancer risk - Zhang, Chenan (Public Health Sciences, 2016)
This dissertation is comprised of two peer-reviewed articles and one manuscript, aiming to identify knowledge gaps in terms of the role of telomere length as a biomarker of cancer. Individuals with relatively short telomeres in peripheral blood cells have been shown in epidemiological studies to be at increased risk for mortality and cancer, leading investigators to hypothesize that telomere length and attrition over the life-course is a critical mechanism underlying cancer and many other age-related health conditions. However, such associations are not consistent across all cancers or even within cancer types, with some studies showing null, or even opposite associations. Furthermore, due to the cross-sectional nature of case-control studies, from which most associations of telomere length and cancer risk are obtained, it is possible that telomere shortening occurs after diagnosis (due to the cancer itself or treatment effects), or is confounded by other common risk factors, and therefore may not be a true biomarker of subsequent cancer risk. I employed three strategies for addressing these potential issues: 1) use genetic polymorphisms that influence telomere length as proxies for telomere length to estimate associations between telomere length and cancer risk; 2) perform careful adjustment of potential confounders of the telomere length-cancer association, including the assessment of time-varying effects on smoking, a potential telomere length correlate; and 3) utilize a prospective study design in which baseline telomere length is measured prior to the development of any adverse health outcomes. In the first study of this dissertation (Chapter 2), I used a Mendelian randomization approach to estimate the associations between nine telomere length-associated SNPs and risk for five common cancer types (breast, lung, colorectal, ovarian and prostate cancer, including subtypes) using data on 51,725 cases and 62,035 controls. The long TL genetic score was significantly associated with increased risk of lung adenocarcinoma (P=6.3E -15), with an estimated odds ratio of 2.78. Under Mendelian randomization assumptions, this estimate was interpreted as the odds ratio for lung adenocarcinoma corresponding to a 1000 base pair increase in telomere length. The SNP score was not associated with other cancer types or subtypes. In the second study of this dissertation (Chapter 3), I estimated the associations between telomere length (measured by quantitative PCR using saliva DNA) and concurrent and past smoking status, reported biennially for up to 16 years prior to telomere length measurement, using data from the Health and Retirement Study (n=5,624). Smoking was associated with shorter telomere length when using prospective data on smoking status among men and women, but the association was strongly attenuated in cross-sectional analyses among men. This attenuation was largely due to a higher rate of smoking cessation during the study period among males with shorter telomere length compared to males with longer telomere length. Short telomere length was also associated with poorer overall health in men, suggesting that male smokers with short telomere length were more likely to quit smoking due to poor health. Analyses of years since cessation, smoking duration, and pack-years all support the hypothesis that increased cigarette use shortens telomere length. In the third study of this dissertation (Chapter 4), I investigated the association between arsenic exposure and telomere length, and the association between telomere length and incident arsenical skin lesion in the Health Effects of Arsenic Longitudinal Study (HEALS) in Araihazar, Bangladesh. In this prospective study, baseline telomere length was assessed in skin lesion-free subjects who were followed for up to 12 years. No association was observed between baseline arsenic exposure and telomere length. However, we observed higher incident skin lesion risk with shorter telomere length (Ptrend =4.6E-5), with odds ratios of 3.05, 1.30, and 1.21 for the first (shortest), second, and third telomere length quartiles compared to the longest. The role of telomere length as a biomarker of cancer appears to be striking yet nuanced. Addressing the existing knowledge gaps is a critical step towards clarifying the causal relationship between telomere length and cancer, and ultimately, improving cancer prediction and prevention.
Keywords: Cancer screenings; Health Conditions and Status; Older Adults; Risk Factors; Telomeres

Studying Cognitive Aging and Dementia in the Health and Retirement Study: Design and Measurement Strategies to Improve Research - M. Maria Glymour; Scott M Hofer (National Institute on Aging, 2016)
Keywords: cognitive aging; Dementia

Subjective Age and Changes in Memory in Older Adults - Yannick Stephan; Angelina R Sutin; Caudroit, Johan; Antonio Terracciano (The Journals of Gerontology Series B: Psychological Sciences and Social Sciences, 2016)
Objective. The subjective experience of aging, indexed by how old or young an individual feels, has been related to well-being and health-related outcomes among older adults. The present study examined whether subjective age is associated with memory level and changes, as indexed by measures of immediate and delayed recall. A complementary purpose was to test the mediating role of depressive symptoms and physical activity in the relation between subjective age and memory changes. Method. Participants were drawn from three waves of the Health and Retirement Study. Subjective age, baseline memory measures, and covariates were assessed during the 2008 wave (N = 5809), depressive symptoms and physical activity were assessed again in the 2010 wave, and the follow-up memory measures were assessed in the 2012 wave. Results. Regression analyses that included demographic, metabolic, and vascular covariates revealed that a younger subjective age at baseline was associated with better concurrent performance and with slower decline in immediate and delayed recall. Bootstrap procedures indicated that fewer depressive symptoms mediated these associations. Additional analyses revealed that memory level and change were unrelated to changes in subjective age. Conclusion. Beyond chronological age, the subjective experience of age is associated with cognitive aging.
Keywords: Expectations; Health Conditions and Status

Subjective cognitive impairment of older adults: a comparison between the US and China - Bei Wu (International Journal of Methods in Psychiatric Research, 2016)
Subjective assessment may be incomparable across countries due to differences in reporting styles. Based on two nationally representative surveys from the US and China, this study used data from three anchoring vignettes to estimate to what extent the US and Chinese older adults aged 50 and above differed in their reporting styles of subjective cognitive impairment. Cross country differences of subjective cognitive impairment were then estimated, both before and after adjusting for reporting heterogeneity. Directly assessed word recall test scores were analyzed to evaluate whether findings based on subjective cognitive impairment was consistent with objective performance. The results revealed a discrepancy between self-reported subjective cognitive impairment and directly assessed memory function among older adults: while Chinese respondents reported lower severity levels of subjective cognitive impairment, the US respondents demonstrated better performance in immediate word recall tests. By accounting for differences in reporting styles using anchoring vignettes data, Chinese older adults showed higher levels of subjective cognitive impairment than the US older adults, which was consistent with results from direct assessment of memory function. Non-negligible differences are present in reporting styles of subjective cognitive impairment. Cross country comparison needs to take into account such reporting heterogeneity.
Keywords: Cross-National; Health Conditions and Status; Methodology

Subjective Life Expectancy: Differences by Smoking, Education and Gender - Sergei Scherbov; Bruno Arpino; Valeria Bordone (European Population Conference 2016, 2016)
Despite the well-known higher mortality rates among smokers than non-smokers, little investigation has focused on subjective survival probabilities (SSP) by smoking behaviour. We give attention to sub-group differences in subjective survival probabilities, comparing subjective predictions to objective ones (SP) and accounting for the role of education. We use biannual data from the Health and Retirement Study (HRS) from 2000 to 2012 carried out in the USA. Based on a sample of 23,895 respondents aged 50-89, we calculate, for each respondent, the “gap” between SSP and the estimated survival probability (SP) from the HRS data. We find that people currently smoking report lower survival probabilities especially if they are low educated. This is consistent with real mortality data that show higher mortality among these groups. When comparing subjective and objective survival probabilities we find that irrespectively of the smoking status, high educated people are more likely to correctly predict their survival probabilities than their low educated counterparts. Within education groups, people who smoked in the past are the best at predicting their mortality. Interestingly, those who currently smoke show the highest probability to incorrectly overestimate their survival probability (i.e., to underestimate the negative effect of smoking on mortality).
Keywords: Education; Gender Differences; Longevity; Mortality; Older Adults; Smoking

Sustained Obesity and Depressive Symptoms over 6 Years: Race by Gender Differences in the Health and Retirement Study. - Julia D. Carter; Shervin Assari (Front Aging Neurosci, 2016)
Although obesity and physical activity influence psychosocial well-being, these effects may vary based on race, gender, and their intersection. Using 6-year follow-up data of a nationally representative sample of adults over age of 50 in the United States, this study aimed to explore race by gender differences in additive effects of sustained high body mass index (BMI) and physical activity on sustained depressive symptoms (CES-D) and self-rated health (SRH). Data came from waves 7, 8, and 10 (2004-2010) of the Health and Retirement Study (HRS), an ongoing national cohort started in 1992. The study enrolled a representative sample of Americans ( = 19,280) over the age of 50. Latent factors were used to calculate sustained high BMI and physical activity (predictors) and sustained poor SRH and high depressive symptoms (outcomes) based on measurements in 2004, 2006, and 2010. Age, education, and income were confounders. Multi-group structural equation modeling (SEM) was used to test the additive effects of BMI and physical activity on depressive symptoms and SRH, where the groups were defined based on race by gender. Group differences were apparent in the direction and significance of the association between sustained high BMI and depressive symptoms. The association between sustained high BMI and depressive symptoms was positive and significant for White women ( = 0.03, = 0.007) and non-significant for White men ( = -0.03, = 0.062), Black men ( = -0.02, = 0.564) and Black women ( = 0.03, = 0.110). No group differences were found in the paths from sustained physical activity to depressive symptoms, or from physical activity or BMI to SRH. Sustained high BMI and high depressive symptoms after age 50 are positively associated only for White women. As the association between sustained health problems such as depression and obesity are not universal across race and gender groups, clinical and public health interventions and programs that simultaneously target multiple health problems may have differential effects across race by gender groups.

Self-employment and health: Barriers or benefits? - Cornelius A Rietveld; van Kippersluis, Hans; A. Roy Thurik (Health Economics (United Kingdom), 2015)
The self-employed are often reported to be healthier than wageworkers; however, the cause of this health difference is largely unknown. The longitudinal nature of the US Health and Retirement Study allows us to gauge the plausibility of two competing explanations for this difference: a contextual effect of self-employment on health (benefit effect), or a health-related selection of individuals into self-employment (barrier effect). Our main finding is that the selection of comparatively healthier individuals into self-employment accounts for the positive cross-sectional difference. The results rule out a positive contextual effect of self-employment on health, and we present tentative evidence that, if anything, engaging in self-employment is bad for one's health. Given the importance of the self-employed in the economy, these findings contribute to our understanding of the vitality of the labor force.
Keywords: Employment and Labor Force; Health Conditions and Status

Self-Rated Health, Social Engagement, and "Older Places" - Eric M Vogelsang (Sociology - LS, 2015)
This dissertation consists of three essays that are motivated by an aging world. Its primary goals are to (a) identify how older adult health and its correlates--with a particular focus on social engagement--systematically differ by residential context; and (b) consider the implications of subjective health changes across older ages. The first chapter explores how the type and intensity of older-adult social participation varies by county-level population density. Using the 2003 and 2011 waves of the Wisconsin Longitudinal Study (n=3,006), I find that older adults living in rural counties with relatively low population densities are less socially active than their counterparts in higher-density counties. I also find that just five (of twelve) social activities are related to better health; while only three are associated with health change. Chapter two examines relationships between older adult health and living in relatively older and younger municipalities. Using a national sample of almost 5,000 Japanese older adults over two decades, I employ growth curve models to estimate how self-rated health and self-rated health trajectories differs by local area age structure. I find older adults living in the "oldest places" of Japan are more likely to report less than good health, when compared to those living in younger areas. In addition, relatively high levels of social engagement among older adults living in oldest areas help mitigate even greater odds of reporting worse health in these places. Chapter three explores how two measures of self-rated health (SRH) change are related to mortality. Data come from the Asset and Health Dynamics survey--the "oldest-old" portion of the Health and Retirement Study--and follow 6,233 individuals over thirteen years. After controlling for morbidity, individual characteristics, and SRH, those who changed SRH categories between survey waves and those who retrospectively reported an improvement in health continue to have a greater risk of death; when compared to those with no change. These findings suggest that the well-established associations between SRH status and mortality may understate the risk of death for oldest-old individuals with recent subjective health improvements.
Keywords: Health Conditions and Status; Healthcare; Methodology

Sequential Patterns of Health Conditions and Financial Outcomes in Late Life: Evidence From the Health and Retirement Study - Hyungsoo Kim; Shin, Serah; Karen A. Zurlo (The International Journal of Aging and Human Development, 2015)
The cost and prevalence of chronic health conditions increase in late life and can negatively impact accumulated wealth. Based on the financial challenges midaged and older adults face, we sought to understand the evolution of distinctive sequences of chronic health conditions and how these sequences affect retirement savings. We used 10 waves of the Health and Retirement Study and tracked the health states and changes in wealth of 5,540 individuals. We identified five typical sequences of chronic health conditions, which are defined as follows: Multimorbidity, Comorbidity, Mild Disease, Late Event, and No Disease. Wealth accumulation differed across the five sequences. Multimorbidity and Comorbidity were the most costly sequences. Individuals with these health patterns, respectively, had 91,205 and 95,140, less net worth than respondents identified with No Disease. Our findings suggest policy makers consider sequential disease patterns when planning for the health-care needs and expenditures of older Americans.
Keywords: Demographics; Net Worth and Assets; Public Policy

The shadow of the past: Financial risk taking and negative life events - Alessandro Bucciol; Luca Zarri (Journal of Economic Psychology, 2015)
Based on data from the four 2004-2010 waves of the US Health and Retirement Study (HRS), we show that financial risk taking is significantly related to life-history negative events out of an individual's control. Using observed portfolio decisions to proxy for risk taking, we find correlation with two of such individual-specific events: having been victim of a physical attack and (especially) the loss of a child are associated with lower and less frequent investments in risky assets, with an intensity similar to that of the beginning, in 2008, of a collectively experienced event such as the recent financial crisis. We also find evidence that the correlation of risk taking with a child loss is long-lasting, as opposed to the correlation with a physical attack that disappears after few years. Our analysis is more in favor of a preference-based - rather than a belief-based - explanation of the observed change in risk taking. Overall our findings indicate that the past, especially through the loss of a child, casts a long shadow that extends over individuals' current decisions also within unrelated domains. 2015 Elsevier B.V.
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets; Risk Taking

Sicker and Poorer: The Consequences of Being Uninsured for People With Disability During the Medicare Waiting Period - Yin, Na (Health Services Research and Managerial Epidemiology, 2015)
Purpose: Disabled individuals younger than 65 years are entitled to Medicare coverage through the Social Security Disability Insurance (DI) program, but only if they have completed a 2-year waiting period. This is the first study that uses longitudinal panel data, the Health and Retirement Study, and examines whether and to what extent the health and economic status are affected among disability beneficiaries who are uninsured during the Medicare waiting period.Methods: In a quasiexperiment research design, using a difference-in-difference (diff-in-diff) estimator, we compare changes in health and economic outcomes pre-/postentering the DI program for disability beneficiaries with alternative public health insurance and those without.Results: The adjusted diff-in-diff estimates suggest that disability beneficiaries who are uninsured during the waiting period, compared to those who are insured, are 13.6 percentage point more likely to report poor health, 6.3 percentage point less likely to be in excellent health, declare more difficulties in activities of daily living, and 30 higher medical expenditures from out of pocket.Conclusions: The findings highlight punitive health and economic effects of the Medicare waiting period for uninsured disability beneficiaries. We also discuss the implications of the findings for the Affordable Care Act reform.
Keywords: Disabilities; Healthcare; Medicare/Medicaid/Health Insurance; Methodology

Slowed or Sidelined? The Effect of Normal Cognitive Decline on Job Performance Among the Elderly - Belbase, Anek; Khan, Mashfiqur R.; Alicia H. Munnell; Anthony Webb (Boston, MA, Center for Retirement Research at Boston College, 2015)
This paper examines the relationship between age-related cognitive decline and three potential workplace outcomes: 1) coping with increased job difficulty; 2) shifting to a less cognitively demanding job; and 3) retiring early. It uses data from the Health and Retirement Study (HRS) and the O NET database. Critical components of the analysis are the metric used to measure cognitive decline, inclusion of cognitive reserve as an independent variable, and the use of overlapping 10-year observation windows. A key limitation is that the study cannot conclusively discern a causal relationship between cognitive decline and workforce exit.
Keywords: Employment and Labor Force; Health Conditions and Status

Smoking and cognitive functioning at older ages: Evidence from the Health and Retirement Study - Padmaja Ayyagari; Asia Sikora Kessler (Journal of the Economics of Ageing, 2015)
It has long been established that smoking has detrimental health effects on the human body and leads to early mortality. However, the evidence regarding the link between smoking behavior and cognitive function in old age is mixed. While nicotine has been shown to improve cognitive functioning in some medical studies, current smokers typically perform worse than non-smokers on cognitive tests in population based studies. We use the Health and Retirement Study to evaluate the role of unobserved factors in explaining these conflicting findings. Results from individual fixed effects models show that much of the lower cognitive function of current and former smokers relative to never smokers can be attributed to unobserved differences between these groups.
Keywords: Demographics; Health Conditions and Status; Methodology

Smoking, Heavy Drinking, and Depression among U.S. Middle-Aged and Older Adults - An, Ruopeng; Xiang, Xiaoling (Preventive Medicine, 2015)
Objective To examine the relationship between smoking, heavy drinking and depression among U.S. middle-aged and older adults. Method Individual-level data came from 1992 2012 waves of the Health and Retirement Study. Smoking was ascertained from self-reported cigarette smoking status at the time of interview. Heavy drinking was defined as one or more drinks per day on average or four or more drinks on any occasion in the past three months for women, and two or more drinks per day on average or four or more drinks on any occasion in the past three months for men. Depression was defined as scoring three and above on the eight-item Center for Epidemiologic Studies Depression Scale. Cox proportional hazards regressions were performed to examine the relationship between smoking, heavy drinking and depression. Results Compared to non-smokers, smokers free from depression and heavy drinking at baseline were 20 (95 confidence interval: 12 28 ) and 34 (20 50 ) more likely to develop depression and engage in heavy drinking during follow-up period, respectively. Compared to non-depressed participants, participants with depression who were nonsmokers and non-heavy drinkers at baseline were 41 (14 74 ) and 18 (6 31 ) more likely to smoke and engage in heavy drinking during follow-up, respectively. Compared to non-heavy drinkers, heavy drinkers who were nonsmokers at baseline were 60 (26 104 ) more likely to smoke during follow-up. Conclusion Health promotion programs in midlife and older age should be mindful of the associations between smoking, heavy drinking and depression in order to improve intervention effectiveness.
Keywords: Demographics; Health Conditions and Status; Methodology; Other

Social Relationships, Gender, and Recovery From Mobility Limitation Among Older Americans. - Kenzie Latham; Philippa J Clarke; Gregory Pavela (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: Evidence suggests social relationships may be important facilitators for recovery from functional impairment, but the extant literature is limited in its measurement of social relationships including an over emphasis on filial social support and a paucity of nationally representative data. METHODS: Using data from Waves 4-9 (1998-2008) of the Health and Retirement Study (HRS), this research examines the association between social relationships and recovery from severe mobility limitation (i.e., difficulty walking one block or across the room) among older Americans. Using a more nuanced measure of recovery that includes complete and partial recovery, a series of discrete-time event history models with multiple competing recovery outcomes were estimated using multinomial logistic regression. RESULTS: Providing instrumental support to peers increased the odds of complete and partial recovery from severe mobility limitation, net of numerous social, and health factors. Having relatives living nearby decreased the odds of complete recovery, while being engaged in one's neighborhood increased the odds of partial recovery. The influence of partner status on partial and complete recovery varied by gender, whereby partnered men were more likely to experience recovery relative to partnered women. The effect of neighborhood engagement on partial recovery also varied by gender. Disengaged women were the least likely to experience partial recovery compared with any other group. DISCUSSION: The rehabilitative potential of social relationships has important policy implications. Interventions aimed at encouraging older adults with mobility limitation to be engaged in their neighborhoods and/or provide instrumental support to peers may improve functional health outcomes.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Family; Female; Humans; Interpersonal Relations; Male; Middle Aged; Mobility Limitation; Peer Group; Recovery of Function; Residence Characteristics; Sex Factors; Social Support; United States

Social relationships, positivity, and personality in older adulthood - Iveniuk, James (Social relationships, positivity, and personality in older adulthood, 2015)
In this dissertation, I examine the implications of personality traits for social relationships in older adulthood. My work brings together insights from mid-20th century sociological theory, recent work by social network scholars, and personality psychologists. I build upon these insights in order to examine not only if personality traits are important for social relationships, but also under what social and relational circumstances. The personality characteristic that I focus on in this dissertation is Positivity, which I conceptualize as a person's overall positive (i.e. upbeat and socially desirable) characteristic patterns of thought and behavior. I measure Positivity using structural equation modeling techniques, applied to a Big Five personality battery in the National Social Life, Health, and Aging Project (NSHAP), a nationally representative, longitudinal survey of older adults. I then employ Positivity scores in three empirical studies. In the first study, I examine older adults' social networks, and I find that Positivity is associated with feeling closer to one's confidants, and being more likely to open up to them about one's health. I also find that Neuroticism (emotional instability) is associated with being more likely to talk to one's friends about one's health. In the second study I use dyadic data from NSHAP to examine the implications of traits for marital conflict, with a focus on gender. I find that the Positivity of a husband is associated with reduced marital conflict according to the reports of his wife, but that a wife's Positivity is not associated with conflict according to her husband. In the final study I examine the implications of Positivity for the diagnosis of chronic conditions, using a combination of biomeasures and self-reports. I find that individuals who are more positive are more likely to be undiagnosed for their hyperglycemia, but not hypertension. I relate this finding to theories of doctor-patient interaction, as well as differences in medical procedures for diagnosing these two chronic conditions. I conclude by offering possibilities for sociological research on personality, arguing that issues related to personality cut across existing subfields of the discipline, and that these issues relate to key questions in sociological theory.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2015 Last updated - 2015-04-14 First page - n/a
Keywords: Adult children; Health Conditions and Status; Healthcare; Methodology

Social Resource Factors that Influence Cognitive Functioning of Aging Black Adults - Swett, Laura (Social Resource Factors that Influence Cognitive Functioning of Aging Black Adults, 2015)
Social workers have found that aging adults are often challenged by reduced cognitive functioning, which impacts their health and mental health. Recent advances in knowledge indicate that social resources such as quality of emotional support and social integration can slow cognitive decline. Aging Black persons are twice more likely to have cognitive impairment than aging White persons. However, the majority of studies investigating associations or predictors of cognitive health are comprised of primarily White samples, and little is known regarding the effect of social resource factors on cognition in aging Black adults. Data for the study came from the 2010 wave of the Health and Retirement Study (HRS), an ongoing, longitudinal, population-based cohort study of adults ages 50 to 98. The analyzed sample was comprised of 338 men and 699 women who self-identified as African American/Black. Controlling for factors known to influence cognitive functioning, a multiple regression analysis of four categories of social resources was conducted, by gender, to determine their effect on global cognitive functioning: quality of social supports, social networks, social integration, and social influence. For Black men, emotional support from family and frequency of contact with their children were predictive of global cognition. For Black women, emotional support from friends was positively predictive of global cognition. Further, locus of control perceived constraints was inversely related with global cognition in men, while education was positively predictive of global cognition across gender. The findings demonstrate that the evaluative aspects of social relationships (perceptions of support) are important in predicting cognitive functioning for both genders, and the structural components (types of relationships or frequency of contacts) are important in predicting cognitive functioning for men. Additionally, this study validated the role of gender as a moderator between quality of social supports and global cognition, and as a moderator between social networks and global cognition in aging Black persons. Research grounded in intersectionality theory yielded unique information for Black men and women that is applicable for evidence-based practice interventions. Practices targeting the reduction of constraints and strengthening family, friend, and children networks in men, and practices assisting women in strengthening their friendship networks, may mitigate their cognitive decline and increase their global cognition as they age.
Copyright - Copyright ProQuest Dissertations Publishing 2015 Last updated - 2015-08-28 First page - n/a
Keywords: Demographics; Event History/Life Cycle; Gerontology; Health Conditions and Status; Healthcare; Methodology; Other; Women and Minorities

Social Status and Personality Traits - Alessandro Bucciol; Cavasso, Barbara; Luca Zarri (Journal of Economic Psychology, 2015)
We provide direct evidence on the relationship between social status and personality traits. Using survey data from the 2006-2012 waves of the US Health and Retirement Study, we show that self-perceived social status is associated with all the Big Five personality traits, after controlling for observable characteristics that arguably reflect one's actual status. We also construct an objective status measure that in turn is associated with personality traits. Objectively measured status is positively but not highly correlated with its subjective counterpart. When incorporated in a regression specification, it still leaves room for significant correlations between personality traits and status perception: traits such as openness, conscientiousness and extraversion predict a higher self-positioning on the social ladder, while agreeableness and neuroticism predict a lower one. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Demographics; Expectations; Health Conditions and Status; Income

Socioeconomic stratification and multidimensional health trajectories: evidence of convergence in later old age. - Xiao Xu; Jersey Liang; Joan M. Bennett; Anda Botoseneanu; Heather G. Allore (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: This research sought to examine socioeconomic stratification in the joint trajectories of physical, emotional, and cognitive functioning among older Americans and how it differs by age groups. METHODS: We used data from a nationally representative sample of 9,237 Americans age 65 or older from the Health and Retirement Study, who were observed biennially from 1998 to 2010. Joint trajectories of physical, emotional, and cognitive functioning were characterized using a group-based mixture model. We then applied multinomial logistic regression analysis to evaluate their linkages with socioeconomic status and how the linkages differ by age groups. RESULTS: We identified four distinct patterns of joint changes in physical, emotional, and cognitive functioning over time. Accounting for 29.3%, 23.5%, 24.5%, and 22.6% of the older Americans, respectively, these trajectory patterns characterized groups of individuals experiencing minimal to severe levels of impairment and deterioration. Lower education, income, and net worth were associated with trajectories featuring greater impairment or more rapid deterioration in these functional dimensions. Disparities based on education, however, attenuated in later old age, whereas health benefits associated with higher income and higher net worth persisted into advanced age. DISCUSSION: Distinct patterns of joint trajectories of physical, emotional, and cognitive functioning exist in old age. There were significant socioeconomic differences in the joint trajectories, with education-based inequality in health converging in later old age. Further research identifying strategies to alleviate the disproportionate burden of poor multidimensional health trajectories in lower socioeconomic groups is important.
Keywords: Aged; Aged, 80 and over; Aging; Cognition Disorders; Disabled Persons; Educational Status; Female; Health Status; Humans; Male; Social Class; United States

Sources of Increasing Differential Mortality Among the Aged by Socioeconomic Status - Barry Bosworth; Gary T. Burtless; Zhang, Kan (Boston College, 2015)
This paper uses data from the Health and Retirement Study (HRS) to explore the extent and causes of widening differences in life expectancy by socioeconomic status (SES) for older persons. We construct alternative measures of SES using educational attainment and average (career) earnings in the prime working ages of 41-50. We also use information on causes of death, health status and various behavioral indicators (smoking, drinking, and obesity) that are believed to be predictors of premature death in an effort to explain the causes of the growing disparities in life expectancy between people of high and low SES. The paper finds that: There is strong statistical evidence in the HRS of a growing inequality of mortality risk by SES among more recent birth cohorts compared with cohorts born before 1930. Both educational attainment and career earnings as constructed from Social Security records are equally useful indicators of SES, although the distinction in mortality risk by education is greatest for those with and without a college degree. There has been a significant decline in the risk of dying from cancer or heart conditions for older Americans in the top half of the income distribution, but we find no such reduction of mortality risk in the bottom half of the distribution. The inclusion of the behavioral variables and health status result in substantial improvement in the predictions of mortality, but they do not identify the sources of the increase in differential mortality. The policy implications of the findings are: Indexing the retirement age to increases in average life expectancy to stabilize OASDI finances may have unintended distributional consequences, because most mortality gains have been concentrated among workers in the top half of the earnings distribution. The fact that we cannot identify the sources of the increase in differential mortality contributes to uncertainty about the distributional effects of increases in the retirement age in future years.
Keywords: Demographics; Expectations; Health Conditions and Status; Methodology

Spousal Effects in Smoking Cessation: Matching, Learning, or Bargaining? - McGeary, Kerry Anne (Eastern Economic Journal, 2015)
Previous research studying the correlation in smoking behavior between spouses has discounted the role of bargaining or learning. Using the Health and Retirement Study, which contains information on smoking cessation and spouse s preferences, this paper presents an essential investigation of the impact of spousal bargaining or learning on the decision to cease smoking. We find that, regardless of gender, when one member of a couple ceases smoking this induces the other member to cease smoking through bargaining. Further, we find that women demonstrate either altruistic behavior toward a spouse who has suffered a health shock, or learning from their spouse s health shock.
Keywords: Health Conditions and Status; Methodology; Net Worth and Assets

Spouse and Child Availability for Newly Disabled Older Adults: Socioeconomic Differences and Potential Role of Residential Proximity. - Choi, Hwajung; Robert F. Schoeni; Kenneth M. Langa; Michele M Heisler (J Gerontol B Psychol Sci Soc Sci, 2015)
OBJECTIVES: To examine the potential role of child and spousal availability in facilitating community-based care for disabled older adults. METHOD: We used the Health and Retirement Study, a nationally representative longitudinal study of older adults. The analysis sample included older adults who were nondisabled at baseline, but who then developed at least one activity of daily living (ADL) limitation over the subsequent 2-year period (N = 2,094). Using multivariate, multinomial logistic regression, we examined the association of child and spouse availability prior to disablement of the older adults with ADL care receipt status after the onset of disablement, after adjusting for other sociodemographic and clinical characteristics. RESULTS: Lower socioeconomic status (SES) was associated with less availability of a spouse but greater availability of children at baseline. Compared with older adults who had no children nearby (i.e., all children lived further than 30 miles), older adults who had at least one child living with or near them prior to the onset of the ADL limitation were less likely to go to a nursing home (adjusted odds ratio [AOR]: 0.26 for coresident; AOR: 0.44 for 1- 30 miles) and less likely to depend on formal care (AOR: 0.39 for coresident; AOR: 0.51 for 1-30 miles) after the onset of new ADL limitation/s. DISCUSSION: Understanding SES variations in the informal care resources, and potential role of child geographic availability, may inform the development of cost-effective community-based care programs and policies.
Keywords: Activities of Daily Living; Adult children; Aged; Aged, 80 and over; Aging; Disabled Persons; Female; Home Nursing; Humans; Male; Middle Aged; Nursing homes; Residence Characteristics; Social Class; Spouses

Spouses and depressive symptoms in older adulthood. - Pradeep, Neeti; Angelina R Sutin (Sci Rep, 2015)
Depressive symptoms may co-occur within couples and follow similar trajectories, but relatively little is known about this process in old age. This study thus examined the association between some spousal characteristics (spouse's depressive symptoms, age difference between spouses) and the trajectory of depressive symptoms in older adults. Participants ≥ 65 years old were drawn from the Health and Retirement Study (N = 12,010; Mean age = 70.60 and 69.16 for target husbands and wives, respectively). Depressive symptoms were measured with a short form of the Center for Epidemiological Studies Depression (CES-D) scale. Hierarchical Linear Modeling was used to model up to 9 assessments of depressive symptoms of target spouses (Mean number of CESD assessments per target spouse = 3, range 1-9). Depressive symptoms between spouses were correlated; convergence over time was modest. For both husbands and wives, having a younger spouse was associated with more depressive symptoms at age 65. These results suggest that there is concordance between spouses' depressive symptoms and that the age difference between spouses contribute to depressive symptoms as couples enter old age. The association between spouses' depressive symptoms is nearly as strong as the effect of each decade increase in age.
Keywords: Aged; depression; Female; Humans; Longitudinal Studies; Male; Sex Distribution; Spouses

SSA Permissions Consent History: 1992-2012 (Public Version) (Data Desription and Usage, 2015)
The Health and Retirement Study (HRS) is a national longitudinal study of the economic, health, marital, and family status, as well as public and private support systems, of older Americans. The HRS is a rich source of longitudinal, cross-sectional data for researchers and policymakers who study aging. Funding for the Health and Retirement Study is provided by the National Institute on Aging at NIH (U01 AG009740), with supplemental support from the Social Security Administration. The study is conducted by the Institute for Social Research (ISR) at the University of Michigan.
Keywords: Data collection; Meta-analyses; Survey Methodology

Subjective health expectations - Kim P. Huynh; Jung, Juergen (Journal of Policy Modeling, 2015)
Subjective health expectations are derived using data from the U.S. Health and Retirement Study (HRS). We first use a Bayesian updating mechanism to correct for focal point responses and reporting errors of the original health expectations variable. We then test the quality of the health expectations measure and describe its correlation with various health indicators and other individual characteristics. Our results indicate that subjective health expectations do contain additional information that is not incorporated in subjective mortality expectations and that the rational expectations assumption cannot be rejected for subjective health expectations. Finally, the data suggest that individuals younger than 70 years of age seem to be more pessimistic about their health than individuals in their 70s. 2015 Society for Policy Modeling.
Keywords: Employment and Labor Force; Expectations; Health Conditions and Status; Healthcare; Methodology; Other

Subjective life horizon and portfolio choice - Spaenjers, Christophe; Spira, Sven Michael (Journal of Economic Behavior & Organization, 2015)
Using data from a U.S. household survey, we examine the empirical relation between subjective life horizon (i.e., the self-reported expectation of remaining life span) and portfolio choice. We find that equity portfolio shares are higher for investors with longer horizons, controlling for gender-specific age effects, socio-economic characteristics, health, and optimism. Our result is robust to accounting for the endogeneity of equity market participation or instrumenting subjective life horizon with parental survival. Finally, we show that the effect of a shortening horizon on portfolio allocation is stronger for households without bequest motives.
Keywords: Bequests; Investment horizon; Life Expectancy; Portfolio choice; Subjective Expectations

Subjective mortality risk and bequests - Gan, Li; Gong, Guan; Michael D Hurd; Daniel McFadden (Journal of Econometrics, 2015)
This paper investigates the ability of subjective expectations about life expectancy to predict wealth holding patterns in later life. Based on panel data from the Asset and Health Dynamics among the Oldest Old, we estimate a structural life-cycle model with bequests. Each individual’s subjective survival rates in the future are estimated with data on his belief of survival probabilities to a target age. This estimation is build upon a Bayesian updating method developed in Gan et al. (2005). We find that life-cycle model using subjective survival rates performs better than using life-table survival rates in predicting wealth holdings. This result suggests that subjective survival expectations play an important role in deciding consumption and savings. In addition, the estimation results show that most bequests are involuntary or accidental.
Keywords: Bequests; Mortality; Older Adults

Subjective, Objective, and Observed Long-term Survival - Rafael D Romo; Sei J. Lee; Yinghui Miao; W John Boscardin (JAMA Internal Medicine, 2015)
Many professional guidelines recommend using life expectancy when considering diagnostic or treatment interventions in which the time to benefit may exceed patients’ survival.1 When subjected to such tests and treatments, these patients are put at risk for up-front harms with little chance of reaping benefits.2 Patients’ perceptions of prognosis are important. Clinicians who follow recommended guidelines may urge patients to change health routines to which they have become accustomed. Patients who underestimate their survival may choose to forego interventions that are likely to help them, while those who overestimate may choose to undergo interventions that are more likely to cause harm. However, little is known about how well older adults estimate their survival, the aim of this analysis. Methods We drew a sample of 64-, 69-, 74-, 79-, 84-, and 89-year-old participants in the 2000 wave of the Health and Retirement Study (HRS), a nationally representative, longitudinal, prospective cohort study of adults in the United States.3 Institutional review board approval for HRS was received from the University of California, San Francisco, Committee on Human Research. Informed consent was obtained by HRS at the time of the interview. Our variable of interest was participants’ subjective estimate of long-term survival, assessed by the question, “What is the percent chance you will live to be x or more?” where x was 75, 80, 85, 90, 95, or 100 years old. Our sampling strategy ensured that all participants predicted survival across the same period. We calculated an objective estimate of life expectancy using the Lee life expectancy calculator.4 Observed survival was determined using mortality through 2010 (confirmed using the National Death Index). We compared participants’ subjective estimates to observed survival (using the C statistic) and the objective estimates (using a best-fit analysis). Participants were classified as underestimating or overestimating their survival if their estimate was more than 25 percentage points less or greater than the calculated prediction, respectively. Results A total of 2018 respondents of the specified ages were interviewed directly in the 2000 wave of the HRS, and our final sample included 1722 participants who had complete responses necessary for the calculator (56% female, 88% white). We combined the 84- and 89-year-olds because of the small number of respondents in each group. Overall, discrimination was moderate for participants’ subjective estimates of survival compared with observed survival (C statistic = 0.62; P < .001). The 64- and 69-year-olds were moderately able to estimate their survival (C statistic = 0.62 and 0.58, respectively; P < .001 for both), but older participants fared no better than chance (Table). Substantial dissimilarity was seen between participants’ subjective and the objective estimates of survival (Figure). Overall, 54.7% of participants had estimates similar to the objective calculation; however, 32.7% underestimated and 11.5% overestimated. Underestimation was relatively similar across age groups, but overestimation increased significantly with age (Table) (P < .001). Discussion Our findings have important implications for clinicians. First, approximately half the time, participants accurately estimated survival compared with an objective clinical estimate, and when in error, they were more likely to underestimate than overestimate. Consequently, disclosing prognosis is not necessarily bad news. Second, because of the substantial dissimilarity between the subjective and objective estimates, patients may be hesitant to follow guideline recommendations to change long-standing regimens. Third, our findings make a case for using prognostic calculators, which were more accurate than participants’ subjective estimates and have been shown to be superior to clinician estimates.5 Fourth, participants in the HRS were willing to make an estimate of their survival and report it. Previous research suggests that older adults are generally willing to discuss long-term prognosis.6 Clinicians should solicit patients’ individual perception of prognosis and use this information as a starting point for further discussion, particularly among older patients who may be more prone to errors. Then, in conjunction with prognostic tools, they can begin to bridge the gap between subjective and objective estimates of survival.
Keywords: Health Conditions and Status; Mortality; Older Adults; Self-reported health

Subjective Well-Being in Context: County- and State-Level Socioeconomic Factors and Individual Moderators - Luhmann, Maike; Murdoch, James C., III; Louise C Hawkley (Social Psychological and Personality Science, 2015)
Subjective well-being (SWB) is not only influenced by people's individual characteristics but also by characteristics of the places where they live. Using data from the Health and Retirement Survey (N = 5,975), we examined whether two indicators of the socioeconomic context (unemployment and poverty rates) are associated with SWB in older adults. The main findings were (a) these contextual variables are differentially related to SWB on the county level and state level in terms of strength and direction, highlighting the importance of distinguishing between different levels of analysis; (b) poverty rate tends to be more strongly associated with life satisfaction and positive affect than with negative affect; and (c) county-level poverty rate is more strongly related to positive affect in poor individuals and county-level unemployment rate is more strongly related to SWB in nonretired individuals, suggesting that the socioeconomic context matters more for people who are directly affected by it.
Keywords: Demographics; Employment and Labor Force; Expectations; Income

Substance-use coping and self-rated health among US middle-aged and older adults. - Pia M Mauro; Sarah L. Canham; Silvia S Martins; Adam P Spira (Addict Behav, 2015)
The prevalence of alcohol, drug, and tobacco use among US middle-aged and older adults is increasing. A subset of this population uses substances to cope with stress, but the characteristics of these individuals, and the association between substance-use coping and health outcomes remain unclear. We identified correlates of substance-use coping and measured its association with self-rated health in a community-based sample of adults aged 54-99 in the Health and Retirement Study (HRS). In the 2008 HRS, 1351 participants reported their frequency of prescription/other drug-, alcohol-, and cigarette-use coping with stress and reported self-rated health (excellent/very good, good, or fair/poor); 1201 of these participants also reported self-rated health in 2010. One in six participants frequently used substances to cope. The oldest participants were least likely to engage in frequent alcohol-use coping. Those with elevated depressive symptoms were more likely to frequently engage in cigarette- and prescription/other drug-use coping. In multivariable-adjusted analyses, participants who frequently used cigarettes (compared to participants who infrequently used cigarettes) to cope had 2.7 times (95% CI=1.1-6.7) the odds of poor (vs. excellent) self-rated health. Relative to participants who infrequently used prescription/other drugs to cope, participants who frequently used prescription/other drugs to cope had 2.4 times (95% CI=1.1-5.1) the odds of reporting poor self-rated health. The association between prescription/other drug-use coping in 2008 and self-rated health in 2010 was statistically significant (relative OR=3.5, 95% CI=1.7-7.2). Participants engaging in substance-use coping likely have particular demographic and clinical characteristics. Interventions to reduce substance-use coping may prevent adverse health outcomes.
Keywords: Adaptation, Psychological; Aged; Aged, 80 and over; Alcohol Drinking; depression; Female; Health Status; Humans; Male; Middle Aged; Smoking; Substance-Related Disorders; United States

Symptom Trends in the Last Year of Life From 1998 to 2010 A Cohort Study - Adam E Singer; Meeker, Daniella; Joan M Teno; Lynn, Joanne; June R Lunney; Karl A Lorenz (Annals of Internal Medicine, 2015)
Background: Calls for improvement in end-of-life care have focused attention on the management of pain and other troubling symptoms at the end of life. Objective: To describe changes in pain intensity and symptom prevalence during the last year of life from 1998 to 2010. Design: Observational study. Setting: The HRS (Health and Retirement Study), a nationally representative longitudinal survey of community-dwelling U. S. residents aged 51 years or older. Participants: 7204 HRS participants who died while enrolled in the study and their family respondents. Measurements: Proxy-reported pain during the last year of life and other symptoms for at least 1 month during the last year of life. Trends in pain intensity and symptom prevalence were analyzed for all decedents and within the categories of sudden death, cancer, congestive heart failure or chronic lung disease, and frailty. Results: Between 1998 and 2010, proxy reports of the prevalence of any pain increased for all decedents from 54.3 (95 CI, 51.6 to 57.1 ) to 60.8 (CI, 58.2 to 63.4 ), an increase of 11.9 (CI, 3.1 to 21.4 ). Reported prevalences of depression and periodic confusion also increased for all decedents by 26.6 (CI, 14.5 to 40.1 ) and 31.3 (CI, 18.6 to 45.1 ), respectively. Individual symptoms increased in prevalence among specific decedent categories, except in cancer, which showed no significant changes. The prevalence of moderate or severe pain did not change among all decedents or in any specific decedent category. Limitation: Use of proxy reports and limited information about some patient and surrogate variables. Conclusion: Despite national efforts to improve end-of-life care, proxy reports of pain and other alarming symptoms in the last year of life increased from 1998 to 2010.
Keywords: Health Conditions and Status; Methodology; Retirement Planning and Satisfaction

Satisfaction with aging and use of preventive health services. - Eric S Kim; Kyle D Moored; Hannah L. Giasson; Jacqui Smith (Prev Med, 2014)
OBJECTIVE: Preventive health service use is relatively low among older age groups. We hypothesized that aging satisfaction would be associated with increased use of preventive health services four years later. METHOD: We conducted multiple logistic regression analyses on a sample of 6177 people from the Health and Retirement Study, a nationally representative study of U.S. adults over the age of 50 (M age=70.6; women n=3648; men n=2529). RESULTS: Aging satisfaction was not associated with obtaining flu shots. However, in fully-adjusted models, each standard deviation increase in aging satisfaction was associated with higher odds of reporting service use for cholesterol tests (OR=1.10, 95% CI=1.00-1.20). Further, women with higher aging satisfaction were more likely to obtain a mammogram/x-ray (OR=1.17, 95% CI=1.06-1.29) or Pap smear (OR=1.10, 95% CI=1.00-1.21). Among men, the odds of obtaining a prostate exam increased with higher aging satisfaction (OR=1.20 95% CI=1.09-1.34). CONCLUSION: These results suggest that aging satisfaction potentially influences preventive health service use after age 50.
Keywords: Aged; Aged, 80 and over; Aging; Chronic disease; Female; Health Behavior; Health Knowledge, Attitudes, Practice; Humans; Influenza Vaccines; Logistic Models; Male; Mammography; Middle Aged; Patient Acceptance of Health Care; Patient Satisfaction; Personal Satisfaction; Preventive Health Services; Prostatic Neoplasms; Surveys and Questionnaires; United States; Vaginal Smears

The schooling of offspring and the survival of parents - Esther M Friedman; Robert D. Mare (Demography, 2014)
Contemporary stratification research on developed societies usually views the intergenerational transmission of educational advantage as a one-way effect from parent to child. However, parents' investment in their offspring's schooling may yield significant returns for parents themselves in later life. For instance, well-educated offspring have greater knowledge of health and technology to share with their parents and more financial means to provide for them than do their less-educated counterparts. We use data from the 1992-2006 Health and Retirement Study (HRS) to examine whether adult offspring's educational attainments are associated with parents' survival in the United States. We show that adult offspring's educational attainments have independent effects on their parents' mortality, even after controlling for parents' own socioeconomic resources. This relationship is more pronounced for deaths that are linked to behavioral factors: most notably, chronic lower respiratory disease and lung cancer. Furthermore, at least part of the association between offspring's schooling and parents' survival may be explained by parents' health behaviors, including smoking and physical activity. These findings suggest that one way to influence the health of the elderly is through their offspring. To harness the full value of schooling for health, then, a family and multigenerational perspective is needed.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare

Self-employment of older Americans: do recessions matter? - Biehl, Amelia M.; Gurley-Calvez, Tami; Hill, Brian (Small Business Economics, 2014)
As high unemployment rates linger following the latest recession, job opportunities can be sparse, especially for older workers. This might prompt older Americans to seek out opportunities in self-employment. Alternatively, recession-related decreases in economic activity might make self-employment less attractive. Using the Health and Retirement Study, we find that unemployed respondents are more likely to enter self-employment and that these decisions are clearly affected by recessions, although the effects differ by recession and gender. Unlike men, women s self-employment decisions are very sensitive to other sources of household income, and women are less likely to become self-employed the deeper the recession.
Keywords: Demographics; Employment and Labor Force; Methodology; Other; Public Policy

Self-rated health changes and oldest-old mortality. - Eric M Vogelsang (J Gerontol B Psychol Sci Soc Sci, 2014)
OBJECTIVES: This study explores how 2 measures of self-rated health (SRH) change are related to mortality among oldest-old adults. In doing so, it also considers how associations between SRH and mortality may depend on prior SRH. METHOD: Data come from the Asset and Health Dynamics survey--the oldest-old portion of the Health and Retirement Study-and follow 6,233 individuals across 13 years. I use parametric hazard models to examine relationships between death and 2 measures of short-term SRH change--a computed measure comparing SRH at time t-1 and t, and a respondent-provided retrospectively reported change. RESULTS: Respondents who demonstrate or report any SRH change between survey waves died at a greater rate than those with consistent SRH. After controlling for morbidity, individual characteristics, and SRH, those who changed SRH categories between survey waves and those who retrospectively reported an improvement in health continue to have a greater risk of death, when compared with those with no change. DISCUSSION: These findings suggest that the well-established associations between SRH status and mortality may understate the risk of death for oldest-old individuals with recent subjective health improvements.
Keywords: Aged; Aged, 80 and over; Diagnostic Self Evaluation; Female; Health Status; Humans; Longitudinal Studies; Male; Mortality; Proportional Hazards Models; Randomized Controlled Trials as Topic; Risk; United States

Self-rated health in the last 12 years of life compared to matched surviving controls: the Health and Retirement Study. - Stenholm, Sari; Pentti, Jaana; Ichiro Kawachi; Westerlund, Hugo; Mika Kivimäki; Vahtera, Jussi (PLoS One, 2014)
Self-rated health (SRH) is a valid measure of health status and associated with mortality. Based on individual-level biannual repeat data on SRH we sought to characterize the natural history of poor SRH during the 12 years prior to death in men and women in different age groups. We conducted a retrospective analysis of the Health and Retirement Study participants who died between 1998 and 2010 and had at least two SRH measurements in the 12 years prior to death. We used a nested case-control design to compare SRH trajectories of deceased men and women aged 30-64, 65-79 and 80 years versus surviving participants. The cases comprised 3,350 deceased participants who were matched to surviving controls (n = 8,127). SRH was dichotomized into good vs. poor health. Men and women dying at age 65-79 and ≥ 80 years had 1.5 to 3 times higher prevalence of poor SRH already 11-12 years prior to death compared to surviving controls. The risk estimates remained statistically significant even after adjusting for life-style related risk factors and diagnosed diseases. Prevalence of poor SRH before death was lowest among those aged ≥ 80 years and highest in 30-64 year-olds. In conclusion, men and women who subsequently die perceive their health worse already 11-12 years prior to death compared to their surviving controls.
Keywords: Adult; Aged; Aged, 80 and over; Diagnostic Self Evaluation; Female; health; Health Status; Humans; Life Style; Male; Middle Aged; Mortality; Retirement; Retrospective Studies

Sex differences in the construct overlap of frailty and depression: evidence from the health and retirement study - Matthew C. Lohman; Dumenci, Levent; Briana Mezuk (Journal of the American Geriatrics Society, 2014)
OBJECTIVES: To determine the degree of diagnostic overlap between frailty and depression and to investigate whether sex differences in symptom endorsement influence this overlap. DESIGN: Cross-sectional latent class analysis. SETTING: Data were from the 2008 wave of the Health and Retirement Study, a nationally representative longitudinal survey of health characteristics of older adults. PARTICIPANTS: Community-dwelling adults aged 65 and older completing a general health questionnaire and consenting to physical measurements (N=3,665). MEASUREMENTS: Frailty was measured using criteria developed in the Cardiovascular Health Study, and depressive symptoms were measured using the eight-item Center for Epidemiologic Studies Depression scale. RESULTS: Frailty and depression were best modeled as two distinct but highly correlated constructs with three and four classes of symptom response, respectively. Measurement overlap was high in men and women. Approximately 73 of individuals with severe depressive symptoms and 86 with primarily somatic depressive symptoms were categorized as concurrently frail. The degree of construct overlap between depression and frailty did not significantly vary according to sex, but women were significantly more likely to endorse all frailty and depressive symptoms. CONCLUSION: Measures of depression and frailty identify substantially overlapping populations of older men and women. More-frequent endorsement of depressive symptoms, but not differential endorsement of somatic symptoms, may contribute to the higher prevalence of frailty in women. The symptom of exhaustion is particularly important to the correlation between these two conditions. Findings will inform clinician and researcher efforts to refine the definition of geriatric syndromes such as frailty and to develop effective interventions.
Keywords: Health Conditions and Status; Methodology

Short- and long-term associations between widowhood and mortality in the United States: longitudinal analyses. - J Robin Moon; M. Maria Glymour; Anusha M Vable; Sze Y Liu; S. V. Subramanian (J Public Health (Oxf), 2014)
BACKGROUND: Past research shows that spousal death results in elevated mortality risk for the surviving spouse. However, most prior studies have inadequately controlled for socioeconomic status (SES), and it is unclear whether this 'widowhood effect' persists over time. METHODS: Health and Retirement Study participants aged 50+ years and married in 1998 (n = 12 316) were followed through 2008 for widowhood status and mortality (2912 deaths). Discrete-time survival analysis was used to compare mortality for the widowed versus the married. RESULTS: Odds of mortality during the first 3 months post-widowhood were significantly higher than in the continuously married (odds ratio (OR) for men = 1.87, 95% CI: 1.27, 2.75; OR for women = 1.47, 95% CI: 0.96, 2.24) in models adjusted for age, gender, race and baseline SES (education, household wealth and household income), behavioral risk factors and co-morbidities. Twelve months following bereavement, men experienced borderline elevated mortality (OR = 1.16, 95% CI: 1.00, 1.35), whereas women did not (OR = 1.07, 95% CI: 0.90, 1.28), though the gender difference was non-significant. CONCLUSION: The 'widowhood effect' was not fully explained by adjusting for pre-widowhood SES and particularly elevated within the first few months after widowhood. These associations did not differ by sex.
Keywords: Bereavement; Female; Humans; Longitudinal Studies; Male; Middle Aged; Mortality; Risk Factors; Sex Factors; Socioeconomic factors; Time Factors; United States; Widowhood

Snapshots of Mixtures of Affective Experiences in a Day: Findings from the Health and Retirement Study - Jacqui Smith; Lindsay H Ryan; Tara L Queen; Sandra E Becker; Gonzalez, Richard (Journal of Population Ageing, 2014)
In 2009, a representative subsample of participants in the Health and Retirement Study (HRS: N = 5333; Age 50 101) responded to a short day reconstruction self-administered questionnaire that asked about their time and experiences on seven activities the previous day. We evaluate the quality and reliability of responses to this 10-min measure of experienced well-being and compare the properties and correlates of three intensity-based composites reflecting mixtures of activity-linked affective experiences (Activity-Positive Affect, Activity-Negative Affect, and Net Affect), and a frequency-based index, Activity Affective Complexity, that summarizes the proportion of activities that include a mixture of positive and negative affective experiences regardless of intensity. On average, older adults reported that 36 of the activities in their day provided some mixture of feelings (e.g., interested and frustrated). Regression models revealed differential associations for the four constructs of affective well-being with socio-demographic factors, physical and mental health, and proximal indicators of the day s context. We conclude that the HRS short day reconstruction measure is reliable and discuss the conceptual issues in assessing, summarizing, and interpreting the complexity of emotional experience in older adults.
Keywords: Demographics; Expectations; Health Conditions and Status; Methodology

The social environment, APOE-e4, and dementia: The social environment as a moderating factor among individuals genetically predisposed to develop dementia - Judith L Poey (The social environment, APOE-e4, and dementia: The social environment as a moderating factor among individuals genetically predisposed to develop dementia, 2014)
Many studies have shown a relationship between the APOE-e4 allele and dementia, as well as a relationship between the social environment and dementia. However, relatively little investigation into the potential moderating effect of the social environment on the relationship between the APOE-e4 allele and cognitive well-being has been reported. Further, studies that did examine these relationships typically have employed clinical populations, along with regional and non-U.S. samples. This study contributed to the research literature, in part, by using the first U.S. nationally representative sample of older adults that included clinical diagnosis of cognition and dementia (Aging, Demographics, and Memory Study from the Health and Retirement Study). A combination of descriptive analyses and multinomial logistic regression models were used to investigate these relationships. Overall, the prevalence of unique APOE genotypic combinations was similar in the ADAMS sample as compared to samples taken from other developed nations. Descriptive results also showed that respondents with and without the APOE-e4 allele were only found to differ on race and ethnic status. Regression results indicated that the APOE-e4 allele was associated with a higher risk of cognitive difficulty, and that being more socially engaged and more socially connected to others was associated with a lower risk of cognitive difficulty and dementia. All aspects of the social environment, except social engagement, were found to moderate the relationship of the APOE-e4 allele to cognitive diagnosis. The relationship of the social environment to dementia, as well as its moderating influence, indicated a need for further investigation into the unique contributions of the social environment for cognitive well-being in later life.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2014-07-28 First page - n/a
Keywords: Demographics; Genetics; Health Conditions and Status; Methodology

Social regulatory processes in adulthood : responding to change and variability in proximal and distal social forces - Shannon T. Mejia (Social regulatory processes in adulthood : responding to change and variability in proximal and distal social forces, 2014)
Adult development and social experiences are intertwined, which has implications for social policy, health, and well-being across the lifespan. This dissertation explores the benefit and risk that close social partners bring to adults' lives, and the efficacy and consequences of engaging social resources to maintain well-being in the face of variability and change in their proximal and distal social environments. The first study, using a life course perspective and a macro analytic lens, traced experiences of financial loss in middle adulthood during the 2008 recession. Using the 2006 and 2010 waves of the Health and Retirement Study (n = 1,881; age range = 51 - 60 years), this study used conditional change models and path analysis to examine the extent to which increasing household complexity, giving help, receiving help, and relationship quality promoted or hindered the capacity to maintain a sense of control in the face of financial loss. Experiencing financial loss was directly associated with decreased control and giving help, and increased household complexity and receiving help. Experiences of financial loss indirectly decreased control through increased household complexity and decreased giving help. Although the experience of financial loss was distributed across differences in income and education, social resources patterned the engagement of interpersonal resources, which translated to engagement patterns that could compromise the sense of control. However, change in relationship quality, which did not systematically differ across experiences of financial loss, created pathways to support or hinder maintaining a sense of control while engaging interpersonal resources. The second study, informed by lifespan developmental theory and developmental systems theory, applied a micro analytic lens to closely examine the within-person processes that connect daily interactions within the social convoy to emotional well-being in older adulthood. Using data from the Personal Understanding of Life and Social Experiences Project, this study linked older adults' (N = 99; age mean = 63.29, SD = 7.93) satisfaction with their five closest social partners to daily experiences of positive and negative affect across 100 days. Multivariate multilevel models suggest that older adults' daily affect is more sensitive to the quality of daily interactions with closest compared to other social partners. The relative strength of positive and negative affect sensitivity also varied within levels of closeness. Negative affect was relatively more sensitive to interactions with the closest social partner, and positive affect was relatively more sensitive to interactions with other close social partners. This study also found emotional sensitivity to vary within individuals. Satisfying contact with other social partners dampened emotional sensitivity to the closest social partner on that day. These patterns differed across overall levels of contact satisfaction. Those with lower overall satisfaction had higher emotional sensitivity, and were less able to regulate the sensitivity of positive affect. Together, the findings from these studies suggest that: (a) how individuals engage their interpersonal resources in response to loss can facilitate or hinder the maintenance of control and well-being; (b) the strategies that individuals engage vary by the presence or absence of socioeconomic and socioemotional resources; and (c) social partners contribute to both emotional reaction and recovery, but this sensitivity can be up and down regulated by reaching out to other close social partners. Relationships with others therefore contribute to well-being by supporting (or hindering) the regulation of self, actions, and emotions. Regulation through close interpersonal ties illustrates a process that links developmental and life course trajectories.
Keywords: Health Conditions and Status; Net Worth and Assets; Public Policy

Social relationships, leisure activity, and health in older adults. - Chang, Po-Ju; Linda A. Wray; Lin, Yeqiang (Health Psychol, 2014)
OBJECTIVE: Although the link between enhanced social relationships and better health has generally been well established, few studies have examined the role of leisure activity in this link. This study examined how leisure influences the link between social relationships and health in older age. METHOD: Using data from the 2006 and 2010 waves of the nationally representative U.S. Health and Retirement Study and structural equation modeling analyses, we examined data on 2,965 older participants to determine if leisure activities mediated the link between social relationships and health in 2010, controlling for race, education level, and health in 2006. RESULTS: The results demonstrated that leisure activities mediate the link between social relationships and health in these age groups. Perceptions of positive social relationships were associated with greater involvement in leisure activities, and greater involvement in leisure activities was associated with better health in older age. CONCLUSION: The contribution of leisure to health in these age groups is receiving increasing attention, and the results of this study add to the literature on this topic, by identifying the mediating effect of leisure activity on the link between social relationships and health. Future studies aimed at increasing leisure activity may contribute to improved health outcomes in older adults.
Keywords: Aged; Aged, 80 and over; Female; Health Status; Humans; Interpersonal Relations; Leisure activities; Longitudinal Studies; Male; Middle Aged; United States

Social Security Programs and Retirement Around the World: Disability Insurance Programs and Retirement - Introduction and Summary - Courtney Coile; Kevin Milligan; David A Wise (NBER, 2014)
This is the introduction and summary to the sixth phase of an ongoing project on Social Security Programs and Retirement Around the World. The first phase described the retirement incentives inherent in plan provisions and documented the strong relationship across countries between social security incentives to retire and the proportion of older persons out of the labor force. The second phase documented the large effects that changing plan provisions would have on the labor force participation of older workers. The third phase demonstrated the consequent fiscal implications that extending labor force participation would have on net program costs–reducing government social security benefit payments and increasing government tax revenues. The fourth phase presented analyses of the relationship between the labor force participation of older persons and the labor force participation of younger persons in twelve countries. We found no evidence that increasing the employment of older persons will reduce the employment opportunities of youth and no evidence that increasing the employment of older persons will increase the unemployment of youth. The fifth phase on "Historical Trends in Mortality and Health, Employment, and Disability Insurance Participation and Reforms" was intended to set the stage for this current phase. This sixth phase of the ongoing ISS project is particularly related to the fifth phase (Wise, 2012) and the second phase (Gruber and Wise, 2004) of the project. This volume continues the focus of the previous volume on DI programs while extending the methodology to study retirement behavior used in the second phase to focus in particular on the effects of the DI programs. The key question this volume seeks to address is: given health status, to what extent are differences in labor force participation across countries determined by the provisions of disability insurance programs?
Keywords: Social Security

The Social Security Windfall Elimination and Government Pension Offset Provisions for Public Employees in the Health and Retirement Study - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (Social Security Bulletin, 2014)
This article uses Health and Retirement Study data to investigate the effects of Social Security's Windfall Elimination Provision (WEP) and Government Pension Offset (GPO) on Social Security benefits received by households. The provisions reduce benefits for individuals or the dependents of individuals whose work histories include jobs for which they were entitled to a pension and were not subject to Social Security payroll taxes ( noncovered employment). We find that about 3.5 percent of households are subject to either the WEP or the GPO, and that the provisions reduce the present value of their Social Security benefits by roughly one-fifth. Households affected by both provisions experience benefit reductions of about one-third. Under the WEP, the Social Security benefit reduction is capped at one-half of the amount of the pension from noncovered employment, which substantially reduces the WEP penalty and prevents the WEP adjustment from falling disproportionately on households in the lowest earnings category.
Date revised - 2015-04-01 Availability - URL:http://www.ssa.gov/policy/docs/ssb/ Publisher's URL
Keywords: Employment and Labor Force; Income; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security

Social support, social strain, loneliness, and well-being among older adults: An analysis of the Health and Retirement Study - Chen, Yixin; Feeley, Thomas Hugh (Journal of Social and Personal Relationships, 2014)
This study proposed that, among older adults, higher support and lower strain received from each of the four relational sources (spouse/partner, children, family, and friends) were associated with reduced loneliness and improved well-being and that loneliness might mediate the relationship between support/strain and well-being. Structural equation modeling was conducted using a national sample of adults aged 50 years and older (N=7,367) from the Health and Retirement Study. Findings indicated that support from spouse/partner and friends alleviated loneliness, while strain from all the four sources intensified loneliness; higher support and lower strain from various sources directly and indirectly improved well-being, with indirect effects mediated through reduced loneliness. It was concluded that, in later life, various sources of support/strain engender distinct effects on loneliness and well-being, and loneliness serves as one of the psychological pathways linking support/strain to well-being.
Keywords: Adult children; Health Conditions and Status; Other

Socioeconomic inequalities in health after age 50: Are health risk behaviors to blame? - Benjamin A Shaw; McGeever, Kelly; Elizabeth Vasquez; Agahi, Neda; Fors, Stefan (Social Science and Medicine, 2014)
Recent studies indicate that socioeconomic inequalities in health extend into the elderly population, even within the most highly developed welfare states. One potential explanation for socioeconomic inequalities in health focuses on the role of health behaviors, but little is known about the degree to which health behaviors account for health inequalities among older adults, in particular. Using data from the Health and Retirement Study (N = 19,245), this study examined the degree to which four behavioral risk factors smoking, obesity, physical inactivity, and heavy drinking are associated with socioeconomic position among adults aged 51 and older, and whether these behaviors mediate socioeconomic differences in mortality, and the onset of disability among those who were disability-free at baseline, over a 10-year period from 1998 to 2008. Results indicate that the odds of both smoking and physical inactivity are higher among persons with lower wealth, with similar stratification in obesity, but primarily among women. The odds of heavy drinking decrease at lower levels of wealth. Significant socioeconomic inequalities in mortality and disability onset are apparent among older men and women; however, the role that health behaviors play in accounting for these inequalities differs by age and gender. For example, these health behaviors account for between 23 and 45 of the mortality disparities among men and middle aged women, but only about 5 of the disparities found among women over 65 years. Meanwhile, these health behaviors appear to account for about 33 of the disparities in disability onset found among women survivors, and about 9-14 among men survivors. These findings suggest that within the U.S. elderly population, behavioral risks such as smoking and physical inactivity contribute moderately to maintaining socioeconomic inequalities in health. As such, promoting healthier lifestyles among the socioeconomically disadvantaged older adults should help to reduce later life health inequalities. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Demographics; Disabilities; Health Conditions and Status; Other

Socio-economic status over the lifecourse and internet use in older adulthood - Silver, Michelle Pannor (Ageing and Society, 2014)
This study explored associations between socio-economic status (SES) at different phases in the lifecourse and regular internet use among older adults. A sample (N=11,035) from the 2010 wave of the United States Health and Retirement Study was used. Odds ratios were estimated to explore the relationship between regular internet use in older adulthood and measures of SES in childhood and in adulthood, and cumulative SES. Findings provided support for the lifecourse perspective, suggesting that variations observed among older adults are reflective of cumulative experiences. Three main themes emerged: higher SES in childhood increased the odds of being an internet user in older adulthood; SES advantages tended to accumulate, so that having at least one period of high SES in the lifecourse increased the odds of being an internet user in older adulthood; age did not appear to modify the positive relationship between cumulative SES and internet use.
Keywords: Demographics; Other

Source of health insurance coverage and employment survival among newly disabled workers: Evidence from the health and retirement study - Matthew J Hill; Nicole Maestas; Kathleen J Mullen (Universitat Pompeu Fabra, 2014)
We use prospective longitudinal data on newly disabled older workers to examine the effect of employer sponsorship of health insurance (ESHI) on post-onset employment and disability insurance claiming. We compare outcomes of workers with ESHI and no access to spousal coverage prior to onset with outcomes of two comparison groups: individuals with ESHI who also have access to spousal coverage and those who are covered by a spouse’s employer prior to onset. We find evidence of "employment lock" among the 20 percent of individuals whose disabilities do not impact their immediate physical capacity but are associated with high medical costs.
Keywords: Disabilities; disability insurance; Disability onset; health; Health Insurance

Spousal social support and strain: impacts on health in older couples. - Lindsay H Ryan; Wylie H Wan; Jacqui Smith (Journal of Behavioral Medicine, 2014)
Using a nationally representative sample of couples aged 51+ in the United States (N = 1,923 couples), the current study investigated whether both partners' perceptions of relationship support and strain are associated with an individual's self-rated health and functional limitations. The sample had an average age of 67.17 years (SD = 9.0; range 50-97). Actor-Partner Interdependence Models adjusting for couple interdependencies were applied using multilevel models. After accounting for age, education, gender, race, and couple differences in length of marriage, results indicate that individual perceptions of support were significantly associated with higher self-rated health and fewer functional limitations. These individual-level benefits increased if the spouse also perceived positive support and low strain. Finally, the negative association of an individual's perceived support on functional limitations was greater in those with a spouse reporting low levels of perceived strain. Findings are discussed relative to theory on behavioral and psychological pathways between partners' perceptions of support and health.
Keywords: Health Conditions and Status; Marriage; Older Adults; Social Support; Stress

Subjective Socioeconomic Status in Daily Cognitive Functioning and Cognitive Aging - Zavala, Catalina (Subjective Socioeconomic Status in Daily Cognitive Functioning and Cognitive Aging, 2014)
The primary purpose of this dissertation is to investigate to what extent objective and subjective socioeconomic status (SES) provide unique information regarding the impact of SES on cognitive aging trajectories, as well as daily individual variability and plasticity in cognitive functioning. For Study 1, two large samples were drawn from publically available data in the Health and Retirement Study (HRS) to examine cross-sectional performance on episodic memory and fluid reasoning tasks, and longitudinal change in general cognitive functioning across 6 years. Analyses of the cross-sectional sample indicated that subjective SES positively predicted performance on episodic memory and fluid reasoning tasks above and beyond the effect of objective SES. For both cognitive tasks, objective SES remained a significant predictor of cognitive performance after controlling for physical and mental health, but subjective SES was no longer a significant predictor. In the longitudinal sample, growth curve analyses suggested a small positive effect of increasing subjective SES to level of overall cognitive functioning beginning at around age 68, though this boost waned by age 90. This effect was maintained even while controlling for objective SES, BMI, self-rated health, and depressive symptoms. For Study 2, cognitive functioning across episodic memory and fluid reasoning domains were examined in a sample of 45 older adults who completed an initial baseline questionnaire including assessment of objective and subjective SES, and a 7-day `burst' repeated-measures design including cognitive tasks self-administered once a day. Overall, findings suggested that intraindividual variance in cognitive functioning across seven days was inversely related to overall mean performance for both episodic memory and fluid reasoning, such that individuals who showed more variability in performance tended to perform lower on cognitive tasks. Additionally, findings suggested that intraindividual variance in cognitive functioning is likely associated with both objective and subjective SES, though a number of the observed associations did not reach statistical significance. Collectively, these results suggest that an individual's perceptions of their SES may have fundamental impacts on later cognitive outcomes or, alternatively, that individuals may be able to provide a unique insight regarding their SES as not fully assessed by commonly used SES indicators.
Copyright - Copyright ProQuest, UMI Dissertations Publishing 2014 Last updated - 2014-12-20 First page - n/a
Keywords: Demographics; Employment and Labor Force; Expectations; Health Conditions and Status; Healthcare

Successful Aging: Multiple Trajectories and Population Heterogeneity - Tang, Fengyan (International Journal of Social Science Studies, 2014)
Following Rowe and Kahn s successful aging model, this study identified successful aging as a distinctive aging trajectory and examined gender differences in the aging process. Using the Health and Retirement Study data (2000-2008), this study applied group-based trajectory analysis to identify multiple aging trajectories in a sample of older Americans aged 65 and over (N=9,226). Six dimensions were analyzed in the multi-trajectory model: chronic disease, physical functional limitation, disability, depressive symptom, cognitive functioning, and active engagement with life. Three aging trajectory groups were identified: successful aging, usual aging, and pathological aging in both samples of men and women. About one third of women and 40 percent of men fell into the successful aging trajectory. Women were more likely than men to experience functional limitations and disability over time, thus less likely to age successfully. Younger age and higher levels of education and income were related to the likelihood of successful aging. Findings provide support for a multidimensional model of successful aging that emphasizes the heterogeneity in physical, cognitive, and social functioning among the older population. Future research need incorporate subjective assessments of successful aging, examine the potential transitions among different aging trajectories, and assess the impacts of health behavior and resource variables on the aging outcomes.
Keywords: Demographics; Other

Savings and Wealth of the Lifetime Rich: Evidence from the UK and US - Bozio, Antoine; Carl Emmerson; Cormac O'Dea; Tetlow, Gemma (London, Institute for Fiscal Studies, 2013)
Whether higher lifetime income household do save a larger share of their income is one of the longstanding empirical questions in economics that has been surprisingly difficult to answer. We use both consumption data and a new dataset containing both individual survey data on wealth holdings and administrative data on earnings histories from the UK to examine this question. We find evidence of a positive relationship between savig rates (and wealth accumulation) and levels of permanent income. Our findings are consistent with earlier results from Dynan, Skinner and Zeldes (2004) using consumption data from the US, but somewhat at odds with evidence from the US which has examined retirement wealth and lifetime earnings in the Health and Reirement Study, HRS (Gustman andSteinmeier 1999, Venti and Wise 1998). We present new evidence using more recent HRS data, applying exactly the same methodology as we have used on the UK data, and find broadly the same results as these earlier papers. This suggests that the differences are not solely driven by differences in methodology or time period considered.
Keywords: ELSA; Net Worth and Assets

Self-employment and Health: Barriers or Benefits? - Cornelius A Rietveld; van Kippersluis, Hans; A. Roy Thurik (Rotterdam, Erasmus School of Economics (ESE), Tinbergen Institute, 2013)
The self-employed are often reported to be healthier than wage workers; however, the cause of this health difference is largely unknown. The longitudinal nature of the US Health and Retirement Study allows us to gauge the plausibility of two competing explanations for this difference: a contextual, causal effect of self-employment on health (benefit effect), or a health-related selection of individuals into self-employment (barrier effect). Our main finding is that the selection of comparatively healthier individuals into self-employment accounts for the positive cross-sectional difference. The results rule out a positive contextual effect of self-employment on health, and we present tentative evidence that, if anything, engaging in self-employment is bad for one's health. Given the importance of the self-employed in the economy, these findings contribute to our understanding of the vitality of the labor force.
Keywords: Employment and Labor Force; Health Conditions and Status; Healthcare

Self-rated health and morbidity onset among late midlife U.S. adults. - Kenzie Latham; Chuck W Peek (J Gerontol B Psychol Sci Soc Sci, 2013)
OBJECTIVES: Although self-rated health (SRH) is recognized as a strong and consistent predictor of mortality and functional health decline, there are relatively few studies examining SRH as a predictor of morbidity. This study examines the capacity of SRH to predict the onset of chronic disease among the late midlife population (ages 51-61 years). METHOD: Utilizing the first 9 waves (1992-2008) of the Health and Retirement Study, event history analysis was used to estimate the effect of SRH on incidence of 6 major chronic diseases (coronary heart disease, diabetes, stroke, lung disease, arthritis, and cancer) among those who reported none of these conditions at baseline (N = 4,770). RESULTS: SRH was a significant predictor of onset of any chronic condition and all specific chronic conditions excluding cancer. The effect was particularly pronounced for stroke. DISCUSSION: This research provides the strongest and most comprehensive evidence to date of the relationship between SRH and incident morbidity.
Keywords: Chronic disease; Cohort Studies; Female; Health Status; Humans; Male; Middle Aged; Morbidity; Predictive Value of Tests; Self Concept; Self Report; United States

Is Self-Rated Health Comparable Between Non-Hispanic Whites and Hispanics? Evidence From the Health and Retirement Study - Su, Dejun; Wen, Ming; Kyriakos S Markides (The Journals of Gerontology, 2013)
Using subsequent all-cause mortality as a yardstick for retrospective health, this study assessed the comparability of self-rated health (SRH) between non-Hispanic whites and Hispanics. Based on longitudinal data from 6,870 white and 886 Hispanic respondents aged between 51 and 61 in the 1992 Health and Retirement Study, we related SRH in 1992 to risk of mortality in the 1992-2008 period. Logit models were used to predict white-Hispanic differences in reporting fair or poor SRH. Survival curves and cox proportional hazard models were estimated to assess whether and the extent to which the SRH-mortality association differs between non-Hispanic whites and Hispanics. Hispanic respondents reported worse SRH than whites at the baseline, yet they had similar risk of mortality as whites in the 1992-2008 period. Overall, Hispanics rated their health more pessimistically than whites. This was especially the case for Hispanics who rated their health fair or poor at the baseline, whereas their presumed health conditions, as reflected by subsequent risk of mortality, should be considerably better than their white counterparts. Health disparities between whites and Hispanics aged between 51 and 61 will be overestimated if the assessment has been solely based on differences in SRH between the two groups. Findings from this study call for caution in relying on SRH to quantify and explain health disparities between non-Hispanic whites and Hispanics in the United States.
Copyright - Copyright Oxford University Press, UK Jul 2013 Last updated - 2013-06-21 SubjectsTermNotLitGenreText - United States--US
Keywords: Demographics; Health Conditions and Status; Methodology; Retirement Planning and Satisfaction; Women and Minorities

Sense of Control and Self-Reported Health in a Population-Based Sample of Older Americans: Assessment of Potential Confounding by Affect, Personality, and Social Support - Ward, Michael M. (International Journal of Behavioral Medicine, 2013)
Sense of control has been linked to improved health outcomes, but it is unclear if this association is independent of other psychosocial factors. The aim of this study is to test the strength of association between sense of control and self-reported health after adjustment for positive and negative affect, Big 5 personality factors, and social support. Data on sense of control (measured by personal mastery, perceived constraints, and a health-specific rating of control), affect, personality, social support, and two measures of self-reported health (global rating of fair or poor health and presence of functional limitations) were obtained on 6,891 participants in the Health and Retirement Study, a population-based survey of older Americans. The cross-sectional association between sense of control measures and each measure of self-reported health was tested in hierarchical logistic regression models, before and after adjustment for affect, personality, and social support. Participants with higher personal mastery were less likely to report fair/poor health (odds ratio 0.76 per 1-point increase) while those with higher perceived constraints were more likely to report fair/poor health (odds ratio 1.37 per 1-point increase). Associations remained after adjustment for affect, but adjustment for affect attenuated the association of personal mastery by 37 and of perceived constraints by 67 . Further adjustment for personality and social support did not alter the strength of association. Findings were similar for the health-specific rating of control, and for associations with functional limitations. Sense of control is associated with self-reported health in older Americans, but this association is partly confounded by affect.
Copyright - International Society of Behavioral Medicine 2013 Last updated - 2013-04-18 DOI - 2895896591; 75515752; 66285; NJBM; 22282403; SPVLNJBM125292019218
Keywords: Adult children; Health Conditions and Status; Healthcare; Methodology; Other

Social Engagement and Physical and Cognitive Health Among American Indian Participants in the Health and Retirement Study - Nelson, Lonnie A.; Carolyn Noonan; Goldberg, Jack; Dedra S. Buchwald (Journal of Cross-Cultural Gerontology, 2013)
Social engagement has many demonstrated benefits for aging non-Hispanic Whites in the U.S. This study examined data from the U.S. Health and Retirement Study to determine whether these benefits were similar among American Indians and Alaska Natives older than 50 years. Linear regression techniques were used to examine the associations between level of social engagement, scores for memory and mental status, and self-reported health among 203 American Indian and Alaska Native elders who participated in the Health and Retirement Study and had data available between 1998 and 2010. Level of social engagement was significantly associated with memory, mental status, and self-reported health. However, only the association of social engagement with mental status and self-reported health remained significant (p = 0.04 and p = 0.05, respectively) after adjusting for sociodemographic variables, number of known health conditions, and scores on the Center for Epidemiologic Studies Depression scale. Level of social engagement was not associated with patterns of decline across time in cognitive or physical health. Higher levels of social engagement are associated with better physical and cognitive functioning in American Indian and Alaska Native elders. Future studies should examine whether this association acts through cognitive stimulation, increase in physical activity resulting from social engagement, or access to resources that support physical and cognitive health.
Keywords: Health Conditions and Status; Public Policy; Women and Minorities

Social position and chronic conditions across the life span and risk of stroke: a life course epidemiological analysis of 22 847 American adults in ages over 50 - Liu, Longjian; Xue, Fuzhong; Ma, Jixiang; Ma, Marshal; Long, Yong; Newschaffer, Craig J. (International Journal of Stroke, 2013)
Background Evidence is limited on the impact of childhood socioeconomic status, adulthood socioeconomic status and chronic conditions on risk of incident stroke in later life. We aimed to examine these associations using data from a nationally representative sample of the Health and Retirement Study. Methods Stroke-free participants (n=22847) aged 50 years in the Health and Retirement Study (1992-2008) were analyzed. Childhood and adulthood socioeconomic status were assessed using parental and participant's education attainments. Incident stroke was defined as self-reported first incident stroke. Results Of the study sample, 2298 subjects experienced first incident stroke (1006 ). Cox's regression models indicate that subjects with low childhood socioeconomic status had 136 times higher risk (95 confidence interval: 118-157) of first incident stroke than those with high childhood socioeconomic status. There was an 8 reduction of this association after adjustment for adulthood socioeconomic status. Adults with diabetes mellitus had the highest hazard ratio (191, 95 confidence interval: 163-223) for incident stroke, followed by heart disease (169, 148-193), and then hypertension (156, 140-175). Significant interaction effect of childhood socioeconomic status and diabetes mellitus, and combined effects of socioeconomic status and chronic conditions on risk of incident stroke were observed. Conclusions Both low socioeconomic status in childhood and adulthood socioeconomic status predict the risk of stroke. There are significantly combined effects of socioeconomic status and chronic conditions on the risk of stroke. Improving socioeconomic status across the life span and aggressive control of chronic conditions may play pivotal roles in the prevention of stroke development.
Keywords: Employment and Labor Force; Health Conditions and Status

Social relationships and dental care service utilization among older adults - Jeffrey A Burr; Lee, Hyo Jung (Journal of Aging and Health, 2013)
This study described the association between dental care service utilization and two domains of social relationships (social integration and social support) among older adults. The study employed data from the 2008 Health and Retirement Study, examining regression models for whether a person visited a dentist in the past 2 years, including adjustments for demographic, socioeconomic, and health characteristics. Social interaction, social participation, neighborhood cohesion, and marital status were related to an increased likelihood of having visited a dentist. Older persons exhibiting loneliness and having received financial aid from network members demonstrated a decreased likelihood of visiting a dentist. The increased likelihood of visiting a dentist when a child lives nearby only occurred after introducing health covariates. The article discusses the implications of the study findings as they relate to social relationships and oral health and recommends some additional research directions to explore the etiology of dental care use.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Methodology

Social Security Benefit Claiming and Medicare Utilization - John Bound; Helen G Levy; Lauren Hersch Nicholas (Ann Arbor, MI, University of Michigan Retirement Research Center, 2013)
Are early Social Security claimers too sick to work? We linked Health and Retirement Study data to Medicare claims to study health care utilization at ages 65 and 70. We find that Social Security Disability Insurance recipients use more health care on average than those who never received DI. At age 65, Medicare spending on SSDI recipients was 4,440 less than spending on retirees who claimed Social Security benefits prior to Full Retirement Age (FRA) and 4,727 less than those claiming at FRA. Differences in Medicare spending persist at all points of the spending distribution. They are robust to a variety of methodological approaches including general linear models, quantile regression, and reweighting, and in specifications limiting comparisons to beneficiaries claiming benefits at initial EEA. Our results suggest that poor health may contribute to EEA claiming decisions, though this group is considerably healthier than those who were too disabled to work and qualified for DI benefits.
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction; Social Security

The Social Security Windfall Elimination and Government Pension Offset Provisions for Public Employees in the Health and Retirement Study - Alan L Gustman; Thomas L. Steinmeier; N. Tabatabai (Ann Arbor, The University of Michigan, 2013)
This paper uses data from the Health and Retirement Study to investigate the effects of Social Security s Windfall Elimination Provision (WEP) and Government Pension Offset (GPO) provision on Social Security benefits received by individuals and households. WEP reduces the benefits of individuals who worked in jobs covered by Social Security and also worked in uncovered jobs where a pension was earned. WEP also reduces spouse benefits. GPO reduces spouse and survivor benefits for persons who worked in uncovered government employment where they also earned a pension. Unlike previous studies, we take explicit account of pensions earned on jobs not covered by Social Security, a key determinant of the size of WEP and GPO adjustments. Also unlike previous studies, we focus on the household. This allows us to incorporate the full effects of WEP and GPO on spouse and survivor benefits, and to evaluate the effects of WEP and GPO on the assets accumulated by affected families. Among our specific findings: About 3.5 percent of households are subject to either WEP or to GPO. The present value of their Social Security benefits is reduced by roughly one fifth. This amounts to five to six percent of the total wealth they accumulate before retirement. Households affected by both WEP and GPO lose about one third of their benefit. Limiting the Social Security benefit to half the size of the pension from uncovered employment reduces the penalty from WEP for members of the original HRS cohort by about 60 percent.
Keywords: Public Policy; Retirement Planning and Satisfaction; Social Security

The socioeconomic origins of physical functioning among older U.S. adults. - Jennifer Karas Montez (Adv Life Course Res, 2013)
Mounting evidence finds that adult health reflects socioeconomic circumstances (SES) in early life and adulthood. However, it is unclear how the health consequences of SES in early life and adulthood accumulate-for example, additively, synergistically. This study tests four hypotheses about how the health effects of early-life SES (measured by parental education) and adult SES (measured by own education) accumulate to shape functional limitations, whether the accumulation differs between men and women, and the extent to which key mechanisms explain the accumulation. It uses data from the 1994-2010 Health and Retirement Study on U.S. adults 50-100 years of age (N=24,026). The physical functioning benefits of parental and own education accumulated additively among men. While the physical functioning benefits generally accumulated among women, the functioning benefits from one's own education were dampened among women with low-educated mothers. The dampening partly reflected a strong tie between mothers' education level and women's obesity risk. Taken together, the findings reveal subtle differences between men and women in the life course origins of physical functioning. They also shed light on a key mechanism-obesity-that may help explain why a growing number of studies find that early-life SES is especially important for women's health.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Educational Status; Female; Health Behavior; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Obesity; Sex Factors; Socioeconomic factors; United States

Socioeconomic Status and Health Well-Being during Later Life: Potential Mediating Factors - Hsu, Tze-Li; Cossman, Jeralynn S. (Sociological Spectrum, 2013)
This study explores the socioeconomic status (SES)-perceived health association, with special attention on living arrangements. It improves upon existing explanations of causal mechanisms underlying the impact of SES on health among the elderly. Using Health and Retirement Study to run ordered logistic regression, it addresses the importance of living arrangements for self-reported health. Income and education are both important predictors of self-reported health and that after controlling them, living arrangements also affect self-reported health. Future research should highlight nuanced measures of living arrangements and should explore longitudinal analyses to determine the long-term effects of these factors on self-reported health.
Keywords: Demographics; Health Conditions and Status; Healthcare; Methodology; Retirement Planning and Satisfaction

Spousal Effects in Smoking Cessation: Matching, Learning, or Bargaining? - McGeary, Kerry Anne (NBER Working Paper, 2013)
Previous research studying the correlation in smoking behavior between spouses has discounted the role of bargaining or learning. Using the Health and Retirement Study (HRS), which contains information on smoking cessation and spouse s preferences, this paper presents an essential investigation of the importance of spousal bargaining or learning on the decision to cease smoking. We find, regardless of gender, when one member of couple ceases smoking this induces the other member to cease smoking through bargaining. Further, we find females demonstrate either altruistic behavior toward a spouse, who has suffered a health shock, or learning from their spouse s health shock.
Keywords: Health Conditions and Status; Healthcare; Methodology; Other; Risk Taking

Spouses of stroke survivors may be at risk for poor cognitive functioning: a cross-sectional population-based study. - Peii Chen; Amanda L. Botticello (Top Stroke Rehabil, 2013)
BACKGROUND: Stroke often results in chronic disability and the need for long-term assistance, which is provided in large part by spouses. Stroke caregivers experience poorer health and well-being compared with non-caregivers, but less is known about the specific toll that caregiving may exact on cognitive functioning. OBJECTIVE: To investigate whether persons caring for a spouse who experienced a recent stroke may be at risk for poor cognitive functioning compared with non-caregivers. METHODS: Existing data from the United States' Health and Retirement Study (HRS) were used to identify 146 caregivers from among couples in which 1 individual reported surviving a recent stroke and experiencing functional limitations. This cross-sectional population-based analysis compared the stroke caregivers with 3,416 non-caregivers in time orientation, working memory, semantic memory, learning, and episodic memory. RESULTS: Overall, the caregiver group was considerably more disadvantaged than the non-caregiver group in terms of background characteristics, socioeconomic status, health, and well-being. Results of weighted Poisson regression models indicated that stroke caregivers were at risk for poorer performance than non-caregivers in working memory, semantic memory, learning, and episodic memory. The gap between stroke caregivers and non-caregivers in episodic memory remained after adjusting for systematic differences between the 2 groups across an array of risk factors. CONCLUSIONS: Spousal caregivers of stroke survivors may be at risk for poor cognitive functioning. More work is needed to identify the processes that may contribute to the diminished cognitive capacity among these adults so that interventions may be developed to reduce caregiver burden and promote cognitive health.
Keywords: Aged; Aged, 80 and over; Cognition Disorders; Community Health Planning; Cross-Sectional Studies; Female; Humans; Male; Neuropsychological tests; Retrospective Studies; Spouses; Stroke; Survivors; United States

SSI Participation Among the Elderly: A Hazard Model Approach - Jin H. Kim (Journal of Poverty, 2013)
This study revisits the historic policy concern over nonparticipation in the Supplemental Security Income (SSI) program. The most contemporary research model suggests that from a cross-sectional perspective, the elderly take-up decision is primarily determined by the financial situation of the eligible individuals. Yet extant studies have yet to establish a longitudinal model of SSI participation that explicitly takes into account the changing circumstances of the elderly. As such, this study extends the current literature by exploring the time-varying processes leading to eventual take-up of benefits among the elderly. Methodologically, the research relies on event history analysis of data from the Health and Retirement Study spanning the years 1996 to 2006 to explain the varying rates of participation over time as well as the role of life events on the take-up decision. 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Demographics; Event History/Life Cycle; Methodology; Other; Retirement Planning and Satisfaction; Social Security

Sticky Ages: Why is Age 65 Still a Retirement Peak? - Norma B Coe; Khan, Mashfiqur R.; Matthew S. Rutledge (Center for Retirement Research at Boston College Working Paper Series, 2013)
When Social Security’s Full Retirement Age (FRA) increased to age 66 for recent retirees, the peak retirement age increased with it. However, a large share of people continue to claim their Social Security benefits at age 65. This paper explores two potential explanations for the “stickiness” of age 65 as a claiming age: Medicare eligibility and workers’ lack of knowledge about their future Social Security benefits. First, we analyze the impact of Medicare eligibility by comparing two groups – one has an FRA of exactly 65; the other, between age 65 and 2 months and age 66. We find that the group with later FRAs who do not have access to retiree health benefits through their employer are more likely to claim Social Security at age 65. We interpret this finding as evidence that Medicare eligibility persuades more people to retire, because they can begin receiving federal health coverage. Individuals without access to retiree health insurance at work are 7.5 percentage points more likely to retire soon after their 65th birthdays and are 5.8 percentage points less likely to delay retirement until the FRA than those with that insurance. This result fits into extensive research showing that access to health insurance is an important component of the retirement decision. On the question of whether misinformation about Social Security benefits may drive individuals to claim at age 65, we find that some individuals are unable to accurately forecast their retirement benefits. However, our analysis suggests that there is no relationship between this confusion and the age 65 peak for claiming Social Security.

Stroke-associated differences in rates of activity of daily living loss emerge years before stroke onset. - Benjamin D Capistrant; Qianyi Wang; Sze Y Liu; M. Maria Glymour (J Am Geriatr Soc, 2013)
OBJECTIVES: To compare typical age-related changes in activities of daily living (ADLs) independence in stroke-free adults with long-term ADL trajectories before and after stroke. DESIGN: Prospective, observational study. SETTING: Community-dwelling Health and Retirement Study (HRS) cohort. PARTICIPANTS: HRS participants who were stroke free in 1998 and were followed through 2008 (average follow-up 7.9 years) (N = 18,441). MEASUREMENTS: Strokes were assessed using self- or proxy-report of a doctor's diagnosis and month and year of event. Logistic regression was used to compare within-person changes in odds of self-reported independence in five ADLs in those who remained stroke free throughout follow-up (n = 16,816), those who survived a stroke (n = 1,208), and those who had a stroke and did not survive to participate in another interview (n = 417). Models were adjusted for demographic and socioeconomic covariates. RESULTS: Even before stroke, those who later developed stroke had significantly lower ADL independence and were experiencing faster independence losses than similar-aged individuals who remained stroke free. Of those who developed a stroke, survivors experienced slower pre-stroke loss of ADL independence than those who died. ADL independence declined at the time of stroke and decline continued afterwards. CONCLUSION: In adults at risk of stroke, disproportionate ADL limitations emerge well before stroke onset. Excess disability in stroke survivors should not be entirely attributed to effects of acute stroke or quality of acute stroke care. Although there are many possible causal pathways between ADL and stroke, the association may be noncausal. For example, ADL limitations may be a consequence of stroke risk factors (e.g., diabetes mellitus) or early cerebrovascular ischemia.
Keywords: Activities of Daily Living; Age of Onset; Aged; Aged, 80 and over; Bayes Theorem; Disability Evaluation; Disabled Persons; Female; Follow-Up Studies; Geriatric Assessment; Humans; Male; Middle Aged; Morbidity; Prospective Studies; Risk Assessment; Risk Factors; Socioeconomic factors; Stroke; Stroke Rehabilitation; Survival Rate; Survivors; Time Factors; United States

Subjective mortality hazard shocks and the adjustment of consumption expenditures - Anikó Biró (Journal of Population Economics, 2013)
I estimate the effect of shocks to subjective mortality hazards on consumption expenditures of retired individuals using the Survey of Health, Ageing and Retirement in Europe. I measure mortality expectations with survey responses on survival probabilities. To create plausibly exogenous variation in mortality hazard, I use the death of a sibling as an instrument. My results show that survey responses contain economically relevant information about longevity expectations and confirm the predictions of life-cycle theories about the effect of these expectations on intertemporal choice.
Keywords: Consumption decisions; IV estimation; Subjective longevity

Symptoms of depression in survivors of severe sepsis: a prospective cohort study of older Americans. - Dimitry S Davydow; Catherine L Hough; Kenneth M. Langa; Theodore J Iwashyna (Am J Geriatr Psychiatry, 2013)
OBJECTIVES: To examine if incident severe sepsis is associated with increased risk of subsequent depressive symptoms and to assess which patient characteristics are associated with increased risk of depressive symptoms. DESIGN: Prospective longitudinal cohort study. SETTING: Population-based cohort of older U.S. adults interviewed as part of the Health and Retirement Study (1998-2006). PARTICIPANTS: A total of 439 patients who survived 471 hospitalizations for severe sepsis and completed at least one follow-up interview. MEASUREMENTS: Depressive symptoms were assessed with a modified version of the Center for Epidemiologic Studies Depression Scale. Severe sepsis was identified using a validated algorithm in Medicare claims. RESULTS: The point prevalence of substantial depressive symptoms was 28% at a median of 1.2 years before sepsis, and remained 28% at a median of 0.9 years after sepsis. Neither incident severe sepsis (relative risk [RR]: 1.00; 95% confidence interval [CI]: 0.73, 1.34) nor severe sepsis-related clinical characteristics were significantly associated with subsequent depressive symptoms. These results were robust to potential threats from missing data or alternative outcome definitions. After adjustment, presepsis substantial depressive symptoms (RR: 2.20; 95% CI: 1.66, 2.90) and worse postsepsis functional impairment (RR: 1.08 per new limitation; 95% CI: 1.03, 1.13) were independently associated with substantial depressive symptoms after sepsis. CONCLUSIONS: The prevalence of substantial depressive symptoms in severe sepsis survivors is high but is not increased relative to their presepsis levels. Identifying this large subset of severe sepsis survivors at increased risk for major depression, and beginning interventions before hospital discharge, may improve outcomes.
Keywords: Aged; Aged, 80 and over; Cohort Studies; depression; Female; Hospitalization; Humans; Longitudinal Studies; Male; Poisson Distribution; Prospective Studies; Regression Analysis; Risk Factors; Sepsis; Severity of Illness Index; Survivors; United States

Self- and other-oriented potential lifetime traumatic events as predictors of loneliness in the second half of life. - Yuval Palgi; Amit Shrira; Menachem Ben-Ezra; Sharon Shiovitz-Ezra; Liat Ayalon (Aging Ment Health, 2012)
OBJECTIVES: This study examined the relationship between self- and other-oriented potential lifetime traumatic events (PLTE) and loneliness at the second half of life. METHOD: The sample was comprised of 7446 respondents who completed the Health and Retirement Study (HRS) 2006 psychosocial questionnaire. PLTE were classified into self-oriented PLTE, defined as traumatic events that primarily inflict the self (e.g., being abused by parents) and other-oriented PLTE, defined as events that affect the self by primarily targeting others (e.g., death of one's child). We evaluated the role of self- and other-oriented PLTE as predictors of loneliness, as evaluated by the short R-UCLA. Analyses were stratified by age at which trauma happened categorized into four life periods (0-17, 18-30, 31-49, 50+). RESULTS: The results showed that PLTE is positively related to loneliness. Moreover, the number of other-oriented PLTE, and even more pronouncedly self-oriented PLTE, that happened up until adulthood were the strongest predictors of loneliness at the second half of life. CONCLUSION: The study suggests that self- and other-oriented PLTE reported to have occurred early in life are associated with perceived loneliness in the second half of life.
Keywords: Age Factors; Aged; Aged, 80 and over; Child; Child Abuse; Cross-Sectional Studies; depression; Female; Forecasting; Humans; Life Change Events; Loneliness; Male; Middle Aged; Self Psychology; Wounds and Injuries

Self-care and health outcomes of diabetes mellitus. - MinKyoung Song; Sarah J Ratcliffe; Nancy C Tkacs; Barbara Riegel (Clin Nurs Res, 2012)
Studies show that self-care improves diabetes mellitus (DM) outcomes; however, previous studies have focused on self-care maintenance, and little is known about self-care management. The objective of this study is to examine the influence of DM self-care maintenance and management on number of hospitalizations and hospitalization days. A cohort design with secondary analysis of data from the Health and Retirement Study 2002-2004 was used. Data from 726 adults with DM were analyzed with logistic regression and negative binomial regression adjusting for covariates. Self-care maintenance and management were significant determinants of hospitalization outcomes. Establishing a goal for HbA1c (self-care management) and eating ≥2 snacks or desserts per day (self-care maintenance) were associated with a decrease in hospitalizations (IRR = 0.860, p = .001; IRR = 0.914, p = .043, respectively). DM self-care maintenance and management influence health outcomes but in different ways. These data provide evidence that both elements are needed in the education of patients about DM.
Keywords: Adult; Aged; Aged, 80 and over; Clinical Nursing Research; Diabetes Mellitus; Female; Follow-Up Studies; Hospitalization; Humans; Length of Stay; Male; Middle Aged; Self Care; Treatment Outcome

Self-rated health and the "first move" around retirement: a longitudinal study of older Americans. - Nan E. Johnson (J Rural Health, 2012)
PURPOSE: I examine whether less favorable self-rated health raises the risk of outmigration more for young-old adults (aged 53-63 at the start of the 10-year longitudinal study in 1994) in nonmetro than metro counties and increases the odds that both groups of outmigrants will choose metro over nonmetro destinations. Finally, I examine whether nonmetro outmigrants are more likely than metro outmigrants to cite a health concern or a desire to get closer to relatives or friends as a reason for the migration. METHODS: I use the Health and Retirement Study (HRS) to track the main residences of nonmetro and metro older adults from 1994-2003. With a discrete-time Event History Analysis, I assess the joint effects of nonmetro/metro residence in 1994 and self-rated health (updated at each biennial wave) upon the risk of a first migration. Those who migrated were asked to recall why. FINDINGS: At worse levels of self-rated health, the odds of remaining in a nonmetro county of residence drop in favor of migrating to another nonmetro county. Among migrants, the worse the self-rated health, the higher the odds of within-type migration (nonmetro-nonmetro and metro-metro) over cross-type migration (nonmetro-metro and metro-nonmetro). The percentages of migrants citing a health concern or a desire to live closer to relatives or friends as a reason for migration do not differ by county type of origin. CONCLUSIONS: An implication for rural health policy is that young-old adults with worse self-rated health tend to remain in nonmetro areas, even when they migrate.
Keywords: Aged; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Population Dynamics; Retirement

Self-reported and measured hypertension among older US- and foreign-born adults. - White, Kellee; Mauricio Avendano; Benjamin D Capistrant; J Robin Moon; Sze Y Liu; M. Maria Glymour (J Immigr Minor Health, 2012)
Self-reported hypertension is frequently used for health surveillance. However, little is known about the validity of self-reported hypertension among older Americans by nativity status. This study compared self-reported and measured hypertension among older black, white, and Hispanic Americans by nativity using the 2006 and 2008 Health and Retirement Study (n = 13,451). Sensitivity and specificity of self-reported hypertension were calculated using the Seventh report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure definition. Sensitivity was high among older blacks (88.9%), whites (82.8%), and Hispanics (84.0%), and both foreign-born (83.2%) and US-born (84.0%). Specificity was above 90% for both US-born and foreign-born, but higher for whites (92.8%) than blacks (86.0%). Despite the potential vulnerability of older foreign-born Americans, self-reported hypertension may be considered a reasonable estimate of hypertension status. Future research should confirm these findings in samples with a larger and more ethnically diverse foreign-born population.
Copyright - Springer Science Business Media, LLC 2012 Language of summary - English Location - United States--US Pages - 721-6 ProQuest ID - 1022672464 Document feature - References SubjectsTermNotLitGenreText - United States--US Last updated - 2012-07-11 Place of publication - New York Corporate institution author - White, Kellee; Avenda o, Mauricio; Capistrant, Benjamin D; Robin Moon, J; Liu, Sze Y; Maria Glymour, M DOI - 2699707771; 70149852; 53471; JIMH; 22109587; SPVLJIMH109031449549
Keywords: Aged; Black or African American; Blood Pressure Determination; Emigrants and Immigrants; Female; Hispanic or Latino; Humans; Hypertension; Male; Middle Aged; Nutrition Surveys; Reproducibility of Results; Self Report; United States; White People

Sense of control and sociodemographic differences in self-reported health in older adults - Ward, Michael M. (Quality of Life Research, 2012)
Stronger sense of control has been associated with improved health outcomes. This study tested whether the association between sense of control and self-reported health varied among demographic groups and whether sense of control attenuated sociodemographic differences in self-reported health. Data from 6,815 participants in the Health and Retirement Study were used to examine moderation between demographic characteristics and sense of control (measured by the personal mastery and perceived constraints scales of the Midlife Developmental Inventory) in their associations with three self-reported health measures (global rating of fair/poor health, functional limitations, and number of comorbid conditions). Higher personal mastery and lower perceived constraints were associated with better self-reported health. There were no significant interactions between the sense of control measures and age, gender, education level, income, or marital status in their associations with either global self-rated health or functional limitations. Higher levels of mastery were associated with lower likelihood of functional limitations among blacks and whites, but not among those of other races. Perceived constraints were slightly more strongly associated with number of comorbid conditions among older than younger individuals. Sense of control measures were generally similarly associated with self-reported health across demographic groups and did not attenuate demographic differences in health. PUBLICATION ABSTRACT
Copyright - Springer Science Business Media Dordrecht 2012 Language of summary - English Pages - 1509-18 ProQuest ID - 1112162539 Last updated - 2013-01-02 Place of publication - Oxford Corporate institution author - Ward, Michael M DOI - 2789326681; 73133172; 138140; QLFR; 22120892; SPVLQLFR1113621968
Keywords: Demographics; Health Conditions and Status; Healthcare; Other

The significance of education for mortality compression in the United States. - Dustin C. Brown; Mark D Hayward; Jennifer Karas Montez; Robert A Hummer; Chi-Tsun Chiu; Mira M Hidajat (Demography, 2012)
Recent studies of old-age mortality trends assess whether longevity improvements over time are linked to increasing compression of mortality at advanced ages. The historical backdrop of these studies is the long-term improvement in a population's socioeconomic resources that fueled longevity gains. We extend this line of inquiry by examining whether socioeconomic differences in longevity within a population are accompanied by old-age mortality compression. Specifically, we document educational differences in longevity and mortality compression for older men and women in the United States. Drawing on the fundamental cause of disease framework, we hypothesize that both longevity and compression increase with higher levels of education and that women with the highest levels of education will exhibit the greatest degree of longevity and compression. Results based on the Health and Retirement Study and the National Health Interview Survey Linked Mortality File confirm a strong educational gradient in both longevity and mortality compression. We also find that mortality is more compressed within educational groups among women than men. The results suggest that educational attainment in the United States maximizes life chances by delaying the biological aging process.
Keywords: Aged; Aged, 80 and over; Aging; Educational Status; Female; Health Status Disparities; Humans; Life Expectancy; Male; Middle Aged; Mortality; Mortality, Premature; Sex Distribution; Socioeconomic factors; United States

A simple measure with complex determinants: investigation of the correlates of self-rated health in older men and women from three continents - D. J. French; Chris Browning; Kendig, H.; Luszcz, M. A.; Saito, Yasuhiko; K. A. Sargent-Cox; Kaarin J. Anstey (Bmc Public Health, 2012)
Background: Self-rated health is commonly employed in research studies that seek to assess the health status of older individuals. Perceptions of health are, however, influenced by individual and societal level factors that may differ within and between countries. This study investigates levels of self-rated health (SRH) and correlates of SRH among older adults in Australia, United States of America (USA), Japan and South Korea. Methods: Cross-sectional data were drawn from large surveys of older respondents ( = 65 years) in Australia (n = 7,355), USA (n = 10,358), Japan (n = 3,541) and South Korea (n = 3,971), collected between 2000 and 2006. Harmonized variables were developed to represent socioeconomic, lifestyle and health indicators. We then assessed whether these variables, and their potentially different impact in different countries, could account for cross-national differences in levels of SRH. Results: SRH differed significantly between countries, with older Koreans reporting much poorer health than those in the other three nations. This was not the result of biases in response patterns (for example central versus extreme tendency). Health-related correlates of SRH were similar across countries; those with more medical conditions, functional limitations or poor mental health gave poorer ratings. After accounting for the differential impact of determinants in different national contexts, Australians reported better SRH than other nations. Conclusions: We conclude that when examining correlates of SRH, the similarities are greater than the differences between countries. There are however differences in levels of SRH which are not fully accounted for by the health correlates. Broad generalizations about styles of responding are not helpful for understanding these differences, which appear to be country, and possibly cohort specific. When using SRH to characterize the health status of older people, it is important to consider earlier life experiences of cohorts as well as national and individual factors in later life. Further research is required to understand the complex societal influences on perceptions of health.
Keywords: Cross-National; Health Conditions and Status; KLoSA; Methodology

Social Determinants and Depression in Later Life - Cross-Denny, Bronwyn (Social Determinants and Depression in Later Life, 2012)
The social determinants of health and mental health have come to the forefront as a global issue as a result of the World Health Organization's (WHO) initiative to close the health equity gap. The aim of this study is to examine social determinants and the impact on depression over the life span utilizing Cumulative Disadvantage Theory. A secondary data analysis was conducted on the 2010 wave of data from the Health and Retirement Study. A path analysis was used to determine predictors of depression in later life. Findings indicated that age and neighborhood cohesion were predictors of perceived discrimination. Although total causal effects were small for predictors of depression, results indicate a possible protective factor provided by neighborhood cohesion and social support. Implications for social work research and practice are discussed for addressing service needs of the growing older adult population.
Depression 3544982 74191332 1237220473 2013-01-03 0351: Gerontology 66569 n/a Social sciences English Copyright ProQuest, UMI Dissertations Publishing 2012 Social determinants 9781267766014 2012 0347: Mental health Health and environmental sciences Older adults 2839293321 Cross-Denny, Bronwyn
Keywords: Adult children; Demographics; Health Conditions and Status; Methodology

Social isolation, loneliness and health among older adults. - Caitlin E. Coyle; Dugan, Elizabeth (J Aging Health, 2012)
OBJECTIVE: To examine the relationship of social isolation, loneliness and health outcomes among older adults. METHODS: Using data from the Leave Behind Questionnaire of the Health and Retirement Study (2006 and 2008), (n = 11,825) several indicators of social isolation were scaled and the Hughes 3-Item Loneliness Scale was used. Two measures of health (self-rated health and mental health conditions) were examined using logistic regression. RESULTS: Loneliness and social isolation were not highly correlated with one another (r = 0.201, p = 0.000). Loneliness was associated with higher odds of having a mental health problem (OR: 1.17; CI: [1.13, 1.21], p = 0.000); and isolation was associated with higher odds of reporting one's health as being fair/poor (OR:1.39; CI: [1.21, 1.59], p = 0.000). DISCUSSION: The results suggest that global measures of isolation, that fail to distinguish between social isolation and feelings of loneliness, may not detect the impact on physical and mental health in older adults.
Keywords: Aged; Cross-Sectional Studies; Diagnostic Self Evaluation; Female; Health Status; Humans; Logistic Models; Loneliness; Male; Mental Disorders; Middle Aged; Risk Factors; social isolation

Socioeconomic and Racial/Ethnic Disparities in Cognitive Trajectories among the Oldest Old: The Role of Vascular and Functional Health - Nicholas J Bishop (Arizona State University, 2012)
Identifying modifiable causes of chronic disease is essential to prepare for the needs of an aging population. Cognitive decline is a precursor to the development of Alzheimer's and other dementing diseases, representing some of the most prevalent and least understood sources of morbidity and mortality associated with aging. To contribute to the literature on cognitive aging, this work focuses on the role of vascular and physical health in the development of cognitive trajectories while accounting for the socioeconomic context where health disparities are developed. The Assets and Health Dynamics among the Oldest-Old study provided a nationally-representative sample of non-institutionalized adults age 65 and over in 1998, with biennial follow-up continuing until 2008. Latent growth models with adjustment for non-random missing data were used to assess vascular, physical, and social predictors of cognitive change. A core aim of this project was examining socioeconomic and racial/ethnic variation in vascular predictors of cognitive trajectories. Results indicated that diabetes and heart problems were directly related to an increased rate of memory decline in whites, where these risk factors were only associated with baseline word-recall for blacks when conditioned on gender and household assets. These results support the vascular hypotheses of cognitive aging and attest to the significance of socioeconomic and racial/ethnic variation in vascular influences on cognitive health. The second substantive portion of this dissertation used parallel process latent growth models to examine the co-development of cognitive and functional health. Initial word-recall scores were consistently associated with later functional limitations, but baseline functional limitations were not consistently associated with later word-recall scores. Gender and household income moderated this relationship, and indicators of lifecourse SES were better equipped to explain variation in initial cognitive and functional status than change in these measures over time. Overall, this work suggests that research examining associations between cognitive decline, chronic disease, and disability must account for the social context where individuals and their health develop. Also, these findings advocate that reducing socioeconomic and racial/ethnic disparities in cognitive health among the aging requires interventions early in the lifecourse, as disparities in cognitive trajectories were solidified prior to late old age.
ISBN 9781124275345Dissertation Abstracts International, A: The Humanities and Social Sciences, vol. 72, no. 09, pp. 3523 0419-4209 9781124701622
Keywords: Demographics; Health Conditions and Status

Spousal caregiving and incident hypertension. - Benjamin D Capistrant; J Robin Moon; M. Maria Glymour (Am J Hypertens, 2012)
BACKGROUND: Caring for one's spouse has been associated with poor health, including risk of cardiovascular disease (CVD) onset and mortality. However, few studies have assessed the risk of incident hypertension associated with spousal caregiving. This paper investigates this association in a large, nationally representative sample of American older adults. METHODS: Married, hypertension-free, Health and Retirement Study (HRS) respondents aged 50+ in 2000, (n = 5,708) were followed up to 8 years (1,708 new self-reported hypertension diagnoses). Current caregiving exposure was defined as assisting a spouse with instrumental or basic activities of daily living (IADLs) 14+ h/week; we define providing ≥14 h/week of care at two consecutive biennial surveys as "long-term caregiving." We used inverse probability weighted discrete-time hazard models with time-updated exposure and covariates to estimate effects of current and long-term caregiving on incident hypertension. We tested for effect modification by race, gender, and recipient memory illness. Sensitivity analyses restricted to respondents whose spouses had care needs. RESULTS: After adjusting for demographic, socioeconomic, and health factors, (including risk behaviors, comorbid conditions, and self-rated health), current caregiving significantly predicted hypertension incidence (risk ratio (RR) = 1.36, 95% confidence interval (CI): 1.01, 1.83). For long-term caregivers, there was significant evidence of risk of hypertension onset associated with caregiving (RR = 2.29, 95% CI: 1.17, 4.49). The risk of hypertension onset associated with both current and long-term caregiving did not vary by race, gender, or recipient memory illness diagnosis. Sensitivity analyses supported the primary findings. CONCLUSIONS: Providing IADL care to a spouse significantly predicted hypertension onset in a nationally representative sample of US adults.
Keywords: Activities of Daily Living; Aged; Cardiovascular Diseases; Caregivers; Female; Follow-Up Studies; Humans; Hypertension; Male; Memory Disorders; Middle Aged; Odds Ratio; Spouses; Stress, Psychological

Spousal support and diabetes management: The role of gender and religion - Estevez, Rosemary (University of North Texas, 2012)
One in four adults over the age of 60 suffers from diabetes. Around 85%-90% of individuals who have diabetes suffer from Type II diabetes. The prevalence of individuals with diabetes is expected to increase. This paper addresses the influence spousal support, friend support, and religion all have on diabetes mellitus. Gender difference in relation to spousal support benefits has also received limited attention. The limited amount of studies that have examined gender differences in relation to spousal support and diabetes management indicate that diabetic men benefit the most from spousal support due to their wives active involvement in meal preparation and grocery shopping. The results showed that neither spousal support nor religious salience was significantly related to diabetes management. There were observed gender differences in religious salience (males = 4.84, females = 5.36, p <.001) and positive spousal support (males = 3.19, females = 3.02, p <.001), but none of the major hypotheses were supported.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Public Policy

Spurious inferences about long-term outcomes: the case of severe sepsis and geriatric conditions. - Theodore J Iwashyna; Netzer, Giora; Kenneth M. Langa; Christine T Cigolle (Am J Respir Crit Care Med, 2012)
RATIONALE: Survivors of critical illness suffer significant limitations and disabilities. OBJECTIVES: Ascertain whether severe sepsis is associated with increased risk of so-called geriatric conditions (injurious falls, low body mass index [BMI], incontinence, vision loss, hearing loss, and chronic pain) and whether this association is measured consistently across three different study designs. METHODS: Patients with severe sepsis were identified in the Health and Retirement Study, a nationally representative cohort interviewed every 2 years, 1998 to 2006, and in linked Medicare claims. Three comparators were used to assess an association of severe sepsis with geriatric conditions in survivors: the prevalence in the United States population aged 65 years and older, survivors' own pre-sepsis levels assessed before hospitalization, or survivors' own pre-sepsis trajectory. MEASUREMENTS AND MAIN RESULTS: Six hundred twenty-three severe sepsis hospitalizations were followed a median of 0.92 years. When compared with the 65 years and older population, surviving severe sepsis was associated with increased rates of low BMI, injurious falls, incontinence, and vision loss. Results were similar when comparing survivors to their own pre-sepsis levels. The association of low BMI and severe sepsis persisted when controlling for patients' pre-sepsis trajectories, but there was no association of severe sepsis with injurious falls, incontinence, vision loss, hearing loss, and chronic pain after such controls. CONCLUSIONS: Geriatric conditions are common after severe sepsis. However, severe sepsis is associated with increased rates of only a subset of geriatric conditions, not all. In studying outcomes after acute illness, failing to measure and control for both preillness levels and trajectories may result in erroneous conclusions.
Iwashyna, Theodore J Netzer, Giora Langa, Kenneth M Cigolle, Christine K08 AG031837/AG/NIA NIH HHS/ K08 HL091249/HL/NHLBI NIH HHS/ K12 RR023250/RR/NCRR NIH HHS/ P30-AG028747/AG/NIA NIH HHS/ P60 DK-20572/DK/NIDDK NIH HHS/ R01 AG030155/AG/NIA NIH HHS/ U01 AG09740/AG/NIA NIH HHS/ UL1RR024986/RR/NCRR NIH HHS/ Am J Respir Crit Care Med. 2012 Apr 15;185(8):835-41. Epub 2012 Feb 9.
Keywords: Aged; Aged, 80 and over; Body Mass Index; Chronic pain; Cohort Studies; Comorbidity; Critical Illness; Disabled Persons; disease progression; Female; Geriatric Assessment; Hearing Disorders; Hospitalization; Humans; Incidence; Male; Musculoskeletal Diseases; Prognosis; Retrospective Studies; Risk Assessment; Sepsis; Survival Analysis; Survivors; Thinness; Time; Treatment Outcome; Urinary incontinence; Vision Disorders

Spurring enrollment in Medicare savings programs through a substitute for the asset test focused on investment income. - Dorn, Stan; Shang, Baoping (Health Aff (Millwood), 2012)
Fewer than one-third of eligible Medicare beneficiaries enroll in Medicare savings programs, which pay premiums and, in some cases, eliminate out-of-pocket cost sharing for poor and near-poor enrollees. Many beneficiaries don't participate in savings programs because they must complete a cumbersome application process, including a burdensome asset test. We demonstrate that a streamlined alternative to the asset test-allowing seniors to qualify for Medicare savings programs by providing evidence of limited assets or showing a lack of investment income-would permit 78 percent of currently eligible seniors to bypass the asset test entirely. This simplified approach would increase the number of beneficiaries who qualify for Medicare savings programs from the current 3.6 million seniors to 4.6 million. Such an alternative would keep benefits targeted to people with low assets, eliminate costly administrative expenses and obstacles to enrollment associated with the asset test, and avoid the much larger influx of seniors that would occur if the asset test were eliminated entirely.
Copyright - Copyright The People to People Health Foundation, Inc., Project HOPE Feb 2012 Language of summary - English Location - United States--US Pages - 367-75 ProQuest ID - 921992803 Document feature - Tables; References SubjectsTermNotLitGenreText - United States--US Last updated - 2012-06-05 Place of publication - Chevy Chase Corporate institution author - Dorn, Stan; Shang, Baoping DOI - 2588825981; 67448192; 15986; HAF; 22323167; INNNHAF0000865869
Keywords: Cost Savings; Eligibility Determination; Financing, Personal; Humans; Medicare; Poverty; United States

Stability and change in financial transfers from adult children to older parents. - Maximiliane E Szinovacz; Adam Davey (Can J Aging, 2012)
We sought to identify the extent and predictors of longitudinal changes in adult children's financial assistance to parents and in transfer networks over a two-year period. Analyses rely on pooled data from 1994 to 2000 of the Health and Retirement Study, using families in which adult children with no more than four siblings financially supported parents over two years. Change in the help network occurred in about 40 per cent of these families over the two-year period. When change occurred, it most commonly involved cessation of support by a child, followed by addition of another child to the network, whereas exchange of supporting children was relatively rare. Change reflected children's ability to provide care and the burden created by parents' needs. However, the size and composition of the adult-child network and of the initial support group also played an important role. Results highlight the dynamic and systemic nature of intergenerational financial networks.
Keywords: Adult children; Aged; Female; Financial Support; Humans; Male; Middle Aged; Parent-Child Relations; Parents

Stroke incidence in older US Hispanics: is foreign birth protective? - J Robin Moon; Benjamin D Capistrant; Ichiro Kawachi; Mauricio Avendano; Subramanian, S V; Lisa M. Bates; M. Maria Glymour (Stroke, 2012)
BACKGROUND AND PURPOSE: Although Hispanics are the fastest growing ethnic group in the United States, relatively little is known about stroke risk in US Hispanics. We compare stroke incidence and socioeconomic predictors in US- and foreign-born Hispanics with patterns among non-Hispanic whites. METHODS: Health and Retirement Study participants aged 50+ years free of stroke in 1998 (mean baseline age, 66.3 years) were followed through 2008 for self- or proxy-reported first stroke (n=15 784; 1388 events). We used discrete-time survival analysis to compare stroke incidence among US-born (including those who immigrated before age 7 years) and foreign-born Hispanics with incidence in non-Hispanic whites. We also examined childhood and adult socioeconomic characteristics as predictors of stroke among Hispanics, comparing effect estimates with those for non-Hispanic whites. RESULTS: In age- and sex-adjusted models, US-born Hispanics had higher odds of stroke onset than non-Hispanic whites (OR, 1.44; 95% CI, 1.08-1.90), but these differences were attenuated and nonsignificant in models that controlled for childhood and adulthood socioeconomic factors (OR, 1.07; 95% CI, 0.80-1.42). In contrast, in models adjusted for all demographic and socioeconomic factors, foreign-born Hispanics had significantly lower stroke risk than non-Hispanic whites (OR, 0.58; 95% CI, 0.41-0.81). The impact of socioeconomic predictors on stroke did not differ between Hispanics and whites. CONCLUSIONS: In this longitudinal national cohort, foreign-born Hispanics had lower incidence of stroke incidence than non-Hispanic whites and US-born Hispanics. Findings suggest that foreign-born Hispanics may have a risk factor profile that protects them from stroke as compared with other Americans.
Moon, J Robin Capistrant, Benjamin D Kawachi, Ichiro Avendano, Mauricio Subramanian, S V Bates, Lisa M Glymour, M Maria T32-HL098048-01/HL/NHLBI NIH HHS/United States Research Support, N.I.H., Extramural Research Support, Non-U.S. Gov't United States Stroke. 2012 May;43(5):1224-9. Epub 2012 Feb 21.
Keywords: Age Factors; Aged; Cohort Studies; Emigration and Immigration; Female; Hispanic or Latino; Humans; Incidence; Longitudinal Studies; Male; Middle Aged; Retrospective Studies; Risk Factors; Socioeconomic factors; Stroke; United States; White People

Subjective social status and functional decline in older adults. - Bonnie Chen; Kenneth E Covinsky; Irena Cenzer; Nancy E Adler; Brie A Williams (J Gen Intern Med, 2012)
BACKGROUND: It is unknown whether subjective assessment of social status predicts health outcomes in older adults. OBJECTIVE: To describe the relationship between subjective social status and functional decline in older adults. DESIGN: Longitudinal cohort study. SETTING: The Health and Retirement Study, a nationally representative survey of community-dwelling older adults (2004-2008). PARTICIPANTS: Two thousand five hundred and twenty-three community-dwelling older adults. MAIN MEASURES: Self-report of social status (SSS), categorized into three groups, reported by participants who marked a 10-rung ladder to represent where they stand in society. Four-year functional decline (new difficulty in any of five activities of daily living, mobility decline and/or death) KEY RESULTS: Mean age was 64; 46% were male, 85% were white. At baseline, lower SSS was associated with being younger, unmarried, of nonwhite race/ethnicity, higher rates of chronic medical conditions and ADL impairment (P < 0.01). Over 4 years, 50% in the lowest SSS group declined in function, compared to the middle and highest groups (28% and 26%), P-trend <0.001. Those in the lowest rungs of SSS were at increased risk of 4-year functional decline (unadjusted RR = 1.91, CI 1.-9-2.46). The relationship between a subjective belief that one is worse off than others and functional decline persisted after serial adjustment for demographics, objective SES measures, and baseline health and functional status (RR 1.36, CI 1.08-1.73). CONCLUSIONS: In older adults, the belief that one is in the lowest rungs of social status is a measure of socioeconomic distress and of significant risk for functional decline. These findings suggest that self-report of low subjective social status may give clinicians additional information about which older adults are at high risk for future functional decline.
Keywords: Activities of Daily Living; Aged; Aging; Female; Health Status Disparities; Humans; Longitudinal Studies; Male; Middle Aged; Mobility Limitation; Risk Factors; Self Report; Social Class

Sample Sizes and Response Rates - HRS Staff (Survey Research Center, Institute for Social Research, University of Michigan, 2011)

Self Assessed Health, Anchoring Vignettes, and Unobserved Heterogeneity in the Health and Retirement Study - Noroski, Paul J. (Economics, 2011)
This dissertation examines the subtleties inherent to socioeconomic models of health. The relative contributions of unobserved heterogeneity and state dependence in explaining the dynamics of health in the U.S. are controlled for as the average partial effects of socioeconomic status are estimated. In addition to these investigations, I use anchoring vignette data from the Health and Retirement Study to investigate health perceptions in the U.S. and how they affect the comparability of self assessments of health across the population. The results imply that just over 30% of the unexplained variation in self-assessed health is attributable to unobserved heterogeneity in the form of a time invariant individual effect. Although attrition bias is detected in the panel, estimates obtained using an inverse probability weighted specification reveal that attrition has virtually no effect on the estimated relationships between health and socioeconomic status. Regarding the vignette analyses, many of the characteristics that affect health status are also found to affect perceptions of health. For example, I find that respondents in lower income groups tend to be more tolerant of mental health problems than the rest of the population and that recipients of federal disability insurance may be more likely to rate a given health problem as being disabling. Upon identifying which personal characteristics influence reporting behavior, I estimate models of self-reported health that enhance comparability of survey responses across the population. I find that failing to account for reporting heterogeneity ultimately leads to a distortion of the estimated relationships between health and socioeconomic status.
ISBN 9781124606002
Keywords: Demographics; Disabilities; Health Conditions and Status; Methodology

Social characteristics and health status of exceptionally long-lived Americans in the Health and Retirement Study. - Jennifer A Ailshire; Hiram Beltrán-Sánchez; Eileen M. Crimmins (J Am Geriatr Soc, 2011)
OBJECTIVES: To characterize the social characteristics and physical, functional, mental, and cognitive health of exceptional survivors in the United States and how the experience of exceptional longevity differs according to social status. DESIGN: Nationally representative longitudinal study of older Americans. SETTING: United States. PARTICIPANTS: One thousand six hundred forty-nine men and women born from 1900 to 1911 from the Health and Retirement Study: 1,424 nonsurvivors who died before reaching the age of 97 and 225 exceptional survivors who survived to age 97 and older. MEASUREMENTS: Self-reported data on sociodemographic characteristics, social environment, physical and mental health, and physical and cognitive function. RESULTS: At baseline, exceptional survivors were more likely to live independently and had fewer diseases, better mental health, and better physical and cognitive function than those who did not survive to age 97. Exceptional survivors experienced declines from baseline in all health domains upon reaching 97 years of age, but between one-fifth and one-third of exceptional survivors remained disease free, with no functional limitations or depressive symptoms, and one-fifth retained high cognitive function. Of exceptional survivors, men were healthier than women, and whites were generally healthier than nonwhites. Highly educated exceptional survivors had better cognitive function than their less-educated counterparts. CONCLUSION: On average, exceptional survivors are relatively healthy and high functioning for most of their lives and experience health declines only upon reaching maximum longevity. Heterogeneity in the population of exceptionally old adults indicates that, although many individuals reach maximum longevity in a state of poor health and functioning, a considerable portion of exceptional survivors remain healthy and high-functioning even in very old age.
Ailshire, Jennifer A Beltran-Sanchez, Hiram Crimmins, Eileen M United States Journal of the American Geriatrics Society J Am Geriatr Soc. 2011 Dec;59(12):2241-8. doi: 10.1111/j.1532-5415.2011.03723.x.
Keywords: Age Factors; Aged, 80 and over; Female; Geriatric Assessment; Health Status; Humans; Longevity; Longitudinal Studies; Male; Social Class; Sociology; United States

Social Connectedness in Health, Morbidity and Mortality, and Health Care The Contributions, Limits and Further Potential of Health and Retirement Study - Pescosolido, Bernice (Forum for Health Economics and Policy, 2011)
This part of the mid-term review of the Health and Retirement Study (HRS) provides an overall assessment of the utility of HRS data for research targeting the nature and influence of social connectedness. As one of the major dimensions of the social aspects of psychosocial influences, social connectedness is among the most complicated in terms of definition, conceptualization, and measurement. However, the century-long body of theory and findings couple with a recent resurgence of research on the critical impact of these ties for health, illness, and health care to call for an examination of the richness in and limitations of current HRS data. This assessment is comprised of three broad steps: 1) an overview of the nature of social connectedness, and of the dimensions and methodological approaches that can and have been used in studying health, health care, and aging; 2) the range, strengths and limitations of the HRS data on each approach; and 3) suggestions for potential directions to increase the utility of data collected and further research contributions from the HRS. While no tabular listing of items relevant to social connectedness is presented, the sets of items that tap this notion are referenced throughout. Overall, the HRS represents one of, if not the most impressive data sets regarding the ability to examine the influence of social connectedness on health, illness and health care. Given different theoretical and methodological traditions of social connectedness (e.g., the local or ego-centered perspective; social support perspective; social capital perspective; Pescosolido 2006a), the HRS either currently offers a way to tap into various views of social connectedness or holds the potential to do so. Specifically, the HRS includes four kinds of social connectedness data: socio-demographic proxies that represent a tie (e.g., marital status) with detailed data on the nature of the bond; social support batteries which offer respondent perceptions of the overall positive and negative aspects of sets of relationships; eco-centric tie data, which provide a list of names or roles that can provide support (i.e. latent ties); and networks of event response in which respondents list individuals who were called upon (e.g., activated ties) under certain conditions. Given the individually-based and national scope of the HRS, the collection of full or complete network data is not feasible at present. Four strategies could improve the collection and use of social connectedness data in the HRS. First, data collection sections that are explicit or implicit ego-centric name generators or activated ties lists could be expanded and refined to provide more complete data. Under the looping structure of the HRS, both the ego-centric and event response batteries can serve as a foundation for expanded network batteries. Second, given the increasing role of social media in contemporary American lives, the HRS section on the use of technology should be reviewed and expanded to tap into virtual ties. Third, locator data designed to improve follow-up of the HRS samples can form the basis of a network roster and for analyses of the dynamics of ties and its influence on health and health care. Fourth, while it is not possible to go back and recapture data about social connectedness, a sub study which targets the named social convoy over a person s life (defined only as time in the HRS) would provide invaluable data that could not be collected from any other existing study. That is, while subject to a variety of criticism (e.g., telescoping effects), the ability to collect data on extent of turnover and the reasons for shifts in social connectedness would allow an analysis of the impact of social network dynamics in later life, potentially reveal key turning points in social network support, and offer targeted points of interventions for fostering the social connectedness that has, to date, been shown (in the HRS and other studies) to be so essential to health and well-being.
Keywords: Health Conditions and Status; Methodology

Social stratification of body weight trajectory in middle-age and older americans: results from a 14-year longitudinal study. - Anda Botoseneanu; Jersey Liang (J Aging Health, 2011)
OBJECTIVE: To depict the trajectory of BMI from middle to late adulthood and to examine social variations in BMI trajectories. METHOD: Eight waves (1992-2006) of the Health and Retirement Study involving a nationally representative sample of Americans aged 51 to 61 years at baseline were used. Changes in BMI were analyzed using hierarchical linear modeling with time-constant and time-varying covariates. RESULTS: BMI increased linearly over time. Compared with Caucasians, African-Americans had higher BMI levels, while Hispanics had similar BMI levels, but lower rates of increase over time. Higher education predicted lower BMI levels and was not associated with the rate of change. Younger age-at-baseline predicted lower BMI level and lower rate of increase. No gender differences were found. DISCUSSION: Observed racial/ethnic and educational differences in BMI trajectory from middle to old age inform policies and interventions aimed at modifying health risks and reducing health disparities in old age.
Keywords: Age Factors; Aged; Aging; Body Mass Index; ethnicity; Female; Health Status Disparities; Humans; Linear Models; Longitudinal Studies; Male; Middle Aged; Multivariate Analysis; Obesity; Psychometrics; Risk Assessment; Self Report; Social Class; Socioeconomic factors; Time Factors; United States

Socioeconomic inequalities in old-age mortality: a comparison of Denmark and the USA. - Rasmus Hoffmann (Soc Sci Med, 2011)
Previous studies have reported important variations in the magnitude of health inequalities between countries that belong to different welfare systems. This suggests that there is scope for reducing health inequalities by means of country-level interventions. The present study adds to this literature by exploring whether the magnitude of socioeconomic inequalities in mortality is associated with social inequality levels. Denmark and the USA belong to fundamentally different welfare systems (social democratic and liberal) and our study thereby contributes to the ongoing debate on whether welfare systems are linked to health inequalities. We analyze Denmark and the USA in terms of socioeconomic differences in mortality above age 58. The data sources were Danish register data from 1980 to 2002 (n = 2,029,324), and survey data from the US Health and Retirement Study (HRS) from 1992 to 2006 (n = 9374). Survival analysis was used to study the impact of socioeconomic status on mortality and the magnitude of mortality differences between the two countries was compared. The results showed surprisingly that mortality differentials were larger in Denmark than in the USA even after controlling for a number of covariates: The poorest 10 percent of the Danish elderly population have a mortality rate ratio of 3.32 (men) and 3.70 (women) compared to the richest 25 percent. In the USA the corresponding rate ratios are 1.67 and 1.56. Low income seems to be a more powerful risk factor for mortality than low education. A number of possible explanations for higher mortality differences in Denmark are discussed: unintended positive correlation between generous health services and health inequality, early life influences, mortality selection, and relative deprivation.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Cross-Cultural Comparison; Denmark; Educational Status; Female; Health Expenditures; Humans; Income; Life Expectancy; Male; Middle Aged; Mortality; Political Systems; Social Class; Social Welfare; United States

Socioeconomic inequalities in self-rated health among middle-aged and older adults. - Kim, Jinhyun (Soc Work Health Care, 2011)
Despite increased attention to health disparities in the United States, few studies have examined the impact of socioeconomic inequalities on self-rated health over time. Using data from the Health and Retirement Study, this article investigates socioeconomic inequalities in self-rated health among middle-aged and older adults. The findings indicated that higher level of income, assets, and education, and having private health insurance predicted better self-rated health. In particular, increases in income or assets predicted slower decline in self-rated health. Interestingly, economic status had greater impact on females' decline in self-rated health. Blacks were less likely to suffer rapid decline in self-rated health than were whites. The findings led to the conclusion that health disparities should be understood as the interplay of socioeconomic status, gender, and race/ethnicity.
Keywords: Aged; Female; Health Status Disparities; Humans; Insurance Coverage; Insurance, Health; Male; Middle Aged; Self Report; Sex Factors; Socioeconomic factors

Socioeconomic status and race/ethnicity independently predict health decline among older diabetics. - Emily J Nicklett (BMC Public Health, 2011)
BACKGROUND: There are pervasive racial and socioeconomic differences in health status among older adults with type 2 diabetes. The extent to which racial/ethnic and socioeconomic disparities unfold to differential health outcomes has yet to be investigated among older adults with diabetes. This study examines whether or not race/ethnicity and SES are independent predictors of steeper rates of decline in self-rated health among older adults in the U.S. with type 2 diabetes. METHODS: The study population was a subset of diabetic adults aged 65 and older from the Health and Retirement Study. Respondents were followed up to 16 years. Multilevel cumulative logit regression models were used to examine the contributions of socioeconomic indicators, race/ethnicity, and covariates over time. Health decline was measured as a change in self-reported health status over the follow-up period. RESULTS: Relative to whites, blacks had a significantly lower cumulative odds of better health status over time (OR: 0.61, p < .0001). Hispanics reported significantly lower cumulative odds better health over time relative to whites (OR: 0.59, p < .05). Although these disparities narrowed when socioeconomic characteristics were added to the model, significant differences remained. Including socioeconomic status did not remove the health effects of race/ethnicity among blacks and Hispanics. CONCLUSIONS: The author found that race/ethnicity and some socioeconomic indicators were independent predictors of health decline among older adults with diabetes.
Nicklett, Emily J Research Support, N.I.H., Extramural Research Support, Non-U.S. Gov't Research Support, U.S. Gov't, P.H.S. England BMC public health BMC Public Health. 2011 Sep 2;11:684.
Keywords: Aged; Aged, 80 and over; Black People; Diabetes Mellitus, Type 2; Diagnostic Self Evaluation; Female; Follow-Up Studies; Health Status Disparities; Hispanic or Latino; Humans; Male; Social Class; United States; White People

Sources of variability in estimates of the prevalence of Alzheimer's disease in the United States. - Robert S Wilson; David R Weir; Sue E Leurgans; Denis A Evans; Liesi Hebert; Kenneth M. Langa; Brenda L Plassman; Brent J. Small; David A Bennett (Alzheimers Dement, 2011)
BACKGROUND: The prevalence of Alzheimer's disease (AD) in the United States was estimated at 2.3 million in 2002 by the Aging, Demographics, and Memory Study (ADAMS), which is almost 50% less than the estimate of 4.5 million in 2000 derived from the Chicago Health and Aging Project. METHODS: We considered how differences in diagnostic criteria may have contributed to these differences in AD prevalence. RESULTS: We identified several important differences in diagnostic criteria that may have contributed to the differing estimates of AD prevalence. Two factors were especially noteworthy. First, the Diagnostic and Statistical Manual of Mental Disorders III-R and IV criteria of functional limitation documented by an informant used in ADAMS effectively concentrated the diagnosis of dementia toward a relatively higher level of cognitive impairment. ADAMS separately identified a category of cognitive impairment not dementia and within that group there were a substantial number of cases with "prodromal" AD (a maximum of 1.95 million with upweighting). Second, a substantial proportion of dementia in ADAMS was attributed to either vascular disease (representing a maximum of 0.59 million with upweighting) or undetermined etiology (a maximum of 0.34 million), whereas most dementia, including mixed dementia, was attributed to AD in the Chicago Health and Aging Project. CONCLUSION: The diagnosis of AD in population studies is a complex process. When a diagnosis of AD excludes persons meeting criteria for vascular dementia, when not all persons with dementia are assigned an etiology, and when a diagnosis of dementia requires an informant report of functional limitations, the prevalence is substantially lower and the diagnosed cases most likely have a relatively higher level of impairment.
Keywords: Aged; Aged, 80 and over; Alzheimer disease; Community Health Planning; Comorbidity; Dementia; Diagnosis, Differential; Female; Humans; Incidence; Male; Prevalence; United States

Spousal associations between functional limitation and depressive symptom trajectories: Longitudinal findings from the study of Asset and Health Dynamics Among the Oldest Old (AHEAD). - Christiane A Hoppmann; Denis Gerstorf; Anita Hibbert (Health Psychol, 2011)
OBJECTIVE: To examine spousal associations between functional limitation and depressive symptom trajectories in a national sample of older long-term married couples. DESIGN: We used 14.5-year longitudinal data on functional limitations and depressive symptoms from 1,704 couples participating in the Study of Asset and Health Dynamics Among the Oldest Old (AHEAD). MAIN OUTCOME MEASURES: Activities of daily living and a short version of the Center for Epidemiologic Studies Depression scale were used. RESULTS: Between-person difference findings corroborate previous research by showing that levels and changes in functional limitations and depressive symptoms are closely interrelated among wives and husbands. Our results further demonstrate sizable associations in levels and changes in functional limitations and depressive symptoms between spouses. For example, functional limitation levels in one spouse were associated with depressive symptom levels in the other spouse. Spousal associations remained after controlling for individual (age, education, cognition) and spousal covariates (marriage duration, number of children) and did not differ between women and men. CONCLUSION: Our findings highlight the important role of marital relationships in shaping health trajectories in old age because they show that some of the well-documented between-person differences in functional limitations and depressive symptoms are in fact related to spouses.
Hoppmann, Christiane A Gerstorf, Denis Hibbert, Anita U01 AG009740-12/AG/NIA NIH HHS/United States U01AG009740/AG/NIA NIH HHS/United States Research Support, N.I.H., Extramural Research Support, Non-U.S. Gov't United States Nihms256806 Health Psychol. 2011 Mar;30(2):153-62.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Aging; depression; Female; Humans; Longitudinal Studies; Male; Psychometrics; Spouses; United States

The State and Future of Blood-Based Biomarkers in the Health and Retirement Study - Thomas W McDade (Forum for Health Economics and Policy, 2011)
The Health and Retirement Study (HRS) is an important national resource for policy makers and investigators across a wide range of disciplines, and it is critical that the study collects the best information possible on the health status of its participants within the constraints of the survey design, and without compromising the integrity of the sample. Potential directions for the collection and analysis of biomarker data in future waves of HRS are discussed, with a primary focus on blood-based biomarkers. Advantages and disadvantages of various methods for collecting blood in the home are considered, with particular attention given to the strengths and weaknesses of dried blood spot (DBS) sampling. DBS sampling has been widely applied in recent biosocial surveys due to the low cost and burden associated with sample collection, but these benefits need to be weighed against challenges associated with quantification in the laboratory. Attention is also given to additional biomarkers that may be of relevance to HRS, and that would expand the survey s current focus on obesity and metabolic syndrome. Measures of inflammation, pathogen exposure, reproductive function, stress, and epigenetic modifications are suggested as potentially productive future directions for the study. In addition, the analysis concludes with the following recommendations for HRS: Continue to collect DBS samples, but consider alternatives; implement enhanced procedures for quality control; calibrate DBS results against plasma values, and invest in methods development.
Keywords: Health Conditions and Status; Methodology

STOCK MARKET CRASH AND EXPECTATIONS OF AMERICAN HOUSEHOLDS. - Péter Hudomiet; Kezdi, Gabor; Robert J. Willis (J Appl Econ, 2011)
This paper utilizes data on subjective probabilities to study the impact of the stock market crash of 2008 on households' expectations about the returns on the stock market index. We use data from the Health and Retirement Study that was fielded in February 2008 through February 2009. The effect of the crash is identified from the date of the interview, which is shown to be exogenous to previous stock market expectations. We estimate the effect of the crash on the population average of expected returns, the population average of the uncertainty about returns (subjective standard deviation), and the cross-sectional heterogeneity in expected returns (disagreement). We show estimates from simple reduced-form regressions on probability answers as well as from a more structural model that focuses on the parameters of interest and separates survey noise from relevant heterogeneity. We find a temporary increase in the population average of expectations and uncertainty right after the crash. The effect on cross-sectional heterogeneity is more significant and longer lasting, which implies substantial long-term increase in disagreement. The increase in disagreement is larger among the stockholders, the more informed, and those with higher cognitive capacity, and disagreement co-moves with trading volume and volatility in the market.

Subjective Health Assessments And Active Labor Market Participation Of Older Men: Evidence From A Semiparametric Binary Choice Model With Nonadditive Correlated Individual-Specific Effects - Jürgen Maurer; Roger Klein; Francis Vella (The Review of Economics and Statistics, 2011)
We use panel data from the U.S. Health and Retirement Study, 1992-2002, to estimate the effect of self-assessed health limitations on the active labor market participation of older men. Self-assessments of health are likely to be endogenous to labor supply due to justification bias and individual-specific heterogeneity in subjective evaluations. We address both concerns. We propose a semiparametric binary choice procedure that incorporates nonadditive correlated individual-specific effects. Our estimation strategy identifies and estimates the average partial effects of health and functioning on labor market participation. The results indicate that poor health plays a major role in labor market exit decisions. PUBLICATION ABSTRACT
Keywords: Demographics; Employment and Labor Force; Health Conditions and Status; Methodology; Other

Subsidized housing not subsidized health: health status and fatigue among elders in public housing and other community settings. - Parsons, Pamela L; Briana Mezuk; Scott M Ratliff; Kate L Lapane (Ethn Dis, 2011)
OBJECTIVES: To estimate trends in the prevalence of fatigue among elders living in public housing or in the community; to compare health status of elders living in public housing to their community-dwelling counterparts. DESIGN: Cross-sectional study. SETTING: Community-dwelling elders who reported ever residing in public housing were compared to those living in other community settings. PARTICIPANTS: Participants of the Health and Retirement Study (seven waves of interviews conducted from 1995 through 2006) interviewed in 2006 with complete data on housing status, self-report measures of health status and measures of functioning (n = 16,191). MEASUREMENTS: Self-reported fatigue, functioning, and other health conditions. We also evaluated four functional indices: overall mobility, large muscle functioning, gross motor functioning, and fine motor functioning. RESULTS: Those reporting having lived in public housing were twice as likely to rate their health as fair or poor relative to those with no public housing experience (57.3% vs 26.9%, respectively). Cardiac conditions, stroke, hypertension, diabetes, arthritis and psychiatric problems were all more prevalent in those living in public housing relative to community-dwelling elders not living in public housing. Fatigue was more prevalent in persons residing in public housing (26.7%) as compared to other community-dwelling elders (17.8%). CONCLUSION: The health status of persons residing in public housing is poor. Fatigue and comorbid conditions are highly prevalent and more common in those living in public housing. Developing care models that meet the needs of this oft-neglected population is warranted.
Parsons, Pamela L Mezuk, Briana Ratliff, Scott Lapane, Kate L K12 HD055881/HD/NICHD NIH HHS/United States UL1 RR031990-01/RR/NCRR NIH HHS/United States UL1RR031990/RR/NCRR NIH HHS/United States Comparative Study Research Support, N.I.H., Extramural United States Ethnicity and disease Nihms287854 Ethn Dis. 2011 Winter;21(1):85-90.
Keywords: Aged; Chronic disease; Comorbidity; Cross-Sectional Studies; Fatigue; Female; Health Status Disparities; Humans; Male; Poverty; Prevalence; Public Housing; United States

Successful Aging and Obesity: Social and Developmental Heterogeneity in Trajectories of Body Weight from Middle to Older Ages - Anda Botoseneanu (University of Michigan, 2011)
Obesity is increasingly prevalent among older adults, yet little is known about the distribution of long-term trajectories of body-weight in this age group. The three essays included in this dissertation aim to depict the trajectories of body-mass index (BMI) from middle to old age and to examine social and behavioral variations in these trajectories. Eight waves (1992-2006) of the Health and Retirement Study involving a nationally representative cohort of Americans aged 51 to 61 years at baseline were used. Changes in BMI were analyzed using alternatively hierarchical linear modeling or semiparametric mixture modeling, with adjustment for time-constant and time-varying covariates. First study finds that over 14 years, respondents followed a linearly increasing BMI trajectory. Compared with Caucasians, African-Americans had higher BMI levels, while Hispanics had similar BMI levels, but lower rates of increase over time. Higher education predicted lower BMI levels and was not associated with the rate of change. Older age-at-baseline predicted lower BMI levels and lower rates of increase. No gender differences were found. The second study shows that smoking and vigorous physical activity (user status and initiation) were associated with significantly lower BMI trajectories over time. Cessation of smoking and physical activity resulted in higher BMI trajectories over time. The weight-gaining effect of smoking cessation increased during the study period, while the strength of association between BMI trajectories and PA or alcohol use were constant. In the third study, five distinct BMI trajectories are identified, differing primarily in their intercept: normal BMI trajectory (19.9% of sample), overweight (43.8%), borderline-obese (25.4%), obese (8.9%), and morbidly-obese (2.1%). Each trajectory showed an upward trend over the study period, although the rate-ofincrease varied between trajectories. Compared with Whites, Blacks and Hispanics had greater probabilities of membership in the higher BMI trajectory groups. Females had approximately half the risk of following the overweight and obese BMI trajectories compared with males. In conclusion, significant racial/ethnic, gender and educational heterogeneity in BMI trajectories exists in older adults. Health behaviors provide beneficial modifications in BMI trajectories. Tailoring of public health and clinical interventions to trajectory group characteristics may reduce obesity-related health disparities in aging.
Keywords: Health Conditions and Status; Healthcare; Women and Minorities

Self-reported neighborhood environment and risk of type 2 diabetes in the Health and Retirement Study and English Longitudinal Study of Ageing - Goldoftas, Barbara (Boston University, 2010)
Keywords: Demographics; Health Conditions and Status; Retirement Planning and Satisfaction

Self-reported versus measured height and weight in the health and retirement study. - Meng, Hongdao; Xiaoxing He; Dixon, Denise (J Am Geriatr Soc, 2010)
Keywords: Aged; Body Height; Body Weight; Female; Humans; Male; Middle Aged; Obesity; Population Surveillance; Prevalence; Reproducibility of Results; Sensitivity and Specificity; United States

Situational versus chronic loneliness as risk factors for all-cause mortality. - Sharon Shiovitz-Ezra; Liat Ayalon (Int Psychogeriatr, 2010)
BACKGROUND: Several international studies have substantiated the role of loneliness as a risk factor for mortality. Although both theoretical and empirical research has supported the classification of loneliness as either situational or chronic, research to date has not evaluated whether this classification has a differential impact upon mortality. METHODS: To establish the definition of situational vs. chronic loneliness, we used three waves of the Health and Retirement Study (HRS), a nationally representative sample of Americans over the age of 50 years. Baseline data for the present study were collected in the years 1996, 1998, and 2000. The present study concerns the 7,638 individuals who completed all three waves; their loneliness was classified as either not lonely, situational loneliness or chronic loneliness. Mortality data were available through to the year 2004. RESULTS: Those identified as "situationally lonely" (HR = 1.56; 95% CI: 1.52-1.62) as well as those identified as "chronically lonely" (HR = 1.83; 95% CI: 1.71-1.87) had a greater risk for all cause mortality net of the effect of possible demographic and health confounders. Nonetheless, relative to those classified as "situationally lonely," individuals classified as "chronically lonely" had a slightly greater mortality risk. CONCLUSIONS: The current study emphasizes the important role loneliness plays in older adults' health. The study further supports current division into situational vs. chronic loneliness, yet suggests that both types serve as substantial mortality risks.
Keywords: Age Factors; Aged; Aged, 80 and over; Aging; Cause of Death; Female; Geriatric Assessment; Health Surveys; Humans; Israel; Life Change Events; Loneliness; Male; Middle Aged; Risk Factors; social isolation; Surveys and Questionnaires; Time Factors

Social security claiming of the elderly in the United States - Peng, Yu-I (Social security claiming of the elderly in the United States, 2010)
This dissertation comprehensively studies the behavior of Social Security retirement benefit claiming of the elderly in the United States, using data from the 1992-2006 Health and Retirement Study (HRS) and the supplement "Prospective Social Security Wealth Measures of Pre-retirees". This dissertation begins by modeling the claiming behavior of Social Security retirement beneficiaries under a framework incorporating the incentives for married couples. For individuals who retire by age 62 (the earliest entitlement age), the results indicate that the expected amount of benefit is a strong predictor for the timing of claiming. However, life expectancy, consistent with previous studies, is not a critical determinant of the claiming decision alone, even after taking into account the dependent spouse's longevity expectation. The second chapter models the claiming behavior among individuals who have not retired by age 62 jointly with their retirement behavior. The results show a high correlation between the two decisions. By breaking down the sample, it is found that claiming is attached to retirement; after withdrawal from the labor force and with no labor income, retirees would rely on the Social Security benefits, and liquidity holding becomes a major factor explaining how soon retirees claim their benefits. However, for late-retiring workers, the Social Security retirement benefits do not give much retirement incentive. The third chapter of this dissertation brings in one of the most important Social Security mechanisms, the Social Security earnings test, and takes advantage of its recent reform, the abolishment of the test above the Normal Retirement Age (NRA) in year 2000, to analyze the role of the earnings test in the decisions of claiming and retirement. The earnings test is found to be a crucial factor that links the dates of them.
Keywords: Employment and Labor Force; Health Conditions and Status; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security

The Social Security Early Retirement Benefit as Safety Net - John Bound; Timothy A Waidmann; Michigan Retirement Research Center (The University of Michigan, Michigan Retirement Research Center, 2010)
In this paper we used the Health and Retirement Study to examine the health and economic status of those who collect Social Security retirement benefits prior to the full retirement age. We used a propensity score reweighting method to estimate the fraction of early retirees who uses early retirement benefits as a safety net against deteriorating health and who might be induced to apply for disability benefits (SSDI) or retire without income replacement if the generosity or availability of early retirement benefits were reduced. We find that while the majority of early retirees would likely not qualify for disability benefits, approximately one in five have health characteristics similar to SSDI beneficiaries, and thus might not be able to replace losses in benefit income with labor income.
Keywords: Demographics; Disabilities; Retirement Planning and Satisfaction; Social Security

Social Security Reform: Raising the Retirement Ages Would Have Implications for Older Workers and SSA Disability Rolls - United States Governmental Office (Washington, DC, U.S. Government Accountability Office, 2010)
Question: What are the characteristics of those nearing retirement and how likely is it that they will be able to continue working should the retirement ages be raised? What policy options might help to reduce adverse effects on those who are unable to work longer? Finding: Using the NIA-funded Health and Retirement Study and citing a number of studies conducted by NIA-funded researchers, GAO found that raising the retirement ages would likely increase the number of workers applying for and receiving benefits through the Disability Insurance (DI) program. This increase would offset some of the savings implied by the retirement age increases, as well as increasing the DI caseload and administrative costs (which tend to be higher than retirement program costs). Waiting until later to receive benefits could also create financial hardship for some workers, namely those that are unable to continue working but do not qualify for DI or other governmental assistance programs. While policy options exist to mitigate the impact on affected workers, doing so will likely require expanding programs and increase benefit costs. Finding the balance between worker protections and costs will likely be challenging.
Keywords: Disabilities; Public Policy; Retirement Planning and Satisfaction

Social Ties and Depression: An Intersectional Examination of Black and White Community-Dwelling Older Adults - Christine A Mair (Journal of Applied Gerontology, 2010)
Aging literature often links social ties to lower depression for older adults; however, research shows inconsistent findings by race and gender. Drawing from an intersectionality framework, this article explores whether the relationship between social ties and depression is moderated by race and gender for a nationally representative sample of diverse, community-dwelling older adults (aged 60 and older). Analysis of the most recent wave of the Health and Retirement Study (HRS) indicates that White men, Black men, White women, and Black women differ in terms of the relationship between social ties and depression. Main findings include (a) the overwhelming benefit of marriage and partnership, (b) pronounced differences between Black women s and White women s friend and kin ties, and (c) the potential vulnerability of older Black men. Findings highlight the importance of catering community-based elder support toward diverse aging populations. Potential community-based care solutions are discussed.
Keywords: Demographics; Health Conditions and Status; Other

Sociodemographic and health-related risks for loneliness and outcome differences by loneliness status in a sample of U.S. older adults. - Laurie A. Theeke (Res Gerontol Nurs, 2010)
This study assesses sociodemographic and health-related factors associated with loneliness and outcome differences between loneliness groups using a sample of 13,812 older adults from the U.S Health and Retirement Study. Descriptive and bivariate analyses were followed by logistic regression to evaluate risks and analysis of covariance testing to determine outcome differences. Overall, prevalence of loneliness was 16.9%. Nonmarried status, poorer self-report of health, lower educational level, functional impairment, increasing number of chronic illnesses, younger age, lower income, and less people living in the household were all associated with loneliness. The chronically lonely group reported less exercise, more tobacco use, less alcohol use, a greater number of chronic illnesses, higher depression scores, and greater average number of nursing home stays. Future research evaluating the effectiveness of both prevention and treatment interventions for loneliness in older adults would provide empirical data to further guide gerontological nursing practice.
Keywords: Aged; Aged, 80 and over; Female; Health Status; Humans; Logistic Models; Loneliness; Male; Middle Aged; Multivariate Analysis; Risk Factors; Socioeconomic factors; United States

Socio-economic Status and Mortality: Perceptions and Outcomes - David R Weir (2010)
This paper draws on over 300,000 person-years of mortality observation on over 30,000 participants in the Health and Retirement Study (HRS) to study the relationship of education, income, and wealth to mortality expectations and mortality outcomes in older Americans. Using quintiles to facilitate comparison across variables, we find that all three SES measures significantly predict mortality, but that in joint models education is dominated by the other two which are realized later in life, and particularly by wealth. As others have found, SES differentials in mortality decline with age, though wealth remains a powerful determinant even at advanced ages. When strictly interpreted as expressions of relative risk, the subjective probabilities of survival offered by HRS respondents substantially understate the true differentials by SES, as they do for other factors like smoking and very low or very high body weight. In particular, the large mortality disadvantage of low wealth is not recognized. SES accounts for most of black-white differentials in mortality, whereas it unveils an Hispanic advantage relative to other whites that was masked by lower SES.
Keywords: Demographics; Health Conditions and Status

Spending Patterns in the Older Population - Michael D Hurd; Susann Rohwedder (Aging Consumer: Perspectives from Psychology and Economics, 2010)
This chapter deals with the concrete differences in consumption behavior across a person's life span. Although there is a prevasive belief that households reduce consumption at retirement, the interpretation that consumers adjust their spending after discovering they have fewer economic resources than they had anticipated prior to retirement is not wholly consistent with empirial evidence. The spending habits of older adults are determined by a variety of factors like age, marital status, and economic resources. Specifically, as the population ages, it will tend to spend less on transportation services, vacations, and food; and more on health care and charitable giving.
Keywords: Consumption and Savings; Demographics; Health Conditions and Status; Retirement Planning and Satisfaction

Spousal loss, children, and the risk of nursing home admission. - Claire Noël-Miller (J Gerontol B Psychol Sci Soc Sci, 2010)
UNLABELLED: OBJECTIVES. Informed by a life course perspective, this study investigates the effects of spousal loss and availability of adult children on elderly husbands' and wives' risk of nursing home entry. METHODS: Based on longitudinal data from the Health and Retirement Study, we studied 2,116 couples who were community residents in 1998. We estimate proportional hazards models for husbands' and wives' duration to first nursing home admission during 8 years of follow-up. RESULTS: Overall, 438 (20.7%) husbands and 382 (18.1%) wives were institutionalized, and 362 (17.1%) husbands and 701 (33.1%) wives lost their spouse. Accounting for measured covariates, the risk of nursing home entry doubled for men following spousal death, but was unchanged for women. Results indicate that adult children reduced wives' risk of nursing home admission regardless of husbands' vital status, but buffered husbands' risk only after the death of their wives. We uncover suggestive evidence of parent-child gender concordance in children's buffering effect of widowed parents' risk of institutionalization. Discussion. Our findings are consistent with gender variations in spousal caregiving and in husbands' and wives' relative reliance on care from a partner and children. This study provides new evidence on the relationship between institutionalization and family structure among married elderly persons.
Keywords: Activities of Daily Living; Adult children; Aged; Aged, 80 and over; Aging; Bereavement; Caregivers; Family Characteristics; Female; Gender Identity; Homes for the Aged; Humans; Long-term Care; Male; Nursing homes; Parent-Child Relations; Patient Admission; Proportional Hazards Models; Social Support; Spouses; Utilization Review

SSI eligibility and participation among the aged: A hazard model approach - Jin H. Kim (The University of Wisconsin - Madison, 2010)
This dissertation revisits the historic policy concern over nonparticipation in the Supplemental Security Income (SSI) program, and more specifically, the question of why take- up of SSI program benefits among the aged is perpetually lower than what theory proposes. The most contemporary research model suggests that from a static or cross-sectional perspective, the aged take-up decision is primarily determined by the financial situation of the eligible individuals (McGarry, 1995). Yet, extant studies have yet to establish a dynamic model of SSI participation that explicitly takes into account the changing circumstances of the elderly. For many elders, the period after age 65 is a time of rapid and considerable changes in the areas of income, health and functioning, as well as living situations. As such, this study extends the current literature by exploring the longitudinal processes leading to both SSI eligibility and eventual take-up of benefits among the aged. Methodologically, the research relies on event history analysis of data from the Health and Retirement Study spanning the years 1996-2006 to explain both the timing of transition to eligibility and participation status, as well as the role of life events on the aforementioned outcomes of interest. Life table analysis yields a cumulative, twelve-year take-up rate of ∼36% among those eligible, and a cumulative, twelve-year eligibility rate of ∼25% among those at risk. Meanwhile, hazard models reveal that changes in health and functioning over time in addition to changes in the expected benefit significantly influence the participation decision.
Keywords: Demographics; Expectations; Methodology; Other; Social Security

Stability and changes in living arrangements: relationship to nursing home admission and timing of placement. - Judith D Kasper; Liliana E Pezzin; Rice, J Bradford (J Gerontol B Psychol Sci Soc Sci, 2010)
OBJECTIVES: To examine whether stability of living arrangements and changes in household composition-both types and frequency-influence nursing home placement or timing to entry among older people. METHODS: Data from the first 5 waves of the Assets and Health Dynamics of the Elderly (1993-2002) on 8,093 persons aged 70 years or older at baseline are used in probit and hazard models to predict nursing home entry and time to entry. RESULTS: Stable living arrangements carry different risks of institutionalization. Those living continuously alone or with others were at highest risk; at lowest risk were those living continuously with a spouse or the same child (lowest overall). Changes in household composition were protective against nursing home entry and slowed time to entry; types of change were not influential when number of changes was taken into account. DISCUSSION: Results suggest that stability of living arrangements in and of itself is not protective against institutionalization. Having options that allow one to change living arrangements over time in response to changing needs for assistance is of importance if the goal is to avoid institutional care or extend community residence prior to entry.
Keywords: Aged; Aged, 80 and over; Family Characteristics; Female; Health Status; Homes for the Aged; Humans; Institutionalization; Male; Marital Status; Multivariate Analysis; Nursing homes; Risk Factors; Single Person; Socioeconomic factors; Time Factors; United States

Subjective Mortality Expectations and Consumption and Saving Behaviours among the Elderly - Salm, Martin (Canadian Journal of Economics, 2010)
Life expectancy is an important factor that individuals have to take into account for saving and consumption choices. The life-cycle model of consumption and saving behaviour predicts that consumption growth should decrease with higher mortality rates. The aim of this study is to test this hypothesis based on data about subjective longevity expectations from the Health and Retirement Study merged with detailed consumption data from two waves of the Consumption and Activities Mail Survey. This study finds that an increase in subjective mortality by 1 corresponds to an annual decrease in consumption of non-durable goods of around 1.8 .
Using Smart Source Parsing August pp
Keywords: Consumption and Savings; Employment and Labor Force; Event History/Life Cycle; Health Conditions and Status; Women and Minorities

Successful aging in the United States: prevalence estimates from a national sample of older adults. - Sara J McLaughlin; Cathleen M. Connell; Steven G Heeringa; Lydia W Li; J Scott Roberts (J Gerontol B Psychol Sci Soc Sci, 2010)
OBJECTIVES: To estimate the prevalence of successful aging in the United States, with the broad aim of contributing to the dialogue on Rowe and Kahn's concept of successful aging. METHODS: Using data from the Health and Retirement Study, the prevalence of successful aging was calculated for adults aged 65 years and older at four time points: 1998, 2000, 2002, and 2004. Successful aging was operationalized in accordance with Rowe and Kahn's definition, which encompasses disease and disability, cognitive and physical functioning, social connections, and productive activities. RESULTS: No greater than 11.9% of older adults were aging "successfully" in any year. The adjusted odds of successful aging were generally lower for those of advanced age, male gender, and lower socioeconomic status. Between 1998 and 2004, the odds of successful aging declined by 25%, after accounting for demographic changes in the older population. DISCUSSION: Few older adults meet the criteria put forth in Rowe and Kahn's definition of successful aging, suggesting the need for modification if the concept is to be used for broad public health purposes. Disparities in successful aging were evident for socially defined subgroups, highlighting the importance of structural factors in enabling successful aging.
Keywords: Affect; Aged; Aging; Female; Health Status; Humans; Male; Middle Aged; Prevalence; United States

Surgery as a teachable moment for smoking cessation. - Yu Shi; David O. Warner (Anesthesiology, 2010)
BACKGROUND: A "teachable moment" is an event that motivates spontaneous behavior change. Some evidence suggests that major surgery for a smoking-related illness can serve as a teachable moment for smoking cessation. This study tested the hypotheses that surgery increases the likelihood of smoking cessation and that cessation is more likely after major surgical procedures compared with outpatient surgery. METHODS: Secondary analyses were performed of longitudinal biennial survey data (1992-2004) from the nationally representative Health and Retirement Study of U.S. adults older than 50 yr, determining the relationship between the incidence of smoking cessation and the occurrence of surgery. RESULTS: Five thousand four hundred ninety-eight individuals reported current smoking at enrollment, and 2,444 of them (44.5%) quit smoking during the period of examination. The incidence of quitting in smokers undergoing major surgery was 20.6/100 person-years of follow-up and 10.2/100 person-years in those undergoing outpatient surgery. In a multivariate negative binomial regression model, the incidence rate ratio of quitting associated with major surgery was 2.02 (95% CI: 1.67-2.44) and that of those associated with outpatient surgery was 1.28 (95% CI: 1.09-1.50). Estimates derived from national surgical utilization data show that approximately 8% of all quit events in the United States annually can be attributed to the surgical procedures analyzed. CONCLUSIONS: Undergoing surgery is associated with an increased likelihood of smoking cessation in the older U.S. population. Cessation is more likely in association with major procedures compared with outpatient surgery. These data support the concept that surgery is a teachable moment for smoking cessation.
Keywords: Aged; Aged, 80 and over; Ambulatory Surgical Procedures; Analysis of Variance; Cohort Studies; Female; Follow-Up Studies; General Surgery; Humans; Longitudinal Studies; Male; Middle Aged; Patient Education as Topic; Regression Analysis; Smoking cessation; Treatment Outcome; United States

Selection Bias in Web Surveys and the Use of Propensity Scores - Matthias Schonlau; Arthur H.O. vanSoest; Arie Kapteyn; Mick P. Couper (Sociological Methods and Research, 2009)
Web surveys have several advantages compared to more traditional surveys with in-person interviews, telephone interviews, or mail surveys. Their most obvious potential drawback is that they may not be representative of the population of interest because the sub-population with access to Internet is quite specific. This paper investigates propensity scores as a method for dealing with selection bias in web surveys. The authors' main example has an unusually rich sampling design, where the Internet sample is drawn from an existing much larger probability sample that is representative of the US 50 population and their spouses (the Health and Retirement Study). They use this to estimate propensity scores and to construct weights based on the propensity scores to correct for selectivity. They investigate whether propensity weights constructed on the basis of a relatively small set of variables are sufficient to correct the distribution of other variables so that these distributions become representative of the population. If this is the case, information about these other variables could be collected over the Internet only. Using a backward stepwise regression they find that at a minimum all demographic variables are needed to construct the weights. The propensity adjustment works well for many but not all variables investigated. For example, they find that correcting on the basis of socio-economic status by using education level and personal income is not enough to get a representative estimate of stock ownership. This casts some doubt on the common procedure to use a few basic variables to blindly correct for selectivity in convenience samples drawn over the Internet. Alternatives include providing non-Internet users with access to the Web or conducting web surveys in the context of mixed mode surveys.
Keywords: Methodology

The SES Health Gradient On Both Sides Of The Atlantic - James Banks; Michael Marmot; Oldfield, Zoë; James P Smith (Developments in the economics of aging, 2009)
Looking across many diseases, average health among mature men is much worse in America compared to England. Second, there exists a steep negative health gradient for men in both countries where men at the bottom of the economic hierarchy are in much worse health than those at the top. This health gradient exists whether education, income, or financial wealth is used as the marker of one's SES status. These conclusions are maintained even after controlling for a standard set of behavioral risk factors such as smoking, drinking, and obesity and are equally true using either biological measures of disease or individual self-reports. In contrast to these disease based measures, health of American men appears to be superior to the health of English men when self-reported general health status is used. The contradiction most likely stems instead from different thresholds used by Americans and English when evaluating health status on subjective scales. For the same objective health status, Americans are much more likely to say that their health is good than are the English. Finally, feedbacks from new health events to household income are one of the reasons that underlie the strength of the income gradient with health in England.
Keywords: Cross-National; Healthcare; Risk Taking

Sin Taxes: Do Heterogeneous Responses Undercut Their Value? - Padmaja Ayyagari; Deb, Partha; Jason M. Fletcher; William T Gallo; Jody L Sindelar (NBER Working Paper, 2009)
This paper estimates the price elasticity of demand for alcohol using Health and Retirement Survey data. To account for unobserved heterogeneity in price responsiveness, we use finite mixture models. We recover two latent groups, one is significantly responsive to price but the other is unresponsive. Differences between these two groups can be explained in part by the behavioral factors of risk aversion, financial planning horizon, forward looking and locus of control. These results have policy implications. Only a subgroup responds significantly to price. Importantly, the unresponsive group drinks more heavily, suggesting that a higher price could fail to curb drinking by those most likely to cause negative externalities. In contrast, those least likely to impose costs on others are more responsive, thus suffering greater deadweight loss yet with less prevention of negative externalities.
Keywords: Health Conditions and Status; Methodology; Public Policy

Smoking and weight change after new health diagnoses in older adults. - Patricia S Keenan (Arch Intern Med, 2009)
BACKGROUND: Smoking and patterns of diet and activity are the 2 leading underlying causes of death in the United States, yet the factors that prompt individuals to adopt healthier habits are not well understood. METHODS: This study was undertaken to determine whether individuals who have experienced recent adverse health events are more likely to quit smoking or to lose weight than those without recent events using Health and Retirement Study panel survey data for 20 221 overweight or obese individuals younger than 75 years and 7764 smokers from 1992 to 2000. RESULTS: In multivariate analyses, adults with recent diagnoses of stroke, cancer, lung disease, heart disease, or diabetes mellitus were 3.2 times more likely to quit smoking than were individuals without new diagnoses (P < .001). Among overweight or obese individuals younger than 75 years, those with recent diagnoses of lung disease, heart disease, or diabetes mellitus lost -0.35 U of body mass index (calculated as weight in kilograms divided by height in meters squared) compared with those without these new diagnoses (P < .001). Smokers with multiple new diagnoses were 6 times more likely to quit smoking compared with those with no new diagnoses. The odds of quitting smoking were 5 times greater in individuals with a new diagnosis of heart disease, and body mass index declined by 0.6 U in overweight or obese individuals with a new diagnosis of diabetes mellitus (P < .001). CONCLUSIONS: Across a range of health conditions, new diagnoses can serve as a window of opportunity that prompts older adults to change health habits, in particular, to quit smoking. Quality improvement efforts targeting secondary as well as primary prevention through the health care system are likely well founded.
Keywords: Age Factors; Aged; Aged, 80 and over; Body Mass Index; Diabetes Mellitus, Type 2; Health Behavior; Health Surveys; Heart Diseases; Humans; Longitudinal Studies; Lung Diseases; Middle Aged; Multivariate Analysis; Neoplasms; Overweight; Racial Groups; Smoking; Smoking cessation; Stroke; United States; Weight Loss

Smoking kills, obesity disables: a multistate approach of the US Health and Retirement Survey. - Mieke Reuser; Luc G Bonneux; Frans J Willekens (Obesity (Silver Spring), 2009)
Increasing BMI causes concerns about the consequences for health care. Decreasing cardiovascular mortality has lowered obesity-related mortality, extending duration of disability. We hypothesized increased duration of disability among overweight and obese individuals. We estimated age-, risk-, and state-dependent probabilities of activities of daily living (ADL) disability and death and calculated multistate life tables, resulting in the comprehensive measure of life years with and without ADL disability. We used prospective data of 16,176 white adults of the Health and Retirement Survey (HRS). Exposures were self-reported BMI and for comparison smoking status and levels of education. Outcomes were years to live with and without ADL disability at age 55. The reference categories were high normal weight (BMI: 23-24.9), nonsmoking and high education. Mild obesity (BMI: 30-34.9) did not change total life expectancy (LE) but exchanged disabled for disability-free years. Mild obesity decreased disability-free LE with 2.7 (95% confidence limits 1.2; 3.2) year but increased LE with disability with 2.0 (0.6; 3.4) years among men. Among women, BMI of 30 to 34.9 decreased disability-free LE with 3.6 (2.1; 5.1) year but increased LE with disability with 3.2 (1.6;4.8) years. Overweight (BMI: 25-29.9) increases LE with disability for women only, by 2.1 (0.8; 3.3) years). Smoking compressed disability by high mortality. Smoking decreased LE with 7.2 years, and LE with disability with 1.3 (0.5; 2.5) years (men) and 1.4 (0.3; 2.6) years (women). A lower education decreased disability-free life, but not duration of ADL disability. In the aging baby boom, higher BMI will further increase care dependence.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Body Mass Index; Disability Evaluation; Educational Status; Female; Health Surveys; Humans; Life Expectancy; Life Tables; Male; Middle Aged; Obesity; Proportional Hazards Models; Prospective Studies; Smoking; United States; White People

Social Security Research at the Michigan Retirement Research Center - R.V. Burkhauser; Alan L Gustman; John Laitner; Olivia S. Mitchell; Amanda Sonnega (Social Security Bulletin, 2009)
Social Security has been a topic of widespread discussion in the last decade. Rising longevity and falling fertility have led to an aging population, which increases solvency challenges for the Social Security system. Public concerns over low national saving have led to an extensive dialog on the merits of reform that might change the U.S. system into one with fully or partially funded personal accounts. Meanwhile, pensions in the private sector have been evolving from predominantly defined benefit (DB) to predominantly defined contribution (DC), raising concerns that workers preparing for retirement have more personal responsibility, with more complex financial challenges, than ever before.
Keywords: Pension; Retirement; Social Security

Social Security Research at the Michigan Retirement Research Center - R.V. Burkhauser; Alan L Gustman; John Laitner; Olivia S. Mitchell; Amanda Sonnega (Social Security Bulletin, 2009)
Social Security has been a topic of widespread discussion in the last decade. Rising longevity and falling fertility have led to an aging population, which increases solvency challenges for the Social Security system. Public concerns over low national saving have led to an extensive dialog on the merits of reform that might change the U.S. system into one with fully or partially funded personal accounts. Meanwhile, pensions in the private sector have been evolving from predominantly defined benefit (DB) to predominantly defined contribution (DC), raising concerns that workers preparing for retirement have more personal responsibility, with more complex financial challenges, than ever before.
Keywords: Meta-analyses; Older Adults; Research; Social Security

Socioeconomic differentials in immune response. - Jennifer B Dowd; Allison E Aiello (Epidemiology, 2009)
BACKGROUND: Lower socioeconomic status (SES) is strongly linked to health outcomes, though the mechanisms are poorly understood. Little is known about the role of the immune system in creating and sustaining health disparities. Here we test whether SES is related to cell-mediated immunity, as measured by the host's ability to keep persistent cytomegalovirus (CMV) antibody levels in a quiescent state. METHODS: Censored regression models were used to test the cross-sectional relationship of education, income, and race/ethnicity with antibody response to CMV, using a nationally representative sample of 9721 respondents aged 25 years and older in the Third National Health and Nutrition Examination Survey (NHANES III, 1988-1994). RESULTS: Among CMV-seropositive respondents, those with less education, lower income, and nonwhite race/ethnicity had higher levels of CMV antibodies at all ages. On average, each additional year of age was associated with CMV antibody levels that were 0.03 units higher (95% confidence interval = 0.03 to 0.04), whereas each additional year of education was associated with antibody levels that were 0.05 units lower (0.02 to 0.09). A doubling of family income was associated with antibody levels that were 0.25 units lower (0.11 to 0.39), the equivalent of 8 fewer years of age-related CMV antibody response. These relationships remained strong after controlling for baseline health conditions, smoking status, and BMI. CONCLUSIONS: SES is associated with an indirect marker of cell-mediated immunity in a nationally representative sample. SES differences in immune control over CMV may have fundamental implications for health disparities over the life course.
Keywords: Adult; Aged; Cytomegalovirus; Cytomegalovirus Infections; Female; Health Status Disparities; Humans; Male; Middle Aged; Nutrition Surveys; Regression Analysis; Social Class; United States

Socioeconomic status and health redux: New evidence from England in a comparative context - Caswell, Kyle J. (Socioeconomic status and health redux: New evidence from England in a comparative context, 2009)
People with higher socioeconomic status (SES) enjoy superior health. For the US, it is especially difficult to identify pathways underpinning this relationship, as it likely reflects differences in access to health care in addition to other factors correlated with SES. In England, however, access to care is universal, so that if SES is positively correlated with health, its main effects must come via alternative pathways other than access to care. This dissertation investigates the effects of SES on health outcomes, and vice versa, using the English Longitudinal Study of Ageing (ELSA). As the ELSA is similar to the US Health and Retirement Study, I compare the SES-health relation between countries. I find that the effect of SES on health is significant in England, with wealth the most important in guarding against negative health outcomes. However, for lower SES individuals, there are important differences between countries, suggesting that access to care has its largest effect among the least advantaged. Furthermore, new health events affect the economic resources of English individuals less than their US counterparts. Finally, there is evidence among married couples that wives respond to their husbands' new health conditions by increasing market labor hours--i.e., an 'added worker effect.'
Keywords: Cross-National; Demographics; Health Conditions and Status; Healthcare; Net Worth and Assets; Other; Public Policy

Spouse-rated vs self-rated health as predictors of mortality. - Liat Ayalon; Kenneth E Covinsky (Arch Intern Med, 2009)
BACKGROUND: The Health and Retirement Study is a national sample of Americans older than 50 years and their spouses. The present study evaluated cross-sectional and longitudinal data from January 2000 through December 2006. The objective of the study was to evaluate the roles of spouse-rated vs self-rated health as predictors of all-cause mortality among adults older than 50 years. METHODS: A total of 673 dyads of married couples were randomly selected to participate in a Health and Retirement Study module examining spouse-rated health. For each couple, one member was asked to rate his or her overall health status, and his or her spouse was asked to report the partner's overall health status. Mortality data were available through 2006. RESULTS: Our findings demonstrate that spouse-rated health (area under the curve, 0.75) is as strong a predictor of mortality as self-rated health (area under the curve, 0.73) (chi(2)(1) = 0.36, P = .54). Combining spouse-rated and self-rated health predicts mortality better than using self-rated health alone (area under the curve, 0.77) (chi(2)(1) = 6.72, P = .009). CONCLUSIONS: Spouse ratings of health are at least as strongly predictive of mortality as self-rated health. This suggests that, when self-rated health is elicited as a prognostic indicator, spouse ratings can be used when self-ratings are unavailable. Both measures together may be more informative than either measure alone.
Keywords: Aged; Cross-Sectional Studies; Female; Health Status; Humans; Longitudinal Studies; Male; Middle Aged; Self-Assessment; Spouses

Statistical design and estimation for the national social life, health, and aging project. - O'Muircheartaigh, Colm; Eckman, Stephanie; Smith, Stephen (J Gerontol B Psychol Sci Soc Sci, 2009)
OBJECTIVES: The paper discusses the sample design of the National Social Life, Health, and Aging Project (NSHAP) and how the design affects how estimates should be calculated from the survey data. The NSHAP study allows researchers to study the links between sexuality and health in older adults. The goal of the design was to represent adults aged 57-85 years in six demographic domains. METHODS: The sample design begins with a national area probability sample of households, carried out jointly with the 2004 round of the Health and Retirement Study. Selection of respondents for NSHAP balanced age and gender subgroups and oversampled African Americans and Latinos. Data collection was carried out from July 2005 to March 2006. RESULTS: The survey obtained an overall response rate of 75.5%. DISCUSSION: The complex sample design requires that the selection probabilities and the field implementation be accounted for in estimating population parameters. The data set contains weights to compensate for differential probabilities of selection and response rates among demographic groups. Analysts should use weights in constructing estimates from the survey and account for the complex sample design in estimating standard errors for survey estimates.
Keywords: Aged; Aged, 80 and over; Aging; Bias; Data collection; Data Interpretation, Statistical; Female; Health Status; Health Surveys; Humans; Longitudinal Studies; Male; Mass Screening; Middle Aged; Research Design; Sampling Studies; Sexual Behavior; Social Behavior; United States

Stock Market Expectations and Portfolio Choice of American Households - Kezdi, Gabor; Robert J. Willis (University of Michigan, 2009)
This paper measures heterogeneity in the stock market expectations of households using survey answers to probability questions. We address survey measurement error in an explicit way and develop a joint model of the effect of expectations on portfolio choice on the one hand and survey answers on the other hand. The model is consistent with documented features of measurement error. We show substantial heterogeneity and that heterogeneity in expectations predicts heterogeneity in stockholding. We show that a general tendency to be optimistic is related to optimism about stock returns and in turn increases stockholding, while a general tendency to be uncertain is strongly related to uncertainty about stock market returns and in turn decreases stockholding. We estimate the level of risk tolerance that links subjective beliefs to stockholding to be moderate. We also show that a significant part of stockholding differences among demographic groups is explained by differences in their expectations.
Keywords: Expectations; Methodology; Net Worth and Assets; Risk Taking

Strange But True: Claim and Suspend Social Security - Alicia H. Munnell; Golub-Sass, Alex; Nadia S. Karamcheva (Center for Retirement Research at Boston College Briefs, 2009)
The brief’s key findings are: During the current economic crisis, many older workers are postponing retirement and some retirees are re-entering the labor force. Re-entrants age 66 and over can put their Social Security benefits “on hold” in exchange for higher benefits later. This “claim and suspend” strategy also offers greater flexibility to one-earner couples, allowing the higher earner to delay benefits while his spouse claims. The potential costs to Social Security are modest.
Keywords: Retirement Planning and Satisfaction; Social Security

Strange But True: Claim Social Security Now, Claim More Later - Alicia H. Munnell; Golub-Sass, Alex; Nadia S. Karamcheva (Center for Retirement Research at Boston College, 2009)
Keywords: Retirement Planning and Satisfaction; Social Security

Strange But True: Free Loan from Social Security - Alicia H. Munnell; Golub-Sass, Alex; Nadia S. Karamcheva (Center for Retirement Research at Boston College, 2009)
Keywords: Retirement Planning and Satisfaction; Social Security

Subjective Expectations: Test for Bias and Implications for Choices - Wang, Yang (Subjective Expectations: Test for Bias and Implications for Choices, 2009)
In expected utility models, individuals' choices critically depend on their subjective expectations of future events (Manski 2004). A common approach in the literature is to evoke the rational expectations assumption and substitute objectively estimated state transitions in the data for the subjective probabilities that individuals assign to future events. This methodology takes a strong stand that individuals' subjective expectations should coincide with objective estimates in the data, which rules out the possibility of biased expectations. This restriction might not be warranted in empirical work, and may lead to misspecification of the model and misleading conclusions regarding individuals' behaviors and the effectiveness of different public policies. In this paper, I relax the rational expectations assumption by directly using subjective expectations elicited from individuals. I theoretically show that the data on subjective expectations can identify the distribution of individuals' expectation bias. Combined with individuals' choices, the subjective expectations data can further be used to identify the structural parameters of binary choice models. In the empirical part of the paper, I focus on individuals' subjective survival probabilities available from the survey data, show how the mortality expectations affect individuals' smoking decisions and discuss policy implications. The theoretical methods developed in this paper provide the tools to quantitatively understand individuals' subjective expectations and their relation to the objective counterparts in the data. In particular, non-parametric identification of individuals' expectation bias can be used to test the rational expectations assumption, assess the extent of individuals' unobserved heterogeneity, and identify the difference in relative importance of factors for subjective versus objective probabilities in the data. In empirical analysis, I propose a new dynamic approach to the formation of subjective expectations, which allows me to back out, in a forward-looking fashion, the one-period ahead subjective expectations of the agents from their expectations of multi-step ahead events elicited in the survey. Applying this method to the subjective longevity expectations from the Health and Retirement Study, I find that while the factors that individuals take into consideration are similar to those identified in the objective mortality data, the relative weights placed on factors can be quite different in the two approaches. For instance, high income and good health tend to increase expected longevity, both objectively and subjectively, However, I find that individuals subjectively put a disproportionately large weight on genetic information and small weight on their health-related choices, relative to the objective estimation. Subjective expectations are further used in a structural dynamic model of smoking choice. I find that individuals subjectively care more about their health and are more forward-looking than estimated based purely on objective data. Hence, the reason that people smoke is not that they do not care about their health or that they are myopic, but that they put much more weight on their genetic makeup and too little weight on their health-related behaviors. The direct implication of these results for public policy is to design information campaigns in a more personalized way to decrease this bias in individuals' subjective expectations.
Keywords: Expectations; Risk Taking

Subjective Probabilities in Household Surveys. - Michael D Hurd (Annu Rev Econom, 2009)
Subjective probabilities are now collected on a number of large household surveys with the objective of providing data to better understand inter-temporal decision making. Comparison of subjective probabilities with actual outcomes shows that the probabilities have considerable predictive power in situations where individuals have considerable private information such as survival and retirement. In contrast the subjective probability of a stock market gain varies greatly across individuals even though no one has private information and the outcome is the same for everyone. An explanation is that there is considerable variation in accessing and processing information. Further, the subjective probability of a stock market gain is considerably lower than historical averages, providing an explanation for the relatively low frequency of stock holding. An important research objective will be to understand how individuals form their subjective probabilities.

Successful Aging among Older Americans: Prevalence, Trends, and Disparities - Sara J McLaughlin (Successful Aging among Older Americans: Prevalence, Trends, and Disparities, 2009)
At the beginning of the last century, 1 in 25 Americans was age 65 or over. By 2050, however, 1 in 5 will be an older adult. Because older adults shoulder a disproportionate share of health problems, concerns have been raised about the impact that an expanding older population will have on American society. Research suggests, though, that good health in the later years is possible and that health promotion efforts may help avert some of the "costs" of a growing older population. Currently, little is known about the prevalence of healthy aging in the US. To help fill this void, Rowe and Kahn's notion of healthy aging, referred to as "successful aging," was examined. Using 1998, 2000, 2002, and 2004 data from a nationally representative study of older adults, the prevalence of successful aging was estimated for the older population as a whole and major subgroups of older adults. Additionally, trends over time in the prevalence of the phenomenon were examined to determine if the percentage of older adults aging "successfully" has changed in recent years. Guided by Rowe and Kahn's framework, successful aging was operationalized as having no difficulty with six activities of daily living, none of five chronic diseases, no more than one difficulty with seven measures of physical functioning, a median or higher score on tests of cognitive functioning, and being actively engaged. Analyses were restricted to the roughly 10,000 adults at each wave who were ages 65 and over. Results indicate that fewer than 10% of older adults were aging "successfully" in any wave. In adjusted analyses, those of lower SES, advanced age, and male gender were consistently found to have lower odds of aging "successfully" than their respective counterparts. In addition, for the most recent wave of data collection, those of non-White race/ethnicity had just half the odds of aging successfully as older White adults. Over the six-year period, the prevalence of successful aging declined by 19%, with differential trends by SES evident in 2004. The implications of these findings for the continued study and development of the concept of "successful aging" are discussed.
Keywords: Health Conditions and Status

Surrogate consent for dementia research: a national survey of older Americans. - Scott Y H Kim; H.M. Kim; Kenneth M. Langa; Jason H. Karlawish; David S Knopman; Appelbaum, P S (Neurology, 2009)
BACKGROUND: Research in novel therapies for Alzheimer disease (AD) relies on persons with AD as research subjects. Because AD impairs decisional capacity, informed consent often must come from surrogates, usually close family members. But policies for surrogate consent for research remain unsettled after decades of debate. METHODS: We designed a survey module for a random subsample (n = 1,515) of the 2006 wave of the Health and Retirement Study, a biennial survey of a nationally representative sample of Americans aged 51 and older. The participants answered questions regarding one of four randomly assigned surrogate-based research (SBR) scenarios: lumbar puncture study, drug randomized control study, vaccine study, and gene transfer study. Each participant answered three questions: whether our society should allow family surrogate consent, whether one would want to participate in the research, and whether one would allow one's surrogate some or complete leeway to override stated personal preferences. RESULTS: Most respondents stated that our society should allow family surrogate consent for SBR (67.5% to 82.5%, depending on the scenario) and would themselves want to participate in SBR (57.4% to 79.7%). Most would also grant some or complete leeway to their surrogates (54.8% to 66.8%), but this was true mainly of those willing to participate. There was a trend toward lower willingness to participate in SBR among those from ethnic or racial minority groups. CONCLUSIONS: Family surrogate consent-based dementia research is broadly supported by older Americans. Willingness to allow leeway to future surrogates needs to be studied further for its ethical significance for surrogate-based research policy.
PMID 19139366
Keywords: Advance directives; Age Factors; Aged; Aged, 80 and over; Alzheimer disease; Biomedical Research; Caregivers; Clinical Trials as Topic; Data collection; ethnicity; Female; Humans; Informed Consent; Legal Guardians; Male; Mental Competency; Middle Aged; Patient Participation; Proxy; Research Subjects; Surveys and Questionnaires; Therapeutic Human Experimentation; Third-Party Consent

The Sacred Enterprise: Religion and attitudes toward work and retirement in the United States - Ebel, Donald J. (The Sacred Enterprise: Religion and attitudes toward work and retirement in the United States, 2008)
Weberian theory suggests that ascetic forms of Protestantism provided the ingredients required for the birth of capitalism in the West. This same theory links doctrinal and behavioral aspects of these religious groups to improved economic outcomes. In 1961, Gerhard Lenski tested these theories against individual attitudes, and a relationship was identified that supported Weber's theories. Since Lenski's study was conducted, dramatic religious and economic changes have unfolded in the United States that may indicate that a process of secularization has ensued. This study follows Lenski's example in testing Weber's theoretical construct using updated methods and data unavailable in 1961. Using data from Wave 1 (1992) of the Health and Retirement Study, this study tests the effect of religious affiliation upon economic attitudes as defined by the age of desired retirement and attitudes toward work. The sample is restricted to men active in the workforce in 1992. The multi-method design follows two stages. First, historical comparative analysis is used to identify trends and transitions in religion and the economy within the United States across the Twentieth Century. The second stage is comprised of two analyses--multi-level random coefficient analysis for the study of the effects of religion upon retirement attitudes, and logistic regression for the study of the effects of religion upon work attitudes. The qualitative and quantitative components of this study are used to inform one another, and to allow the statistical findings to be accurately placed within their historical context. The study finds that religion has little to no influence upon attitudes toward retirement. Findings in the analysis of religion and work indicate a weak relationship between religion and work attitudes that is mediated by the presence of other factors such as health status, age and the level of anticipated Social Security benefits. In both analyses, level of commitment indicates a suppressive effect. Ultimately, changes in the religious and economic experience of Americans, the social institution of retirement, and in population structures have led to a process of secularization which restricted religion's influence upon economic attitudes as of 1992 for working men in the United States.
Keywords: Demographics; Employment and Labor Force; Retirement Planning and Satisfaction

Screening mammography in older women. Effect of wealth and prognosis. - Brie A Williams; Lindquist, Karla; Rebecca L. Sudore; Kenneth E Covinsky; Louise C Walter (Arch Intern Med, 2008)
BACKGROUND: Wealthy women have higher rates of screening mammography than poor women do. Screening mammography is beneficial for women with substantial life expectancies, but women with limited life expectancies are unlikely to benefit. It is unknown whether higher screening rates in wealthy women are due to increased screening in women with substantial life expectancies, limited life expectancies, or both. This study examines the relationship between wealth and screening mammography use in older women according to life expectancy. METHODS: A cohort study was performed of 4222 women 65 years or older with Medicare participating in the 2002 and 2004 Health and Retirement Survey. Women were categorized according to wealth and life expectancy (based on 5-year prognosis from a validated prognostic index). The outcome was self-reported receipt of screening mammography within 2 years. RESULTS: Overall, within 2 years, 68% of women (2871 of 4222) received a screening mammogram. Screening was associated with wealth (net worth, > $100 000) and good prognosis (< or = 10% probability of dying in 5 years). Screening mammography was more common among wealthy women than among poor women (net worth, < $10 000) both for women with good prognosis (82% vs 68%; P < .001) and for women with limited prognoses (> or = 50% probability of dying in 5 years) (48% vs 32%; P = .02). These associations remained after multivariate analysis accounting for age, race, education, proxy report, and rural residence. CONCLUSIONS: Poorer older women with favorable prognoses are at risk of not receiving screening mammography when they are likely to benefit. Wealthier older women with limited prognoses are often screened when they are unlikely to benefit.
Keywords: Aged; Breast Neoplasms; Chi-Square Distribution; Female; Humans; Longitudinal Studies; Mammography; Mass Screening; Prognosis; Risk Factors; Social Class

Self-Employment Transistions among Older American Workers with Career Jobs - Michael D. Giandrea; Kevin E. Cahill; Joseph F. Quinn (US Dept. of Labor, Bureau of Labor Statistics, 2008)
What role does self-employment play in the retirement process? Older Americans are staying in the labor force longer than prior trends would have predicted and many change jobs later in life. These job transitions are often within the same occupation or across occupations within wage-and-salary employment. The transition can also be out of wage-and-salary work and into self employment. Indeed, national statistics show that self employment becomes more prevalent with age, partly because self employment provides older workers with opportunities not found in traditional wage-and-salary jobs, such as flexibility in hours worked and independence. This paper analyzes transitions into and out of self employment among older workers who have had career jobs. We utilize the Health and Retirement Study, a nationally-representative dataset of older Americans, to investigate the prevalence of self employment among older workers who made a job transition later in life and to explore the factors that determine the choice of wage-and-salary employment or self employment. We find that post-career transitions into and out of self employment are common and that health status, career occupation, and financial variables are important determinants of these transitions. As older Americans and the country as a whole face financial strains in retirement income in the years ahead, self employment may be a vital part of the pro-work solution.
Keywords: Employment and Labor Force

Self-Reported Vision, Upper/Lower Limb Disability, and Fall Risk in Older Adults - Bernard A Steinman (Journal of Applied Gerontology, 2008)
The purpose of this study was to examine independent and interactive roles of self-reported vision status and upper and lower limb disability as predictors of falls in people 65 and older. Data from the 2002 and 2004 panels of the Health and Retirement Study were analyzed using binary logistic regression. Results indicated a reduced or eliminated role of vision status after upper and lower limb disabilities were controlled. Gender differences were found with respect to health conditions that predicted falls; however, vision status was not found to have a moderating influence on upper and lower limb disability in predicting falls for men or women. Implications for exercise programs designed for older people with visual impairments are discussed.
Keywords: Health Conditions and Status

SKIP SEQUENCING: A DECISION PROBLEM IN QUESTIONNAIRE DESIGN. - Charles F Manski; Molinari, Francesca (Ann Appl Stat, 2008)
This paper studies questionnaire design as a formal decision problem, focusing on one element of the design process: skip sequencing. We propose that a survey planner use an explicit loss function to quantify the trade-off between cost and informativeness of the survey and aim to make a design choice that minimizes loss. We pose a choice between three options: ask all respondents about an item of interest, use skip sequencing, thereby asking the item only of respondents who give a certain answer to an opening question, or do not ask the item at all. The first option is most informative but also most costly. The use of skip sequencing reduces respondent burden and the cost of interviewing, but may spread data quality problems across survey items, thereby reducing informativeness. The last option has no cost but is completely uninformative about the item of interest. We show how the planner may choose among these three options in the presence of two inferential problems, item nonresponse and response error.

Social Security and the Retirement and Savings Behavior of Low Income Households. - van der Klaauw, Wilbert; Wolpin, Kenneth I. (J Econom, 2008)
In this paper, we develop and estimate a model of retirement and savings incorporating limited borrowing, stochastic wage offers, health status and survival, social security benefits, Medicare and employer provided health insurance coverage, and intentional bequests. The model is estimated on sample of relatively poor households from the first three waves of the Health and Retirement Study (HRS), for whom we would expect social security income to be of particular importance. The estimated model is used to simulate the responses to changes in social security rules, including changes in benefit levels, in the payroll tax, in the social security earnings tax and in early and normal retirement ages. Welfare and budget consequences are estimated.

Social security and the retirement and savings behavior of low-income households - van der Klaauw, Wilbert; Wolpin, Kenneth I. (Journal of Economics, 2008)
In this paper, we develop and estimate a model of retirement and savings incorporating limited borrowing, stochastic wage offers, health status and survival, social security benefits, Medicare and employer-provided health insurance coverage, and intentional bequests. The model is estimated on a sample of relatively poor households from the first three waves of the Health and Retirement Study (HRS), for whom we would expect social security income to be of particular importance. The estimated model is used to simulate the responses to changes in social security rules, including changes in benefit levels, in the payroll tax, in the social security earnings tax and in early and normal retirement ages. Welfare and budget consequences are estimated.
Keywords: Retirement; Social Security; structural estimation

Socializing Appears to Delay Memory Problems - Lott, joshua (New York Times, 2008)
Keywords: Health Conditions and Status

Socioeconomic Differences in Old Age Mortality - Rasmus Hoffmann (The Springer series on Demographic Methods and Population Analysis, 2008)
Social differences in health and mortality constitute a persistent finding in epidemiological, demographic, and sociological research. This topic is increasingly discussed in the political debate and is among the most urgent public health issues. However, it is still unknown if socioeconomic mortality differences increase or decrease with age. This book provides a comprehensive, thoughtful and critical discussion of all aspects involved in the relationship between socioeconomic status, health and mortality. In a well-written language, it synthesizes the sociological theory of social inequality and an empirical study of mortality differences that has been performed at the Max Planck Institute for Demographic Research (Rostock, Germany). The best available datasets from Denmark and the USA, as two very different countries, are used to analyze the age pattern of social mortality differences, the Danish register data covering the whole Danish population between 1980 and 2002. This study is the most comprehensive analysis of socioeconomic mortality differences in the literature, in terms of data quantity, quality, and the statistical method of event-history modeling. It makes important new theoretical and empirical contributions. With a new method it also addresses the question whether the measurement of social mortality differences in old age so far has been biased by mortality selection due to unobserved heterogeneity.
Keywords: Demographics; Health Conditions and Status

Sources of Advantageous Selection: Evidence from the Medigap Insurance Market - Fang, Hanming; Keane, Michael P.; Daniel S. Silverman (Journal of Political Economy, 2008)
We provide evidence of advantageous selection in the Medigap insurance market and analyze its sources. Conditional on controls for Medigap prices, those with Medigap spend, on average, 4,000 less on medical care than those without. But if we condition on health, those with Medigap spend 2,000 more. The sources of this advantageous selection include income, education, longevity expectations, and financial planning horizons, as well as cognitive ability. Conditional on all these factors, those with higher expected medical expenditures are more likely to purchase Medigap. Risk preferences do not appear as a source of advantageous selection; cognitive ability is particularly important.
Keywords: Medicare/Medicaid/Health Insurance

Spousal caregiving in late midlife versus older ages: implications of work and family obligations. - Julie C Lima; Susan M Allen; Goldscheider, Frances; Intrator, Orna (J Gerontol B Psychol Sci Soc Sci, 2008)
OBJECTIVES: This study examined life-stage differences in the provision of care to spouses with functional impairment. METHODS: We examined 1,218 married adults aged 52 and older from the 2000 wave of the Health and Retirement Study who received impairment-related help with at least one activity of daily living. We examined the differential likelihood that spouses served as primary caregiver and the hours of care provided by spousal primary caregivers by life stage. RESULTS: We found that late middle-aged care recipients were more likely than their older counterparts to receive the majority of their care from their spouse but received fewer hours of spousal care, mostly when spouses worked full time. Competing demands of caring for children or parents did not affect the amount of care provided by a spouse. DISCUSSION: Late middle-aged adults with functional limitations are more likely than older groups to be married and cared for primarily by spouses; however, they may be particularly vulnerable to unmet need for care. As the baby boom generation ages, retirement ages increase, and federal safety nets weaken, people with health problems at older ages may soon find themselves in the same caregiving predicament as those in late middle age.
Keywords: Activities of Daily Living; Age Factors; Aged; Aged, 80 and over; Caregivers; Employment; Family Relations; Female; Gender Identity; Health Surveys; Humans; Longitudinal Studies; Male; Middle Aged; Mobility Limitation; Spouses; Time Factors; United States

Spousal concordance in health behavior change. - Tracy Falba; Jody L Sindelar (Health Serv Res, 2008)
OBJECTIVE: This study examines the degree to which a married individual's health habits and use of preventive medical care are influenced by his or her spouse's behaviors. STUDY DESIGN: Using longitudinal data on individuals and their spouses, we examine changes over time in the health habits of each person as a function of changes in his or her spouse's health habits. Specifically, we analyze changes in smoking, drinking, exercising, cholesterol screening, and obtaining a flu shot. DATA SOURCE: This study uses data from the Health and Retirement Study (HRS), a nationally representative sample of individuals born between 1931 and 1941 and their spouses. Beginning in 1992, 12,652 persons (age-eligible individuals as well as their spouses) from 7,702 households were surveyed about many aspects of their life, including health behaviors, use of preventive services, and disease diagnosis. SAMPLE: The analytic sample includes 6,072 individuals who are married at the time of the initial HRS survey and who remain married and in the sample at the time of the 1996 and 2000 waves. PRINCIPAL FINDINGS: We consistently find that when one spouse improves his or her behavior, the other spouse is likely to do so as well. This is found across all the behaviors analyzed, and persists despite controlling for many other factors. CONCLUSIONS: Simultaneous changes occur in a number of health behaviors. This conclusion has prescriptive implications for developing interventions, treatments, and policies to improve health habits and for evaluating the impact of such measures.
Keywords: Attitude to Health; Cross-Sectional Studies; Exercise; Family Characteristics; Female; Health Behavior; Health Care Surveys; Health Promotion; Health Status; Humans; Interpersonal Relations; Life Style; Male; Marriage; Middle Aged; Preventive Health Services; Prospective Studies; Risk-Taking; Smoking; Spouses; United States

Spousal smoking and incidence of first stroke: the Health and Retirement Study. - M. Maria Glymour; Triveni DeFries; Ichiro Kawachi; Mauricio Avendano (Am J Prev Med, 2008)
BACKGROUND: Few prospective studies have investigated the relationship between spousal cigarette smoking and the risk of incident stroke. METHODS: Stroke-free participants in the U.S.-based Health and Retirement Study (HRS) aged >or=50 years and married at baseline (n=16,225) were followed, on average, 9.1 years between 1992 and 2006) for proxy or self-report of first stroke (1,130 events). Participants were stratified by gender and own smoking status (never-smokers, former smokers, or current smokers), and the relationship assessed between the spouse's smoking status and the risk of incident stroke. Analyses were conducted in 2007 with Cox proportional hazards models. All models were adjusted for age; race; Hispanic ethnicity; Southern birthstate; parental education; paternal occupation class; years of education; baseline income; baseline wealth; obesity; overweight; alcohol use; and diagnosed hypertension, diabetes, or heart disease. RESULTS: Having a spouse who currently smoked was associated with an increased risk of first stroke among never-smokers (hazard ratio=1.42, 95% CI=1.05, 1.93) and former smokers (hazard ratio=1.72, 95% CI=1.33, 2.22). Former smokers married to current smokers had a stroke risk similar to respondents who themselves smoked. CONCLUSIONS: Spousal smoking poses important stroke risks for never-smokers and former smokers. The health benefits of quitting smoking likely extend to both the individual smoker and his or her spouse.
Keywords: Age Factors; Confidence Intervals; Female; Humans; Incidence; Male; Middle Aged; Prospective Studies; Risk Factors; Smoking; Spouses; Stroke; Time Factors; Tobacco Smoke Pollution; United States

Stature and status: Height, ability, and labor market outcomes. - Case, Anne; Paxson, Christina (J Polit Econ, 2008)
The well-known association between height and earnings is often thought to reflect factors such as self esteem, social dominance, and discrimination. We offer a simpler explanation: height is positively associated with cognitive ability, which is rewarded in the labor market. Using data from the US and the UK, we show that taller children have higher average cognitive test scores, and that these test scores explain a large portion of the height premium in earnings. Children who have higher test scores also experience earlier adolescent growth spurts, so that height in adolescence serves as a marker of cognitive ability.

Stroke disparities in older Americans: is wealth a more powerful indicator of risk than income and education? - Mauricio Avendano; M. Maria Glymour (Stroke, 2008)
BACKGROUND AND PURPOSE: This study examines the independent effect of wealth, income, and education on stroke and how these disparities evolve throughout middle and old age in a representative cohort of older Americans. METHODS: Stroke-free participants in the Health and Retirement Study (n=19,565) were followed for an average of 8.5 years. Total wealth, income, and education assessed at baseline were used in Cox proportional hazards models to predict time to stroke. Separate models were estimated for 3 age-strata (50 to 64, 65 to 74, and >or=75), and incorporating risk factor measures (smoking, physical activity, body mass index, hypertension, diabetes, and heart disease). RESULTS: 1542 subjects developed incident stroke. Higher education predicted reduced stroke risk at ages 50 to 64, but not after adjustment for wealth and income. Wealth and income were independent risk factors for stroke at ages 50 to 64. Adjusted hazard ratios comparing the lowest decile with the 75th-90th percentiles were 2.3 (95% CI 1.6, 3.4) for wealth and 1.8 (95% CI 1.3, 2.6) for income. Risk factor adjustment attenuated these effects by 30% to 50%, but coefficients for both wealth (HR=1.7, 95% CI 1.2, 2.5) and income (HR=1.6, 95% CI 1.2, 2.3) remained significant. Wealth, income, and education did not consistently predict stroke beyond age 65. CONCLUSIONS: Wealth and income are independent predictors of stroke at ages 50 to 64 but do not predict stroke among the elderly. This age patterning might reflect buffering of the negative effect of low socioeconomic status by improved access to social and health care programs at old ages, but may also be an artifact of selective survival.
Keywords: Age Distribution; Age Factors; Aged; Cohort Studies; Educational Status; Female; Humans; Incidence; Income; Life Style; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Socioeconomic factors; Stroke; United States

Safe Alcohol Limits Similar for Younger and Older Adults - Wellbery, Caroline (American Family Physician, 2007)
The study used data from the U.S. Health and Retirement Study (HRS) and the English Longitudinal Study of Aging (ELSA). For those drinking more than one to two drinks per day, the odds ratios (ORs) in the pooled analysis were 0.96 for reported difficulty with ADLs, 0.75 for reported difficulty with IADLs, and 0.82 for poor cognitive function.
Keywords: Cross-National; Health Conditions and Status

Saving Between Cohorts: The Role of Planning - Annamaria Lusardi; Beeler, Jason (Redefining Retirement: How Will Boomers Fare?, 2007)
We compare the saving behavior of two cohorts: the Early Baby Boomers (EBB, age 51- 56 in 2004) and the HRS cohort (age 51-56 in 1992). We find that EBB have accumulated more wealth than the previous cohort but they benefited from a large increase in house prices, which lifted the wealth of many home-owners. In fact, there are many families among EBB, particularly those headed by respondents with low education, low income, and minorities, which have less wealth than the previous cohort. Lack of wealth can be traced to lack of retirement planning. Notwithstanding the many initiatives aimed at fostering planning in the 1990s, a large portion of EBB still do not plan for retirement even though most respondents are close to it. The effect of planning is remarkably similar between the two cohorts; those who do not plan accumulate much lower amounts of wealth from 20 to 45 percent depending on the location in the wealth distribution- than those who do plan. Thus, for both the EBB and the HRS cohort, lack of planning is tantamount to lack of saving irrespective of the many changes in the economy between 1992 and 2004.
ProCite field 6 : In ProCite field 8 : eds
Keywords: adequacy; Baby Boomer; Education; Housing; Income; minorities; Retirement Planning; Saving

Self-rated health trajectories and mortality among older adults. - Thomas R Miller; Frederic D Wolinsky (J Gerontol B Psychol Sci Soc Sci, 2007)
OBJECTIVES: For this article, we evaluated whether measures of prior self-rated health (SRH) trajectories had associations with subsequent mortality that were independent of current SRH assessment and other covariates. METHODS: We used multivariable logistic regression that incorporated four waves of interview data (1993, 1995, 1998, and 2000) from the Asset and Health Dynamics Among the Oldest Old Survey in order to predict mortality during 2000-2002. We defined prior SRH trajectories for each individual based on the slope estimated from a simple linear regression of their own SRH between 1993 and 1998 and the variance around that slope. In addition to SRH reported in 2000, other covariates included in the mortality models reflected health status, health-related behaviors, and individual resources. RESULTS: Among the 3,129 respondents in the analytic sample, SRH in 2000 was significantly (p <.0001) associated with mortality, but the measures of prior SRH trajectories were not. Prior SRH trajectory was, however, a significant determinant of current SRH. We observed significant independent associations with mortality for age, sex, education, lung disease, and having ever smoked. DISCUSSION: Although measures of prior SRH trajectories did not have significant direct associations with mortality, they did have important indirect effects via their influence on current SRH.
Keywords: Age Factors; Aged; Aged, 80 and over; Attitude to Health; Cardiovascular Diseases; Cause of Death; Female; Follow-Up Studies; Health Status; Health Status Indicators; Humans; Logistic Models; Longitudinal Studies; Lung Diseases; Male; Mortality; Multivariate Analysis; Risk Factors; Sex Factors; Smoking; Socioeconomic factors; Survival Analysis; United States

Should health studies measure wealth? A systematic review. - Craig E Pollack; Chideya, Sekai; Cubbin, Catherine; Brie A Williams; Dekker, Mercedes; Paula Braveman (Am J Prev Med, 2007)
BACKGROUND: Health researchers rarely measure accumulated wealth to reflect socioeconomic status/position (SES). In order to determine whether health research should more frequently include measures of wealth, this study assessed the relationship between wealth and health. METHODS: Studies published between 1990 to 2006 were systematically reviewed. Included studies used wealth and at least one other SES measure as independent variables, and a health-related dependent variable. RESULTS: Twenty-nine studies met inclusion criteria. Measures of wealth varied greatly. In most studies, greater wealth was associated with better health, even after adjusting for other SES measures. The findings appeared most consistent when using detailed wealth measures on specific assets and debts, rather than a single question. Adjusting for wealth generally decreased observed racial/ethnic disparities in health. CONCLUSIONS: Health studies should include wealth as an important SES indicator. Failure to measure wealth may result in under-estimating the contribution of SES to health, such as when studying the etiology of racial/ethnic disparities. Validation is needed for simpler approaches to measuring wealth that would be feasible in health studies.
Keywords: Bias; Biomedical Research; Female; Financing, Personal; Health Services Research; Health Status Indicators; Humans; Male; Research Design; Socioeconomic factors

Social Predictors of Driving Cessation Among Older Adults: Understanding the driving continuum - Murtha, Jenai (Social Predictors of Driving Cessation Among Older Adults: Understanding the driving continuum, 2007)
The purpose of this study was to understand the critical factors, both independently and jointly defined, that condition driving behavior among older persons. The sample was comprised of 6,623 respondents 70+, who completed driving questions for two waves of the Health and Retirement Study. The primary goal was to determine whether social engagement variables, both social involvements and obligations and access to alternative drivers, influence driving behavior. Results provide support showing that social involvements and obligations variables increase the likelihood of driving continuation, and that access to alternative drivers variables increase the likelihood of driving cessation.
Keywords: Health Conditions and Status

The Social Security Earnings Test and Work Incentives - Hugo Benítez-Silva; Frank Heiland (Journal of Policy Analysis and Management, 2007)
The labor supply and benefit claiming incentives provided by the early retirement rules of the Social Security Old Age benefits program are of growing importance as the Normal Retirement Age (NRA) increases to 67, the labor force participation of Older Americans rises, and a variety of reforms to the Social Security system are considered. Any reform needs to take into account the effects and rationale of the Social Security Earnings Test and the Actuarial Adjustment Factor, which are likely to be widely misunderstood due to the relatively little attention paid by policymakers and researchers to the fact that Americans are willing to work while receiving benefits. We describe these incentives and emphasize that individuals who claim benefits before the NRA but continue to work, or return to the labor force, can reduce the early retirement penalty by suspending the collection of monthly benefits if they earn above the Earnings Test limit. We then argue that the Earnings Test can be distortionary and is costly to administer, and that these characteristics are inflated by the lack of information given to Older Americans regarding the consequences of working while receiving retirement benefits. We present results from statistical models of labor force exit behavior using data from the Health and Retirement Study showing the relevance of these incentives, and investigate the importance of informational asymmetries among beneficiaries regarding benefit withholding using a dynamic life-cycle model of labor supply and benefit claiming. We then use the latter framework to compare the behavioral and welfare implications of a removal of the Earnings Test to the policy of providing more information regarding the Earnings Test and the adjustment of the rate of benefit pay to Older Americans. 2007 by the Association for Public Policy Analysis and Management.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction; Social Security

Sociodemographic and Health-Related Risks for Loneliness and Outcome Differences - Laurie A. Theeke (Nursing, 2007)
Background. Loneliness is a prevalent problem for older adults and has been shown to be associated with negative physical, psychological, and social variables. There has been limited research focusing on the relationship of loneliness to health. There is a gap in the literature when it comes to understanding how the problem of loneliness relates to the health of older adults in the United States. Purpose. The purpose of this study was to address this gap in the literature through the testing of two models, the first model represented the postulated risks for loneliness and the second model represented the postulated outcomes for those who experience loneliness. Variables were chosen for inclusion in the models based on a review of pertinent quantitative and qualitative literature. Methods. The models were tested using a representative sample of U.S. older adults. Data analysis was performed using data from the 2002 and 2004 waves of the Health and Retirement Study. The sample was limited to respondents aged 50 and older who participated in wave 6 (2002) and wave 7 (2004) without proxy, answered the lonely question at both waves, were community-dwelling in 2002 and who had complete data on selected variables in the model. Univariate and bivariate analyses were followed by logistic regression analysis to identify risks. One-way ANOVAs, comparative means testing and independent analysis of covariance tests were used to evaluate the difference in outcomes for those who were never lonely, briefly lonely, or chronically lonely. Results. Non-married status was consistently the primary predictor of self-report of loneliness, followed by poorer self-report of health status, lower educational level, functional impairment, increasing number of chronic illnesses, younger age, lower income, and less people living in the household. Gender and use of home care were not significant predictors of loneliness. Those who were chronically lonely reported less exercise, more tobacco use, less alcohol use, a greater increase in number of chronic illnesses, higher depression scores, more physician contacts and greater average number of nights in a nursing home than those who were never lonely or briefly lonely. After controlling for significant covariates of loneliness, those who were chronically lonely did not have significantly more physician contacts. Discussion. Loneliness is a prevalent problem for older adults in the United States with its own unique health-related risks and outcomes. Given the prevalence, it should be considered a healthcare priority in the United States. Based on the results of this study, inclusion of loneliness and loneliness risk screening as part of routine health histories for those aged 50 and over should be considered. Future research needs to focus on evaluating the effectiveness of both prevention and treatment interventions for loneliness to provide empirical data to guide evidenced based practice.
Keywords: Demographics; Health Conditions and Status

Some Chronically Ill Adults Wait for Medicare to Arrive - Gina Kolata (New York Times, 2007)
"When uninsured adults with common chronic illnesses became eligible for Medicare, they saw doctors and were hospitalized more often and reported greater medical expenses than people who had had insurance." This article references results of a reseach study led by Dr. John Z. Ananian, published in the New England Journal of Medicine, that used data from the Health and Retirement Study. "Dr. Ayanian and his colleagues focused on 5,158 [of 9,760 adults aged 51 to 61 in 1992] ... who survived to age 65 by 2004 and who either had private insurance or no insurance at all before receiving Medicare."
Keywords: Health Conditions and Status; Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

Is the 'stroke belt' worn from childhood?: risk of first stroke and state of residence in childhood and adulthood. - M. Maria Glymour; Mauricio Avendano; Lisa F Berkman (Stroke, 2007)
BACKGROUND AND PURPOSE: Most Stroke Belt studies define exposure based on residence at stroke onset. We assessed whether residence in the Stroke Belt during childhood confers extra stroke risk in adulthood, even among people who left the region. METHODS: Stroke-free Health and Retirement Study participants (n=18 070) followed up (average, 8.4 years) for first stroke (1452 events) were classified as living in 1 of 7 Stroke Belt states in childhood or at study enrollment (average age, 63 years). We used Cox proportional-hazards models to compare stroke risk for people who had never lived in the Stroke Belt with those who had lived there at both ages, in childhood only, or in adulthood only. RESULTS: Compared with never having lived in the Stroke Belt, the hazard ratio for Stroke Belt residence in both childhood and adulthood was 1.23 (95% CI, 1.06, 1.43) and for Stroke Belt residence in childhood only was 1.25 (95% CI, 1.02, 1.55). Stroke Belt residence at enrollment but not during childhood was not significantly related to stroke risk (hazard ratio=1.01; 95% CI, 0.70, 1.46), but the small sample in this group resulted in wide CIs. Results changed little after risk factor adjustment, including comprehensive adult socioeconomic measures. Subgroup analyses found similar patterns by sex and birth cohort. In contrast, blacks who had lived in the Stroke Belt in childhood only did not appear to have significantly elevated stroke risk compared with blacks who had never lived in the Stroke Belt. CONCLUSIONS: The excess stroke risk for people who had lived in Stroke Belt states during childhood implicates early life exposures in the etiology of the Stroke Belt.
Keywords: Adult; Child; Female; Follow-Up Studies; Humans; Longitudinal Studies; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Southeastern United States; Stroke

Subjective Survival Probabilities in the Health and Retirement Study: Systematic Biases and Predictive Validity - Todd E. Elder (Michigan Retirement Research Center Research Paper, 2007)
Recent research has demonstrated that retirement planning and well-being are closely tied to probabilistic forecasts about future events. Using longitudinal data from the Health and Retirement Study, I show that individuals subjective survival forecasts exhibit systematic biases relative to life table data. In particular, many respondents fail to account for increases in yearly mortality rates with age, both longitudinally and in crosssection. Additionally, successive cohorts of the near elderly do not appear to revise survival forecasts to match increases in longevity. Forecasting bias may merely be due to the framing of questions designed to elicit expectations, but real biases may result in suboptimal savings rates and timing of retirement. Cross-sectional variation in subjective survival forecasts also appears to reflect differences in cognitive ability across respondents, suggesting that subjective information is more relevant for some individuals than others. Despite these shortcomings, subjective mortality probabilities predict actual mortality and portfolio choice, and they contain information not found in selfreported health status or objective measures of health limitations.
Keywords: Expectations; Health Conditions and Status; Net Worth and Assets; Retirement Planning and Satisfaction

The Sufficiency of Retirement Savings: Comparing Cohorts at the Time of Retirement - Haveman, Robert; Karen C. Holden; Barbara Wolfe; Romanov, Andrei (Redefining Retirement: How Will Boomers Fare?, 2007)
Assessing savings sufficiency requires detailed information on both potential retirement benefits and the characteristics of a national sample of older citizens. This chapter uses the Health and Retirement Survey and the New Beneficiary Survey linked to administrative records to assess and compare the saving adequacy of two different cohorts. Specifically we compare the two groups in terms of their annuitized net wealth (ANW) and ANW relative to the poverty line, as well as the near-poverty line. We find that the mean wealth levels of both new retiree cohorts rose over time (by about two-thirds for wealth and by half for ANW), but the chance of meeting social adequacy targets has also risen. This shortfall we believe is concentrated increasingly among nonmarried persons, and those with low human capital and labor force attachment. In other words, vulnerability during the working life appears to persist into retirement.
ProCite field 6 : In ProCite field 8 : eds
Keywords: Consumption and Savings; Income; Other

Savings, Portfolio Choice, and Retirement Expectations - Arthur H.O. vanSoest; Katpeyn Arie (The University of Michigan, Michigan Retirement Research Center, 2006)
Studying household investment behavior is essential for understanding the full consequences of old age social security benefits. Using data from six waves of the Health and Retirement Study, we analyze the dynamics of portfolio composition before respondents start claiming social security benefits. We consider ownership as well as amounts held of several types of assets and debts. Using panel data censored regression models, portfolio adjustment is explained on the basis of demographics like gender, race, and year of birth, education level, household income, and perceived social security entitlements. We find that expectations of old age social security benefits have little effect on portfolio decisions, although there is some evidence that higher expected social security benefits lead to more risky financial investments, particularly in IRAs.
Keywords: Consumption and Savings; Expectations; Net Worth and Assets

Self-Assessed Retirement Outcomes: Determinants and Pathways - Susann Rohwedder (The University of Michigan, Michigan Retirement Research Center, 2006)
There is increasing interest among policy makers in measuring well-being in ways that go beyond purely economic indicators, also with special focus on older individuals who constitute an increasing fraction of the population. However there is little consensus on which other indicators should be included. An alternative approach is to use individuals own assessments and relate these to a rich set of covariates to find what factors influence individuals own perceptions. This is the approach adopted in this paper, using data from the Health and Retirement Study (HRS). Retired respondents are asked how satisfying their retirement has turned out to be, how retirement years compare to pre-retirement years and whether they are worried about not having enough income to get by in retirement. I relate these self-assessed measures to a rich set of covariates to investigate which aspects weigh in individuals perceptions. I use the longitudinal nature of the HRS to study the pathways that lead up to the observed retirement outcomes, and to examine the persistence of the outcomes over time. Bad health, changes towards worse health, social isolation and increase in social isolation lead most significantly to lower satisfaction in retirement and a greater sense of financial insecurity in retirement. A short financial planning horizon and past shocks, like unexpected large expenses or divorce, also have a noticeable negative impact.
Keywords: Consumption and Savings; Expectations; Health Conditions and Status

The Size and Characteristics of the Residential Care Population: Evidence from Three National Surveys - Brenda C Spillman; Black, Kirsten J. (U.S. Department of Health and Human Services Assistant Secretary for Planning and Evaluation Office of Disability, Aging and Long-Term Care Policy, 2006)
This report is the second of two prepared as part of a project to better understand the size and characteristics of the long-term care population in all settings. Identified were three recently federally supported surveys the 2002 Health and Retirement Survey, the 2002 Medicare Current Beneficiary Survey Cost and Use file, and the National Long-Term Care Survey as being best suited for the purpose because of their focus on the older population and data elements that allow identification of residential care alternatives by name, services available, or both. In this report, the authors report on their analysis of these surveys and discuss the implications of our findings for improving collection of data on residential settings.
Keywords: Healthcare; Housing

Social Security Replacement Rates for Alternative Earnings Benchmarks - Olivia S. Mitchell; John W R Phillips (Benefits Quarterly, 2006)
Social Security reform proposals are often presented in terms of their differential impacts on hypothetical or example workers. This article explores how different benchmarks produce different replacement rate outcomes. The authors use the Health and Retirement Study (HRS) from the University of Michigan to evaluate how Social Security benefit replacement rates differ for actual versus hypothetical earner profiles, and examine whether these findings are sensitive to alternative definitions of replacement rates. They conclude that more precise analyses of possible distributional patterns from Social Security reform proposals would follow if benefit estimates were derived from actual earnings profiles, rather than hypothetical scaled patterns.
Keywords: Retirement Planning and Satisfaction; Social Security

Social Security Replacement Rates for Alternative Earnings Benchmarks - John W R Phillips; Olivia S. Mitchell (Pension Research Council Working Paper, 2006)
Social Security reform proposals are often presented in terms of their differential impacts on hypothetical or example workers. Our work explores how different benchmarks produce different replacement rate outcomes. We use the Health and Retirement Study (HRS) to evaluate how Social Security benefit replacement rates differ for actual versus hypothetical earner profiles, and we examine whether these findings are sensitive to alternative definitions of replacement rates. We find that workers with the median HRS profile would be estimated to receive benefits worth 55 of lifetime average earnings, versus 48 for the SSA medium scaled profile. Since US policymakers tend to prefer a replacement rate measure tied to workers own past earnings, using these metrics would yield higher replacement rates compared to commonly used scaled illustrative profiles. However, benchmarks that use population as opposed to individual earnings measures to compare individual worker benefits to pre-retirement consumption produce lower replacement rates for HRS versus hypothetical earners.
Keywords: Public Policy; Social Security

Social status, risky health behaviors, and diabetes in middle-aged and older adults. - Linda A. Wray; Duane F. Alwin; Ryan J McCammon; Manning, Timothy; Best, Latrica E. (J Gerontol B Psychol Sci Soc Sci, 2006)
OBJECTIVE: This article investigates: (a) how social status influences diabetes prevalence and incidence; (b) how risky health behaviors contribute to the prediction of incident diabetes; (c) if the effects of health behaviors mediate the effects of social status on incident diabetes; and (d) if these effects differ in midlife and older age. METHODS: We examined nationally representative data from the 1992/1993-1998 panels of the Health and Retirement Study for middle-aged and older adults using logistic regression analyses. RESULT: The odds of prevalent diabetes were higher for people of older age, men, Black adults, and Latino adults. Higher early-life social status (e.g., parental schooling) and achieved social status (e.g., respondent schooling, economic resources) reduced the odds in both age groups. We observed similar patterns for incident diabetes in midlife but not in older age. Risky health behaviors--particularly obesity--increased the odds of incident diabetes in both age groups independent of social status. The increased odds of incident diabetes in midlife persisted for Black and Latino adults net of other social status factors. DISCUSSION: Risky health behaviors are key predictors of incident diabetes in both age groups. Economic resources also play an important protective role in incident diabetes in midlife but not in older age.
Keywords: Aged; Body Mass Index; Diabetes Mellitus; Female; Follow-Up Studies; Health Behavior; Humans; Incidence; Male; Middle Aged; Prevalence; Risk-Taking; Social Behavior; Social Class; Surveys and Questionnaires

Solving problems of disclosure risk in an academic setting: using a combination of restricted data and restricted access methods. - Willard L Rodgers; Michael A. Nolte (J Empir Res Hum Res Ethics, 2006)
THE HEALTH AND RETIREMENT STUDY collects a vast amount of information about a sample of the U.S. population over age 50 from biennial interviews, supplemental questionnaires, and through linkages with administrative data including Social Security earnings and benefits records and Medicare claims records. To h onor i ts p ledge to t he r espondents that their data will be kept confidential, but at the same time meet its objective of providing useful data to researchers, it has develop ed procedures for stripping sensitive information (i.e., information that could facilitate re-identification of sample members) from data sets that are publicly released, and also for providing mechanisms for qualified researchers to gain access to a variety of restricted-access data files. These mechanisms include a procedure whereby highly qualified researchersin particular, only those who have a current grant from a federal agencycan apply to obtain restricted-access data sets for a limited amount of time, with the understanding that they will make no attempt to r e-identify s amp le m embers and t hat they w ill be audited to ensure that they have adhered to the agreedupon safeguards. For those who meet some but not all of the requirements for receiving these data, the files can be analyzed in a data enclave (a controlled, secure environment in which eligible researchers can perform analyses). This paper focuses on approaches to restricting data access that may need to be considered by investigators who plan to share their data, and by their institutional officials who will need to support that effort with appropriate infrastructure and policies. It also provides guidance to investigators and institutional review boards (IRBs) who seek access to restricted data generated and archived elsewhere.

State Fiscal Institutions and Empty-Nest Migration: Are Tiebout voters hobbled? - Martin P. Farnham; Purvi Sevak (Journal of Public Economics, 2006)
Using the Health and Retirement Study and a national panel of local fiscal data, we test a lifecycle model of Tiebout sorting. On average, cross-state, empty-nest movers-presumed to be out of fiscal equilibrium-experience large fiscal gains in the form of reduced exposure to local school spending and property taxes, while local empty-nest movers experience no fiscal adjustment. We find evidence that within-state fiscal adjustment is constrained by state institutions that limit local discretion. Empty-nest households moving within states with school finance equalization do not engage in Tiebout-consistent fiscal adjustment, while those moving within states lacking school finance equalization adjust substantially. (c) 2005 Elsevier B.V. All rights reserved.
Article English
Keywords: Demographics; Methodology; Public Policy

Saving Shortfalls and Delayed Retirement - Au, Andrew; Olivia S. Mitchell; John W R Phillips (University of Michigan Retirement Research Center Working Paper, 2005)
Prior research has suggested that many older Americans have not saved enough to maintain consumption levels in old age. One way older persons might respond to inadequate savings would be to extend their worklives by delaying retirement. This paper examines evidence on this matter using the Health and Retirement Study, a nationally representative panel survey of people age 51-61 in 1992 followed for several years in a panel. We use the data to project household retirement assets and to determine how much more saving would be needed to preserve post-retirement consumption levels. Our research then examines the links between derived saving shortfall measures and delayed retirement patterns. Among nonmarried persons, there is evidence that larger shortfalls do produce delayed retirement, though the effect is not quantitatively large. For married couples, pre-retirement wealth shortfalls do not appear to be significantly associated with delayed retirement. Evidently couples have other means of handling saving shortfalls.
Keywords: Consumption and Savings; Retirement Planning and Satisfaction

The Selection of Partial or Full Retirement by Older Workers - Kim, Haejeong; DeVaney, Sharon A. (Journal of Family and Economic Issues, 2005)
The study investigated whether older workers chose partial or full retirement instead of full-time work. Partial or full retirement status was modeled as a combination of self-reported retirement status and change in number of hours worked. The results of multinomial logistic regression using data from the first and fifth waves of the Health and Retirement Study collected in 1992 and 2000 showed that age and gender had similar effects on the likelihood of partial and full retirement. Full retirement was also influenced by investment assets, pensions, employee health insurance, and poor health. The likelihood of partial retirement was also influenced by self-employment, chronic health conditions, and education. Workers who seek partial retirement need working conditions that allow them to make this choice.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction

Setting eligibility criteria for a care-coordination benefit. - Christine T Cigolle; Kenneth M. Langa; Mohammed U Kabeto; Caroline S Blaum (J Am Geriatr Soc, 2005)
OBJECTIVES: To examine different clinically relevant eligibility criteria sets to determine how they differ in numbers and characteristics of individuals served. DESIGN: Cross-sectional analysis of the 2000 wave of the Health and Retirement Study (HRS), a nationally representative longitudinal health interview survey of adults aged 50 and older. SETTING: Population-based cohort of community-dwelling older adults, subset of an ongoing longitudinal health interview survey. PARTICIPANTS: Adults aged 65 and older who were respondents in the 2000 wave of the HRS (n=10,640, representing approximately 33.6 million Medicare beneficiaries). MEASUREMENTS: Three clinical criteria sets were examined that included different combinations of medical conditions, cognitive impairment, and activity of daily living/instrumental activity of daily living (ADL/IADL) dependency. RESULTS: A small portion of Medicare beneficiaries (1.3-5.8%) would be eligible for care coordination, depending on the criteria set chosen. A criteria set recently proposed by Congress (at least four severe complex medical conditions and one ADL or IADL dependency) would apply to 427,000 adults aged 65 and older in the United States. Criteria emphasizing cognitive impairment would serve an older population. CONCLUSION: Several criteria sets for a Medicare care-coordination benefit are clinically reasonable, but different definitions of eligibility would serve different numbers and population groups of older adults.
Keywords: Activities of Daily Living; Aged; Aged, 80 and over; Case Management; Chronic disease; Cognition Disorders; Comorbidity; Cross-Sectional Studies; Disability Evaluation; Disease Management; Eligibility Determination; Female; Geriatric Assessment; Health Surveys; Humans; Longitudinal Studies; Male; Medicare; Middle Aged; Retirement; United States

The significance of nonmarital cohabitation: marital status and mental health benefits among middle-aged and older adults. - Susan L. Brown; Jennifer R. Bulanda; Lee, Gary R. (J Gerontol B Psychol Sci Soc Sci, 2005)
OBJECTIVES: According to the 2000 Census, about 1.2 million persons over age 50 are currently cohabiting. Do these unmarried cohabiting partnerships provide adults with mental health benefits that are similar to those enjoyed by marrieds? We extended prior work on marital status and depression by including cohabitation in our conceptualization of marital status. METHODS: We used data from the 1998 Health and Retirement Study (N = 18,598) to examine the relationship between marital status and depressive symptoms among adults over age 50. We also examined gender differences in this association. RESULTS: We found that cohabitors report more depressive symptoms, on average, than do marrieds, net of economic resources, social support, and physical health. Additional analyses revealed that only among men do cohabitors report significantly higher depression scores. Cohabiting and married women as well as cohabiting men experience similar levels of depression, and all of these groups report levels that are significantly higher than married men's. DISCUSSION: Our findings demonstrate the importance of accounting for nontraditional living arrangements among persons aged 50 and older. Cohabitation appears to be more consequential for men's than women's depressive symptoms.
Keywords: Aged; depression; Female; Humans; Insurance Benefits; Male; Marital Status; Mental Health Services; Middle Aged; Sexual Partners; Social Support; United States

A Slippery Slope: Essays on Income, Wealth, and the Health Gradient - Wenzlow, Audra T. (A Slippery Slope: Essays on Income, Wealth, and the Health Gradient, 2005)
The relationship between health and socioeconomic status (SES), often called the health gradient, is a complex and perplexing research puzzle. Individuals with higher incomes tend to be healthier (although at a declining rate with higher income), yet it is unclear why this is so. Here, I argue that wealth and savings, largely neglected in past empirical work, provide important insights into the health-SES relationship. An empirical model in which income and wealth are transformed using the inverse hyperbolic sine is shown to capture important variations in health throughout the income and wealth distributions for U.S. working-age adults. The three-dimensional gradient in income, wealth, and health illustrates two patterns that are investigated in the following chapters: the predominance of poor health among those with little savings, and variations in health disparities by wealth over the life cycle. Panel data from the Health and Retirement Study are used to investigate a likely mode through which wealth may have a causal effect on health among the poor: through financial constraints that limit access to health care at the time of illness. I capitalize on recent research suggesting that income and wealth do not cause the onset of certain acute illnesses, conditional on past health. Viewing unexpected costs associated with such illnesses as financial shocks, I find that approximately one quarter of the population that experiences a stroke, cancer, heart problem, or high blood pressure has insufficient liquid assets to cover typical costs of unexpected medical care. Furthermore, this study suggests that a causal relationship between lack of savings and health recovery is plausible, possibly contributing to the steep slope of the gradient about zero. In the final chapter, I test a number of hypotheses that could account for the observed life cycle pattern of declining socioeconomic disparities in health in old age. I find that poor measurement of financial resources and possible cohort, Medicare, or retirement effects, but not attrition, are likely contributors to this phenomenon. Taking into account life-cycle patterns of income receipt and wealth decumulation, I find a large health gradient in wealth among the oldest old.
Keywords: Health Conditions and Status; Income; Net Worth and Assets

Social Security and Retirement Dynamics - Alan L Gustman; Thomas L. Steinmeier (Michigan Retirement Research Center Research Project, 2005)
This paper is based on a structural model of retirement and saving, estimated with data for a sample of married men in the Health and Retirement Study. It explains the relation of specific features of Social Security -- the benefit amount, the early entitlement age, the normal retirement age, earnings test parameters, and the delayed retirement credit -- to the full range of retirement outcomes -- continued work on the main job, full time work outside the main job after a period of partial or full retirement, as well as partial retirement and full retirement. The project also estimates the relation of Social Security to the flows among these states. We consider not only the effect of Social Security on movement from states of greater to lesser work, the probability of either moving from full time work to partial retirement or directly to full retirement, or from partial retirement to full retirement, but the reverse flows from states of lesser work to states of greater work. The largest effects of the policies examined are from increasing the early entitlement age from 62 to 64 and reducing benefits to 75 percent of their promised levels, the approximate amount benefits would have to be reduced when the trust fund runs out if there are no changes in funding. With the older early entitlement age, about 5 percent more of the population continues to work full time at their main job at 62 and 63 than would otherwise. In addition, another 4.5 percent of the male population works full time after having retired, as does another 4 percent at age 63. Partial retirement is reduced at ages 62 and 63 by about 3 percentage points when the early entitlement age is 64. Overall, complete retirements are about 6 percentage points lower at 62 and 63 when the early retirement age is higher. From age 64 on, the percent completely retired is about two percentage points lower in each year when the early entitlement age is 64 rather than 62. The effects of reducing promised Social Security benefits by about a quarter are also large. The probability of remaining on the main job is higher for those in their sixties, with the difference ranging from 3 to 5 percentage points for those ages 62 and older. At each year of age, an additional 1 percentage point will be in full time work after having retired. There is little difference in the fraction partially retired, so the probability of being fully retired is reduced by 4 to 6 percentage points when benefits are reduced by a quarter.
Keywords: Consumption and Savings; Social Security

Social Security and the Retirement and Savings Behavior of Low Income Households - van der Klaauw, Wilbert; Wolpin, Kenneth I. (Penn Institute for Economic Research, University of Pennsylvania, 2005)
In this paper, we develop and estimate a model of retirement and savings incorporating limited borrowing, stochastic wage offers, health status and survival, social security benefits, Medicare and employer provided health insurance coverage, and intentional bequests. The model is estimated on sample of relatively poor households from the first three waves of the Health and Retirement Study (HRS), for whom we would expect social security income to be of particular importance. The estimated model is used to simulate the responses to several counterfactual experiments corresponding to changes in social security rules. These include changes in benefit levels, in the payroll tax, in the social security earnings tax and in early and normal retirement ages.
RDA
Keywords: Consumption and Savings; Social Security

The Social Security Early Entitlement Age In A Structural Model of Retirement and Wealth - Alan L Gustman; Thomas L. Steinmeier (Journal of Public Economics, 2005)
A structural life cycle model of retirement and wealth attributes retirement peaks at both ages 62 and 65 to Social Security rules and wide heterogeneity in time preferences. Those with high discount rates often retire at 62. They have few assets and heavily value lost benefits from working after 62, largely ignoring potential increases in later benefits. Declining actuarial adjustments beginning at 65 induce those with low discount rates to retire at 65. Raising the Social Security early entitlement age to 64 induces 5 of the population to delay retiring, shifting the retirement spike from 62 to 64.
RDA 1996-005
Keywords: Methodology; Net Worth and Assets

Social status and risky health behaviors: results from the health and retirement study. - Linda A. Wray; Duane F. Alwin; Ryan J McCammon (J Gerontol B Psychol Sci Soc Sci, 2005)
OBJECTIVES: We focus on a hypothesized mechanism that may underlie the well-documented link between social status and health-behavioral health risks. METHODS: We use longitudinal data from representative samples of 6,106 middle-aged and 3,636 older adults from the Health and Retirement Study to examine the relationships between social status-including early life social status (e.g., parental schooling), ascribed social status (e.g., sex, race-ethnicity), and achieved social status (e.g., schooling, economic resources)-and behavioral health risks (e.g., weight, smoking, drinking, physical activity) to (1) assess how early life and ascribed social statuses are linked to behavioral health risks, (2) investigate the role of achieved factors in behavioral health risks, (3) test whether achieved status explains the contributions of early life and ascribed status, and (4) examine whether the social status and health risk relationships differ at midlife and older age. RESULTS: We find that early life, achieved, and ascribed social statuses strongly predict behavioral health risks, although the effects are stronger in midlife than they are in older age. DISCUSSION: Ascribed social statuses (and interactions of sex and race-ethnicity), which are important predictors of behavioral health risks even net of early life and achieved social status, should be explored in future research.
Keywords: Aged; Aging; Alcohol Drinking; Body Weight; Exercise; Female; Health Behavior; Humans; Life Style; Likelihood Functions; Logistic Models; Longitudinal Studies; Male; Middle Aged; Smoking; Social Class; United States

Socioeconomic Differentials in Mortality and Health at the Older Ages - Eileen M. Crimmins (Genus, 2005)
Keywords: Demographics; Health Conditions and Status; Healthcare

A socioeconomic profile of older adults with HIV. - Joyce, Geoffrey F.; Dana P Goldman; Leibowitz, Arleen A.; Abby Alpert; Bao, Yuhua (J Health Care Poor Underserved, 2005)
The objective of this study was to assess the socioeconomic circumstances of older patients with HIV and acquired immunodeficiency syndrome (AIDS). The investigators compared subjects from a national probability sample of 2,864 respondents from the HIV Cost and Services Utilization Study (HCSUS, 1996) with 9,810 subjects from Wave 1 (1992) of the Health and Retirement Survey (HRS). Bivariate analyses compare demographic characteristics, financial resources, and health insurance status between older and younger adults and between older adults with HIV and the general population. It was found that nearly 10% of the HIV-positive population is between the ages of 50 and 61 years. Older whites with HIV are mostly homosexual men who are more well educated, more often privately insured, and more financially stable than the HIV population as a whole. In contrast, older minorities with HIV possess few economic resources in either absolute or relative terms. The success of new drug therapies and the changing demographics of the HIV population necessitate innovative policies that promote labor force participation and continuous access to antiretroviral therapies.
Keywords: Female; HIV Infections; Humans; Insurance, Health; Male; Middle Aged; Social Class

Supplemental private health insurance and depressive symptoms in older married couples. - Min, Meeyoung O.; Aloen L. Townsend; Baila Miller; Rovine, Michael J. (Int J Aging Hum Dev, 2005)
Stress process theory is applied to examine lack of supplemental private health insurance as a risk factor for depressive symptomatology among older married couples covered by Medicare. Dyadic data from 130 African-American couples and 1,429 White couples in the 1993 Asset and Health Dynamics Among the Oldest-Old Survey were analyzed using hierarchical generalized linear modeling. Lack of supplemental insurance is operationalized at the household level in terms of neither spouse covered, one spouse covered, or both spouses covered. Controlling for covariates at both individual and couple levels, supplemental insurance has significant impact on depression, but the pattern differs by race. White couples report the highest depression when neither spouse is covered by private health insurance; African-American couples report the highest depression when only one spouse is covered. Results suggest lack of supplemental private health insurance coverage is a stressor that significantly affects depressive symptoms.
Keywords: Aged; Aged, 80 and over; Analysis of Variance; Black People; Chi-Square Distribution; depression; Female; Humans; Insurance Coverage; Insurance, Health; Linear Models; Male; Risk Factors; Spouses; United States; White People

Survey Design and Methodology in the Health and Retirement Study and the Wisconsin Longitudinal Study - Hauser, Robert M.; Robert J. Willis (Aging, Health and Public Policy: Demographic and Economic Perspectives, 2005)
Large-scale data collection has become the kernel of the growth of knowledge in the social sciences. Nowhere is this more evident than in research in the demography of aging and the life course, where scientific progress has been stimulated and sustained by complementary longitudinal studies of aging populations. In this chapter, we review the history, organization, and design of two of these public resources, the Wisconsin Longitudinal Study (WLS) and the Health and Retirement Study (HRS). Recent innovations in each of these studies hold promise for major advances in knowledge about the demography, economics, sociology, and epidemiology of aging. The stories of the WLS and HRS highlight important clues about the creation of systems of continuing surveys to inform science and public policy.
Keywords: Methodology

Survival expectations of the obese: Is excess mortality reflected in perceptions? - Tracy Falba; Susan H. Busch (Obes Res, 2005)
OBJECTIVE: This study compared self-reported subjective life expectancy (i.e., probability of living to age 75) for normal-weight, overweight, and obese weight groups to examine whether individuals are internalizing information about the health risks due to excessive weight. RESEARCH METHODS AND PROCEDURES: Using data from the Health and Retirement Study, a total of 9035 individuals 51 to 61 years old were analyzed by BMI category. The primary outcome measure was individuals' reports about their own expectations of survival to age 75. Absolute and relative risks of survival were compared with published estimates of survival to age 75. RESULTS: Consistently, higher levels of BMI were associated with lower self-estimated survival probabilities. Differences relative to normal weight ranged from 4.9% (p < 0.01) for male nonsmokers to 8.8% (p < 0.001) for female nonsmokers. However, these differences were substantially less than those obtained from published survival curve estimates, suggesting that obese individuals tended to underestimate mortality risks. DISCUSSION: Individuals appeared to underestimate the mortality risks of excessive weight; thus, knowledge campaigns about the risks of obesity should remain a top priority.
Keywords: Aged; Body Mass Index; Body Weight; Diabetes Mellitus; Female; Health Surveys; Humans; Hypertension; Male; Obesity; Perception; Retirement; Smoking; Surveys and Questionnaires; Survival Rate

Sample Weights and Sample Selection Indicator for the Physical Measures in HRS 2004 - HRS Staff (Survey Research Center, Institute for Social Research, University of Michigan, 2004)

Saving for Retirement: Taxes Matter - James M. Poterba (Center for Retirement Research at Boston College Briefs, 2004)
This Issue in Brief begins with a brief description of the types of accounts that individuals may consider for retirement saving. It then analyzes two separate issues that are relevant to different stages of the investment process: 1) where to invest; and 2) how to value existing investments. The first issue involves what type of account individuals should choose in order to maximize their after-tax rate of return, assuming that each account offers the same pre-tax return. The analysis of this fundamental saving decision considers both taxes that are paid “up front” on contributions and taxes that are paid when funds are withdrawn. The second issue involves how to determine the after-tax value of existing assets in order to assess progress toward meeting a retirement saving target. Since, once the investments are made, “up-front” taxes are no longer relevant, this analysis looks only at taxes that are paid when funds are withdrawn or, in the case of taxable accounts, taxes that are due along the way.
Keywords: Consumption and Savings; Public Policy

Saving, Risk Sharing, and Preferences for Risk - Mazzocco, Maurizio (The American Economic Review, 2004)
An important feature of household saving decisions is the ability of individual members to share risk among them. With few exceptions, theoretical and empirical studies characterize household saving as if a single agent were making the decision. Under this assumption, the risk-sharing component of household saving is largely ignored. This paper is one of the first attempts to analyze the effect of risk sharing on saving by characterizing the household as a group of agents making efficient decisions.
Keywords: Risk Factors; Risk Taking; Savings

Savings and Retirement in the New Millennium - Anthony Webb (Economics, 2004)
The typical pension plan has changed dramatically in the past twenty-five years. There has been a large increase in the coverage of defined contribution (DC) plans, in which the pension is generally paid in unannuitized form, and where the amount of the pension depends on investment returns and the amount contributed. There has been a corresponding decline in the coverage of defined benefit (DB) plans in which the pension is some function of salary and years of service. DC plans place greater responsibility on the individual to make adequate provision for his retirement. They also lack many of the age related incentives of DB plans that have been shown to influence retirement. The first chapter, "The Effect of 401(k) Eligibility on Household Asset Holdings: New Evidence from the Health and Retirement Study", examines the question of whether contributions to 401(k) plans, the most common type of DC plan, have merely displaced other non pension savings, or whether they represent additional saving that would not otherwise have been made. A comparison of the savings of participants with those of non-participants would likely produce biased estimates, as participants probably have a stronger unobserved taste for savings than non-participants. I therefore follow previous practice in comparing eligible with ineligible households. Eligibility is, however correlated with DB plan membership, which may also affect savings behavior. I therefore restrict my analysis to households that are also members of DB plans, a relatively homogenous group. Previous researchers use asset balances imputed from donor households of a different pension type, leading to further potential bias. I therefore re-impute missing data, including eligibility among my covariates. Using the Health and Retirement Study, a panel dataset, I find no evidence of any displacement of other savings in either financial assets or home equity by 401(k) contributions. If anything, eligible households save more in other financial assets, a finding that I attribute to the financial education often associated with the introduction of DC plans. In my second chapter, co-authored with Professor Friedberg, I use data from the same dataset to show that retirement patterns have changed as DC plans have spread. We estimate that the financial incentives in DB plans lead people to retire almost two years earlier on average, and that the decline in DB plan coverage over the period 1983 to 1995 has increased average retirement age by two to four months. In my third chapter, I examine whether the observed failure of the elderly to dissave is a result of concerns about end-of-life expenditure. Using data from the Asset and Health Dynamics among the Oldest Old (AHEAD) dataset, I show that married couples save more if they expect to enter long-term care, but that single women do not. I attribute the difference in behavior between the two groups to a desire on the part of couples to make adequate provision for the surviving spouse.
Keywords: Pensions; Retirement Planning and Satisfaction

Selection Correction and Sensitivity Analysis for Ordered Treatment Effect on Count Response - Lee, Myoung Jae (Journal of Applied Econometrics, 2004)
In estimating the effect of an ordered treatment on a count response y with an observational data where tau is self selected (not randomized), observed variables x and unobserved variables epsilon can be unbalanced across the control group (tau = 0) and the treatment groups (tau = 1, . . . , J). While the imbalance in x causes overt bias which can be removed by controlling for x, the imbalance in epsilon causes covert (hidden or selection) bias which cannot be easily removed. This paper makes three contributions. First, a proper counter factual causal framework for ordered treatment effect on count response is set up. Second, with no plausible instrument available for tau, a selection correction approach is proposed for the hidden bias. Third, a nonparametric sensitivity analysis is proposed where the treatment effect is nonparametrically estimated under no hidden bias first, and then a sensitivity analysis is conducted to see how sensitive the nonparametric estimate is to the assumption of no hidden bias. The analytic framework is applied to data from the Health and Retirement Study: the treatment is ordered exercise levels in five categories and the response is doctor office visits per year. The selection correction approach yields very large effects, which are however ruled out by the nonparametric sensitivity analysis. This finding suggests a good deal of caution in using selection correction approaches.
ProCite field 3 : Singapore Management U
Keywords: Health Conditions and Status; Methodology

Self-Employment Among Older U.S. Workers - Lynn A Karoly; Julie M Zissimopoulos (Monthly Labor Review, 2004)
The 1990s showed a downward trend in self-employment rates, however, the fact that self-employment rates rise at older ages and that the baby-boom cohort is approaching retirement suggests that demographics alone may halt or reverse that trend.
Keywords: Employment and Labor Force

Self-Employment and the 50 Population - Lynn A Karoly; Julie M Zissimopoulos (Washington, DC, AARP Public Policy Institute, 2004)
Keywords: Employment and Labor Force

A Short Scale for Measuring Loneliness in Large Surveys: Results From Two Population-Based Studies. - Mary Elizabeth Hughes; Linda J. Waite; Louise C Hawkley; John T. Cacioppo (Res Aging, 2004)
Most studies of social relationships in later life focus on the amount of social contact, not on individuals' perceptions of social isolation. However, loneliness is likely to be an important aspect of aging. A major limiting factor in studying loneliness has been the lack of a measure suitable for large-scale social surveys. This article describes a short loneliness scale developed specifically for use on a telephone survey. The scale has three items and a simplified set of response categories but appears to measure overall loneliness quite well. The authors also document the relationship between loneliness and several commonly used measures of objective social isolation. As expected, they find that objective and subjective isolation are related. However, the relationship is relatively modest, indicating that the quantitative and qualitative aspects of social relationships are distinct. This result suggests the importance of studying both dimensions of social relationships in the aging process.

Should We Raise Social Security's Earliest Eligibility Age? - Alicia H. Munnell; Meme, Kevin B.; Natalia A. Jivan; Kevin E. Cahill (Center for Retirement Research at Boston College Briefs, 2004)
Social Security’s Earliest Eligibility Age (EEA) allows one to claim reduced benefits as early as age 62. For full benefits, individuals must wait until the Normal Retirement Age (NRA), which was traditionally 65 but is gradually increasing to 67. So, Americans have a choice to make when they reach their early 60s: claim a reduced Social Security benefit right away or delay until some further date and receive a larger benefit. The reduction for claiming benefits early is designed to be actuarially fair, i.e. monthly benefits are lowered by an amount that offsets the longer period for which they will be received. The total amount that the average person can expect to receive over his or her lifetime thus does not depend on when benefits are claimed…
Keywords: Social Security

Social, Cultural, and Economic Capital, and Behavioral Investments in Health - Patrick M. Krueger (University of Colorado at Boulder, 2004)
I develop a health stratification perspective to examine whether differential access to social, cultural, and economic capital account for differences in individuals' abilities and proclivities to behaviorally invest in their health. I suggest that each form of capital derives from key social institutions. To test my theoretical framework, I use the 1998 and 2000 waves of the Health and Retirement Study (HRS) to examine changes in health behaviors over a two year period. The HRS provides a nationally representative sample of adults aged 51 and older and has detail on six key behaviors, including physical activity, smoking, binge drinking, preventive blood cholesterol tests, preventive cancer screening behaviors, and flu shot receipt. First, Chapter 4 examines the relationship between socioeconomic status (SES) and behavioral investments in health. I find that socioeconomic position is multidimensional and indicates people's locations in diverse institutions including the occupational hierarchy, education, employment, and the financial marketplace. Although much prior work assumes that diverse socioeconomic measures are indicators of a single underlying concept, I find that each dimension of SES has a unique association with various health behaviors. Second, Chapter 5 examines the relationship between employment, gender, and marital status. Prior research suggests that employment enhances the health of both men and women. Further, wives often have better health if their husbands work, but husbands typically have worse health if their wives work. I fail to find support for this relationship when examining health behaviors; thus prior theoretical work may not adequately explain various dimensions of health. Finally, Chapter 6 finds that marriage generally promotes healthier lifestyles among men and women. However, the quality of the marriage is important--those whose spouses have healthier lifestyles undertake healthier behaviors than those whose spouses have less healthy lifestyles. Further, prior work suggests that marriage benefits the health of men more than women. But I find that marriage benefits women more than men for some health behaviors. Thus, health research may be inadequate if it focuses on a limited number of health indicators.
Keywords: Adult children; Demographics; Health Conditions and Status; Methodology

Social Integration of Older Immigrants in 21st Century America - Janet M Wilmoth (The Policy Brief, 2004)
There are various reasons for the burgeoning interest in detailed research into the determinants of social well-being among older immigrants in this country. As a result of shifting federal government policies, the total volume of immigrants has increased significantly, the countries from which they migrate have changed, and more immigrant families have brought their parents into the United States than ever before. Consequently, the older adult population is becoming more diverse due in part to the aging-in-place of younger immigrants and an increasing number of immigrants who are older upon arrival in the United States. These trends create challenges for social service providers, who are encountering language and cultural differences among their clients for which they are unprepared. This report provides an overview of research about older adult immigrants in the United States that my colleagues and I have conducted over the past few years. Various demographic and cultural aspects of today’s immigrants that differ from the past are described. The importance of social integration to older immigrants’ well-being is considered. Then some intriguing research about the “new immigrants” is summarized and additional areas for future research are suggested
Keywords: Demographics

Social Interaction and Stock Market Participation - Hong, Harrison; Kubik, Jeffrey D.; Stein, Jeremy C. (Journal of Finance, 2004)
We propose that stock-market participation is influenced by social interaction. In our model, any given social investor finds the market more attractive when more of his peers participate. We test this theory using data from the Health and Retirement Study, and find that social households those who interact with their neighbors, or attend church are substantially more likely to invest in the market than non-social households, controlling for wealth, race, education, and risk tolerance. Moreover, consistent with a peer-effects story, the impact of sociability is stronger in states where stock-market participation rates are higher.
Keywords: Health Conditions and Status; Net Worth and Assets

Social Security, Pensions and Retirement Behaviour Within the Family - Alan L Gustman; Thomas L. Steinmeier (Journal of Applied Econometrics, 2004)
This paper estimates a structural model of family retirement using US data from the Health and Retirement Study (HRS). It provides further insight into household retirement decision making and the reasons for interdependence in the retirement decisions of each spouse. Improvements in HRS data and matched employer provided pension histories allow more precise identification of key parameters governing interdependent behaviour within the household. In an earlier study we found that interdependence was due to preferences rather than coordination of retirement incentives in the budget, and in particular that it is not a correlation in preferences, but the appearance of the spouse's retirement status in the husband's and wife's utility function that is largely responsible for coordination of retirement between spouses. We now find that a measure of how much each spouse values being able to spend time in retirement with the other accounts for a good portion of that apparent interdependence. For the wife, the husband's retirement status influences her retirement decision only if she values spending time in retirement with her husband. For husbands, the effect of having the wife already retired on his retirement decision is roughly doubled if he enjoys spending time in retirement with his wife, but there is some effect even if he does not. This is consistent with our earlier findings that the husband is more influenced by having a retired spouse than the wife is. The increase in the extent of the dependence of the wife's labour supply on the husband's retirement from our past work probably is traceable to better measurement of the opportunity set facing the husband in HRS data. Once estimated, we use the model to investigate the labour supply effects of alternative social security policies, examining the effect of dividing credit for earnings evenly between spouses, or of basing social security benefits on the amounts accumulated in private accounts. Both policies change the relative importance of spouse and survivor social security benefits within the household and both raise the relative reward to work later in the life cycle. The incentives created are modest, and retirement responds accordingly. Nevertheless, at some ages, such as 65, there may be as much as a 6 increase in the old age work force under privatized accounts. Copyright 2004 John Wiley and Sons, Ltd.
RDA 1996-005; HRS 1992
Keywords: Adult children; Pensions; Retirement Planning and Satisfaction; Social Security

Saving, Public Policy, and Late-Life Inequality - Annamaria Lusardi; Jonathan S Skinner; Steven F Venti (Focus on Economic Outcomes in Later Life: Public Policy, Health, and Cummulative Advantage, 2003)
RDA 1998-006 (Lusardi) ProCite field 6 : Chapter 10 in ProCite field 8 : eds.
Keywords: Consumption and Savings; Public Policy

Saving, Wealth and Retirement: Evidence from the Health and Retirement Study - Khitatrakun, Surachai (Saving, Wealth and Retirement: Evidence from the Health and Retirement Study, 2003)
This dissertation examines household saving and retirement decisions using data from the 1992 to 2000 Health and Retirement Study (HRS). After a brief introduction, the second chapter examines the relationship between children and household net worth around the time of retirement. Restricting the sample to first-time married couples and controlling for many factors including lifetime earnings and unearned income, I find that households with more children generally have less net worth than households with fewer, but the difference is small. Moreover, there is no strong evidence that the difference is a result of the adverse effect of college financial aid rules on savings. In addition, there is little evidence that children affect parents' subjective assessments of retirement security. These findings are consistent with the basic principle of the life-cycle framework where parents plan optimally for their retirement consumption. The third chapter examines how wealth changes affect retirement decisions. I focus on the differences between self-reported expected retirement dates in one survey and either the actual or expected retirement dates in the next survey for the same individuals, and relate these to changes in household net worth. Moreover, I recognize that institutional constraints could deter individuals from adjusting their retirement dates to accommodate unanticipated events, such as wealth shocks. I find that the relationship between wealth changes and retirement is generally significant in the expected direction, and more pronounced for the respondents unlikely to face binding institutional constraints. The fourth chapter examines whether Americans are preparing adequately for retirement. My coauthors and I construct a life-cycle model that incorporates detailed HRS data on family structure and age of retirement and allows for uncertainties in earnings, social security benefits, and defined benefit pension receipts. Then, we solve every household's life-cycle problem and, using data on the household's entire history of earnings realizations, derive optimal wealth at given ages. The model explains over 70 percent of the variation in wealth for married households, and over 80 percent for never-married single households. Comparing the derived optimal wealth targets with the observed amount of net worth, we find little evidence that HRS households have under-saved.
Keywords: Net Worth and Assets; Retirement Planning and Satisfaction

Screening mammography and Pap tests among older American women 1996-2000: results from the Health and Retirement Study (HRS) and Asset and Health Dynamics Among the Oldest Old (AHEAD). - Truls Ostbye; Gary N. Greenberg; Donald H. Taylor Jr.; Lee, Ann Marie M. (Ann Fam Med, 2003)
BACKGROUND: We wanted to determine the frequency of self-reported receipt of screening mammography and Papanicolaou (Pap) tests in older women and investigate important predictors of utilization, based on 2 national longitudinal surveys. METHODS: This cohort study includes participants from 4 waves (1994-2000) of the Health and Retirement Study (HRS)--5,942 women aged 50 to 61 years, and 4 waves (1993-2000) of the Asset and Health Dynamics Among the Oldest Old (AHEAD) survey--4,543 women aged 70 years and older. The self-reported receipt of screening mammograms and Pap smears in the most recent 2 years were reported in 1996 and 2000 for HRS, with predictors of receipt measured in 1994 and 1998. In AHEAD, the self-reported receipt of screening mammograms and Pap smears in the most recent 2 years were reported in 1995 and 2000, with predictors of receipt measured in 1993 and 1998. RESULTS: Receipt of mammography is stable at 70% to 80% among women aged 50 to 64 years, then declines to around 40% among those aged 85 to 90 years. For Pap tests there is a decline from 75% among women aged 50 to 54 years to 25% in those aged 85 to 90 years. For both mammography and Pap tests, the rates increased in all groups from 1995/1996 to 2000. Higher education, being married, higher income, not smoking, and vigorous exercise were consistently associated with higher rates of receipt. CONCLUSIONS: Although the use of mammography and Pap tests for screening declines into old age, use has been increasing recently. The large and increasing number of tests performed might not be justified given the lack of evidence of effect in older age-groups.
Keywords: Age Factors; Aged; Aged, 80 and over; Breast Neoplasms; Cost-Benefit Analysis; Female; Health Services for the Aged; Humans; Longitudinal Studies; Mammography; Middle Aged; Multivariate Analysis; Papanicolaou Test; Patient Acceptance of Health Care; Risk; United States; Uterine Cervical Neoplasms; Vaginal Smears

Searching for Better Prospects: Endogenizing Falling Job Tenure and Private Pension Coverage - Friedberg, Leora; Owyang, Michael T.; Sinclair, T. (Federal Reserve Bank of St. Louis Working Paper, 2003)
Recent declines in job tenure have coincided with a shift away from traditional defined benefit (DB) pensions, which reward long tenure. New evidence also points to an increase in job-to-job movements by workers, and we document gains in relative wages of job-to-job movers over a similar period. We develop a search model in which firms may offer tenure-based contracts like DB pensions to reduce the incidence of costly on-the-job search by workers. Either reduced search costs or an increase in the probability of job matches can, under fairly general conditions, lower the value of deterring search and the use of DB pensions.
Keywords: Contracts; Job tenure; Pensions

Self-Employment Trends and Patterns Among Older U.S. Workers - Lynn A Karoly; Julie M Zissimopoulos (RAND Working Paper, 2003)
Although self-employment is an important labor force phenomenon at older ages, there is a paucity of studies that examine the patterns of self-employment among older U.S. workers. With the leading edge of the baby boom cohort reaching retirement years, the rising rates of self employment with age suggest that it is important to have a solid understanding of who is self employed at older ages and how patterns of self-employment may be changing over time. Using cross-sectional time-series data from the annual Current Population Survey from 1968 to 2002 and cross-sectional data from the Health and Retirement Study from 1998, we examine the trend in rates of self-employment among workers age 50 and above. We describe the characteristics of older self-employed workers, in total and for subgroups, and compare them with their wage and salary counterparts.
Keywords: Employment; Entrepeneurship; Unemployment

Self-rated life expectancy as a predictor of mortality: evidence from the HRS and AHEAD surveys. - Michele J. Siegel; Elizabeth H Bradley; Stanislav V Kasl (Gerontology, 2003)
BACKGROUND: An extensive literature has demonstrated that self-ratings of health predict mortality, even after controlling for more objective measures of health, health habits and sociodemographic characteristics. We examine the role of a related concept, self-rated life expectancy, in predicting mortality. OBJECTIVE: To assess whether self-rated life expectancy predicts mortality after controlling for measures of health, self-rated health, and sociodemographic characteristics. METHODS: Using data from the 1992 Health and Retirement Survey (HRS), the 1993 Asset and Health Dynamics Among the Oldest Old (AHEAD) survey, and the second Tracker file (2.0), Cox proportional hazard models were estimated to assess whether self-rated life expectancy predicts mortality, after adjusting for self-rated health and several potential confounders that might otherwise explain this relationship. The AHEAD sample included 2,102 men and 3,160 women. During the 2 years of follow-up, 9% (n = 185) of the men died and 5% (n = 166) of the women died. The HRS sample was comprised of 4,090 men and 4,885 women. Four percent (n = 164) of the men died and 2% (n = 99) of the women died in the 3 years of follow-up. RESULTS: In the older, AHEAD sample, both self-rated life expectancy (p < 0.01) and self-rated health (p < 0.05) predicted mortality for both men and women, even when the two measures were included in the model together. In the younger, HRS sample, self-rated life expectancy was not significantly associated with mortality when self-rated health was included in the model. CONCLUSION: Our findings suggest that, although self-rated life expectancy and self-rated health may be conceptually related, they have independent empirical effects on mortality.
Keywords: Aged; Female; Health Status; Health Surveys; Humans; Life Expectancy; Male; Mortality; Prognosis; Proportional Hazards Models; Self Concept; Sex Distribution; Survival Analysis

Sickness and preventive medical behavior. - Stephen Wu (J Health Econ, 2003)
Using data from two sources, the Health and Retirement Study (HRS) and the Medical Expenditure Panel Survey (MEPS), I analyze the relationship between health status and the likelihood of engaging in medical screening and other preventive behavior. The results show that individuals who are in poorer health are more likely to get flu shots and cholesterol checks, but less likely to have mammograms, pap smears, breast examinations and prostate checks. There is some evidence that suggests that psychological factors such as fear and anxiety may be important reasons why sicker people are less likely to get cancer screens.
Keywords: Aged; Anxiety; Breast Self-Examination; Cholesterol; Female; Health Behavior; Health Expenditures; Health Status; Humans; Influenza Vaccines; Male; Mammography; Mass Screening; Middle Aged; Papanicolaou Test; Patient Acceptance of Health Care; Preventive Health Services; Primary Prevention; Prostatic Neoplasms; Retirement; Risk Factors; Vaginal Smears

Smoking Cessation and Lifestyle Changes - Gabriel A. Picone; Frank A Sloan (Frontiers in Health Policy Research, 2003)
ProCite field 6 : In ProCite field 8 : eds
Keywords: Health Conditions and Status

Social Security Reform and the Exchange of Bequests for Elder Care - Brown, Meta (Center for Retirement Research at Boston College Working Papers, 2003)
The majority of elderly Americans who receive long-term care outside of institutions are cared for in part by their children. We have little evidence, however, on the financial and social mechanisms securing the supply of elder care. In recent data on older U.S. families, I find that children rarely receive direct payment for their help. Further, inter-vivos transfers from unmarried parents to their adult children do not favor caregivers. Given the lack of evidence of any spotmarket for family care, the central question of this study is whether end-of-life transfers act as compensation for caregiving children. An empirical study of parents division of bequests and life insurance among their children shows a positive association between children s transfer shares and both current and predicted caregiver status. In order to investigate the dependence of family care outcomes on children s time costs and parents wealth and care needs, I present a dynamic model of the asset choices of an elderly parent who wishes to elicit care from her children. Model estimates indicate that children respond to parents care needs and bequeathable wealth in the decision to provide care, and that children with greater time costs provide care only at higher levels of bequeathable wealth. Finally, a policy simulation based on model estimates predicts that a 5 to 6 percentage point increase in the rate at which unmarried elderly parents receive family care would result from reforms in which the expected present values of both public and private pensions were included in parents bequests. However, a more modest change in public retirement benefits, designed to mimic the broad-brush characteristics of an existing proposal for Social Security reform, is predicted to have a negligible effect on care rates.
Keywords: Adult children; Healthcare

Socioeconomic Status and Health over the Life Course: Capital as a Unifying Concept - Frytak, Jennifer R.; Harley, Carolyn R.; Finch, Michael D. (Handbook of the Life Course, 2003)
On average, individuals of lower socioeconomic status (SES)—based on education, income, or occupation—have worse health than their higher SES counterparts (Adler, Boyce, Chesney, Folkman, & Syme, 1993; Antonovsky, 1967; Feinstein, 1993; Feldman, Makuc, Kleinman, & Cornoni-Huntley, 1989; House, Kessler, & Herzog, 1990; Kitagawa & Hauser, 1973; Marmot, Shipley, & Rose, 1984; Pappas, Queen, Hadden, & Fisher, 1993; Preston & Taubman, 1994; Townsend & Davidson, 1982). This relationship is best depicted as a gradient in health with a fairly linear trend in better health associated with increasing levels of SES, rather than a threshold effect. Furthermore, this relationship is stratified by age; lower SES individuals begin to experience health problems shortly after adolescence, while higher SES individuals experience little health decline until around retirement age (House et al, 1990, 1994). This life course patterning of SES and health is intriguing since it suggests substantial variation in the ability of each group to sustain good health over the life course.
ProCite field 6 : Chapter 28 in ProCite field 8 : eds.
Keywords: Demographics; Event History/Life Cycle; Health Conditions and Status; Net Worth and Assets

Special Issue on Cross-National Comparative Research Using Panel Surveys (Introduction) - James P Smith; Stafford, Frank; Walker, James R. (Journal of Human Resources, 2003)
Until recently, international comparative research had a poor reputation, especially in economics. Panel surveys comparable to those in the United States either did not exist or were viewed as being of low quality. However, the number and quantity of international panels surveys are improving rapidly and in many dimensions will soon exceed those of their U.S. counterparts, particularly as foreign-born academics trained in the United States use data from their home countries in their research. This article introduces a series of papers presented at a conference on comparative international research using panel surveys, which took place in Ann Arbor, Michigan in October 2000. Its goal was to encourage researchers in the social sciences to use panel surveys to address critical scientific and policy issues that would be better informed by international comparisons and the variation in policy environments across countries. Five of the seven papers explicitly or implicitly examine international differences in savings behavior and wealth accumulation; the two remaining papers use international comparisons to assess the status of young children.
Keywords: Households; retirement savings; Wealth; Workforce

SSI Eligibility and Participation Among the Oldest Old: Evidence from the AHEAD - Davies, Paul S. (Social Security Bulletin, 2003)
This article models Supplemental Security Income (SSI) eligibility and participation among persons aged 70 or older using data from the Study of Assets and Health Dynamics Among the Oldest Old. An econometric model estimates the influence of socioeconomic characteristics on the probability of SSI participation among eligible units. Finally, a policy simulation is conducted by increasing the unearned income disregard from 20 to 125.
Keywords: Consumption and Savings; Public Policy

A Structural Model of the Effect of Retiree Health Insurance on Early Retirement - Tunceli, Kaan (A Structural Model of the Effect of Retiree Health Insurance on Early Retirement, 2003)
This study contributes to the existing literature by pursuing two complementary goals: (1) To estimate the effect of planning to retire early on access to employer provided retiree health insurance (ERHI); and (2) to produce a consistent estimate of the effect of ERHI on the probability of early retirement, allowing for the possibility that access to retiree health insurance is an endogenous variable. The empirical analysis uses the data from the first five Waves of the Health and Retirement Study (HRS), which were conducted every other year from 1.992 to 2000. The analysis focuses on men who were less than 65 in 2000, full-time workers, and had insurance as active workers in 1996. The retirement model is specified with three sequential equations: Planning to retire early in 1992, access to retiree health insurance in 1996, and retirement between 1996 and 2000. Not only demographic and socioeconomic characteristics of men, but also those of spouses to estimate the structural retirement model are included in all three equations. Alternative estimation techniques are used including univariate probit, bivariate probit, and trivariate probit models. The results vary significantly across estimation techniques. Planning to retire early encourages access to ERHI in the bivariate and trivariate models, while it does not in the univariate model. The effect of access to ERHI on early retirement is positive and significant in all three models. However, the effect is larger for bivariate and trivariate models compared to the univariate model. The trivariate model provides evidence that correlations between error terms across the structural equations are significant. The correlation between errors in the access equation and the retirement equation is negative. Therefore, it is likely that previous literature underestimated the effect of access to retiree health insurance on early retirement. One important implication for public policy is that policy initiatives such as a Medicare buy-in or health insurance tax credits that increase access to retiree health insurance are likely to have large effects on retirement decisions. In other words, the unintended effects on labor force participation of policies that increase access to retiree health insurance might be greater than previous research has suggested.
Keywords: Medicare/Medicaid/Health Insurance; Retirement Planning and Satisfaction

A Study of Health Human Capital - Ippolito, Richard A. (George Mason University School of Law, 2003)
Keywords: Adult children; Demographics; Health Conditions and Status

Saving for Retirement: Wage Growth and Unexpected Events - Michael D Hurd; Julie M Zissimopoulos (MRDRC Projects, 2002)
We found that there is a perception of ‘under-saving’ for retirement among many individuals. Individuals who perceive they have saved inadequately attribute this mainly to having insufficient income. Under a lifecycle model of consumption with a known income path this is not a reasonable answer. Those with low income today who fail to save will have even lower consumption levels in the future and could increase lifetime utility by reallocating consumption from pre-retirement to post-retirement. Unexpected outcomes in earnings, however, may cause households that planned to reach retirement with adequate savings, not to realize their plans. The decline in real wages that began in 1973 suggests a compelling explanation for low wealth levels: individuals were surprised by low earnings growth and thus under-saved relative to their lifetime incomes. We find that the hypothesis fits the data for those with extreme outcomes but does not explain large wealth differences for individuals on average.
Keywords: Consumption and Savings

Self-defined Retirement Status and Engagement in Paid Work Among Older Working-age Women: Comparison Between Childless Women and Mothers - Namkee G Choi (Sociological Inquiry, 2002)
From changes in retirement laws and incentives many people, including working women, can decide when to retire based on their own preferences and needs. Family structure and familial roles are a major issue of when people will decide to retire, especially if considering women. Differences between women without children and those with children that are no longer living at home, and the likelihood of retirement among people of the two groups, is assessed. The author, also considers those women that take part in bridge jobs as a path to retirement. Detailed demographic findings comparing and contrasting those women with children living at home, those women with children not living at home, and those women who are childless, are given. Analyses of the data showed that women with children living at home were the least likely to claim retirement. Over the 2 years of data studied none of the three groups showed a change in their work status. The author feels that retirement is becoming a symbol of status, rather than a symbol that one has served in the workforce for many years and is now withdrawn
Keywords: Adult children; Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction; Women and Minorities

The Size and Composition of Wealth Holdings in the United States, Italy, and the Netherlands - Arie Kapteyn; Panis, Constantijn (RAND Unrestricted Draft, 2002)
This report analyzes retirement-saving behavior and portfolio choice in the United States, Italy, and the Netherlands. The authors test hypotheses on the implications of institutional differences for wealth accumulation and portfolio composition.
Keywords: Methodology; Net Worth and Assets

Size of Incentive Effects in a Longitudinal Study - Rogers, Willard (American Association for Public Research 2002, 2002)
This paper describes an experiment conducted as part of one wave of the Health and Retirement Study (HRS), which is a longitudinal survey of a nationally representative sample of persons who were born in 1947 or before. Interviews have been conducted biennially since 1992. The general practice, after wave 1, has been to include a check for $20 along with an advance letter sent to each sample member prior to their being contacted, by telephone or face-to-face, by an interviewer. The experiment consisted of changing the amount of the incentive check for randomly selected sample members, with the objective of examining the effect of incentive size in the response rate, on the amount of effort required to finalize the case, and the quality of the data obtained from respondents. In this paper, we examine the effects of the size of the incentive on the response rate on the immediate wave, and also briefly examine the effects on the number of calls.
Keywords: Healthcare; Methodology

Social Security, Pensions and the Savings and Retirement Behavior of Households - van der Klaauw, Wilbert; Wolpin, Kenneth I. (University of North Carolina at Chapel Hill, 2002)
In this paper we formulate and estimate an explicit sequential decision model of savings and work behavior of elderly individuals and couples. More specifcally, we develop a stochastic dynamic model of retirement behavior in which forward-looking individuals are making employment and savings decisions in a setting that accounts for uncertainty about future labor market opportunities, health insurance coverage, health status, survival, and the future generosity of the social security system. The choice environment is characterized by an incomplete health insurance market, the presence and characteristics of employer provided health insurance and private pension plans, the Social Security and Medicare insurance system, and a capital market which applies borrowing limits. The model is estimated using longitudinal data from the Health and Retirement Study. The estimates are used to evaluate the importance of potential earnings, health, social security benefits and employer provided health insurance coverage and pensions in explaining observed retirement behavior, and to simulate the impact of potential social security reforms on life cycle employment and savings behavior and on welfare.
RDA
Keywords: Consumption and Savings; Employment and Labor Force; Methodology

The socio-economic and Health Differences in Parents' Provision of Help to Adult Children: A British-USA Comparison - John C Henretta; Emily M D Grundy; Harris, Susan (Ageing and Society, 2002)
Transfers of assistance from older to younger family members are an important, though often ignored, component of intergenerational exchanges. The ability to help younger family members, either financially or practically, may be influenced by the health and socio-economic status of older parents, but very little is known about these patterns. This article examines the effects of socio-economic and health status on the help that late mid-life parents in Britain and the United States give their children with money, domestic tasks, and grandchild care. Results for the different types of family support yield three main findings. First, there are relatively few differences between Britain and the USA in the factors affecting the provision of support. Secondly, socio-economic factors appear to be more important among married respondents while health is more important among the unmarried. Thirdly, children's co-residence has greater effects on the provision of domestic task help in Britain than in the United States.
Keywords: Adult children; Demographics; Health Conditions and Status

State expenditures on home and community based services and use of formal and informal personal assistance: a multilevel analysis. - Muramatsu, Naoko; Richard T. Campbell (J Health Soc Behav, 2002)
Despite wide state variation in commitment to home and community-based services (HCBS) for functionally impaired older persons, little is known about how such variation affects older adults' strategies to compensate for their functional limitations. This study examines the association of state HCBS expenditures with use of formal and informal personal assistance among non-institutionalized older Americans aged 70 and older with functional limitations. We conducted multilevel multinomial logistic regression analysis using data from the first wave of the Assets and Health Dynamics among the Oldest Old Survey, combined with data on state HCBS expenditures. Controlling for individuals' demographic, socioeconomic, and care needs factors, persons residing in states with higher HCBS expenditures were more likely to use formal personal assistance, but not less likely to use informal assistance. Our study suggests state variation in HCBS expenditures leads to inequitable access to formal personal assistance, especially among those with high functional limitations.
RDA 1996-025
Keywords: Aged; Aged, 80 and over; Community Health Services; Female; Financing, Government; Frail Elderly; Health Care Surveys; Health Expenditures; Home Care Services; Humans; Logistic Models; Male; State Government

Study: Marriage Builds Partners in Health - USA Today (USA Today, 2002)
Keywords: Adult children; Health Conditions and Status

Saving Puzzles and Saving Policies in the United States - Annamaria Lusardi; Jonathan S Skinner; Steven F Venti (NBER, 2001)
In the past two decades the widely reported personal saving rate in the United States has dropped from double digits to below zero. First, we attempt to account for the decline in the National Income and Product Accounts (NIPA) saving rate. The macroeconomic literature suggests that about half of the drop since 1988 can be attributed to households spending stock market capital gains. Another thirty percent is accounting transfers from personal saving into government and corporate saving because of the way pensions and capital gains taxes are treated in the NIPA. Second, while NIPA saving measures are well suited for measuring the supply of new funds for investment and capital accumulation, it is not clear that they should be the target of government saving policies. Finally, we emphasize that the NIPA saving rate is not useful in judging whether households are preparing for retirement or other contingencies. Many households have accumulated significant wealth, primarily through retirement saving vehicles and capital gains, even as the saving rate slid. There remains a segment of the population, however, who save little and whose behavior appears untouched either by the stock market boom or the slide in personal saving. We explore reasons and policy options for their puzzlingly low saving rate.
Keywords: Saving; Saving behavior; Wealth; wealth accumulation

Savings of Young Parents - Annamaria Lusardi; Cossa, Ricardo; Krupka, Erin L. (The Journal of Human Resources, 2001)
In this paper, we examine household savings using data from the National Longitudinal Survey, Cohort 1997. This data set provides detailed information about assets and liabilities of parents with teenage children. In our empirical work, we have to first deal with several problems in measuring wealth. Although many responding parents report owning assets and liabilities, they often do not report their values. To get around the nonresponse problem, we impute the missing values for assets and liabilities. To study the patterns of accumulation of young parents, we examine wealth holdings and asset ownership across several demographic groups.
Keywords: Consumption and Savings; Net Worth and Assets

Self-restriction of medications due to cost in seniors without prescription coverage. - Michael A Steinman; Laura Sands; Kenneth E Covinsky (J Gen Intern Med, 2001)
OBJECTIVE: Little is known about patients who skip doses or otherwise avoid using their medications because of cost. We sought to identify which elderly patients are at highest risk of restricting their medications because of cost, and how prescription coverage modifies this risk. DESIGN AND PARTICIPANTS: Cross-sectional study from the 1995-1996 wave of the Survey of Asset and Health Dynamics Among the Oldest Old, a population-based survey of Americans age 70 years and older. MEASUREMENTS: Subjects were asked the extent of their prescription coverage, and whether they had taken less medicine than prescribed for them because of cost over the prior 2 years. We used bivariate and multivariate analyses to identify risk factors for medication restriction in subjects who lacked prescription coverage. Among these high-risk groups, we then examined the effect of prescription coverage on rates of medication restriction. MAIN RESULTS: Of 4,896 seniors who regularly used prescription medications, medication restriction because of cost was reported by 8% of subjects with no prescription coverage, 3% with partial coverage, and 2% with full coverage (P <.01 for trend). Among subjects with no prescription coverage, the strongest independent predictors of medication restriction were minority ethnicity (odds ratio [OR], 2.9 compared with white ethnicity; 95% confidence interval [95% CI], 2.0 to 4.2), annual income <$10,000 (OR, 3.8 compared with income > or =$20,000; 95% CI, 2.4 to 6.1), and out-of-pocket prescription drug costs >$100 per month (OR, 3.3 compared to costs < or =$20; 95% CI, 1.5 to 7.2). The prevalence of medication restriction in members of these 3 risk groups was 21%, 16%, and 13%, respectively. Almost half (43%) of subjects with all 3 risk factors and no prescription coverage reported restricting their use of medications. After multivariable adjustment, high-risk subjects with no coverage had 3 to 15 times higher odds of medication restriction than subjects with partial or full coverage (P <.01). CONCLUSIONS: Medication restriction is common in seniors who lack prescription coverage, particularly among certain vulnerable groups. Seniors in these high-risk groups who have prescription coverage are much less likely to restrict their use of medications.
Keywords: Aged; Aged, 80 and over; Cohort Studies; Cross-Sectional Studies; Female; Humans; Insurance, Pharmaceutical Services; Male; Prescription Fees; Risk Factors; Socioeconomic factors; Treatment Refusal; United States

Seniors Most in Need of Home Care May Not Get It - Reuters (New York Times on the Web, 2001)
ProCite field[2]: Press Release
Keywords: Healthcare

Should a Lump-Sum Payment Replace Social Security's Delayed Retirement Credit? - Orszag, Peter R. (Center for Retirement Research at Boston College Briefs, 2001)
Transforming Social Security’s delayed retirement credit into a lump-sum payment rather than an increased monthly payment would likely encourage more workers to defer retirement and benefit claiming. The idea is thus worthy of further exploration. Several important design issues, however, must be addressed before policymakers give serious consideration to the reform. The most problematic aspect of the proposal is that implementing a lump-sum payment system for individuals older than the normal retirement age may create political pressure to extend this approach to those who are younger than the normal retirement age. Such an extension would risk a significant increase in elderly poverty rates relative to the current Social Security system…
Keywords: Retirement Planning and Satisfaction; Social Security

Social Security Expectations and Retirement Savings Decisions - Dominitz, Jeff; Charles F Manski; Heinz, Jordan (NBER Working Paper, 2001)
Retirement savings decisions should depend on expectations of Social Security retirement income. Persons may be uncertain of their future Social Security benefits for several reasons, including uncertainty about their future labor earnings, the formula now determining social security benefits, and the future structure of the Social Security system. To learn how Americans perceive their benefits, we have elicited Social Security expectations from respondents to the Survey of Economic Expectations. We have also performed a more intensive face-to-face survey on a small sample of respondents. This paper presents the empirical findings. It also illustrates how data on expectations may help predict how Social Security policy affects retirement savings.
National Institute on Aging Grant 2 P01 AG10179-04A1 and National Science Foundation grant SES-0001436.
Keywords: Consumption and Savings; Social Security

Social Security Incentives for Retirement - Courtney Coile; Gruber, Jonathan (Themes in the Economics of Aging, 2001)
The 'tax effect' is one of the effects used to explain the rapid decline in the labor force participation of older men over age 62. This paper provides a thorough investigation of this 'tax effect' by studying it along four different dimensions. Using HRS data, the impact of SS retirement incentives are considered and the distribution of the incentives across the population is assessed. The paper then examines the role of private pensions and the importance of considering retirement incentives in the next year vs. considering incentives for all possible years.
ProCite field 8 : ed.
Keywords: Demographics; Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction

Social Security: What is it good for? - Van Wesep, Edward P. (Michigan State University, 2001)
I develop three life cycle models that are designed to examine under what circumstances social security can improve the welfare of societies in the Pareto sense: can at least one person be made better off, without harming young and all old people are assumed to be identical. Rather, the focus is on intergenerational redistribution, which can occur three ways: (1) via private intergenerational transfers, (2) via private saving, and (3) via social security. Externalities play a prominent role in two of the models. In chapter 1, young people make private transfers to their parents, but the quantity of the total transfer from children to parents is not optimal because of an externality. Social security plays a Pigovian role in that model, setting up an incentive system designed to cause private behavior to yield the optimum result. In chapter 3, pay-as-you-go social security is revealed to be a system of intergenerational externalities. Because of this, there is avoidance of social security taxes by the young. This phenomenon of social security tax avoidance leads to a stricter welfare test for pay-as- you-go social security than the traditional Samuelsonian test. There are no externalities in chapter 2, since social security is treated there as an investment plan for workers: workers thus internalize all of the utility impacts of social security tax payments, just as they internalize the utility impacts of their private saving decisions. The welfare impact of social security in that model is a pure "moneysworth," or rate of return effect. The simplicity of the welfare criterion developed in the model of chapter 2 makes it possible to develop an empirical test of the welfare properties of the United States' Social Security system, using data from the Health and Retirement Study.
Keywords: Adult children; Demographics; Event History/Life Cycle; Methodology; Other; Public Policy

Socioeconomic Differences in Having Living Parents and Children: A U.S.-British Comparison of Middle-Aged Women - John C Henretta; Emily M D Grundy; Harris, Susan (Journal of Marriage and the Family, 2001)
The authors observe the differences in socioeconomic status among women in Britain and the U.S. who have living parents as well as children in the middle-aged cohort. Those people in the middle generation are likely to encounter many demands, both from their parents and their children. What is the magnitude of the socioeconomic effects in these two countries? What is the pattern of socioeconomic differences in parent survival when inspecting the socioeconomic status of the middle-aged children? Data from the 1988 Office of National Statistics Retirement and Retirement Plans Survey was gathered for the British population and compared to Wave 1 (1992) and Wave 2 (1994) of the Health and Retirement Study. Findings from this study are that: (1) the U.S. has much greater levels of kin availability; (2) the pattern of socioeconomic effects is rather similar between the two countries; (3) socioeconomic status is negatively correlated with the number of children one has; and (4) people with greater socioeconomic status are more likely to have a living parent and children. Policies that change the amount of responsibility a person has with regard to other generations of the family will have differing consequences depending on the country, status, and whom the policy is concerning (elderly or young).
Keywords: Adult children; Demographics

Socioeconomic status and the prevalence of health problems among married couples in late midlife. - Sven E. Wilson (Am J Public Health, 2001)
OBJECTIVES: This study analyzed the association between socioeconomic status (SES) and the prevalence of mutually occurring health problems among married couples in late midlife. METHODS: Data consisted of 4746 married couples aged 51 to 61 years from the 1992 US Health and Retirement Study. Two health measures were used: (1) self-assessed health status and (2) an index of functional limitations and activity restrictions. SES indicators were household income, education, and insurance coverage. RESULTS: In general, after adjustment for age cohort, a strong association was found between the health of a married individual and the health of his or her spouse. SES was highly associated with the joint occurrence of health problems among marriage partners. CONCLUSIONS: Public health policy should pay particular attention to the interaction between health, SES, and interpersonal relationships.
Keywords: Activities of Daily Living; Cohort Studies; Female; Health Status; Humans; Male; Marital Status; Middle Aged; Odds Ratio; Risk Factors; Socioeconomic factors; Spouses; United States

Stretching Social Surveys to Include Bioindicators: Possibilities for the Health and Retirement Study, Experience from The Taiwan Study of the Elderly - Weinstein, Maxine; Robert J. Willis (Cells and Surveys: Should Biological Measures Be Included in Social Research?, 2001)
ProCite field 6 : In ProCite field 8 : eds.
Keywords: Methodology; Mortality

Study Reveals Today's Seniors Are More Apt to Be of Sound Mind - Goldsmith, Rebecca (Study Reveals Today's Seniors Are More Apt to Be of Sound Mind, 2001)
ProCite field[2]: Press Release
Keywords: Health Conditions and Status

Surveys of the Life Course and Aging: Some Comparisons - Kuo, Hsiang-Hui Daphne; Park, Hyunjoon; Hauser, Taissa S.; Hauser, Robert M.; Marks, Nadine F. (University of Wisconsin-Madison, 2001)
In this paper, we introduce, compare, and evaluate the design and content of five major longitudinal studies of aging: the Wisconsin Longitudinal Study (WLS), Health and Retirement Survey (HRS), National Survey of Families and Households (NSFH), Americans' Changing Lives (ACL), and Midlife in the United States (MIDUS). We first compare population coverage, sampling design, response rate, observational duration, sources of relational and multi-level data, and links to public records. Overall, WLS, HRS, and NSFH excel in many respects. We also evaluate questions and measures in each study. In topical coverage, WLS and NSFH are the most complete. In question quality, WLS, HRS, and NSFH excel in several areas, while MIDUS and ACL stand out mainly in life event inventories, psychological measures and some health measures.
Keywords: Methodology

Saver Behavior and 401(k) Retirement Wealth - James M. Poterba; Steven F Venti; David A Wise (American Economic Review, 2000)
Contributions to 401(k) plans are now the most important form of retirement saving. Since 401(k) plans were introduced in the early 1980's, they have expanded rapidly and continuously. By 1998, roughly half of all households were eligible to participate in 401(k) plans, and more than 36 million workers made contributions to these employer-provided saving plans. In 1995, the last year for which the U.S. Department of Labor has released definitive data, 401(k) contribu- tions amounted to $87.4 billion, or 55 percent of all contributions to employer-sponsored pension plans. The level of contributions, and their share of all pension contributions, is probably signifi- cantly higher today. The spread of 401(k) plans is the most important indicator of the move to personal retirement saving. In 1980, almost 92 percent of pension-plan contributions were to tradi- tional employer-provided plans, and about 64 percent of these contributions were to conventional defined-benefit plans. Today, almost 60 percent of contributions are to personal retirement accounts, including 401(k), IRA, and Keogh plans. Including employer- provided, non-40 1 (k) defined-contribution plans, over 76 percent of contributions are to plans that are controlled in large measure by individuals. These individuals make partici- pation, contribution, asset-allocation, and withdrawal decisions. In this paper, we describe the likely impor- tance of 401(k) assets for future older Ameri- cans and the effect of investment decisions on asset accumulation. We also examine the extent to which retirement assets may be affected by several decisions: preretirement withdrawals, management fees and expenses, contribution rates, and early retirement. Our analysis focuses on 401(k) saving, but applies more broadly to other forms of individual retirement saving.
RDA 1999-002
Keywords: Consumption and Savings; Net Worth and Assets; Pensions; Retirement Planning and Satisfaction; Social Security

Saving for Retirement: Household Bargaining and Household Net Worth - Lundberg, Shelly J.; Jennifer L. Ward-Batts (University of Michigan, Michigan Retirement Research Center, 2000)
Traditional economic models treat the household as a single individual, and do not allow for separate preferences of and possible conflicts of interest between husbands and wives. Since wives are typically younger than their husbands and life expectancy for women exceeds that for men, wives may prefer to save more for retirement than do their husbands. This suggests that households in which wives have greater relative bargaining power may accumulate greater net worth as they approach retirement. Most empirical models of net worth in the literature do not include characteristics of both spouses. We present a more complete unitary model of household net worth and find, among couples in the first wave of the Health and Retirement Survey, that the characteristics of both husband and wife are determinants of net worth. We explore the importance of bargaining in marriages of older couples by examining the empirical relationship between their net worth and factors such as relative control over current income sources, relative age, and relative education. We find some evidence that low relative education of wives is associated with low net worth.
Keywords: Consumption and Savings; Net Worth and Assets

Saving for Retirement: The Importance of Planning - Annamaria Lusardi (TIAA-CREF Institute Research Dialogue, 2000)
In this article, I examine saving and planning behavior of households whose head is only a few years away from retirement using data from the Health and Retirement Study (HRS), a survey of a sample of U.S. households in which the head was born between 1931 and 1941. This survey reports detailed information on wealth and the retirement process, with a focus on health, participation in labor markets, and economic and psychosocial factors. These data provide the researcher with an unusually rich set of information to analyze household behavior. I also use data from the Survey of Consumer Finances (SCF), a triennial survey of U.S. families sponsored by the Board of Governors of the Federal Reserve System. This survey is designed to provide detailed information on families' balance sheets and their use of financial services. Finally, in a few instances, data from the 1997 Retirement Confidence Survey are mentioned; this survey collected information on American workers' retirement planning and saving behavior (Yakoboski and Dickemper, 1997).
RDA 1998-002
Keywords: Employment and Labor Force; Health Conditions and Status; Net Worth and Assets

Scaling the Semantics of Satisfaction - Hazelrigg, Lawrence E.; Melissa A. Hardy (Social Indicators Research, 2000)
Self-assessed satisfaction is typically measured on an ordinal scale of verbal categories. Here, data from the 1992 Wave 1 of the US Health and Retirement Study (N = 12,654 respondents) are used to investigate whether the boundaries that persons implicitly set between contiguous categories are uniformly set across persons and/or across domains of satisfaction, or are variably sensitive to status characteristics and/or to domain. Analysis demonstrates systematic variations and sensitivities in the semantics of satisfaction. This semantic elasticity affects other estimates in models of self-assessed satisfaction. 3 Tables, 3 Figures, 43 References. Adapted from the source document
Keywords: Methodology; Retirement Planning and Satisfaction

Self-employment and Labor Market Transitions at Older Ages - Bruce, Donald; Holtz-Eakin, Douglas; Joseph F. Quinn (Boston College, 2000)
Self-employment is an important aspect of the labor market activity of older workers and many wage and salary workers choose a period of self-employment before complete labor force withdrawal. Our analysis of the HRS data indicates that the determinants of self-employment transitions among these workers reflect those of younger workers. In particular, there appears to be an important effect of credit market imperfections, but little impact of employer-provided health insurance. In light of the demographic shift toward a relatively elderly population, these results suggest that the degree to which older workers utilize self-employment as a bridge to complete retirement will be more influenced by the distribution of wealth than by the private sector promise of medical insurance. Viewed from a research perspective, these results suggest the need for explicit modeling of joint life-cycle evolution of asset accumulation and the choice of working in the salaried and self-employed sectors. In addition, our results emphasize the importance of viewing retirement as a process. In addition to transitions from wage and salary work to self-employment (and vice versa), there are interesting patterns of re-entry to the labor force, and to self-employment in particular, that merit further attention.
Keywords: Employment and Labor Force

The Significance of Socioeconomic Status in Explaining the Racial Gap in Chronic Health Conditions - Mark D Hayward; Eileen M. Crimmins; Toni Miles; Yang, Yu (American Sociological Review, 2000)
Using Wave 1 (1992) and Wave 2 (1994) of the Health and Retirement Study the researchers try to detect the differences in life without health problems between different races so as to understand disparities in mortality rate and quality of life. Do Blacks have a higher risk of acquiring chronic health impairments of all types? How do differences in social conditions produce differences in the prevalence of fatal chronic diseases among races? The researchers notice that Blacks have a lower chance of surviving to middle age then do Whites. Blacks have a far greater level of morbidity in middle age, as well as, chances in having multiple fatal disease conditions. The author s give possible reasons for their findings, with much of it based on social status and life events.
Keywords: Health Conditions and Status; Net Worth and Assets

Social Security and Retirement - Courtney Coile; Gruber, Jonathan (NBER Working Paper, 2000)
A critical question for Social Security policy is how program incentives affect retirement behavior. We use the wealth of new data available through the Health and Retirement Survey (HRS) to examine the impact of Social Security incentives on male retirement. We implement forward-looking models of retirement whereby individuals consider not just the incentives to work in the next year but in all future years as well. We find that such forward looking incentive measures for Social Security are significant determinants of retirement decisions. Our findings suggest that Social Security policies which increase the incentives to work at older ages can significantly reduce the exit rate of older workers from the labor force.
Keywords: Retirement Planning and Satisfaction; Social Security

Social Security Benefits of Immigrants and U.S. Born - Alan L Gustman; Thomas L. Steinmeier (Issues in the Economics of Immigration, 2000)
Immigrants realize higher Social Security benefits per year worked in the U.S. then U.S. born, even when earnings are identical in all years the immigrant has been in the U.S. The benefit formula favors those with low lifetime covered earnings, and the years prior to immigration are treated as years of zero earnings. If instead earnings were averaged only over years of residence in the U.S., and benefits were prorated based on the share of a 35 or 40 year base period spent in residence, immigrants would receive the same return on their social security taxes as U.S. born. For a sample from the Health and Retirement Study, a group born between 1931 and 1941, prorating reduces immigrants' social security benefits by 7 to 15 percent. For immigrants who entered in the 1980's, the reductions would be over 30 percent. Prorating would reduce the present value of benefit payments to immigrants born from 1932 to 1941 by 7.5 billion to 15 billion. Most immigrants will still pay slightly more in taxes than they will receive in benefits. Taxes received from immigrants who subsequently emigrate without collecting benefits tip the balance in favor of including immigrants.
RDA 1996-005 ProCite field 8 : ed.
Keywords: Consumption and Savings; Demographics; Employment and Labor Force; Pensions; Public Policy; Retirement Planning and Satisfaction; Social Security

Social Security Earnings and Projected Benefits - Olivia S. Mitchell; Olson, Jan; Thomas L. Steinmeier (Forecasting Retirement Needs and Retirement Wealth, 2000)
Keywords: Pensions; Social Security

Studies on the Relationship Between the Elderly and Public Policies - Harris, Amy Lenae (Studies on the Relationship Between the Elderly and Public Policies, 2000)
A number of important demographic phenomena--rising life expectancy, the post-war baby boom, and the subsequent baby bust--will have dramatic effects on the age distribution of the U.S. population well into the next century. In particular, the American population is aging. This dissertation looks at the relationships between two very different public policies and the aging population. The first relationship is a possible intergenerational conflict over public education spending at the local level. Previous research by Poterba (1997) shows a negative effect from aging on public education spending at the state level. Using school district data, the second chapter shows that at the local level the elderly also have a negative and statistically significant effect on per-pupil education spending; however, the district-level results are much smaller than previous state-level results. Several pieces of evidence are then presented to bolster my results which indicate that the elderly are much less likely to support increased spending at the state level than at the local level. The second relationship is the interaction between elderly retirement behavior and the largest federal public spending program, Social Security. To project the aging population's future claims for Social Security benefits, it is crucial to have a reliable model of retirement behavior which incorporates the incentives of the Social Security system. A promising model of retirement is the Stock and Wise (1990a) option-value model. Their structural retirement model predicts retirement behavior based on the forward-looking incentives created by social security and pensions. However, they estimated their model using an unrepresentative sample of 1,500 salesmen working for one large firm. The third chapter tests whether the Stock and Wise option-value model can be applied to a more representative sample of males from the Health and Retirement Study. When the option-value model is applied to the HRS sample, the model fails to yield economically meaningful parameters. My results suggest that additional work is needed to accurately model and project future retirement behavior of the growing elderly population.
Keywords: Demographics; Employment and Labor Force; Methodology; Other; Public Policy; Retirement Planning and Satisfaction

Subjective Expectations of Nursing Home Use, Medicaid, and Economic Behavior by Older Americans - Merrill, Angela (Subjective Expectations of Nursing Home Use, Medicaid, and Economic Behavior by Older Americans, 2000)
Keywords: Consumption and Savings; Healthcare; Medicare/Medicaid/Health Insurance

Scale Simplification of Expectations for Survival: Cognitive Ability and the Quality of Survey Responses - Robert F. Belli; A. Regula Herzog; Van Hoewyk, John (Cognitive Technology, 1999)
This paper examines how data quality (specifically data that uses response scales designed to measure event probability) is affected by the cognitive ability of respondents and whether or not respondents provide a simplification process. Cognitive ability does have an affect on how respondents answer survey questions that use a high number of response options. Evidence of satisficing and providing simplification responses does show up in respondents with lower cognitive abilities, but the bunching phenomenon (due to satisficing) appears to have only limited effects on the data quality. Regardless of this limited effect, the results suggest ways of improving the quality of survey questions that use many response options. Better data quality will result when questioning leads respondents with higher cognitive abilities to maximize the number of response options while leading lower able respondents to deal with a reduced set of response options. The unfolded bracket technique is an example of such a method.
Keywords: Expectations; Health Conditions and Status; Methodology

Self-employment and Wealth Disparities between Black and White Households Approaching Retirement - Daeumer, Roland; Mark D Hayward (The Pennsylvania State University, Population Research Institute WP 99-17, 1999)
This article examines the role that self-employment and wage/salary employment play in determining racial disparities in wealth among persons approaching retirement. Findings indicate that black households exclusively linked to the labor market via selfemployment are the worst prepared financially for retirement. White self-employed households also suffer from a lack of liquid assets, although they have accumulated the most wealth when housing equity and real assets are taken into consideration. Inheritances do not constitute the principal basis of the wealth advantages they enjoy but do reinforce wealth inequality. The results suggest that choice in terms of retirement timing and labor supply decisions is much more a characteristic of white self-employed persons than of their black counterparts. Self-employed blacks will also heavily depend on Social Security during retirement and on the pension wealth of a wage/salary spouse, if married.
Keywords: Demographics; Employment and Labor Force

The Several Cultures of Research on Subjective Expectations - Dominitz, Jeff; Charles F Manski (Wealth, Work and Health: Innovations in Measurement in the Social Sciences, 1999)
ProCite field 8 : eds.
Keywords: Expectations; Methodology

The Size Distribution of Wealth in the United States: A Comparison Among Recent Household Surveys - Wolff, Edward (Wealth, Work and Health: Innovations in Measurement in the Social Sciences, 1999)
ProCite field 8 : eds.
Keywords: Income; Methodology

Social Security Disability Insurance and Older Workers - Park, Cheolsung (Social Security Disability Insurance and Older Workers, 1999)
The objective of this study is to estimate how individuals respond to policies designed to reduce the financial cost of the Social Security Disability Insurance (SSDI) program. In this study, I develop a dynamic stochastic discrete choice model of work, leisure, and application for SSDI benefits for single workers and for married couples. I estimate the structural parameters of the model, using first three waves of the Health and Retirement Study (HRS), allowing for unobserved heterogeneity in preferences. The model is shown to fit to the data well. Based on the estimated parameters, three policies aimed at reducing the number of applications and subsequently the number of recipients are simulated: reducing the SSDI benefit amount by half, lowering the acceptance rate of applications by half, and lowering renewal rate of SSDI benefits by half. The results of the policy experiments show that all three policies can successfully reduce the number of applicants and recipients. Individuals who would receive low benefits and/or earn high wages stop applying. Among the three policies, reducing the renewal rate has the biggest impact. The results also show that the disabled reduce the application rate more do those who are not disabled. Policy experiments which reduce errors in the SSA's acceptance also are performed. They show that reducing the Type I error (rejection of an application from a truly disabled individual) and the Type II error (acceptance of an application from an able individual) in a symmetric fashion increases the number of applications for and recipients of disability benefits and total disability benefit payment.
Keywords: Disabilities; Employment and Labor Force; Public Policy; Social Security

Social Security, Pensions, and the Retirement Decisions of Individuals and Couples - Courtney Coile (Social Security, Pensions, and the Retirement Decisions of Individuals and Couples, 1999)
This thesis presents three empirical studies of Social Security, private pensions, and retirement decisions. Chapter 2 is a study of the retirement decisions of women and couples. Motivated by the fact that the typical household is a dual-worker family, this chapter addresses three issues. The first is the effect of retirement incentives from Social Security and pensions on women's retirement behavior. The second is the spillover effects of incentives on the retirement behavior of spouses. The third is the joint retirement decision-making of couples. Using the Health and Retirement Study (HRS), the retirement incentives from Social Security and pensions are calculated and reduced form models of the impact of each spouse's incentives on their own and spouse's retirement decisions are estimated, as well as two-stage models using incentives as instruments for retirement behavior. The principal findings are that women are as responsive to their own retirement incentives as men and that women's incentives have large spillover effects on men's behavior, while men's incentives do not. The latter result is attributed to asymmetric complementarities of leisure. Chapter 3, joint with Jonathan Gruber, examines the retirement decisions of men. This chapter also uses the HRS to compute retirement incentives and aims to overcome a lack of attention in previous work to dynamic incentives, to the separate effect of Social Security and pensions, to the identification of retirement impacts, and to data deficiencies. Forward-looking incentive measures are found to be more important in explaining behavior and policy simulations suggest that incentive effects may be large. Chapter 4, joint with Peter Diamond, Jonathan Gruber, and Alain Jousten, examines Social Security benefit claiming behavior. The key findings are that delays are optimal in a wide variety of cases, that a non-trivial share of early retirees delays at least one year, and that delays are consistent with cross-sectional predictions.
Keywords: Employment and Labor Force; Methodology; Retirement Planning and Satisfaction

Social Security Reform: Implications of Raising the Retirement Age - United States General Accounting Office (Washington, DC, U.S. General Accounting Office, 1999)
Question: How might increases to the Social Security retirement age affect the solvency of the Old-Age Survivors Insurance, Disability Insurance, and Supplemental Security Income programs? Finding: Raising the Social Security early or full eligibility retirement ages could improve the OASDI balance sheet by reducing benefits paid out and increasing payroll taxes collected as well as contribute to economic growth as workers staying in the labor force for longer. However, this could lead to higher unemployment at younger ages and increases in applications for DI and SSI (among those who for health reasons are not able to stay in the labor force longer). Some portions of the population (e.g., less-healthy older workers and those in blue-collar occupations) may encounter difficulties remaining in the labor force. Recommendation: There is a need for greater understanding through further research on how to prevent effects of any changes from falling disproportionately on already-vulnerable populations.
Keywords: Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction; Social Security

Study: Depression as deadly as smoking - Webster, Sarah A. (Detroit News, 1999)
Keywords: Health Conditions and Status

Social Security Reform: Raising Retirement Ages Improves Program Solvency but May Cause Hardship for Some - United States General Accounting Office (U.S. General Accounting Office, 1998)
Question: Evaluate the proposals before Congress to reform and improve the solvency of the Social Security system. Finding: Using the NIA-funded Health and Retirement Study, GAO found that raising the Social Security retirement ages could improve long-term solvency for the program by increasing revenues and reducing benefits, but it is unclear whether employers will be willing to retain or hire older workers. Older blue-collar workers may be adversely affected because they are at risk for certain health problems that limit their ability to continue working.
Keywords: Employment and Labor Force; Public Policy; Retirement Planning and Satisfaction

Social Security Reform: Raising Retirement Ages Improves Program Solvency but May Cause Hardship for Some - Bovbjerg, Barbara D. (GAO Testimony before the Special Committee on Aging, U.S. Senate, 1998)
This report examines how raising the retirement age could affect Social Security (SS) and the economy and how the labor market might respond to these changes. It then looks at the possible impacts this raising of the age would have on the Disability Insurance (DI) and Supplemental Security Income (SSI) programs. The analysis shows that due to high life expectancies and the overall good health condition of the elderly, raising the retirement age could improve SS program's long-term solvency and could increase economic output. However, potential negative effects arise from the fact that older workers who have been laid off or have been retired may experience difficulties finding jobs. While the elderly may be willing to continue working, it is questionable whether employers will be willing to retain and hire them. Another possible drawback to raising the retirement age is explained by using the Health and Retirement Study. HRS data demonstrated that blue-collar workers in particular would be disproportionately affected by this age increase because due to the nature of their jobs which puts them at an increased risk of incurring health problems, they may be unable to remain in the workforce in later ages. These poor health, predominately blue-collar workers who will not receive SS retirement benefits because they cannot continue working up until the new age set by the increase, may apply for DI or be eligible for SSI, which would increase the costs of those programs.
Keywords: Demographics; Disabilities; Employment and Labor Force; Health Conditions and Status; Net Worth and Assets; Social Security

Socioeconomic Status and Health - James P Smith (American Economic Review, 1998)
ProCite field 3 : RAND
Keywords: Consumption and Savings; Demographics; Health Conditions and Status

Subjective Survival Curves and Life Cycle Behavior - Michael D Hurd; Daniel McFadden; Gan, Li (Inquiries in the Economics of Aging, 1998)
ProCite field[3]: SUNY, Stony Brook, RAND, and NBER; U CA, Berkeley and NBER; U CA, BerkeleyProCite field[6]: InProCite field[8]: ed.
Keywords: Consumption and Savings; Event History/Life Cycle; Health Conditions and Status

Symposium on Work, Retirement and Wealth: Current Data and Future Needs: An International Perspective - R.V. Burkhauser; Robert Clark; Richard M. Suzman (Australasian Journal on Ageing, 1998)
Discusses a cross-national symposium on elderly work, retirement, and wealth that drew on the US Health and Retirement Study and Panel Study of Income Dynamics, the Netherlands Household Panel Study, the German Socioeconomic Panel, and several East and Southeast Asian datasets.
Keywords: Demographics; Employment and Labor Force; Net Worth and Assets; Retirement Planning and Satisfaction

Selection of Children to Provide Care: The effect of earlier parental transfers - John C Henretta; Martha S. Hill; Li, Wei; Beth J Soldo; Douglas A. Wolf (The Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 1997)
We use the first wave of data from the Asset and Health Dynamics Among the Oldest Old (AHEAD) study to examine the effects of past parent-to-child financial transfers on selection of a child to provide assistance with basic personal care for unmarried parents. We estimate a fixed-effects conditional logit model and find a positive and significant association between past financial transfers and a child's current helping behavior. The coefficient of past financial transfers is in the direction hypothesized, and its magnitude is 80 as large as that of gender, a well-documented powerful predictor of parental caregiving. There appears to be substantial evidence that earlier parent-to-child financial gifts play a role in determining which child in the family will provide assistance.
Keywords: Adult children; Demographics; Health Conditions and Status; Healthcare; Income; Methodology; Other

Social Security Reform: Implications for Women s Retirement Income - United States General Accounting Office (Washington, DC, U.S. General Accounting Office, 1997)
Question: evaluate (1) why women s benefits are lower than men s under the current Social Security system, (2) the possible differential effects on women of the new privatization reform proposals, and (3) what can be done to minimize the possibly negative effect on women of certain elements of the Social Security reform proposals. Finding: Using the NIA-funded Health and Retirement Study, as well as citing some research conducted by NIA-funded grantees, GAO noted that women s Social Security benefits are often lower than men s due to lower wages and fewer years in the workforce. Some of the proposals to reform Social Security by shifting responsibility of saving for retirement to individuals via accounts funded as a proportion of their salary could make the difference between men s and women s benefits worse. For example, greater risk aversion among women could lead to lower investment returns; further, women could face substantially lower benefits (and hence a lower likelihood of retirement income adequacy) if annuitization formulae take their longer life expectancy into account. Recommendation: Improve information about investment objectives and financial planning to reduce differences in investment strategy and improve retirees ability to manage their assets. Consider mandatory annuitization to reduce the possibility of individuals outliving their savings. Use unisex lifetables to ensure those with comparable savings at retirement have comparable monthly benefits.
Keywords: Employment and Labor Force; Retirement Planning and Satisfaction; Social Security; Women and Minorities

Social Security Reform: Implications for Women's Retirement Income - Cackley, Alicia Puente (Washington, DC, United States General Accounting Office, 1997)
This report examines why women's benefits are lower than men's under the current Social Security system and evaluates the possible differential effects of the new privatization reform proposals on women. Average SS benefits are currently lower for women because of their lower rates of labor force participation and lower earning levels- both factors that contribute to the calculation of benefits. The reform proposals that would most affect women differently than men are the ones that create individual private savings accounts and change the way benefits would be distributed from those accounts. Because women earn less than men on average and are less likely to engage in risky high yielding assets, they would have less to invest and most likely would accumulate relatively less. Although differences in labor force participation and earnings between genders are expected to be reduced, they will not disappear. Therefore, any reform that bases benefits on earnings will continue to benefit men more than women. A system that relied mostly on individual investments would allow women workers a chance to increase their retirement benefits.
Keywords: Adult children; Demographics; Net Worth and Assets; Social Security; Women and Minorities

Socioeconomic Status and Racial and Ethnic Differences in Functional Status Associated with Chronic Diseases - Raynard Kington; James P Smith (American Journal of Public Health, 1997)
OBJECTIVES: This study examined the relationships between wealth and income and selected racial and ethnic differences in health. METHODS: Cross-sectional data on a national sample of 9744 men and women aged 51 through 61 from the 1992 Health and Retirement Survey were analyzed to examine the association between socioeconomic status and racial and ethnic differences in functional status among those with hypertension, diabetes, a heart condition, and arthritis. RESULTS: Compared with Whites, African Americans report higher rates of hypertension, diabetes, and arthritis, while Hispanics report higher rates of hypertension and diabetes and a lower rate of heart conditions. Accounting for differences in education, income, and wealth had little effect on these prevalence differences. In general, among those with chronic diseases, African Americans and Hispanics reported worse function than Whites. This disadvantage was eliminated in every case by controlling for socioeconomic status. CONCLUSIONS: While socioeconomic status, including wealth, accounts for much of the difference in functional status associated with these chronic diseases. It plays a relatively small role in explaining differences in the prevalence of chronic disease, possibly reflecting different causal pathways.
Keywords: Demographics; Health Conditions and Status; Income; Methodology; Other; Retirement Planning and Satisfaction; Women and Minorities

The Structure of Health Status among Hispanic, African American, and White Older Adults - Timothy E. Stump; Daniel O. Clark; Johnson, R.J.; Frederic D Wolinsky (The Journals of Gerontology, Series B: Psychological Sciences and Social Sciences, 1997)
Activities of daily living (ADLs), instrumental ADLs, and disability markers have traditionally been the most common indicators of functional status. The study on Asset and Health Dynamics Among the Oldest Old (AHEAD) is used to replicate a five-dimensional measurement model composed of these observable indicators among the older adult self-respondents. The items available to measure upper body disability were found wanting, but the lower body disability, and the basic, household, and advanced ADL constructs were confirmed. Analyses of the measurement model separately among subgroups of women, men, Hispanics, Mexican Americans, African Americans, and Whites found no meaningful differences. Two structural models linking the lower body disability, and the basic, household, and advanced ADL constructs to perceived health and depression were also replicated among the older adult self-respondents, as well as separately among African Americans and among Whites. These models reaffirmed the dominant role of lower body disability on the everyday activities of older adults, and on their perceived health and depression.
Keywords: Demographics; Disabilities; Health Conditions and Status; Methodology; Women and Minorities

Stability and Change in Plans for Retirement - David J Ekerdt; Stanley DeViney; Karl Kosloski (University of Michigan, 1996)
Health and Retirement Study panel data make it possible to investigate workers' prior decision making for retirement far in advance of the event. Using a multinomial construct that profiles general types of retirement plans, we found relative persistence of workers' intentions to retire completely, but relative instability of intentions to pursue more complex paths to retirement (e.g., partial retirement, successive jobs). Considering also the continued prevalence of large proportions with vague plans for retirement, these results show a cohort with a common expectation of retirement but quite unsettled as to how and when it will come about.
Keywords: Retirement Planning and Satisfaction

The Subjective Probabilities of Retirement of White, Black, and Hispanic Married Women - Honig, Marjorie (University of Michigan, 1993)
Analyses by race and ethnicity of several important dimensions of labor market behavior have been constrained in the past by limited samples of black and especially of Hispanic populations in nationally representative data sets. This paper uses a partial sample from the new Health and Retirement Survey, and provides the first comparative picture of the current labor force status, accumulated labor force experience, and pension and health insurance coverage of pre-retirement non-Hispanic white, non-Hispanic black, and Hispanic married women, as well as the first insights into the factors influencing retirement decisions of black and Hispanic married women. A model of the subjective probability that married women currently working full-time will continue to work full-time after age 62 is estimated for each population. The analysis focuses on the extent to which married women, in forming retirement expectations, take account of their own economic opportunities as well as factors related to the value of their time to the family. The results provide evidence that important aspects of current compensation such as health and disability insurance, as well as expected deferred compensation in the form of pension and Social Security benefits, are significant determinants of the likelihood of continued work for each of the three populations.
Keywords: Expectations; Retirement Planning and Satisfaction; Women and Minorities

State-level desegregation in the U.S. South and mid-life cognitive function among Black and White adults. - Walsemann, Katrina M; Hair, Nicole L; Farina, Mateo P; Tyagi, Pallavi; Jackson, Heide; Jennifer A Ailshire (Social Science & Medicine (1983))
RATIONALE: Black adults experience worse cognitive function than their White peers. Although educational attainment is an important predictor of cognitive function, other aspects of education, including school desegregation, may also shape this relationship. For Black adults who grew up in the U.S. South in the 1950s-1970s, exposure to school desegregation may have altered life course pathways critical for later cognitive function. OBJECTIVE: We determined if state variation in exposure to school desegregation in the U.S. South was associated with cognitive function at mid-life, if the association varied by race, and if the association remained after adjustment for state-level education quality and respondents' educational attainment. METHODS: We linked historical data on state-level school desegregation to the Health and Retirement Study, a nationally representative sample of U.S. adults aged 50 and older. We restricted our sample to Black (n = 1443) and White (n = 1507) adults born between 1948 and 1963 who resided in the U.S. South during primary school. We assessed three cognition outcomes: total cognitive function, episodic memory, and mental status. We estimated race-stratified linear regression models with cluster adjustment and a final model using state fixed effects. RESULTS: Greater exposure to desegregated primary schooling was associated with higher cognitive function and episodic memory among Black but not White adults. Among Black adults, the association between school desegregation and cognitive function and episodic memory remained after adjustment for state-level education quality and educational attainment. CONCLUSIONS: Our findings suggest that state-level school desegregation efforts played a consequential role in shaping the cognitive function of Black adults who grew up in the U.S. South.
Keywords: Education; historical data; life course; school segregation